Raising readers: Kenya schools use of technology to improve parent and carers' engagement in literacy learning: Inception Report - Nicolai, Susan; Zubairi, Asma; Bapna, Akanksha; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5784255 2405685:ZT3TGJ26
Keywords: _r:AddedByZotZen

Social Emotional Learning and EdTech: Resources, Examples, and Effective Practices - Rui, Yang (Tingting) (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5778309 2405685:8TZZZUMT
Keywords: F: Helpdesk response; _r:AddedByZotZen

Mapping the education data ecosystem in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652942 10.53832/edtechhub.0068 2339240:GXUF5TA5 2339240:HHY6M835 2339240:SUEMN855 2405685:8S3IIB2B 2405685:EE9QCGHI 2405685:Q7YZW4YW 2405685:RN79UTQY 4656463:GIIQKETU 4656463:Y8LQGZWY
Keywords: _r:AddedByZotZen

Guidebook to Successful Implementation of Digital Education - Traore, Moussa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5719833 2405685:RTJ2Z8MX
Keywords: _r:AddedByZotZen

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5611467 10.53832/edtechhub.0064 2339240:E542Q29N 2405685:2A5NQEV8 2405685:6JC7RU69 2405685:T3ZQ74QF
Keywords: _r:AddedByZotZen

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5602863 10.53832/edtechhub.0063 2339240:I3JETHDB 2405685:5ZF9VGMK 2405685:6P5Q5IRZ 2405685:BIRTYTRC
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:AD3D9NRM 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:SNBG3VHT 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

All Programmes Recorded, All Outputs Reported - Haßler, Björn; Adam, Taskeen; Blower, Thomas; El-Serafy, Yomna; Kaye, Tom; Khalayleh, Abdullah; McBurnie, Chris; Megha-Bongnkar, Ghislaine; Regis, Callista (EdTech Hub, 2021)
previousDOI: 10.5281/zenodo.4698917 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4698917 10.53832/edtechhub.0050 2129771:WSQ43VG8 2405685:VJYXV8JP
Keywords: AuthorFirst:Haßler; _yl:q

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524840 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524840 10.53832/edtechhub.0047 2339240:LSC89UVX 2339240:RIE9TWUK 2339240:SI398B6V 2405685:54BCQ23M 2405685:6NNCFPHE 2405685:77NJVUB6 2405685:HUY7VUM6 2405685:VTQDT65R 2405685:WFDCC7KZ 2534378:BQ8BJBGF
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

test - jac, nyili (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524863 2405685:86XEZU2S
Keywords: _r:AddedByZotZen

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524805 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524805 10.53832/edtechhub.0048 2339240:5D6SMESW 2339240:7NDUJC6J 2339240:M8IZH5DT 2339240:SIZUDNKL 2339240:XAXIKZJX 2339240:YPDDA6JD 2405685:45G9SKWR 2405685:5ENZ6TFU 2405685:EJ4PXU4S 2405685:JZM7W6QE 2405685:LCHJ5D5W 2405685:RUAJ8C8M
Keywords: _r:AddedByZotZen

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5512134 2405685:8M6GXINE 2405685:JGTWVQI4
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
2339240:7FA4YDWJ 2339240:YBKKN8XE KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5498054 10.5281/zenodo.5498054 2339240:3H4M8YJ8 2339240:5S4BZY48 2339240:SRWI5WQJ 2405685:BCFK4Q23 2405685:JR65CZU2 2405685:JTKTA5X5 2405685:VQ3F9NQ7 2405685:ZLATZSGU 4656463:RIFY2UNL
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5495857 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5495857 10.53832/edtechhub.0045 2339240:23D7YNSM 2339240:ESWRJBRS 2339240:PVDW8BXZ 2405685:69W2G8TJ 2405685:6KFAB5ML 2405685:UYDUMKBR 2405685:V9Y8MUDX 2405685:W8DB96IE
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

LGA Implementation Guide for Teacher Continuous Professional Development - Tanzania Institute of Education; Ministry of Education, Science & Technology; President’s Office — Regional and Local Governance (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5202057 2405685:U7NR3KP4
Keywords: _r:AddedByZotZen

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5256847 2405685:FQP8MJIY 2405685:SNBW6BK6
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Five ways geospatial analysis can help visualize and solve some of education’s biggest challenges - the Education Commission (the Education Commission, 2021)
As the education community continues to mobilize efforts towards achieving Sustainable Development Goal 4 (SDG 4), stakeholders at all levels of the system are grappling with questions on how to deliver inclusive quality education. What communities will benefit most...
Section: Updates KerkoCite.ItemAlsoKnownAs: 2129771:QDUZU3YQ 2405685:2ST897UD
Keywords: _yl:c

EdTech and Equity: Position Paper - Zubairi, Asma; Jefferies, Kate; Kreimeia, Adam (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5140323 2405685:9KIUKW7T
Keywords: _r:AddedByZotZen

Hello and Welcome to the Sandbox - Simpson, Lea; Carter, Alice; Rahman, Asad (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5123366 2405685:CQQURC65
Keywords: _EdTechHub_Output; _r:AddedByZotZen

Keeping Kenya Learning: The importance of caregiver engagement in supporting learning beyond the classroom - Kimathi, Deborah; El-Serafy, Yomna; Plaut, Daniel; Kaye, Tom (EdTech Hub, 2021)
Since the Covid-19 pandemic began, parents, teachers, students and policymakers have been exploring how to support students to learn at home. The emphasis on education at home has made evident the need to better equip caregivers to support their children’s learning. The Keep Kenya Learning (KKL) initiative is helping parents and caregivers build their capacity and confidence to support learning…
KerkoCite.ItemAlsoKnownAs: 2405685:LZM9KHE6
Keywords: _EdTechHub_Output

Embracing EdTech: four critical questions answered through a rapid prototype programme on teachers’ professional development (TPD) - Sabbab, Salman; Shakil, Abdullah All; Alam, Faria (EdTech Hub, 2021)
Seventy-one teachers participating in the ‘Onneshon’ prototype were flooding the WhatsApp group with messages about the challenges and hiccups they were experiencing, either with watching the video content or with taking a quiz in the first two weeks. Problems were pouring in and so were solutions being innovated and offered through diverse channels. In the space of two weeks, the…
KerkoCite.ItemAlsoKnownAs: 2405685:ZWUKU2YL
Keywords: _EdTechHub_Output

Social And Emotional Learning and EdTech: An Evidence Review - Kalifa, Damani (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5094331 2405685:FNJUHA6J
Keywords: _EdTechHub_Output; _r:AddedByZotZen

Verna Lalbeharie joins EdTech Hub as incoming Executive Director - Hub, EdTech (EdTech Hub, 2021)
We are excited to announce that Verna Lalbeharie is joining EdTech Hub as the incoming Executive Director. A native of South Africa, now living in North Carolina (USA), Lalbeharie brings not only 25 years of EdTech expertise to the role, but also a career-spanning commitment to evidence-building in education technology to create a more equitable future for all students. “When…
KerkoCite.ItemAlsoKnownAs: 2405685:GWTBTPXG
Keywords: _EdTechHub_Output

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5120788 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5120788 10.5281/zenodo.5142473 2405685:3C8VWLJP 2405685:772S7Z4R 2405685:CW2FHVT8
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

How Bangladesh repurposed pre-existing online platforms to reimagine education during Covid-19 - Bangladesh), Anir Choudhury (a2i (EdTech Hub, 2021)
Forty-two million. That is the total number of students in Bangladesh. Forty-two million potential leaders of tomorrow. Forty-two million reasons to be hopeful for the country’s future. Forty-two million students who, because of Covid-19, were left without classrooms, without their friends, without their schools and colleges – without formal education.
KerkoCite.ItemAlsoKnownAs: 2405685:HVNU4INN 2405685:TA8WC382
Keywords: _EdTechHub_Output

EdTech and Covid-19: the story so far - Gould, Briony (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4899740 2405685:IWGMZ8QI
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651981 previousDOI: 10.5281/zenodo.5109678 previousDOI: 10.5281/zenodo.4943272 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4943272 10.5281/zenodo.5109678 10.5281/zenodo.5651981 2339240:TCHKGQZS 2405685:QUJHNPRD 2405685:XH44AG5R 2405685:YULPZE4D
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651935 previousDOI: 10.5281/zenodo.4923094 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4923094 10.5281/zenodo.5651935 2339240:6ELB8P84 2339240:HZ3EBZ29 2405685:79JJ5T29 2405685:P8IAN448 2405685:RU8ET9S2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

EdTech and Emergency Remote Learning: A Systematic Review - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Sam; Nicolai, Susan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651932 previousDOI: 10.5281/zenodo.4917221 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4917221 10.5281/zenodo.5651932 2405685:V6UCUGBZ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4917252 10.5281/zenodo.4917252 2339240:G2X4SJI9 2339240:MUSPGK9F 2339240:MVU3QIHM 2339240:NQF22P32 2405685:B2ABXUCR 2405685:D6PWMC4I 2405685:HW7NU96L 2405685:JWIHBL5M 2405685:PXBXCZ29 2405685:YHC5ZPU8
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

EdTechTools Relaunched with TVET Resources - EdTech Hub; Generation Unlimited (EdTech Hub, 2021)
EdTechHub, Generation Unlimited (GenU), UNESCO and UNESCO-UNEVOC have joined forces to relaunch EdTechTools (formerly the Tools Database): a global repository of education technology tools and platforms designed to help decision makers at all levels in the global education and training community find resources that facilitate and support remote learning. More than a year after the world experienced an education disruption…
KerkoCite.ItemAlsoKnownAs: 2405685:HNAI38V8
Keywords: _EdTechHub_Output

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4896502 10.53832/edtechhub.0066 2339240:9A7P2GEI 2339240:PA2CB3JF 2339240:Q3RLYCNW 2339240:TMHE9JIR 2405685:2CEZ2LKN 2405685:9B56X45X 2405685:FAJLNB8S 2405685:KFTXK9K2 2405685:MPRD5RKR 2405685:PGUR927P 2405685:UKHA4WKY 2486141:A5SQMX8T 4656463:XTGYWNYB
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

What we learnt in the Sandbox between onebillion, VSO Malawi and EdTech Hub (Sprint Review Draft) - Dinham, Nat; Plaut, Daniel; Rahman, Asad; Schmit, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4959811 2405685:M78SQRBW
Keywords: _EdTechHub_Output; _MELA_seen; _comingsoon; _r:AddedByZotZen

A mixed-methods evidence assessment for emergent fields of knowledge - Haßler, Björn (EdTech Hub, 2021)
previousPreviousDOI: 10.5281/zenodo.4698915 PreviousDOI: 10.5281/zenodo.4698915 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4698915 10.53832/edtechhub.0003 2129771:E3W7NXR9 2405685:PUVVR28E
Keywords: _EdTechHub_Output; _yl:m

The global stakes of digitalization in education - Haßler, Björn (2021)
PreviousDOI: 10.5281/zenodo.4888604 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4888887 2405685:J49DGN5M
Keywords: _DOILIVE; _EdTechHub_Output; _zenodo:submitted

WhatsApp-Assisted Learning for Refugees. End of Sandbox Sprint 3 - Boujikian, Michèle; Carter, Alice; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4783017 2405685:89DPN3SP 2405685:EVSZNGMA
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Determining the suitability of Whatsapp for Jusoor Azima Project - Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4783101 2405685:MIQMEJK2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Advancing evidence-based decision making in LMICs: Focus of EdTech Hub’s work - Hennessy, Sara (EdTech Hub, 2021)
This blog sets out the Hub’s aims and approaches to identifying appropriate and effective uses of EdTech that can potentially raise learning outcomes in low- and middle-income countries (LMICs). Research shows that EdTech offers immense potential, but sustainable and positive change at scale has largely proved elusive in practice – particularly for marginalised learners where we focus our work. To…
KerkoCite.ItemAlsoKnownAs: 2405685:33PABHJH 2405685:Q8R8G8WG
Keywords: _EdTechHub_Output

Lack of Means or Lack of Awareness? Survey findings: barriers to learning with WhatsApp in refugee camps in Lebanon - Boujikian, Michèle; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4780972 2405685:4UQT8WRN 2405685:WWUQ7VRT
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
ZenodoArchiveID: 4746391 previousDOI: 10.5281/zenodo.4746391 previousDOI: 10.5281/zenodo.4664510 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4664510 10.5281/zenodo.4746391 2339240:CJNJNHNU 2405685:RTQ64R3P 2405685:TD3Y79BH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Covid-19 and EdTech in Africa: A Country-Level Review Based on eLearning Africa Data - Damani, Kalifa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4703718 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4703718 2405685:CDC2W7Q6 2405685:HVQVC8TU
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

L'utilisation des preuves pour renforcer la formation pédagogique à travers les technologies à Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4645807 10.5281/zenodo.4728174 2405685:552YTW72 2405685:BBWJNPNA
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodoETH

Let's Read — How Tusome Leveraged EdTech to Improve National Learning Outcomes. Governing Digital Transformation: Improving Outcomes in Education Systems - Myers, Christina; Kaye, Tom; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4699337 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4699337 2339240:MQFC486E 2339240:YAXCDGIK 2405685:3GQXS67C 2405685:Q9F2PISN
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

EdTech for learners with disabilities: urgent need to focus on access, engagement and learning outcomes - Singal, Nidhi; Lynch, Paul; Kaye, Tom; Francis, Gill (EdTech Hub, 2021)
The current approaches to providing high quality learning experiences to learners with disabilities in low and middle-income (LMICs) countries requires radical rethinking. To date, significant numbers of learners with disabilities are not enjoying the benefits of barrier-free and meaningful engagement with the school curriculum in order to reach their potential. Appropriately matched technology to learner needs – in terms of…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4728168 2405685:6QJYLAD7 2405685:BZDFHTPM
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

How Can EdTech Support Primary School Learners with Disabilities in LMICs? Recommendations for Policy - Lynch, Paul; Singal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4701259 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4701259 2339240:K42SWARR 2405685:DGECLZII 2405685:J83BVHG6 2405685:UXWEBRCC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Helping improve the Kenya Education Cloud with a SWOT analysis - Groeneveld, Caspar; Kimenyi, Eric; Kaye, Tom (EdTech Hub, 2021)
In early 2021, EdTech Hub partnered with the Kenya Institute of Curriculum Development to support them to analyse the strengths, weaknesses, opportunities and threats of the Kenya Education Cloud. This blog highlights what we learnt, and lessons that can inform the development of Virtual Learning Environments around the world. Governments all over the world responded to Covid-19 school closures by…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707900 2405685:F5HJ29AQ
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

The Use of Technology in the CPD Implementation Plan in Tanzania - Adam, Taskeen; El-Sefary, Yomna; Haßler, Björn; Khalayleh, Abdullah; Kremeia, Adam; Proctor, Jamie; Mtebe, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4665846 2405685:N5HMII3R
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

Support provided for K-12 teachers teaching remotely with technology during emergencies: A systematic review - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel (Journal of Research on Technology in Education, 2021)
Emergencies can cause disruption to education. This study is unique in providing the first empirical systematic review on teacher support for Emergency Remote Education (ERE) from 2010 to 2020. A total of 57 studies emerged from the PRISMA search. This mixed-method study used deductive and inductive iterative methods to examine the data. The data reveal teacher support strategies from across 50 different high and low-income countries. Few studies focused on a teacher’s subject and the age range taught. In the examination of professional development provided to prepare K-12 teachers to conduct ERE, eight codes emerged from the grounded coding as; 1) prior preparation, 2) understanding ERE, 3) needs analysis, 4) digital pedagogical strategies, 5) technology tools, 6) frameworks, 7) digital equity, and 8) mental wellness.
ZenodoArchiveID: 5652026 Publisher: Routledge _eprint: https://doi.org/10.1080/15391523.2021.1899877 KerkoCite.ItemAlsoKnownAs: 10.1080/15391523.2021.1899877 10.1111/bjet.13114 10.5281/zenodo.5652026 2339240:258WF4VH 2339240:RAP22KJU 2405685:5UAQ3N5K 2405685:BKMMRYCD 2405685:IA5XF32V 2405685:SU6FMBKT 2405685:XERPP4G9 2534379:UVB8PHFN
Keywords: COVID-19; Teacher education; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:CopiedFromEvLib; _yl:a; disasters; emergencies; emergency remote education; pandemic; remote education

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
ZenodoArchiveID: 4557015 PrevoousDOI: 10.5281/zenodo.4502122 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4502122 10.5281/zenodo.4557015 2339240:6Z8Q4VYT 2339240:KCTXJNS6 2405685:HZRHPNI5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4966322 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4966322 10.53832/edtechhub.0115 10.53832/edtechhub.0116 2405685:8HKCSIRC
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
ZenodoArchiveID: 5652007 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652007 2405685:KZ6FTNMC
Keywords: _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

A Monitoring and Evaluation Framework for Blended Learning: Pakistan Ministry of Federal Education and Professional Training - Khalayleh, Abdullah; Baloch, Imdad; Dele-Ajayi, Opeyemi; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4633326 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4633326 2339240:DNCQ88UV 2339240:ILPGZU8E 2339240:SGQPIKMM 2405685:AR7EAIDU 2405685:XBPZPS3P 2405685:YP4V829F 2405685:ZL7H9N8P
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Sierra Leone Series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health - McBurnie, Chris; Swaray, Abdulai; Kamara, Bai (EdTech Hub, 2021)
ZenodoArchiveID: 5652005 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652005 2405685:RT5H8XNG
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector. In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707910 2405685:7HCBSU4P
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

A Work Plan for Content Creation - Groeneveld, Caspar; Kibga, Elia; Proctor, Jamie; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4617798 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4617798 2339240:V3PGSF2W 2405685:EH6F8M5P
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4618376 10.5281/zenodo.5652060 2339240:F8ER2X27 2339240:KZ7L8K2X 2339240:YKGMJASP 2405685:3F4ASVFA 2405685:IA77HHMV 2405685:RQGJRKVS 2405685:TYZ4Y65R 2405685:VRE5DB5K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4776960 2339240:JASYN9AV 2339240:URJVJP9H 2405685:7QBDH9I4 2405685:MXMPWAA2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Bibliography on teacher distribution and allocation - Haßler, Björn (2021)
ZenodoArchiveID: 4608425 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4608425 2339240:2DAZHLTB 2405685:WX9A6Z7X
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; dode_eth-src-eth

A Case for a Systems Approach to EdTech - Bapna, Akanksha; Nicolai, Susan; Myers, Christina; Pellini, Arnaldo; Sharma, Namrata; Wilson, Sam (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651995 previousDOI: 10.5281/zenodo.4604769 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4604769 10.5281/zenodo.5651995 2339240:5JZ4FURY 2339240:5MG5JK99 2339240:8CEUGJ7E 2339240:N7XVM2BS 2339240:QL5LSA92 2339240:UIDN49MT 2405685:5HSPDN5N 2405685:AMGEVSIH 2405685:JMP2BJ2E 2405685:M8P5BVVK 2405685:ST8IBIUV 2405685:UR6CQL9K 2405685:VBZ4N4AM 2534378:PDNLLG9Y 4656463:RA69ZQLB
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Highlights from EdTech and Covid-19: Lessons learned, future plans - Team, EdTech Hub (EdTech Hub, 2021)
On March 2nd EdTech Hub brought together education leaders, including teachers, program managers and policymakers, to reflect on a year of EdTech and Covid-19, discuss the lessons learned so far and consider how we can prepare for the future. Over 200 people joined from around the world for a lively and thought-provoking discussion. Speakers included: Helen Grant MP, UK Prime…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707919 2405685:UKK52XU7
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Introducing: A political economy framework for EdTech evidence uptake - Pellini, Arnaldo; Nicolai, Susan; Kreimeia, Adam; Wilson, Sam (EdTech Hub, 2021)
“Without context, words and actions have no meaning at all” – Gregory Bateson Evidence only makes a difference if it is used. While the EdTech field suffers from significant gaps in knowledge, more research won’t mean much unless it can be used to inform policy and decision-making. And to do this, an understanding of the context and of how individuals…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707924 2405685:24RG82ZT
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

GIS for Education Working Group launches to promote data-driven decision-making - the Education Commission (the Education Commission, 2021)
Around the world, individuals are using maps to power everyday decisions: how do I navigate from my home to the nearest hospital? How many supermarkets are in my community? What public transportation is available for me to take to work?
Section: Updates KerkoCite.ItemAlsoKnownAs: 2129771:5XRHZSJ4 2405685:FJZKNYJI
Keywords: _yl:b

Using evidence to strengthen tech-supported teacher professional development in Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4585511 10.5281/zenodo.4728170 2405685:G2SH3FP6 2405685:HLMSBECU 2405685:MKH2ZP2T 2405685:TYXJSKEP
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _r:AddedByZotZen; _zenodoETH

Sierra Leone series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health. - Tahi (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector. In week one, we connected with Abdulai Swaray and Bai Kamara from the Pikin-to-Pikin Movement.…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707926 2405685:FB4FWFP9
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Mango Tree Literacy Labs’ Radio Programme Sandbox - Esbeck, Craig; Oloa, Charles; Brown, Victoria; Plaut, Daniel; Salami, Taiye (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4747475 2405685:RIPJWUDB
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
previousPreviousDOI: 10.5281/zenodo.4557484 previousPreviousDOI: 10.5281/zenodo.4557484 previousPreviousDOI: 10.5281/zenodo.4557484 PreviousDOI: 10.5281/zenodo.4557484 KerkoCite.ItemAlsoKnownAs: 2129771:HT9D5C8E 2129771:HT9D5C8E 10.5281/zenodo.4557484 10.53832/edtechhub.0001 2129771:HT9D5C8E 2339240:HPLKGS4I 2339240:RQGHJZV7 2339240:S3YSSL2W 2405685:K2FX6IVZ 2405685:T6YJ3L5G 2405685:TD2ASC4G 2405685:ZNQCJ5R7
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Keep Kenya Learning: Helping Caregivers Support Learning at Home Sprint 1 - Mbatha, FaithMbithe; Crook, Rebecca; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org Our research indicates that guidance and resources are necessary but insufficient in equipping caregivers to support their children’s learning. In Sprint 1, caregiver confidence and community emerged as important enablers of home learning. In our interviews, caregivers communicated how they felt limited by their lack of or outdated education. Global interventions indicate that reinforcing a sense of community for caregivers and enabling them to learn from modelling by trusted messengers are pathways to building greater engagement. Caregivers in both rural and urban communities expressed a willingness to engage with SMS (short message service) and online educational resources. However, it is clear that resource design must be: Accessible and understandable Credible and trusted Relevant and actionable.
ZenodoArchiveID: 4928926 PreviousDOI: 10.5281/zenodo.4747301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4928926 2339240:PXT8SGSZ 2405685:9P9W4I53 2405685:A2D9FVTA 2405685:C2579UKC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted; ⛔ No INSPIRE recid found

Sierra Leone series: Freetown Teachers College and its multimodal approach to teacher professional development - McBurnie, Chris; Moriba, Sambo; Brainard, Prince (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector. In week two, we connected with Dr Samba Moriba and Prince Brainard from Freetown Teachers…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4584801 2339240:F47KL5P7 2339240:VJ2SHXTR 2405685:DJHAECID 2405685:JV4FPSJW
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodoETH; dode_eth-src-eth

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
ZenodoArchiveID: 4613150 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4613150 2339240:7RV99GRF 2339240:KNG7CIPW 2405685:BHZPG5ZX 2405685:HH8PFJJE 2405685:IG4J94RS 2405685:YMAME8E6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Mother Language Day 2021 - Haßler, Björn; Castillejo, Alice; Marzotto, Mia; El-Serafy, Yomna; Khalayleh, Abdullah; Koomar, Saalim; Langa, Ancha; Nyilinkindi, Jacques; Saadeddin, Zeina; Tegha, Ghislaine; Villavicencio Peralta, Xuzel Ana (2021)
To celebrate International Mother Language Day 2021, Björn spoke with Alice Castillejo and Mia Marzotto at Translators without Borders. We talked about the importance of mother tongue-based education and the need to support speakers of marginalised languages. Research around the world shows that educational outcomes are worse for students studying in a second language. The use of an unfamiliar language is linked to high dropout rates and low academic achievement. We also know that 40% of children worldwide are not educated in a language they speak at home. We need to put aside our assumptions about what languages people speak and understand. For example, Portuguese is only one of many languages spoken in Mozambique. To really understand the richness of different languages, we need to collect, share, and visualise the real picture. Having done that, we can then apply this information. Do children who speak a particular language drop out early? We can then develop multilingual educational tools for learners and teachers based on improved data about relevant languages. We can also track educational outcomes by primary language, to ensure no learner is left behind. We can use language data to take action on three levels: children, teachers, and systems. With children, we can identify which language groups didn’t register for school, dropped out early, or consistently underperform. We can then adjust our communication and programming to meet their needs, leaving no one behind. We can also take action to support teachers. With language data, we can also take action on a system level. If over 40% of children are educated in a language they don’t speak at home, we need to know how this affects their education. Much as we did for gender, if we don’t gather the data on inequality, we cannot begin to address it. Collective gathering and sharing of language data can allow us to understand how to increase learning outcomes for speakers of marginalised languages and provide the support they need and deserve.
ZenodoArchiveID: 5651994 previousDOI: 10.5281/zenodo.4555228 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4555228 10.5281/zenodo.5651994 2339240:CME4837H 2405685:BSJEPIY4 2405685:ZQCX7TX3
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Mother Language Day 2021: Improving data on mother-tongue languages for better learning outcomes - Haßler, Björn; Castillejo, Alice; Marzotto, Mia; El-Serafy, Yomna; Khalayleh, Abdullah; Koomar, Saalim; Langa, Ancha; Nyilinkindi, Jacques; Saadeddin, Zeina; Tegha, Ghislaine; Villavicencio Peralta, Xuzel Ana (EdTech Hub, 2021)
To celebrate International Mother Language Day 2021, EdTech Hub’s Björn Haßler spoke with Alice Castillejo and Mia Marzotto of Translators without Borders. They talked about the importance of mother tongue-based education and the need to support speakers of marginalised languages. This blog post captures their conversation. “How do we know that speakers of marginalised languages are left behind?” Alice: Research…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707931 2405685:E65E8VY5
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech and Covid-19: lessons from around the world - Pellini, Arnaldo (EdTech Hub, 2021)
Arnaldo Pellini, Susan Nicolai, Moizza Binat Sarwar, Sam Wilson, Akanksha Bapna, Chris McBurnie, Adedoyin Adesina, Oladele Akogun, Ernest Ngabo, Hind Al-Hindawi, Ni Wayan Suriastini, Vollan Ochieng, Moses Ngware, Asma Rabi , Abdul Musawir, Clement Sefa-Nyarko, Edem Agbe , Rabia Tabassum, Amna Zaidi, Jeroen Groenewegen, Harish Doraiswamy, Sudhansu Sharma, Liangdi Xu In this blog we summarise four takeaways from a reflection…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707940 2339240:PAIL2F6F 2405685:27J8ETI9 2405685:G34FUWKA
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (EdTech Hub, 2021)
ZenodoArchiveID: 4540204 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4540204 10.5281/zenodo.4540204 2339240:26GYDUTU 2339240:2Q9AWGM3 2339240:IQ36IBT8 2339240:MDUWMNQ5 2339240:P9XQBBQC 2405685:856UY54Y 2405685:CZZ5WHT7 2405685:P9T68ACJ 2405685:UGZDH4LB
Keywords: _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Consultants needed for UNESCO ACCRA's review of ICT in Education Policy in Ghana - Tahi (EdTech Hub, 2021)
ICT Transforming Education in Africa: Review of ICT in Education Policy in Ghana TERMS OF REFERENCE (TOR) FOR INDIVIDUAL CONSULTANTS 1. Background/Context UNESCO Korean Funds-In-Trust ICT Transforming Education in Africa is a project developed under the UNESCO-Korea Funds-in-Trust framework to support a selected number of Sub-Saharan African countries to test scalable and effective models of using information and communication technologies…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707948 2405685:P2RAXUE3
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

How to Guide: Delivering High-Quality Radio Learning - Rising Academies; EdTech Hub (2021)
ZenodoArchiveID: 4486906 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4486906 2339240:NTGE2FPC 2405685:DU497D8A 2405685:HCV5X9YJ
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
previousPreviousDOI: 10.5281/zenodo.4557508 PreviousDOI: 10.5281/zenodo.4557508 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4557508 10.53832/edtechhub.0002 2129771:BKEP82PS 2339240:KF364I3I 2405685:2CKWI7RR 2405685:ESKCB3SZ 2405685:SRFG8S6C
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
ZenodoArchiveID: 5652063 previousDOI: 10.5281/zenodo.4430545 previousZenodoArchiveID: 4430545 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4430545 10.5281/zenodo.5652063 2339240:94IZR4ET 2339240:TST2YB8H 2405685:3BWKQDYQ 2405685:FEXGB4IJ 2405685:ZGYUEEZQ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Investigating the Impact on Learning Outcomes Through the Use of EdTech During Covid-19: Evidence from an RCT in the Punjab province of Pakistan - Adil, Fareeha; Nazir, Rabia; Akhtar, Misbah (EdTech Hub, 2021)
The objective of the current study is to test the impact of low-tech solutions on maths, Urdu, and English scores for students in the underdeveloped district of Bahawalnagar, which is situated in the southern part of Punjab in Pakistan. The target population for this study is Grade 8 students attending private schools. We have tested the impact of three interventions, namely: Teaching at the right level (TaRL), Fortnightly assessments (FAS) Digital teacher training sessions (DTS) Our findings show a significant and positive ‘Intention to Treat’ (ITT) impact on Urdu and English scores of the students in the TaRL treatment group. The students increased their English and Urdu scores by 0.56 SD. However, we found no significant impact of the intervention on maths scores in the TaRL treatment group. Fortnightly assessments and digital teacher training sessions were also found to contribute to higher English scores of the students. However, we found no ITT impact on the maths and Urdu scores for these treatment groups. The Local Average Treatment Effect (LATE) analysis revealed positive and significant improvement in Urdu and English scores of the students in the TaRL treatment group. Key stakeholders whom we interviewed suggested that redesigning the curriculum and incorporating TaRL within this approach could facilitate enhancement in learning outcomes in students in deprived areas. Our findings are important to help inform policymakers on the importance of designing and implementing cost-effective, low-tech solutions to help reduce learning gaps. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5654887 10.53832/edtechhub.0067 2339240:VNTPMCJQ 2339240:XLHSGBDA 2405685:FSVST5BF 2405685:HVDCZZVG 2405685:L5WPA5SN 2405685:YWENAQDF
Keywords: _r:AddedByZotZen

Using innovative methods to train teachers of blind children: what we learned - Kweyu, Ignatius; Koszorus, Ferenc (EdTech Hub, 2021)
Governments all over the world have closed learning institutions because of the Covid-19 pandemic, including in Kenya. This has exacerbated the global learning crisis and made it more difficult for teachers, parents, and caregivers to include children with disabilities in quality education. To ensure learners with disabilities were not left behind during Covid-19 school closures, eKitabu partnered with EdTech Hub…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707952 2339240:Y7EARNQ6 2405685:HKG7DF93 2405685:WD8FQQ9D
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

SWOT Analysis of the Kenya Education Cloud - Groeneveld, Caspar; Kimenyi, Eric; Kaye, Tom (EdTech Hub, 2021)
ZenodoArchiveID: 4745991 prevDOI: 10.5281/zenodo.4486279 prevDOI: 10.5281/zenodo.4742327 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4486279 10.5281/zenodo.4742327 10.5281/zenodo.4745991 2129771:LSCJ2AJX 2339240:95YP93VL 2339240:PBZKVTI5 2339240:WW642LX9 2405685:R3E3KVHX 2405685:TAWFGNE2 2405685:UMJTLGUE
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _cover:v3; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Structured Pedagogy and EdTech - Adam, Taskeen; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2021)
ZenodoArchiveID: 4460344 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4460344 2129771:DDU3QPXM 2339240:5XNMEGSN 2339240:XIRCF4HG 2339240:XXL72KUQ 2405685:2QM825CH 2405685:5RMUBA3Q 2405685:GBS5KW7S
Keywords: _EdTechHub_Output; _MELA_seen; _coming soon; _cover:analysis:nopdf; dode_eth-src-eth; dode_eth-trf2-dode

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
10.5281/zenodo.4913283 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0048 10.53832/edtechhub.0049 2339240:487NSL2N 2339240:96WXZFG3 2339240:BXUFCQ98 2339240:QUJFSUDE 2405685:4NFT3P7H 2405685:MZSKKWUZ 2405685:NVIUXYC6 2405685:PIXT9J66 2405685:RL5CTZU3 2405685:U8GMZZ48 2486141:7MQA6V3G 4656463:6378IJC5 4656463:TD3MYCHJ
Keywords: _EdTechHub_Output; _MELA_seen

T-TEL Covid-19 Impact Assessment Study - Ananga, Eric; Kadiri, Abdul-Karim; Kporwodu, Marie; Nkrumah, Yahya; Whajah, Francis; Tackie, Majorie (2021)
ZenodoArchiveID: 4895400 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4895400 2339240:F8IYBAPY 2405685:57DYPNLR 2405685:DR6BDMJS 2405685:PTC9PGZW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted

Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651978 previousDOI: 10.5281/zenodo.5213890 previousPreviousDOI: 10.5281/zenodo.4897985 previousPreviousDOI: 10.5281/zenodo.4897985 PreviousDOI: 10.5281/zenodo.4897985 PreviousDOI: 10.5281/zenodo.4897985 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5213890 10.5281/zenodo.4897985 10.5281/zenodo.5213890 10.5281/zenodo.5651978 2339240:C93CUDGR 2339240:XJDIEYV8 2405685:DQX9SUB6 2405685:FZ937TYM 2405685:WEFTUGTJ 2405685:YU9RLZ98
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
ZenodoArchiveID: 4140412 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4140412 2129771:9X3BTTLU 2339240:9PYYNK6J 2405685:ISTFVCA7 2405685:NS927T5K
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

A Theory of Change for a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Kaye, Tom (EdTech Hub, 2021)
The first of a trilogy of Theories of Change (TOCs) that focuses on learners as the main beneficiaries of an increasingly technology-enhanced education system in Bangladesh. Initially created with stakeholders to support the monitoring and evaluation of programmes designed to offer distance learning during the 2020 Covid-19 school closures, the TOC describes how access to educational activities of different modalities (TV, Radio, Smartphone, online platforms etc.) should lead to improved educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5652015 KerkoCite.ItemAlsoKnownAs: 10.5281/edtechhub.0044 10.5281/zenodo.4610089 10.53832/edtechhub.0044 2339240:D4Q4RX94 2339240:YKVDDCEI 2405685:2T7DPIBU 2405685:BUHD2X9T 2405685:E4I95IWF 2405685:NP95DHA2 2405685:Q2MS5ZSE 2405685:ZSEHKGUN
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
ZenodoArchiveID: 5652042 _eprint: https://bera-journals.onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13114 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13114 10.5281/zenodo.5652042 2339240:ELI3E5RF 2339240:TJNJX997 2405685:3KJJW6XZ 2405685:9V69ZAFP 2405685:BDG6N6PJ 2405685:JE8I8566 2405685:YY7LXWQB
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

Digital Personalised Learning to Improve Numeracy Outcomes in Kenyan Primary School Classrooms - EdTech Hub (EdTech Hub, 2021)
ZenodoArchiveID: 5596872 ZenodoArchiveConcept: 5596871 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0054 2405685:4N5VUGJG

Low-Tech Personalised Learning to Improve Girls' Education in Kenya - EdTech Hub (EdTech Hub, 2021)
ZenodoArchiveID: 5596885 ZenodoArchiveConcept: 5596884 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0059 2405685:7TUWEUKZ

Optimising Messaging to Promote Returns to School in Ghana for Marginalised Learners - EdTech Hub (EdTech Hub, 2021)
ZenodoArchiveID: 5596883 ZenodoArchiveConcept: 5596882 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0058 2405685:DMVKGJWQ

The Impact of a Tech-Supported, School-Based TCPD Model on Learning Outcomes in Tanzania - EdTech Hub (EdTech Hub, 2021)
ZenodoArchiveID: 5596877 ZenodoArchiveConcept: 5596876 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0056 2405685:PFMSZZ8N

Les Technologies De L’enseignement Et Le Covid-19 - 10 Choses À Savoir - EdTech Hub Team (2021)
ZenodoArchiveID: 4709702 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709702 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:VJ488Z7L
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Summary Brief: Problem Analysis and Focus of EdTech Hub’s Work - EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4612141 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4612141 2339240:M4WB4UIZ 2405685:GNY5ZSWM
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

تكنولوجيا التعليم وجائحة كوفيد 19 - .10 أشياء يجب معرفتها - EdTech Hub Team (2021)
ZenodoArchiveID: 4709700 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709700 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:VJ488Z7L
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Strategy for Tanzania — Focus Area: TCPD in primary schools - El-Serafy, Yomna; Khalayleh, Abdullah; Carter, Alice; Haßler, Björn; Proctor, Jamie; Adam, Taskeen (EdTech Hub, 2021)
ZenodoArchiveID: 4742727 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4742727 2405685:BPHSJBH7
Keywords: _EdTechHub_Output

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4332693 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4332693 2339240:2FHWWFA3 2339240:322MPSF7 2339240:8BXMXD7P 2339240:BTJ8QHAD 2339240:BTPX7CIX 2339240:DZSHD5WZ 2339240:EEUENHU3 2339240:HSFA8Z7Q 2339240:M3YUXFYS 2339240:Q2I8K6L8 2339240:SILWX2ZS 2339240:WEEFFITS 2339240:XHVAUXYZ 2405685:347U73VH 2405685:4LA8N3BT 2405685:8F46F44X 2405685:94F2MYRK 2405685:BHLDEAHG 2405685:CQXKYRLY 2405685:CSJHU24F 2405685:DYB6V7DK 2405685:EIQD4I2E 2405685:GUHMK274 2405685:HXF4GM6M 2405685:PBXBB7LF 2405685:QVG25MBV 2405685:R2YGTN82 2405685:R7Q7CT4P 2405685:SNZ55MKE 2534378:42JICVEU
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo; Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
ZenodoArchiveID: 5652036 Dates: 13-11-2020 — Actualizado el 09-01-2021 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652036 10.6018/red.453621 2405685:2BIQKP9C 2405685:IVHRNTQ7 2405685:L7Y5JD68 2405685:ZXQZ3FVV
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

EdTech for Learners with Disabilities in Primary School Settings in LMICS: A Systematic Literature Review - Lynch, Paul; Singhal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
This systematic literature review was guided by the overarching aim of establishing the categories of EdTech that may be appropriate to support the learning of children with disabilities aged 4–12 years in low-and middle-income countries. A critical review of the published literature was deemed essential as the field of disability and EdTech (mirroring larger trends in disability and educational research) has remained dominated by anecdotal commentaries and strong personal assertions, but substantiated by little evidence. In framing the review we drew on a dual model of access which provides a helpful lens into how EdTech can support a learner’s development trajectory across different interventions (e.g. learning to read Braille or sign language), targeted educational outcomes, inclusive practices and suitable accommodations in different educational settings. This approach is underpinned by a human rights agenda, as articulated in the UN Convention for the Rights of Persons with Disabilities (CRPD) and the Sustainable Development Goals (SDGs) which demand fair and equal access to education for all children and young people. They are also concerned, though, that an individual child/young person should have agency, self-determination and independence. Article 2 of the CRPD unambiguously recognizes that reasonable accommodation is vital in enabling persons with disabilities to enjoy and exercise their rights on an equal basis with others.
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4348995 10.5281/zenodo.4348995 2339240:6VEXVUL7 2339240:BAU4D8ER 2339240:PAABA4B7 2339240:RHJJP4E2 2339240:TWQV2AGE 2339240:Z4FHRC9L 2405685:7IEM9MCP 2405685:88MZ92YX 2405685:ATYBHAIH 2405685:DGRQM9XQ 2405685:KKZ3ET5W 2405685:KL56SD42 2405685:VZNCHGEG 2405685:XJ42VUQG 2534378:3A5TU66J
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Archive: https://zenodo.org/record/4817787 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13116 10/gj6k5n 2339240:382K6GCA 2339240:53R3ZYT5 2339240:6HPRIAVP 2339240:7C7I9C4I 2339240:CYQPAERV 2339240:EXFAZMDQ 2339240:P2I2EU98 2339240:RM59PWFE 2405685:4MGG3JS3 2405685:5U948655 2405685:6UZHTZ8G 2405685:FIXCCB5I 2405685:HBGSTQ7X 2405685:QFTDGH3C 2405685:RZNJVMWH 2405685:V8UFGT52 2405685:WTT4UQ43 2405685:ZD4YGMMJ 4042040:G8KVDVSC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted; computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning; ⛔ No DOI found

A Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs. - McIntyre, Nora; Sabates, Ricardo; Eberhardt, Molly Jamieson (EdTech Hub, 2021)
ZenodoArchiveID: 4575561 PreviousDOI: 10.5281/zenodo.4468852 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4575561 2339240:DTA9GETP 2339240:V8PHTCMI 2405685:5TQ3YM2R 2405685:AI9EYM2F 2405685:E5W5QCIE
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech and Covid-19: 10 Things to Know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2021)
EDTECH AND COVID-19 10 THINGS TO KNOW Covid-19 has reshaped our world. In education, mass school closures have accelerated the global use of education technologies. Yet the benefits do not reach everyone. Since the start of the pandemic, EdTech Hub and its partners have been researching and applying evidence on what works in technology for education in different contexts. Here…
ZenodoArchiveID: 5651983 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5651983 2339240:C67KNIJR 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2339240:W7FD9YT3 2405685:26VNTFQU 2405685:94AITL9D 2405685:DQ5URLSY 2405685:GT33JADA 2405685:VJ488Z7L zotzenLib.CopiedFrom: 2339240:C67KNIJR
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5576416 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5576416 10.53832/edtechhub.0052 2339240:282R466B 2339240:EQWZQPHA 2405685:2B2RMIDY 2405685:AEQDZV3T 2405685:DX6WMTLN 2405685:NNN9EZ7J
Keywords: _r:AddedByZotZen

EdTech Interventions for Deaf Learners: Sprint 2 Review - Rahman, Asad; Siddiqui, Maira; Shaikh, Sarah; Geary, Richard; Awasen, Aaron; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4924787 10.53832/edtechhub.0131 2405685:D7JX8S7S
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

GIS for Education Working Group - the Education Commission (the Education Commission, 2021)
KerkoCite.ItemAlsoKnownAs: 2129771:PEEHJ6D6 2405685:6NKZST4H
Keywords: _yl:a

Country-Level Research Review: EdTech in Pakistan - Zubairi, Asma; Halim, Waqas; Kaye, Tom; Wilson, Sam (EdTech Hub, 2021)
ZenodoArchiveID: 4596486 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4596486 2129771:3CUB9UK6 2339240:3JHAWKKZ 2339240:NHJQTPKC 2339240:R2MHQ7R6 2405685:BTQ4CU7R 2405685:NZUHTJBG 2405685:R4LUIDP5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

From face-to-face to teaching at a distance: Lessons learned from emergency remote teaching - Corcuera, Lovely; Abel Alvarez, Jr (Asian Journal of Distance Education, 2021)
The Covid-19 disrupts not only the health, economic, and tourism sectors but it paralyzed the education sector as well. Since face-to-face teaching and learning environment is still not possible in the Philippine context, this phenomenon leaves the teachers to use various alternative ways of instructional delivery. The sudden shift of teaching and learning delivery continuously challenges not only the students but also the teachers who are serving as educational front liners at the time of the pandemic crisis. The lack of proper training and experiences of teachers in online teaching and distance education served as educational loopholes in the context of emergency remote education.  Hence, this case study attempts to explore the experiences of K-12 senior high school teachers who have been immersed in emergency remote teaching. In analyzing the data gathered, the descriptive coding process was used. Interestingly, there were three themes reported in this study: getting the right mix of instructional methods, engaging in different open educational resources and information, and highlighting the need for the pedagogy of care and understanding. Although this study does not aim to make any generalities, however, the researchers saw the need to understand and investigate the journey of the K-12 senior high school teachers, which are essential in providing lending ears about their transitioning experiences from the traditional classroom environment to emergency remote education. This study concludes with the implications of the findings that emerged and the direction for further research.
Number: 2 KerkoCite.ItemAlsoKnownAs: 2339240:A25FB7R2 2405685:8KPX8NZC
Keywords: Covid-19; K-12 teachers; distance education; emergency remote education; teaching modality; ⛔ No DOI found

Engaging extensive reading practice through Let’s Read Asia in the online classroom - Prihartono, Dwi; Miftakh, Fauzi; Rachmawati, Maya (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
This research aims to find out the process of students’ engagement during extensive reading practice mediated by Let’s Read Asia and students’ responses during extensive reading practice mediated by Let’s Read Asia at the eleventh grade in one of the Senior High School at Karawang. This research used the qualitative approach and a basic interpretive research as the research design. The data were collected by observation checklist based on guidelines from the Extensive Reading Foundation, online interview by using Whatsapp application, online documentation, and written artifact of students. This research included 4 participants of eleventh grade of senior high school. The result of this research showed that the teacher can engage students, it because students actively followed teacher instructions during the process of extensive reading practice that mediated by Let’s Read Asia. During the extensive reading practice that mediated by Let’s Read Asia students could make their interest to read with books that have self selected by students. The students also give the positive responses in the process of extensive reading practice that mediated by Let’s Read Asia as a media of students reading activity.
KerkoCite.ItemAlsoKnownAs: 10.17977/um006v5i22021p191-202 2339240:K9YU96NC 2405685:AEHWIWJT

Encouraging Community Action Against Teacher Absenteeism: A Mass Media Experiment in Rural Uganda - Wilke, Anna M.; Green, Donald P.; Tan, Benjamin (The Journal of Development Studies, 2021)
Chronic teacher absenteeism is widespread in Uganda, with approximately one-third of public school teachers absent on any given day. Absenteeism and other problems that arise in Uganda’s public education system are often attributed to a lack of public oversight and parental involvement. In an effort to develop a scalable method of encouraging community engagement on this issue, the present study assesses the extent to which entertainment-education videos increase willingness among Ugandans to take action against absenteeism. Working in collaboration with Ugandan screenwriters and local actors, we developed video dramatisations that depicted the problem of absenteeism and how parents mobilised to address it. We assess the persuasive effects of these dramatisations both under lab-like conditions, to gauge immediate effects, and in the field, to gauge effects two months and eight months after a placebo-controlled media campaign attended by over 10,000 Ugandans in 112 villages. Although the persuasive effects are weaker in the field than the lab setting, the former remain substantial even after eight months. The demonstrated ability of entertainment-education to change public views on this issue sets the stage for policy experiments that test whether entertainment-education campaigns have downstream effects on absenteeism and public school performance more generally.
Publisher: Routledge _eprint: https://doi.org/10.1080/00220388.2021.2008367 KerkoCite.ItemAlsoKnownAs: 10.1080/00220388.2021.2008367 2129771:MEAS58AG 2339240:9PCHFF4I 2405685:GLI5RLLR 4556019:Z9A72XEC
Keywords: Africa; access to education; education quality

PLANE Education Place Level Assessment: Federal Government - DAI; FHI 360; Social Development Direct; Bluetree Group; Sightsavers; Achieving Health Nigeria Initiative; Overseas Development Institute; The Policy Practice; The Education Partnership (TEP) Centre; Accadian Ltd (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:MWMZEJSU 2405685:XRIP36VV

Language education in emergencies: A systematic review - Thumvichit, Athip; Varaporn, Savika; Tuvachit, Vorakorn (Journal of Language and Education, 2021)
In response to the Covid-19 pandemic, education systems around the globe suspended on-site classes and transitioned instruction to various remote environments, creating a distinctive context for teaching and learning. This systematic review brings together the available research in language education within the current emergency setting to examine the state of affairs, as well as the situation’s inherent challenges and opportunities for language learners and teachers. A total of 38 studies were collected to reflect the current trend, with 16 of these in-depth reviewed. Research focusing on learners was dominant. Most research was conducted at the tertiary level. The studies highlighted digital tools that are capable of engaging language learners in an interactive learning experience, though they are unable to replace face-to-face instruction. Outside-of-class support such as extra channels of communication, self-access language learning (SALL) materials, and advising in language learning (ALL) were all found to complement remote learning. It is recommended that teachers try to retain their teaching principles and put them into practice regardless of the abrupt transition. Teachers’ wellbeing can be promoted when teachers accept the changes and see them as opportunities.
KerkoCite.ItemAlsoKnownAs: 10.17323/jle.2021.12462 2339240:BUPKYWZY 2405685:RIWWRKXY

Teachers’ adoption of an open and interactive e-book for teaching K-12 students Artificial Intelligence: a mixed methods inquiry - Zhang, Xiangling; Tlili, Ahmed; Shubeck, Keith; Hu, Xiangen; Huang, Ronghuai; Zhu, Lixin (Smart Learning Environments, 2021)
With the rapid development of information technology, e-books have become convenient for students to improve their learning performance, especially when learning complicated concepts. However, research showed that acceptance of e-books by teachers is fragmented, due to several factors including the e-book design. Therefore, this study combined the potential positive impacts of openness and interaction on learning to design an open and interactive e-book for teaching K-12 students AI. It then applied a mixed method to investigate the factors that affect teachers’ acceptance of this open and interactive e-book based on the technology acceptance model (TAM) and interviews. The obtained results showed that teachers’ intention to continue using this e-book is significantly influenced by their perceived usefulness and attitude towards this e-book. Additionally, both the interactive and openness features were very helpful for teachers in using this e-book in their teaching plans. However, some of them raised several concerns like the interactive coding platform should be personalized based on students’ age. The findings of this study could help different stakeholders (e.g., instructional designers, teachers, policymakers) in facilitating the design and adoption of open and interactive e-books.
KerkoCite.ItemAlsoKnownAs: 10.1186/s40561-021-00176-5 2339240:2U8R2BFF 2405685:395HKI8Z

Digital Learning Solutions | Digital Learning For Every Child - Giraldo, Juan Pablo; Tungatarova, Auken; Cooper, Rachel (EdTech Hub, 2021)
UNICEF and EdTech Hub are partnering together to improve learning outcomes through effective uses of EdTech and digital learning. Read this guest post from UNICEF team members which focuses on the first pillar of UNICEF’s Reimagine Education initiative, world-class digital learning solutions.
KerkoCite.ItemAlsoKnownAs: 2339240:CF8CHKIM 2405685:9WZQKU59

Preparation, Practice, and Beliefs: A Machine Learning Approach to Understanding Teacher Effectiveness - Filmer, Deon; Nahata, Vatsal; Sabarwal, Shwetlena (Research on Improving Systems of Education (RISE), 2021)
This paper uses machine learning methods to identify key predictors of teacher effectiveness, proxied by student learning gains linked to a teacher over an academic year. Conditional inference forests and the least absolute shrinkage and selection operator are applied to matched student-teacher data for Math and Kiswahili from Grades 2 and 3 in 392 schools across Tanzania. These two machine learning methods produce consistent results and outperform standard ordinary least squares in out-of-sample prediction by 14-24 percent. As in previous research, commonly used teacher covariates like teacher gender, education, experience, and so forth are not good predictors of teacher effectiveness. Instead, teacher practice (what teachers do, measured through classroom observations and student surveys) and teacher beliefs (measured through teacher surveys) emerge as much more important. Overall, teacher covariates are stronger predictors of teacher effectiveness in Math than in Kiswahili. Teacher beliefs that they can help disadvantaged and struggling students learn (for Math) and they have good relationships within schools (for Kiswahili), teacher practice of providing written feedback and reviewing key concepts at the end of class (for Math), and spending extra time with struggling students (for Kiswahili) are highly predictive of teacher effectiveness, as is teacher preparation on how to teach foundational topics (for both Math and Kiswahili). These results demonstrate the need to pay more systematic attention to teacher preparation, practice, and beliefs in teacher research and policy.
KerkoCite.ItemAlsoKnownAs: 10.35489/BSG-RISE-WP_2021/084 2339240:36V6MWVY 2405685:LBATNMUL

State releases rules on learner capitation grants, school funds - Githinji, Irene (People Daily, 2021)
One of the policy goals is to enhance access and disbursement of learner capitation grants and other school funds to all public schools.
KerkoCite.ItemAlsoKnownAs: 2339240:DRAWWYNI 2405685:KPF3QK8G 4656463:5ZEV3KM2

Education for non-citizen children in Malaysia during the COVID-19 pandemic: A qualitative study - Loganathan, Tharani; Chan, Zhie X.; Hassan, Fikri; Kunpeuk, Watinee; Suphanchaimat, Rapeepong; Yi, Huso; Majid, Hazreen Abdul (PLOS ONE, 2021)
The COVID-19 pandemic disrupted schooling for children worldwide. Most vulnerable are non-citizen children without access to public education. This study aims to explore challenges faced in achieving education access for children of refugee and asylum-seekers, migrant workers, stateless and undocumented persons in Malaysia during the pandemic. In-depth interviews of 33 stakeholders were conducted from June 2020 to March 2021. Data were thematically analysed. Our findings suggest that lockdowns disproportionately impacted non-citizen households as employment, food and housing insecurity were compounded by xenophobia, exacerbating pre-existing inequities. School closures disrupted school meals and deprived children of social interaction needed for mental wellbeing. Many non-citizen children were unable to participate in online learning due to the scarcity of digital devices, and poor internet connectivity, parental support, and home learning environments. Teachers were forced to adapt to online learning and adopt alternative arrangements to ensure continuity of learning and prevent school dropouts. The lack of government oversight over learning centres meant that measures taken were not uniform. The COVID-19 pandemic presents an opportunity for the design of more inclusive national educational policies, by recognising and supporting informal learning centres, to ensure that no child is left behind.
Publisher: Public Library of Science KerkoCite.ItemAlsoKnownAs: 10.1371/journal.pone.0259546 2339240:BUAJG2VR 2405685:H3TXCFFE
Keywords: COVID 19; Children; Education; Human learning; Pandemics; Refugees; Schools; Teachers

Lessons Learned from Education Initiatives Implemented During the First Wave of COVID-19: A Literature Review - Sims, Kate (Institute of Development Studies (IDS), 2021)
It is important to assume that the learning crisis caused by COVID-19 is not over. As highlighted by 2021 school closures in response to the Delta variant, lessons learned from school closures in 2020 are required and applicable. There is therefore a need for reflection and a consolidation of lessons learned to protect education outcomes. Lessons include the need for parental engagement and support, the mobilisation of community actors, and inclusive and accessible remote learning approaches (Kapur, 2020, p. 38). This literature review seeks to better understand what worked and what did not work in education interventions during the first wave of COVID-19, in order to support planning on current and future school closures and/or disruptions to education systems. It focuses on three key areas: 1. Support to teachers to continue teaching during school closures, and the role of teachers in supporting marginalised learners; 2. Approaches to ensure the continuation of learning; and 3. Approaches to reach the most marginalised learners.
KerkoCite.ItemAlsoKnownAs: 10.19088/K4D.2021.134 2339240:JZRWLVTZ 2405685:85KMGD6V

Building State Capacity - Di Maro, Vincenzo; Evans, David K.; Khemani, Stuti; Scot, Thiago (2021)
Although research has established the importance of state capacity in economic development, less is known about how to build that capacity and the role of external partners in the process. This paper estimates the impact of a typical development project designed to build state capacity in a low-income country. Specifically, it evaluates a multilateral development bank project in Tanzania, which incentivized investments in local state capacity by offering grants conditional on institutional performance scores. The paper uses a difference-in-differences methodology to estimate the project impact, comparing outcomes between 18 project and 22 non-project local governments over 2016–18. Outcomes were measured through two rounds of primary surveys of nearly 500 local government officials and nearly 3,000 households. Over the course of the project, measured state capacity improved in project areas, but due to comparable gains in non-project areas, the project’s value-added to change in state capacity is estimated to be zero across all the dozens of relevant variables in the surveys. The data suggest that state capacity is evolving in Tanzania through endogenous changes in trust and legitimacy in the country rather than from financial incentives offered by external partners.
Publisher: World Bank, Washington, DC KerkoCite.ItemAlsoKnownAs: 2339240:JPXRZ2XQ 2405685:5ZSUJQ6H 4656463:RBLHVDBX
Keywords: ⛔ No DOI found

Unlocking Learning: The implementation and effectiveness of digital learning for Syrian refugees in Lebanon - Dreesen, Thomas; Kamei, Akito; Karamperidou, Despina; Fakher, Sara Abou; Marji, Lama; Correa, Javier Santiago Ortiz (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ZIZFIX2H 2405685:GDI8ED4N

Statistical Yearbook of Cambodia 2021 - Royal Government of Cambodia Ministry of Planning (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KUKE8JDT 2405685:DRJPZIV2

M-Lugha: Improving Student’s Access to Literacy and Numeracy by using Local Language Instruction in Northern Kenya - Cordeiro, Paula (Global Ed Leadership, 2021)
Abdinoor Alimahdi is a former telecommunications engineer from Kenya. He is an Award winning EdTech innovator and social entrepreneur. Some of the awards include: Best 100 startups (StartupIs…
KerkoCite.ItemAlsoKnownAs: 2405685:4T6JUN7V 4042040:68NXCIFI

Remote Learning During COVID-19: Lessons from Today, Principles for Tomorrow - Munoz-Najar, Alberto; Gilberto, Alison; Hasan, Amer; Cobo, Cristobal; Azevedo, Joao Pedro; Akmal, Maryam (World Bank, 2021)
School closures during COVID-19 (coronavirus) led to an unprecedented global experiment in the delivery of remote learning. This report seeks to assess what lessons can be drawn from experiences of remote learning during COVID-19 in K-12 education, with a focus on low- and middle-income countries. It focuses on the period from March 2020 to October 2021 and addresses the following key questions: 1. Was remote learning during COVID-19 taken up and if so, was it effective That is, did children learn as much as they did during pre-pandemic, in-person learning 2. What lessons can governments derive from this wide-spread experience 3. How might policymakers use these lessons to reimagine learning as schools begin to reopen This report is part of a larger effort led by the World Bank to provide guidance and technical assistance to optimize country effectiveness in the design and execution of remote learning strategies. It has been developed in conjunction with Remote Learning During the Global School Lockdown: Multi-Country Lessons, a qualitative study conducted between May and November 2020 to understand the perceived effectiveness of remote and remedial learning solutions implemented across 17 countries.
KerkoCite.ItemAlsoKnownAs: 10.1596/36665 2339240:DECH7NNY 2339240:K4ED7NM9 2339240:PF8DATUL 2405685:6MM7PBEE 2405685:PY2ACUYU 2405685:TXJBN4V3

Behavioral nudges to prevent learning losses and dropout risk during the pandemic: experimental evidence from Brazil - Lichand, Guilherme; Christen, Julien; van Egeraat, Eppie (University of Zurich Department of Economics, 2021)
Using a cluster-randomized control trial with 18, 256 high-school students across 87 schools in the State of Goiás, Brazil, this paper documents that behavioral nudges, sent through text messages to students or their caregivers during remote learning in the context of COVID-19, significantly increased test scores in a standardized assessment test conducted with high-school seniors on the following year. Impacts were positive across the entire test score distribution, but nudges increased inequality in test scores. Relying on missing scorecard grades as a proxy for dropout risk across all high-school grades during remote learning, we show that nudges decreased this metric by 20% (although the effect is only imprecisely estimated). In contrast to test scores, nudges decreased inequality in dropout risk. Additional experiments that varied the content of nudges at the student level illustrate the opportunities and challenges of using behavioral insights to motivate students in the context of remote learning.
KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.3724386 2339240:VMRHPQ3G 2405685:FXZ3IKVM
Keywords: COVID-19; Dropouts; Learning Losses; Nudges; Remote Learning

Impact of Covid-19 on the education of children with disabilities in Malawi: reshaping parental engagement for the future - Singal, Nidhi; Mbukwa-Ngwira, Jenipher; Taneja-Johansson, Shruti; Lynch, Paul; Chatha, Gertrude; Umar, Eric (International Journal of Inclusive Education, 2021)
Covid-19 has led to unparalleled school closures and bought about extraordinary and unique challenges to ensuring continuity of learning for children across countries. This paper focuses on the educational experiences of children with disabilities in Malawi. Using a telephone survey, 99 parents/carers were interviewed about the impact of school closure on them and their child with disabilities. Parents reported as being overwhelmingly dissatisfied with the educational experiences of their child with disabilities, with a significant number reporting that they had no contact with the school or the teachers during closures. Children with disabilities were reported as spending very little time on formal learning activities. Nonetheless, parents were confident that their child with disabilities would return to school once these re-opened, as parents noted the loss of structure for their child’s day and increased loneliness arising from lack of contact with their friends. As schools reopen, the mental health of children with disabilities, alongside their learning, will need to be a priority. Finally, parents highlighted the need for more active involvement in their child’s schooling, so that they are able to support them better when they are at home.
Publisher: Routledge _eprint: https://doi.org/10.1080/13603116.2021.1965804 KerkoCite.ItemAlsoKnownAs: 10.1080/13603116.2021.1965804 2339240:QH5LTGZL 2405685:GDE8Q2X8
Keywords: Covid-19; Malawi; disability; education; parent; telephone survey

Developing a teacher-focused theory of change for technology-enhanced teaching and learning - EdTech Hub Team (2021)
Internal Brief
KerkoCite.ItemAlsoKnownAs: 2405685:2SL6PDSS

Helping families help themselves? Heterogeneous effects of a digital parenting program - Amaral, Sofia; Dinarte Diaz, Lelys; Dominguez, Patricio; Perez-Vincent, Santiago M. (The World Bank, 2021)
Parenting practices are crucial for the development of children’s brains and social skills. However, parenting styles may be far from ideal, particularly those of caregivers with high stress levels. Using an individual-level experiment with male and female caregivers of young children in El Salvador, this paper evaluates the impact of a free digital stress management and positive parenting intervention. The results indicate that, for males, the intervention increased stress and anxiety and lowered caregiver-child interactions.
KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-9850 2339240:EX5ZSVPT 2405685:I2CW3M3E

Rayyan - AI Powered Tool for Systematic Literature Reviews (2021)
Rayyan is an intelligent research collaboration platform that saves you time completing literature reviews and systematic reviews. Intuitive, scalable, fast.
KerkoCite.ItemAlsoKnownAs: 2405685:DFTNNFWJ 2486141:3P8XGBYL
Keywords: _Added-ailr-2024

Ed tech, long overhyped, missed its moment amid COVID-19. What now? - Cheney, Catherine (Devex, 2021)
Devex speaks with the experts about how low-cost education technology might ensure more equitable access to remote learning during the pandemic and in any future disruptions to schooling.
KerkoCite.ItemAlsoKnownAs: 2339240:SA86GYJN 2405685:S289T9JY

Social media tools for educational sustainability in conflict-affected regions - Baytiyeh, Hoda (Education Sciences, 2021)
This conceptual paper demonstrates the potential role of social media in providing students with access to education during emergency situations when schools cannot ensure students’ safety or provide safe learning environments. It is based on conceptual analysis that transforms face-to-face education into a cost-free, online educational environment by relying on social-media learning tools during short-term disruptions caused by violence and conflict. This article proposes a framework that outlines how technology can be used to maintain education in schools during conflicts and emergency situations: cloud computing to access administrative resources and social media tools to maintain teaching/learning resources and student–teacher as well as student–student interactions. The proposed strategy could be greatly beneficial to educational leaders and administrators in regions vulnerable to sectarian conflicts where student safety and the delivery of educational services can become major challenges. This paper contributes to the literature by emphasising the advantages of social media tools for educational delivery in conflict-afflicted regions.
Number: 11 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/educsci11110662 2339240:TJR4F5EU 2405685:NH5QWGZZ
Keywords: disaster risk reduction; educational sustainability; emergency education; sectarian violence; social media tools

Neurodiversity and the social ecology of mental functions - Chapman, Robert (Perspectives on Psychological Science: A Journal of the Association for Psychological Science, 2021)
In psychiatry, mental dysfunction is typically framed in relation to models that seek to be continuous with physiology or evolutionary biology and that compare individual fitness to a broader functional norm. Proponents of the neurodiversity movement, however, challenge the pathologization of minority cognitive styles and argue that we should reframe neurocognitive diversity as a normal and healthy manifestation of biodiversity. Neurodiversity proponents have thus far drawn on social-relational models of disability to challenge the medical model of disability, but they have not developed an alternative functional analysis to replace conceptions of neurological dysfunction or impairment. Here I clarify and defend the neurodiversity perspective by drawing on ecological functional models that take relational contributions to collectives, and group functioning, into account alongside individual functionality. Using the example of autism as well as recent developments in the study of cognitive diversity, I apply these models to human mental functioning and argue that what I call the ecological model has greater utility for research and practice than the leading psychiatric functional analyses of mental functioning.
KerkoCite.ItemAlsoKnownAs: 10.1177/1745691620959833 2339240:Y42DL72T
Keywords: Autistic Disorder; Biological Evolution; Humans; Persons with Disabilities; Psychiatry; Social Environment; health; mental disorder; mental functions; neurodiversity

Understanding Teacher Digital Competence in the Framework of Social Sustainability: A Systematic Review - De la Calle, Ana Maria; Pacheco-Costa, Alejandra; Gomez-Ruiz, Miguel Ángel; Guzman-Simon, Fernando (MDPI Journals, 2021)
Due to the global COVID-19 pandemic, ICT has been urgently introduced in education systems in a generalised manner. In this context, it is essential for teachers to master a spectrum of basic digital competencies and manifest digital leadership in the classroom. In addition, it is necessary to consider the relationship between digital competence development and social sustainability, that is, social and cultural heritage, and to what extent they contribute to improving social cohesion and living conditions in a community. This study presents a systematic review of research on teacher digital competence and social sustainability based on the PRISMA model and a review of 22 studies indexed in SCOPUS. The review reveals that most are intended to measure the digital competence level of teachers, usually in compulsory stages of the educational system and through quantitative studies based on virtual questionnaires comprised of closed-ended questions. However, the studies tend to ignore questions related to social sustainability (access to resources, heritage culture, intergenerational transmission, employability, or gender equality). It is therefore urgent to develop research committed to a sustainable society that is oriented towards social justice.
KerkoCite.ItemAlsoKnownAs: 10.3390/su132313283 2339240:KETKPSD6 2405685:GWCW5FRL

Kenya Partnership Compact. 2021 | Documents | Global Partnership for Education - Global Partnership for Education (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:TZEUP59V 2405685:FABDEDV3

Out-Of-School Children Study Sierra Leone - Government of Sierra Leone; Irish Aid; UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:FUGDDXTR 2405685:8IWQ2ZSL

Policy Guidelines on School Approvals - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ABRJGSC5 2405685:WMH7EW6P

Gender-responsive education in emergency in Nigeria: Safeguarding Girls' Presents and Futures - Ossai, Edem D (Brookings Institution, 2021)
This policy brief highlights ways that a gender-responsive perspective can be fully incorporated into planning, policy design, and implementation models for education in emergencies (EiE) in Nigeria, so that governments and education stakeholders can ensure that girls, like boys, can continue learning in times of crisis.
KerkoCite.ItemAlsoKnownAs: 2339240:5S7KQM66 2405685:ZMSKJPQP

Mapping education data in sub-Saharan Africa: Our experience from the Unlocking Data campaign and Sierra Leone - Unlocking Data (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:HAKTFJKU 2405685:YPE9D2W3

World Bank: pandemic threatens to drive unprecedented number of children into learning poverty - World Bank (2021)
World Bank: Pandemic Threatens to Drive Unprecedented Number of Children into Learning Poverty
KerkoCite.ItemAlsoKnownAs: 2339240:FD3S4QP4 2405685:WECGJJ5S

Global emergency remote education in secondary schools during the COVID-19 pandemic: A systematic review - Bond, Melissa; Bergdahl, Nina; Mendizabal-Espinosa, Rosa; Kneale, Dylan; Bolan, Faye; Hull, Poppy; Ramadani, Fjolla (International Public Policy Observatory, 2021)
The worldwide shift to emergency remote education in 2020 as a result of the COVID-19 pandemic impacted billions of students and teachers. A range of teaching and learning strategies were employed by schools as a result, despite confusing and sometimes contradictory government guidance, with systemic issues such as equity and access impacting heavily on disadvantaged students. In light of the findings of a recent IPPO evidence snapshot and roundtable event, and in order to gain further insight into how emergency remote education was experienced by secondary school students, parents and educators, a systematic review was conducted that collates and synthesises primary empirical studies across five key research questions focusing on student engagement, online assessment, peer collaboration, parent engagement, and future directions for online learning. Studies were searched for in May 2021 using Web of Science, Scopus, ERIC, Microsoft Academic Graph, ResearchGate and the COVID-19 living map, and were included if they focused on teaching and learning using blended or online approaches in secondary schools during the pandemic, that were published in English. Following quality assessment on scope and methodological rigour, 81 studies were included for narrative synthesis. The research studies were conducted in 38 countries, with 37% of studies from low or lower-middle income countries, and 63% from upper-middle income or high-income countries. Most of the evidence came from students (64%), followed by teachers (53%), with very few studies exploring the perceptions and experiences of parents (6%) or school leaders (5%). Findings reveal that self-regulation and understanding were the most frequently reported indicators of student engagement, with online assessment tools, learning management systems with collaborative tools, live synchronous lessons with peer and teacher interaction, and teacher-made videos considered particularly engaging. Social isolation was the most frequently reported indicator of disengagement, characterised by poor attendance in live lessons, a lack of opportunities to seek help with challenges and difficulties facilitating peer collaboration. Although many articles reported that assessment online was particularly challenging, 21 different types of online assessments strategies were identified, with online quizzes and formative online feedback the most frequently used. Live marking or recorded feedback and assessment were found to be particularly beneficial, as providing feedback during live lessons was sometimes challenging. Peer collaboration was facilitated through peer assessment, inquiry-based group work and experiments, aided by the use of collaborative software and combining multiple applications. Parental involvement and support contributed to student learning, although issues of equity impacted the extent to which they could engage with their children's learning, alongside gaps in family content knowledge and technological skills. Numerous implications for future policy relating to online and blended learning are provided.
KerkoCite.ItemAlsoKnownAs: 2339240:2E8EYFJA 2405685:JNJ5HLG9

Pakistan - Data Protection Overview - Rehman, Shafaq (DataGuidance, 2021)
October 2021 INTRODUCTION Pakistan does not have any extensive data protection legislation in place that specifically regulates matters in connection with the processing of personal data. The Prevention of Electronic Crimes Act, 2016 ('PECA') is currently the primary legislation that provides a legal framework in relation to various kinds of electronic crimes and also extends to the unauthorised access to personal data.
KerkoCite.ItemAlsoKnownAs: 2339240:XWWK2XCE 2405685:VLSFBU3F

New drive launched to get 250,000 out-of-school children back to class in 16 counties - UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:6RX7TX9N 2405685:CY6AHZ2A

EdTech in Sierra Leone: Reimagining education for continuous learning and teaching - Sengeh, David Moinina (Global Partnership for Education, 2021)
Read how the government of Sierra Leone is using technology to address the profound ongoing teaching and learning crisis, and deliver inclusive, quality education.
KerkoCite.ItemAlsoKnownAs: 2339240:IH3IUFW4 2405685:PDME63H4

Wonders of the world: NVIDIA emerging chapters program spurs AI innovation across developing countries - Kallot, Kate (NVIDIA Blog, 2021)
The new program supports local communities in emerging markets to build and scale their AI, data science and graphics projects.
KerkoCite.ItemAlsoKnownAs: 2405685:9CZPR8F8

FCDO - GEC - Belfield, Sophie; Mathur, Meenu; Caine, Ellie (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:83NFRUKM 2405685:KL5VN6CJ

Using learning profiles to inform education priorities: An editors’ overview of the Special Issue - Crouch, Luis; Kaffenberger, Michelle; Savage, Laura (International Journal of Educational Development, 2021)
This special issue explores the use of learning profiles for analysing the dynamics of low learning in low- and middle-income countries and informing priorities to address the learning crisis. The 12 papers in the special issue draw on learning data from more than 50 countries and 6 million individuals, with implications for education policy and practice. Taken together, they point to a need to steepen learning trajectories by prioritizing early mastery of foundational skills for all children. The papers show that addressing the learning crisis will not be achieved through more school grade attainment alone, nor through within-country equality across groups (such as girls and boys or rich and poor). Positive examples show that programs focused on foundational learning both improved average learning and reduced inequality. Addressing the learning crisis will require a focus on systems improvement, using foundational learning as a case in point for making the needed systems improvements to steepen learning throughout children’s time in school. Learning profiles can provide a guide for education actors aiming to improve learning outcomes.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2021.102477 2339240:URQN9N62 2405685:XXLGUC8W
Keywords: Education systems; Foundational skills; Inequality; Learning crisis; Learning profiles

COVID-19 learning losses: Early grade reading in South Africa - Ardington, Cally; Wills, Gabrielle; Kotze, Janeli (International Journal of Educational Development, 2021)
• In South Africa in 2020 around 60 % of early grade school days were lost due to COVID. • Grade 2 students have reading losses of between 57 % and 70 % of a year of learning. • Grade 4 students have reading losses of between 62 % and 81 % of a year of learning. • These losses imply learning to schooling loss ratios in the region of 1–1.4. • Students with stronger initial reading proficiency are more negatively impacted. Using three different studies on early grade reading from no-fee schools across in South Africa, this paper establishes short-term learning losses in reading for grade 2 and 4 students from under-resourced school contexts. We find that in 2020 grade 2 students lost between 57 % and 70 % of a year of learning relative to their pre-pandemic peers. Among a grade 4 sample, learning losses are estimated at between 62 % and 81 % of a year of learning. Considering that in 2020 students in the samples lost between 56 %–60 % of contact teaching days due to school closures and rotational timetabling schedules compared to a pre-pandemic year, this implies learning to schooling loss ratios in the region of 1–1.4. There is some evidence from the grade 4 sample that the reading trajectories of children benefiting more from attending school pre-pandemic – namely girls and children with stronger initial reading proficiency - are more negatively impacted. Mitigating the long-run implications of these learning losses will require a significant pivoting of the education system to ensure that instructional practices are appropriately levelled to optimise learning.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2021.102480 2339240:3AG6DC4Z 2405685:UZD3F4EQ
Keywords: BEGINNING reading; COVID-19; COVID-19 pandemic; Early grade reading; Learning losses; READING (Preschool); READING ability testing; SCHOOL closings; School closure

Educational technology in Abu Dhabi public schools: Teaching with interactive whiteboards (IWBs) - Samsonova, Olga (International Journal of Technology Enhanced Learning, 2021)
PDF | The main purpose of this study was to evaluate Abu Dhabi public school teachers' perceptions of interactive whiteboards (IWBs) and find out how... | Find, read and cite all the research you need on ResearchGate
KerkoCite.ItemAlsoKnownAs: 10.1504/IJTEL.2021.10032781 2339240:UKKS96JA 2405685:B399BE5G

ClassRoute: An English to Punjabi Educational Video Translation Pipeline for Supporting Punjabi Mother-Tongue Education - Shaghaghi, Navid; Ghosh, Smita; Kapoor, Raghav (2021 IEEE Global Humanitarian Technology Conference (GHTC), 2021)
Information Communication Technology (ICT) permeates almost every aspect of our daily lives and has become one of the most important priorities for formal and informal education. However, many people particularly those in least developed countries, are unable to reap the benefits due to lack of access to ICT but also due to lack of access to quality educational material. Additionally, in Punjab India, due to a shortage of resources and lack of infrastructure, the education system suffers from massive gaps including high student to teacher ratios, shortage of qualified teachers, and poor teacher training programs. This all has also been further exacerbated due to the COVID19 Pandemic as schools shut down globally and all teaching/learning activities moved online where possible or were canceled otherwise. In an effort to help relieve some of the burden on the Punjabi education system, and motivated by the proven efficiency of mother-tongue based education as well as the importance of visual-based learning, this paper introduces a pipeline for translating English educational videos into Punjabi equivalents which seeks to go beyond simple translation and in future iterations take into consideration the cultural needs of the learners in order to better connect them with the topics being taught. This pipeline is among a series of under construction pipelines aimed at translating English educational videos into other languages, dubbed as ClassRoute.
ISSN: 2377-6919 KerkoCite.ItemAlsoKnownAs: 10.1109/GHTC53159.2021.9612485 2405685:S27BBK9U 4042040:GWNJB5CP
Keywords: Bridging the Digital Divide; Education; Education Technology (EdTech); Humanitarian Information Communications Technology (ICT); Language Translation; Natural Language Processing (NLP); Pandemics; Pipelines; Quality Education; Semantics; Tongue; Tools; Training

Situation analysis on the effects of and responses to COVID-19 on the education sector in Asia - UNICEF ROSA; UNICEF EAPRO; UNESCO Bangkok; Cambridge Education (UNICEF, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:X4I7DTV2 2405685:8K3IJB8S

Situation Analysis on the Effects of and Responses to COVID-19 on the Education Sector in Asia: Regional Synthesis Report - UNICEF; UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:JSNQQLQJ 2405685:NWEZS22I
Keywords: ⛔ No INSPIRE recid found

Poverty and Equity Brief: Pakistan - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:B7JZ5PAL 2405685:HWGIHZ4M

Educational Technology: How Important Is It In Today's Education Industry? - Lim, Alexander (eLearning Industry, 2021)
Technological advancement has impacted a lot on education. Find out the 7 most common benefits of educational technology!
KerkoCite.ItemAlsoKnownAs: 2339240:I6IJMXVZ 2405685:79G9FM7F

Parental support to learning - UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:SZK6LQAP 2405685:LT2IJ8XM

Perceived Efficacy of e-Proctoring Software for Emergency Remote Online Based Assessment: Perceptions of Proctored Examinations - Ironsi, Chinaza (EDEN Conference Proceedings, 2021)
The switch from traditional teaching methods to emergency remote online learning as a result of the outbreak of COVID-19 necessitated a change in approaches to measurement and evaluation in our educational system. A lot of methods were adopted yet the need for credible, properly monitored, valid and reliable assessment continues to be an issue of debate. E-proctoring as a popular strategy for monitoring and administering online-based examinations has witnessed tremendous success over the years yet ethical issues and many more are yet to be extensively examined. While a teacher may embrace the use of this software for monitoring examination, the perception of preservice teachers has not been explored adequately, much more the opinions of the instructors and preservice teachers on the level of efficacy with regards to the use of e-proctoring strategy for monitoring online-based examinations in a hybrid/emergency remote online educational model has not been investigated. It is in this light that this study intends to examine the perceptions of instructors and preservice teachers on the use of e-proctoring devices during online-based assessments, two research questions were investigated through a quantitative research design. A structured questionnaire was used to elicit information from 40 participants comprising of 36 students and 4 teachers on their perceptions of the effectiveness and efficacy of the e-proctored software while administering and monitoring examinations. Findings from the study will be beneficial in drawing valid conclusions on the use of e-proctored devices in monitoring emergency remote online-based assessment. The conclusions will prepare school administrators and equip them with the possible approaches to adopt in ensuring that a credible valid and reliable evaluation process is conducted during the post-COVID 19 semesters.
Number: 1 KerkoCite.ItemAlsoKnownAs: 10.38069/edenconf-2021-ac0026 2339240:7UAR7MC2 2405685:9NMH5XJQ

Online Course Satisfaction in a Holistic Flipped Classroom Approach - Ilic, Ulaş (Journal of Educational Technology and Online Learning, 2021)
The present study aimed to investigate the satisfaction of pre-service teachers with the completely online course instructed with the flipped classroom model. The study was conducted with the explanatory sequential mixed design. The participants included 117 pre-service teachers. Data were collected during the 2020-2021 academic year fall semester with the Online Course Satisfaction Scale and face-to-face interviews. The study findings demonstrated that the pre-service teachers were satisfied with the online course. The satisfaction level of female participants was higher, and the differences were not significant based on the student department. On the other hand, the participants stated that there were systemic and instructor-oriented problems. Furthermore, it was determined that ease of use was an important factor in predicting satisfaction. Ease of use varied based on PC ownership, but not based on tablet ownership. Satisfaction did not differ based on both PC and tablet ownership. It was found that the flipped classroom model exhibited interactional challenges. However, the model had advantages due to its structure that allowed flexibility. It could be suggested that the findings of the present study would contribute to future studies that would address flipped classroom method and satisfaction with online courses.
KerkoCite.ItemAlsoKnownAs: 10.31681/jetol.935325 2339240:XJ8SSCBR 2405685:FXMJU98K

Reimagining Education for Continuous Learning and Teaching - Sengeh, Hon Minister David Moinina; Team, MBSSE Delivery; Team, Hon Minister David Moinina Sengeh and MBSSE Delivery (EdTech Hub, 2021)
EdTech Hub has partnered with the Ministry of Basic and Senior Secondary Education in Sierra Leone to increase the use of evidence in decisions around EdTech. Click to read more.
KerkoCite.ItemAlsoKnownAs: 2339240:6JKPNDHR 2405685:SQ7GPXQJ

Education in Emergencies, Mental Wellbeing and E-Learning - Shohel, M. Mahruf C.; Mahmud, Arif; Urmee, Munira Azhar; Anwar, Muhammad Naveed; Rahman, Mohammad Mojibur; Acharya, Dev Raj; Ashrafuzzaman, Md; Shohel, M. Mahruf C.; Mahmud, Arif; Urmee, Munira Azhar; Anwar, Muhammad Naveed; Rahman, Mohammad Mojibur; et al. (IntechOpen, 2021)
The world has been going through an unprecedented situation due to the world-wide health crisis created by the COVID-19 pandemic. It affected all sectors across the globe, including education. This chapter highlights the importance of education in emergencies and how a situation like the COVID-19 pandemic creates challenges alongside opportunities to learn for personal and professional development as well as to ensure mental wellbeing of individuals through e-learning. The chapter explores literature to draw on different perspectives regarding the issues related to effectiveness in handling education and learning in an emergency in addition to preparedness for post and future emergencies. However, it focuses mainly on the role of the education sector in supporting individuals, especially learners and educators during and after emergencies. It also reflects on educational professionals’ work with students during this pandemic i.e. how educational professionals report on their adaptation journey and how the pandemic impacted the ability to serve and engage learners. From the professionals’ best practices to assist students in being successful through online education or hybrid teaching and learning formats, many opportunities arose to shape and reform education for a better future and transform the process of lifelong learning. This chapter outlines strategies, in general, for the education sector, and in particular, institutions and individuals to be better prepared for future emergencies through the opportunities e-learning offers.
Publication Title: E-Learning and Digital Education in the Twenty-First Century KerkoCite.ItemAlsoKnownAs: 10.5772/intechopen.97425 2339240:B2NKF79D 2405685:MVSKZIW2

Transition to online learning by a teacher education program with limited 4IR affordances - Tsakeni, Maria (Research in Social Sciences and Technology, 2021)
This study used the community of inquiry (CoI) framework and the affordances of Internet of things (IoT) to explore how the faculty of education of a rural campus of a university transitioned from face-to-face to online modes of instruction. In this qualitative interpretive study, data were collected through open-ended questionnaires from four purposely selected teacher educators and five final-year bachelor of education preservice teachers. Thematic content analysis techniques were used to analyze the data collected. The findings indicated the tensions experienced by the teacher educators as they negotiated the limited IoT affordances to ensure effective teaching, cognitive, and social presence in the newly formed online classrooms. Some of the tensions included the choices that were made on whether to use synchronous or asynchronous modes of instruction and the selection of effective communication modes. The teacher educators used a combination of the official learning management system (LMS) tools of the university and a social media platform as way of navigating the limited 4IR environments experienced by the preservice teachers.
Number: 2 KerkoCite.ItemAlsoKnownAs: 10.46303/ressat.2021.15 2339240:M4H98T8W 2405685:FMGDCFMJ
Keywords: COVID-19; Internet of things; community of inquiry; online learning; teacher education

Measuring poverty in Timor-Leste: Using census data to develop a national Multidimensional Poverty Index - Jendrissek, Dan (Asia-Pacific Sustainable Development Journal, 2021)
0 citations (Crossref) [2024-03-22] KerkoCite.ItemAlsoKnownAs: 10.18356/26178419-28-1-1 2339240:KZ4VCC7L 2405685:GE3ZYFNH
Keywords: ⛔ No INSPIRE recid found

Emergency remote teaching during COVID19: The role of teachers’ online community of practice (CoP) in times of crisis - Ulla, Mark B.; Perales, William F. (Journal of Interactive Media in Education, 2021)
While previous studies in the literature may have used the concept of a community of practice (CoP) to investigate its role for teachers’ professional development, this study identifies the role of a teachers’ CoP in navigating the challenges in online/remote teaching faced by six teachers of English as a foreign language (EFL) in a university in Thailand during the COVID19 pandemic. This study employed a purposive-convenience sampling method with an individual online interview to gather qualitative data. Findings revealed that although teacher-participants pointed out the lack of students’ interaction, lack of time to do assessment and feedback, and the lack of students’ concentration in online teaching, they greatly acknowledged the role of the teachers’ CoP in navigating the demands and challenges of online teaching during the pandemic. Some of the ascribed roles of the teachers’ CoP in online teaching include; a support group, a source of solutions to online teaching issues, and a learning community. Implications are discussed and suggestions for future studies are offered.
KerkoCite.ItemAlsoKnownAs: 10.5334/jime.617 2339240:DEHH5VVW 2405685:JDIKNP9W

What Explains Vietnam’s Exceptional Performance in Education Relative to Other Countries? Analysis of the Young Lives Data from Ethiopia, Peru, India and Vietnam - Glewwe, P.; James, Z.; Lee, J.; Rolleston, C.; Vu, K. (2021)
Vietnam’s strong performance on the 2012 and 2015 PISA assessments has led to interest in what explains the strong academic performance of Vietnamese students. Analysis of the PISA data has not shed much light on this issue. This paper analyses a much richer data set, the Young Lives data for Ethiopia, India (Andhra Pradesh and Telangana), Peru and Vietnam, to investigate the reasons for the strong academic performance of 15-year-olds in Vietnam. Differences in observed child and household characteristics explain 37-39 percent of the gap between Vietnam, and Ethiopia, while observed school variables explain only about 3-4 additional percentage points (although an important variable, math teachers’ pedagogical skills, is not available for Ethiopia). Differences in observed child and household characteristics explain very little of the gaps between Vietnam and India and between Vietnam and Peru, yet one observed school variable has a large explanatory effect: primary school math teachers’ pedagogical skills. It explains about 10-12 percent of the gap between Vietnam and India, raising the overall explained portion to 14-21 percent of the gap. For Peru, it explains most (65-84 percent) of the gap.
KerkoCite.ItemAlsoKnownAs: 10.35489/BSG-RISE-WP_2021/078 2339240:D6LBZ8BL 2405685:V7SA8NJA

Kenya lauded for achieving 75% electricity access rate - Common Market for Eastern and Southern Africa (COMESA) (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:LE4N8QYZ 2405685:4RF5ZB4L

17 EdTech Frameworks and Who Needs to Know Them - Bapna, Akanksha; Nicolai, Susan; Myers, Christina; Pellini, Arnaldo; Sharma, Namrata; Wilson, Sam; Wilson, Susan Nicolai, Christina Myers, Arnaldo Pellini, Namrata Sharma and Sam, Akanksha Bapna (EdTech Hub, 2021)
17 EdTech frameworks that provide a valuable bridge between theory and practice. EdTech resources for policy-makers, educational institutions, teachers and multi-stakeholders.
KerkoCite.ItemAlsoKnownAs: 2339240:ZT8D763J 2405685:9TG8YM2I

Intergenerational transmission of lockdown consequences: prognosis of the longer-run persistence of COVID-19 in Latin America - Neidhöfer, Guido; Lustig, Nora; Tommasi, Mariano (The Journal of Economic Inequality, 2021)
The shock on human capital caused by COVID-19 is likely to have long lasting consequences, especially for children of low-educated families. Applying a counterfactual exercise we project the effects of school closures and other lockdown policies on the intergenerational persistence of education in 17 Latin American countries. First, we retrieve detailed information on school lockdowns and on the policies enacted to support education from home in each country. Then, we use these information to estimate the potential impact of the pandemic on schooling, high school completion, and intergenerational associations. In addition, we account for educational disruptions related to household income shocks. Our findings show that, despite that mitigation policies were able to partly reduce instructional losses in some countries, the educational attainment of the most vulnerable could be seriously affected. In particular, the likelihood of children from low educated families to attain a secondary schooling degree could fall substantially.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10888-021-09501-x 2339240:WXRB3PSQ 2405685:DI7L98CJ
Keywords: COVID-19; Education; Human capital; I24; I38; Inequality; Intergenerational persistence; J62; Latin America; Lockdowns; School closures

Intergenerational transmission of lockdown consequences: prognosis of the longer-run persistence of COVID-19 in Latin America - Neidhöfer, Guido; Lustig, Nora; Tommasi, Mariano (The Journal of Economic Inequality, 2021)
The shock on human capital caused by COVID-19 is likely to have long lasting consequences, especially for children of low-educated families. Applying a counterfactual exercise we project the effects of school closures and other lockdown policies on the intergenerational persistence of education in 17 Latin American countries. First, we retrieve detailed information on school lockdowns and on the policies enacted to support education from home in each country. Then, we use these information to estimate the potential impact of the pandemic on schooling, high school completion, and intergenerational associations. In addition, we account for educational disruptions related to household income shocks. Our findings show that, despite that mitigation policies were able to partly reduce instructional losses in some countries, the educational attainment of the most vulnerable could be seriously affected. In particular, the likelihood of children from low educated families to attain a secondary schooling degree could fall substantially.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10888-021-09501-x 2339240:WXRB3PSQ 2405685:DI7L98CJ
Keywords: COVID-19; Education; Human capital; I24; I38; Inequality; Intergenerational persistence; J62; Latin America; Lockdowns; School closures

Ed-tech within limits: Anticipating educational technology in times of environmental crisis - Selwyn, Neil (E-Learning and Digital Media, 2021)
Despite climate heating and rising ecological instability, environmental issues feature rarely in discussions of educational technology. Most commentators presume the continued unfettered use of digital education resources bolstered by occasional claims that emerging technologies might support the ‘greening’ of school and university provision. In contrast to such business-as-usual complacency, this article anticipates ongoing environmental degradation of the planet as radically upending the continued expansion of digital technologies in education. On the one hand, depletion of natural resources and energy curtailments might put paid to established ‘abundant’ forms of digital technology use. On the other hand, more frequent climate-related disasters might necessitate emergency forms of education for displaced and unsettled populations. As such, the article argues for a new paradigm of educational technology that is both wholly sustainable and targeted towards displaced and disadvantaged populations. The article considers a number of ways that such an ‘Ed-Tech Within Limits’ might be pursued – outlining fundamental shifts in thinking necessary to reorient educational technology along environmentally concerned lines.
Publisher: SAGE Publications KerkoCite.ItemAlsoKnownAs: 10.1177/20427530211022951 2339240:U4D6A632 2405685:7JJ9CIWZ

Ed-Tech Within Limits: Anticipating educational technology in times of environmental crisis - Selwyn, Neil (E-Learning and Digital Media, 2021)
Despite climate heating and rising ecological instability, environmental issues feature rarely in discussions of educational technology. Most commentators presume the continued unfettered use of digital education resources bolstered by occasional claims that emerging technologies might support the ?greening? of school and university provision. In contrast to such business-as-usual complacency, this article anticipates ongoing environmental degradation of the planet as radically upending the continued expansion of digital technologies in education. On the one hand, depletion of natural resources and energy curtailments might put paid to established ?abundant? forms of digital technology use. On the other hand, more frequent climate-related disasters might necessitate emergency forms of education for displaced and unsettled populations. As such, the article argues for a new paradigm of educational technology that is both wholly sustainable and targeted towards displaced and disadvantaged populations. The article considers a number of ways that such an ?Ed-Tech Within Limits? might be pursued ? outlining fundamental shifts in thinking necessary to reorient educational technology along environmentally concerned lines.
Publisher: SAGE Publications KerkoCite.ItemAlsoKnownAs: 10.1177/20427530211022951 2339240:IAI4JMQG 2405685:8GL436EN

Nudging in education: from theory towards guidelines for successful implementation - Weijers, Robert J.; de Koning, Björn B.; Paas, Fred (European Journal of Psychology of Education, 2021)
Nudging is one of the strategies from behavioral economics that aims to influence behavior by changing the environment. We propose that it could also be a valuable means to influence behavior in educational contexts. However, implementation of nudging in education is yet sparse. We describe the relevant issues to consider when applying nudging in education, arguing that a focus on the long-term effects and underlying processes of a nudge is necessary for successful implementation. Then, we aim to facilitate this implementation of nudging in education by making a distinction between nudges that is relevant for overcoming these issues. Based on the framework proposed by Hansen and Jespersen (European Journal of Risk Regulation, 4(1), 3–28, 2013), we distinguish between Type 1 and Type 2 nudges, and transparent and non-transparent nudges, resulting in four nudge categories. For each of these nudge categories, we determine its suitability for different educational goals. The resulting decision matrix can help researchers and practitioners when designing nudges for an educational context.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10212-020-00495-0 2339240:E6XK7JIR 2405685:RC3MYCEA
Keywords: Educational psychology; Instructional support; Learning behavior; Nudging; Teaching strategies

Teaching and Testing by Phone in a Pandemic - Crawfurd, Lee; Evans, David K.; Hares, Susannah; Sandefur, Justin (Center for Global Development, 2021)
How did children learn while schools were closed during 2020 due to the COVID-19 pandemic? In this paper we evaluate the effectiveness of live tutoring calls from teachers, using a randomized controlled trial with 4,399 primary school students in Sierra Leone.
KerkoCite.ItemAlsoKnownAs: 2339240:474HKXRJ 2339240:FTSVR76S 2339240:GAPVTT3N 2339240:K9KUNITI 2405685:5RJW9S5N 2405685:7AP7H3CG 2405685:DTZ6IE85 2405685:H3J9AJ2Z 2405685:KW3QGYS5 2534379:ZTWPMXUG
Keywords: ___working_potential_duplicate

Where is EdTech working? Leveraging data for better EdTech policies - Marin, Sergio Venegas; Cobo, Cristobal; Cloutier, Marie-Helene; Lambert-Porter, Emma (Where is EdTech working? Leveraging data for better EdTech policies, 2021)
The COVID-19 pandemic has disrupted schooling for over 1.6 billion students worldwide. Many education systems fell short of their goal to ensure the continuity of learning due to the digital divide that kept many without access to any kind of remote learning opportunity.
KerkoCite.ItemAlsoKnownAs: 2339240:ERJ4KFAX 2405685:463WE282

An analysis of the reach and effectiveness of distance learning in India during school closures due to COVID-19 - van Cappelle, Frank; Chopra, Vidur; Ackers, Jim; Gochyyev, Perman (International Journal of Educational Development, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2021.102439 2339240:RRVFL86Y 2405685:L6WAUQMA

Connecting Learning Spaces: Possibilities for Hybrid Learning - Working Group on Digital Learning (Broadband Commission for Sustainable Development, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:B6YJG67Z 2405685:HB5PH6ML

Development of a mobile app to improve numeracy skills of children with autism spectrum disorder: Participatory design and usability study - Ntalindwa, Theoneste; Nduwingoma, Mathias; Karangwa, Evariste; Rashid Soron, Tanjir; Uworwabayeho, Alphonse; Uwineza, Annette (JMIR Pediatr Parent, 2021)
Background: The use of information and communication technologies is transforming the lives of millions of people including children with autism spectrum disorder (ASD). However, the process of developing a user-friendly and effective mobile app needs to follow a complex standard protocol and culture-sensitive customization, and involves multiple sectors. This complex work becomes even more challenging when considering children with ASD in low- and middle-income countries as the users. Objective: This study aimed to design and develop a more intuitive mobile app to improve numeracy skills of children with ASD in Rwanda and evaluate the usability of the app. Methods: A participatory design approach was utilized in this study in which 40 children with ASD, 5 teachers, and 10 parents of children with ASD participated in focus group discussions (FGDs) and usability testing. A narrative literature review was performed to explore existing mobile apps and compare previous studies to design the questions for FGD and facilitate a framework for designing the app. The agile methodology was used to develop the mobile app, and the heuristics evaluation method was used to test and evaluate the usability of the initial version of the app to improve its functionalities. The interviews were recorded, transcribed, and analyzed following the guidelines of the qualitative narrative analysis (QNA) method. Results: During the FGDs the respondents shared their need for a mobile app in teaching and learning numeracy for children with ASD and pointed to possibilities of integrating the mobile app into existing curriculum. Ten themes emerged from the FGDs and exercise of developing the mobile app. The themes were related to (1) teaching and learning numeracy for children with ASD, (2) planning and development of a mobile app for a person with ASD, (3) testing a mobile app, (4) strength of the developed app against the existing ones, (5) behavioral maintenance and relapse prevention, (6) possibilities to integrate the mobile app into the existing curriculum, (7) data protection for users, (8) social implications, (9) challenges in Rwanda, and (10) focus on future. Conclusions: The community plays an important role in the planning, development, and evaluation of a mobile app for children with ASD. In this study, inputs from teachers and parents resulted in an optimally designed mobile app that can improve numeracy skills in children diagnosed with ASD to support the implementation of competency-based curriculum in Rwanda.
KerkoCite.ItemAlsoKnownAs: 10.2196/21471 2339240:BBJFJG68 2405685:QYR6FYRS
Keywords: autism spectrum disorder; education; information and communication technologies; learning; mathematics; mobile app; numeracy

Projetos de inclusão digital na educação em Angola: avanços e recuos - Barbante, Cesário José Sanajmbo (Revista Brasileira de Estudos Africanos, 2021)
The inclusion of technology in education in Angola marks yet another moment of transition in the Education and Teaching System, with the integration of new digital tools that have provided a new use, new learning and management standards for administrative processes. The study presented in this document aims to reflect on the digital inclusion initiatives in education in Angola, mainly in basic education. Contextualized in the domain of the inclusion of information and communication technologies in Angolan schools and focused, in particular, on existing projects, this study is part of an empirical approach of a qualitative nature, assuming a descriptive investigation. In comparative terms, the Escola Meu Kamba Project was the most solid, due to the fact that it had direct financial coverage from the State; the ProFuturo Project was the most innovative when using mobile and tactile devices, in addition to having an alternative power supply to the public network; and, finally, the E-Net project was the one that had contributed the most to Internet access by the school community. On the other hand, there are regrets about the discontinuities of both projects.
Number: 11 KerkoCite.ItemAlsoKnownAs: 10.22456/2448-3923.104401 2339240:ZSR8MEIA 2405685:HDMKHXTG
Keywords: Ensino de base.; inclusão digital na educação; projetos tecnológicos

Reimagining Teacher Professional Development for Scalable, Sustainable and Equitable Outcomes - Using EdTech Research Evidence - Hennessy, Sara; Koomar, Saalim (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:8NPXTAKN

Exploring EFL teachers’ professional identity development in a CALL teacher preparation program - Meihami, Hussein; Esfandiari, Rajab (The JALT CALL Journal, 2021)
KerkoCite.ItemAlsoKnownAs: 10.29140/jaltcall.v17n2.404 2339240:W2D7U4LI 2405685:KX4C93E2

Intergovernmental fiscal transfers, equity and service delivery: lessons from Uganda - Long, Cathal; Fraser, Alasdair; Mbate, Michael; Lacroix, Antoine (ODI: Think change, 2021)
Analysing the equity of government fiscal resource allocation
KerkoCite.ItemAlsoKnownAs: 2339240:ZR6FLK9A 2405685:BGCRN4D3 4656463:6IGGVE36

First day of school 'indefinitely postponed' for 140 million first-time students around the world - UNICEF - UNICEF (2021)
At least eight million of these young learners have been waiting for over a year
KerkoCite.ItemAlsoKnownAs: 2339240:NUQ9QBE3 2405685:JAQTAKT4 2405685:WMXY3AMI

Scaling Personalised Learning Technology in Malawi - Schmitt, Laurel (EdTech Hub, 2021)
Want to know more about the lessons we learnt from our sandbox with onebillion? Read our blog, Scaling personalized learning technology in Malawi.
KerkoCite.ItemAlsoKnownAs: 2339240:KWP37J8V 2339240:QWF5YPUM 2405685:3JNLR2A9 2405685:PMDAD9XJ

Scaling Personalised Learning Technology in Malawi: Lessons from our sandbox with onebillion - Schmitt, Laurel (EdTech Hub, 2021)
Want to know more about the lessons we learnt from our sandbox with onebillion? Read our blog, Scaling personalized learning technology in Malawi.
KerkoCite.ItemAlsoKnownAs: 2339240:YWIIWQ2X 2405685:ZBHGFZXD

Enhancing Teaching Recovery Techniques (TRT) with parenting skills: RCT of TRT + parenting with trauma-affected Syrian refugees in Lebanon utilising remote training with implications for insecure contexts and COVID-19 - El-Khani, Aala; Cartwright, Kim; Maalouf, Wadih; Haar, Karin; Zehra, Nosheen; Çokamay-Yılmaz, Gökçe; Calam, Rachel (International Journal of Environmental Research and Public Health, 2021)
Child psychosocial recovery interventions in humanitarian contexts often overlook the significant effect that caregivers can have on improving children's future trajectory. We enhanced the well-established, evidenced-based child trauma recovery programme Teaching Recovery Techniques (TRT) intervention with parenting sessions, i.e., TRT + Parenting (TRT + P), which aims to improve parent mental health and their ability to support their children's mental health. We describe the findings of a three-arm randomised controlled trial comparing enhanced TRT + P vs. TRT and waitlist. The primary aim was to test if children in the enhanced arm of the programme show improved child and caregiver mental health. We recruited 119 Syrian refugee children and one of their caregivers in Beqaa Valley in Lebanon. They were randomised to the TRT, TRT + P, or waitlist control group. Data were collected at baseline and 2 weeks and 12 weeks post intervention. Training of facilitators was via remote training from the United Kingdom. Results showed a highly consistent pattern, with children in the enhanced TRT + P group showing the greatest levels of improvement in behavioural and emotional difficulties compared to children in the TRT or waitlist control groups. Caregivers in the TRT + P group also reported significant reductions in depression, anxiety, and stress. Findings indicate that the addition of the evidence-based parenting skills components has the potential to enhance the effects of interventions designed to improve children's mental health in contexts of trauma, conflict, and displacement. Implications for COVID-19 remote learning are also discussed.
KerkoCite.ItemAlsoKnownAs: 10.3390/ijerph18168652 2405685:GILUY59Y
Keywords: COVID-19; Child; Humans; Lebanon; Parenting; Refugees; SARS-CoV-2; Syria; conflict; displaced population; family skills; parenting; refugee; war

Schooling, interrupted: a critical account of motivation and education during the first wave of the COVID-19 pandemic in Quebec - Thompson, Jennifer; Fraser, Sarah; Archambault, Isabelle; Beauregard, Nancy; Dupéré, Véronique; Frohlich, Katherine (Journal of Teaching and Learning, 2021)
Among the concerns about youth wellbeing during the COVID-19 pandemic, one well-documented impact is youth motivation, particularly in relation to schooling. Yet many questions remain: How are youth experiencing motivation? What factors affect their motivation? How are youth differentially experiencing motivation? This article addresses young people’s experiences of motivation during the first wave of the pandemic as explored through participatory visual research. In Spring 2020, the Quebec private and public secondary school systems responded very differently to school closures. Private schools pivoted to distance learning within about two weeks, whereas public schools took almost two months to provide formal instruction. Bringing youth’s accounts of motivation into conversation with youth’s concerns about the inequities across the private and public school systems offers a rich opportunity to revisit Self-Determination Theory as an established theory of motivation. Youth’s analyses urge us to revisit the conceptualization of “structure” within this theory and how structure might offer a junction for accounting for more macrostructural inequalities within motivation research.
KerkoCite.ItemAlsoKnownAs: 10.22329/jtl.v15i2.6722 2339240:YNB9HL6M 2405685:IZXQTPC9

A Framework to Democratise the Design of Educational Games on Social Issues during Game Jams - Myers, Christina (The Open University, 2021)
Game Jams are events organised to create computer games, usually taking place during weekends. These events have become a popular way to enable participants to experience processes and practices of game development as well as to offer multidisciplinary learning opportunities, accessed through the variety of skills involved in game design. However, these events tend to be attended predominantly by male game developers and present barriers to participation for more diverse groups. This thesis investigates how to support diverse group participation in Game Jams, including people from different ethnicities, genders, ages, sexual orientations and who do not have any prior experience of designing games; and explores Game Jam participation as an opportunity to discuss social issues. To this end, a framework to democratise the design of educational games on social issues in Game Jams is proposed. The framework consists of a process with structured resources and activities to enhance learning by supporting egalitarian participation and agency. It offers collaborative learning opportunities for groups to engage with a social issue, relying on storytelling and on the exchange of perspectives and experiences. It also provides support and access to research-based principles to design games for education, and egalitarian opportunities to acquire game development skills, considered relevant opportunities given the wide-spread use of games and increasing interest in games as engaging tools for online education. The development of the framework is grounded in Critical Pedagogy, an educational approach providing principles and processes to democratise learning initiatives based on egalitarian participation and agency. Following a Design-Based Research methodology, the framework is developed through a case study on creating educational games on everyday sexism. A set of formative design studies are undertaken to co-design resources and activities that enable participants to elaborate solutions to the social issue and create educational games themselves. An evaluative study is then presented with the realisation of two Game Jams to assess and validate the proposed framework. The theoretical contributions of this work validate two new applications of Critical Pedagogy. The first one is to apply Critical Pedagogy to shape Game Jams to enhance learning through the active involvement of participants as equal learners and agents of social change. The second one applies Critical Pedagogy to democratise knowledge of design principles to create educational games on social issues. Lastly, access to a co-created tool for raising awareness of everyday sexism and insights on how to enable broad audiences to acquire games development skills are some of the practical contributions of this thesis.
KerkoCite.ItemAlsoKnownAs: 2339240:8JDXC44I 2405685:CNBR3BS2

Countries using data to inform education policies - Kelly, Peggy (Education for All, 2021)
How can data be transformed into policy so that children everywhere, even the most disadvantaged, can realize their right to learn? Read how a project has helped countries like Lao PDR, Georgia and Mongolia to just do that.
KerkoCite.ItemAlsoKnownAs: 2339240:EEWA9327 2405685:HW883XL9

Five ways geospatial analysis can help visualize and solve some of education’s biggest challenges - The Education Comission (2021)
As the education community continues to mobilize efforts towards achieving Sustainable Development Goal 4 (SDG 4), stakeholders at all levels of the system are grappling with questions on how to deliver inclusive quality education. What communities will benefit most...
Section: Updates KerkoCite.ItemAlsoKnownAs: 2405685:2HMKI9VR 4042040:UQU9GND7

EdTech in developing countries: a review of the evidence - Rodriguez-Segura, Daniel (The World Bank Research Observer, 2021)
The emergence of educational technology (“EdTech”) in developing countries has been received as a promising avenue to address some of the most challenging policy questions within educational systems. In this paper, I review and synthesize all existing studies with credible causal identification frameworks of EdTech interventions in developing countries. While other studies review the evidence for EdTech interventions in developed countries, there is currently no equivalent study for developing contexts, in spite of the rising number of studies being produced. I classify studies into four thematic categories based on the type of EdTech intervention analyzed: Access to technology; technology-enabled behavioral interventions; improvements to instruction; and self-led learning. I find that EdTech interventions centered around self-led learning and improvements to instruction are the most effective forms of EdTech at raising learning outcomes. Similarly, technology-enabled behavioral interventions are less promising for generating large effects but highly cost-effective given their typically low marginal costs. Although expanding access to technology alone is not sufficient to improve learning, it is a necessary first step for some other types of interventions. More broadly, the overall success of interventions rests on the thoughtful customization of the EdTech solution to the policy constraints at hand. Finally, EdTech interventions across all thematic areas can and should act as complements by leveraging their respective comparative advantages to address deficiencies within educational systems in developing countries.
KerkoCite.ItemAlsoKnownAs: 10.1093/wbro/lkab011 2339240:DEKZ2C9I 2405685:ZS3CD2X6

What drives successful economic diversification in resource-rich countries? - Lashitew, Addisu A; Ross, Michael L; Werker, Eric (The World Bank Research Observer, 2021)
The “resource curse” is often understood to imply poor growth in the non-resource sectors of the economy, but research into the diversification performance of resource-rich countries is limited. This paper surveys recent evidence and identifies empirical patterns in the economic diversification of resource-rich countries. Diversification is measured using the growth of per capita non-resource (manufacturing and services) sectors in domestic and export markets, which has a cleaner interpretation than competing measures. This measure is used to evaluate the long-term diversification of countries that started off as resource-dependent, and to rank countries according to their performance. We then identify policy-relevant correlates of diversification at the national level, including the acquisition of human capital, public and intellectual capital, and firm dynamism. More resource-dependent countries appear to perform worse on measures of human capital and intellectual capital, but more resource-abundant countries perform better on public capital and human capital accumulation. We examine the mechanisms behind diversification performance through in-depth case studies of Oman, Laos, and Indonesia, and conclude by identifying policy lessons and future research directions.
37 citations (Crossref) [2024-04-29] KerkoCite.ItemAlsoKnownAs: 10.1093/wbro/lkaa001 2339240:V8J8XJDX 2405685:YXRXML66
Keywords: ⛔ No INSPIRE recid found

Timor-Leste education: Supporting sustainable system-wide reform and school leader capacity-building through collaborative foreign aid - Owen, Susanne; Wong, Debbie (Journal of Educational Change, 2021)
Effective school leadership and ongoing teacher capacity-building are essential aspects of school reform and improving educational outcomes for students in developing countries. This paper examines a Timor-Leste curriculum reform and associated school leader capacity-building and the implementation processes for building sustainability, within the context of research literature regarding effective professional development and successful foreign aid principles. The Timor-Leste leadership program was developed using an interpretivist paradigm and action research, with the authors being program designers and managers embedded in the context. School leader interviews and surveys, meeting notes and monitoring and evaluation reports, also teacher skills and student achievement data, were continuously examined to analyse issues and plan actions and solutions. Findings outline early impacts in relation to changing school leader behaviours, improved teacher skills and increased student literacy and numeracy, while also presenting implementation processes and actions taken to overcome challenges in relation to research-informed foreign aid principles.Given the importance of foreign aid for supporting significant educational improvement in developing countries, this Timor-Leste leadership capacity-building case study provides an example relevant to an under-researched area. While the focus is on one particular country and reform involving curriculum and professional development, the paper has value for other education contexts and system change initiatives which involve collaborations with foreign aid donors.
4 citations (Crossref) [2024-02-28] KerkoCite.ItemAlsoKnownAs: 10.1007/s10833-020-09397-w 2339240:7CBH4P4D 2405685:HCP8M782
Keywords: Foreign aid; International development; School leadership capacity-building; School reform; School-based professional development; ⛔ No INSPIRE recid found

Current initiatives, barriers, and opportunities for networked learning in Latin America - Romero-Hall, Enilda (Educational Technology Research and Development, 2021)
This paper explores and describes the current initiatives, barriers, and opportunities for formal, non-formal, and informal networked learning experiences using social media in Latin America. It focuses on networked learning initiatives such as the use of institutional social media accounts, educational hashtags, social media in the classroom, educational channels via video hosting platforms, and government established networked learning programs for connected classrooms. The same multiplicity, diversity, and heterogenicity that represent the culture, languages, and socio-economic status of the people of Latin America also characterize the vast mixture of networked learning initiatives across the region. Potential barriers (i.e., the digital divide, Internet filtering policies, lack of research) and opportunities for implementation (i.e., networked learning educational reforms, mobile learning technology, and social media ethical considerations) are explored. The paper concludes with recommendations that policymakers and education leaders in Latin America should keep in mind to engage in fruitful networked learning initiatives.
KerkoCite.ItemAlsoKnownAs: 10.1007/s11423-021-09965-8 2339240:25TY743U 2405685:SXGL4TF6
Keywords: Connected learning; Information and communications technology; Latin America; Mobile learning; Networked learning; Social media

COVID-19 Education Situation Analysis in Southeast Asia - UNICEF East Asia and Pacific (2021)
This sub-regional situation analysis initiated by UNICEF and UNESCO provides a snapshot of the educational responses and effects of COVID-19 across Southeas
KerkoCite.ItemAlsoKnownAs: 2339240:GHMBLPPX 2405685:PJYDQK4N
Keywords: ⛔ No INSPIRE recid found

Automation of systematic literature reviews: A systematic literature review - van Dinter, Raymon; Tekinerdogan, Bedir; Catal, Cagatay (Information and Software Technology, 2021)
Context Systematic Literature Review (SLR) studies aim to identify relevant primary papers, extract the required data, analyze, and synthesize results to gain further and broader insight into the investigated domain. Multiple SLR studies have been conducted in several domains, such as software engineering, medicine, and pharmacy. Conducting an SLR is a time-consuming, laborious, and costly effort. As such, several researchers developed different techniques to automate the SLR process. However, a systematic overview of the current state-of-the-art in SLR automation seems to be lacking. Objective This study aims to collect and synthesize the studies that focus on the automation of SLR to pave the way for further research. Method A systematic literature review is conducted on published primary studies on the automation of SLR studies, in which 41 primary studies have been analyzed. Results This SLR identifies the objectives of automation studies, application domains, automated steps of the SLR, automation techniques, and challenges and solution directions. Conclusion According to our study, the leading automated step is the Selection of Primary Studies. Although many studies have provided automation approaches for systematic literature reviews, no study has been found to apply automation techniques in the planning and reporting phase. Further research is needed to support the automation of the other activities of the SLR process.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.infsof.2021.106589 2405685:D5JR22C8 2486141:MUGRSX6T
Keywords: Automation; Machine learning; Natural language processing; Review; Systematic literature review (SLR); Text mining; _Added-ailr-2024

The latent digital divide and its drivers in e-learning among Bangladeshi students during the COVID-19 pandemic - Badiuzzaman, Md; Rafiquzzaman, Md; Rabby, Md Insiat Islam; Rahman, Mohammad Mustaneer (Information, 2021)
The devastating COVID-19 pandemic forced academia to go virtual. Educational institutions around the world have stressed online learning programs in the aftermath of the pandemic. However, because of insufficient access to Information Communication Technology (ICT), a substantial number of students failed to harness the opportunity of online learning. This study explores the latent digital divide exhibited during the COVID-19 pandemic while online learning activities are emphasised among students of Bangladesh. It also investigates the digital divide exposure and the significant underlying drivers of the divide. In order to accomplish this, a cross-sectional survey was employed to collect quantitative data, mixed with open-ended questions were utilised to gather qualitative information from the student community. The findings revealed that despite the majority of students having physical access to ICT, only 32.5% of students could attend online classes seamlessly. In total, 34.1% reported data prices as the critical barrier, while 39.8% identified poor network infrastructure as the significant barrier preventing them from participating in online learning activities. Although most students possess physical access to various devices and the Internet, they face the first-level digital divide due to the quality of access and price of cellular Internet. Consequently, they fail to take advantage of physical access, resulting in the third-level digital divide (utility gap), which submerges them into a digital divide cycle. The primary objective of this study is to explore the underlying issues of the digital divide among Bangladeshi students. This will assist relevant stakeholders (e.g., the Bangladesh government, educational institutions, and researchers) to gain necessary insights and theoretical understanding of underlying limitations and emergent directions to arrange adequate support for underprivileged students to undertake essential online learning activities.
Number: 8 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/info12080287 2339240:6S36DZH9 2405685:BTG5QS57
Keywords: COVID-19; digital divide; multi-level digital divide; online learning

National Policy on Education Management Information System (EMIS) and Implementation Guidelines - Federal Ministry of Education (Federal Government of Nigeria, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:DNI3YH4B 2405685:RI3FTWS3

Telementoring and homeschooling during school closures: A randomized experiment in rural Bangladesh - Hassan, Hashibul; Islam, Asad; Siddique, Abu; Wang, Liang Choon (Centre for Development Economics and Sustainability, 2021)
Prolonged school closures due to political unrests, teacher strikes, natural disasters, and public health crises can be detrimental to student learning in developing countries. Using a randomized controlled experiment in 200 Bangladeshi villages, we evaluate the impact of over-the-phone mentoring and homeschooling support delivered by volunteers on the learning outcomes of primary school children during school closures caused by the coronavirus pandemic. The telementoring program improved the learning outcomes of treated children by 0.75 SD and increased homeschooling involvement of treated mothers by 0.64 SD. The impacts on learning are driven primarily by the direct mentoring of children and to some extent also by the increased homeschooling involvement of mothers. Academically weaker children and households from relatively lower socioeconomic backgrounds benefitted the most from telementoring. These findings suggest that learning crises in low-resource settings can be addressed by simple and very low-cost technology solutions.
KerkoCite.ItemAlsoKnownAs: 2339240:5YSHGI3S 2339240:7WBML8RC 2405685:6J9MZIZY 2405685:XE45G75X 2405685:XU7PCDNA 2534379:RF4FNWBS
Keywords: ___working_potential_duplicate

Child education in the time of pandemic: Learning loss and dropout - Khan, Muhammad Jehangir; Ahmed, Junaid (Children and Youth Services Review, 2021)
The disruptive effects of the COVID-19 pandemic had affected the education sector at an unprecedented scale. In order to contain the spread of the virus, a large number of countries across the globe have shut their schools to handle the pandemic. However, it has adversely affected students' learning and school attendance. In this regard, we assess the impact of COVID-19 on the learning loss, school dropout, and the economic costs in term of foregone earnings for children in Pakistan. The study finds a substantial decrease in Learning Adjusted Years of Schooling (LAYS) with worsening consequences for girls than boys. Likewise, the aggregate economic cost amounts to 107 billion dollars when adjusted for human capital utilisation. Besides, our simulation results suggest that about 7.2 million children dropout due to a reduction in household expenditure by 50 percent. In comparison, the dropout is more pronounced at the primary level of schooling. The results recommend that the government design robust social protection and remote education strategies to mitigate school closure’s adverse effect on children's learning. The emphasis should be rather on the long run strategies to cope with a resilient education system of futuristic orientation. (PsycInfo Database Record (c) 2021 APA, all rights reserved)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.childyouth.2021.106065 2339240:YF7YC22M 2405685:DWQ4UZX5
Keywords: Adjustment; COVID-19; Education; Learning Strategies; Learning loss; Pakistan; Pandemics; School Dropout; School Dropouts; School Learning

How to integrate Value for Money assessments within the External Evaluations of the GEC - Shah, Valsa (Foreign, Commonwealth & Development Office, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:32NCMKDK 2405685:NQ22KZWA

Intergenerational transmission of lockdown consequences: prognosis of the longer-run persistence of COVID-19 in Latin America - Neidhöfer, Guido; Lustig, Nora; Tommasi, Mariano (Journal of Economic Inequality, 2021)
The shock on human capital caused by COVID-19 is likely to have long lasting consequences, especially for children of low-educated families. Applying a counterfactual exercise we project the effects of school closures and other lockdown policies on the intergenerational persistence of education in 17 Latin American countries. First, we retrieve detailed information on school lockdowns and on the policies enacted to support education from home in each country. Then, we use these information to estimate the potential impact of the pandemic on schooling, high school completion, and intergenerational associations. In addition, we account for educational disruptions related to household income shocks. Our findings show that, despite that mitigation policies were able to partly reduce instructional losses in some countries, the educational attainment of the most vulnerable could be seriously affected. In particular, the likelihood of children from low educated families to attain a secondary schooling degree could fall substantially.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10888-021-09501-x 2339240:WN3LXJPD 2405685:TR8PDKM5

Intergenerational transmission of lockdown consequences: prognosis of the longer-run persistence of COVID-19 in Latin America - Neidhöfer, Guido; Lustig, Nora; Tommasi, Mariano (Journal of Economic Inequality, 2021)
The shock on human capital caused by COVID-19 is likely to have long lasting consequences, especially for children of low-educated families. Applying a counterfactual exercise we project the effects of school closures and other lockdown policies on the intergenerational persistence of education in 17 Latin American countries. First, we retrieve detailed information on school lockdowns and on the policies enacted to support education from home in each country. Then, we use these information to estimate the potential impact of the pandemic on schooling, high school completion, and intergenerational associations. In addition, we account for educational disruptions related to household income shocks. Our findings show that, despite that mitigation policies were able to partly reduce instructional losses in some countries, the educational attainment of the most vulnerable could be seriously affected. In particular, the likelihood of children from low educated families to attain a secondary schooling degree could fall substantially.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10888-021-09501-x 2339240:WN3LXJPD 2405685:TR8PDKM5

E-waste and planned obsolescence - Selwyn, Neil (Critical Studies of EDUCATION & TECHNOLOGY, 2021)
Notes from Guardian report (15.04.20) by John Harris on e-waste and planned obsolescence ** There is a pressing need to talk about educational technology in terms of the disposal – rather than adop…
KerkoCite.ItemAlsoKnownAs: 2339240:MJVFPJ7K 2405685:8DUFXTJF

Vietnam approves Education Society Scheme in 2021-2030 amid digital transformation - Vietnam Investment Review (2021)
Vietnam approved the Scheme on Development of Education Society in 2021-2030 to improve the quality of human resources for digital transformation.
Section: Society KerkoCite.ItemAlsoKnownAs: 2339240:MPY96XUY 2405685:R8BRMW2R

Handbook of Regression Modeling in People Analytics: With Examples in R and Python - McNulty, Keith (CRC Press, 2021)
Despite the recent rapid growth in machine learning and predictive analytics, many of the statistical questions that are faced by researchers and practitioners still involve explaining why something is happening. Regression analysis is the best ‘swiss army knife’ we have for answering these kinds of questions. This book is a learning resource on inferential statistics and regression analysis. It teaches how to do a wide range of statistical analyses in both R and in Python, ranging from simple hypothesis testing to advanced multivariate modelling. Although it is primarily focused on examples related to the analysis of people and talent, the methods easily transfer to any discipline. The book hits a ‘sweet spot’ where there is just enough mathematical theory to support a strong understanding of the methods, but with a step-by-step guide and easily reproducible examples and code, so that the methods can be put into practice immediately. This makes the book accessible to a wide readership, from public and private sector analysts and practitioners to students and researchers. Key Features:• 16 accompanying datasets across a wide range of contexts (e.g. academic, corporate, sports, marketing) • Clear step-by-step instructions on executing the analyses. • Clear guidance on how to interpret results. • Primary instruction in R but added sections for Python coders. • Discussion exercises and data exercises for each of the main chapters.• Final chapter of practice material and datasets ideal for class homework or project work.
Google-Books-ID: Nt4zEAAAQBAJ KerkoCite.ItemAlsoKnownAs: 2339240:73W8T3RZ 2405685:5DS6D5VM
Keywords: Business & Economics / Statistics; Mathematics / Probability & Statistics / General

Pesquisa revela sistemas de ensino melhor avaliados no país - Blog do EX - Escolas Exponenciais, (Escolas Exponenciais, 2021)
Diagnóstico Nacional da Educação aponta qual é o sistema de ensino mais bem avaliado por pais e responsáveis por alunos em todo Brasil.
KerkoCite.ItemAlsoKnownAs: 2339240:ZJP4J9X9 2405685:WCD5LB3Q

Silenced by an unknown language? Exploring language matching during rransitions from complementary education to government schools in Ghana - Daly, Kieran; Carter, Emma; Sabates, Ricardo (Compare: A Journal of Comparative and International Education, 2021)
Mother tongue-based education has been central to the promotion of early literacy skills in many multilingual contexts of the Global South. However, learners in such environments may face significant linguistic challenges when changing language of instruction during schooling. In particular, the linguistic distance between mother tongue and official language may be a significant barrier to learners. This paper provides an empirical approach to this issue by employing language matching based on linguistic distance between languages to explore changes in literacy scores for learners who change language of instruction. Findings show that the greater the linguistic distance between two languages, the larger the loss in foundational literacy. We conclude that language matching could be introduced as a tool to identify at-risk learners during transitions and, if possible, as a tool for linguistic allocation of students who have the possibility of selecting between schools with different languages for instruction.
Publisher: Routledge _eprint: https://doi.org/10.1080/03057925.2021.1941772 KerkoCite.ItemAlsoKnownAs: 10.1080/03057925.2021.1941772 2405685:KV9RQPGW 4042040:F4XHI9TM
Keywords: Ghana; Mother tongue education; language matching; literacy; multilingualism

Critical Digital Literacies framework for educators - DETECT Project Report 1 - Gouseti, Anastasia; Bruni, Isabella; Ilomäki, Liisa; Lakkala, Minna; Mundy, Darren; Raffaghelli, Juliana Elisa; Ranieri, Maria; Roffi, Alice; Romero, Marc; Romeu, Teresa (Zenodo, 2021)
This is the first report of the DETECT project. The report presents the Critical Digital Literacies framework that has been created as part of the project’s Intellectual Output 1. This framework is the result of collaborative work across all project partners and has been informed by a range of research and other activities. These included: i) a systematic literature review in the area of critical digital literacies, ii) empirical research conducted across our four primary and secondary EU school partners, and iii) expert panel meetings at various stages that helped to refine and finalise the framework Acknowledgement This project was funded by Erasmus+, KA2. Project Reference: 2019-1-UK01-KA201-061508.
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5070329 2339240:AFPBQPFT 2405685:YELXY9SV
Keywords: critical digital literacies; digital competences; schools; teachers

The Role of Intergovernmental Fiscal Transfers in Improving Education Outcomes - Al-Samarrai, Samer; Lewis, Blane (World Bank, 2021)
The majority of the world’s children live in countries where local governments are responsible for the provision of basic education services. Although subnational governments manage their own education systems, they often rely on transfers from the central government for funding. The main purpose of this study is to assess how these fiscal transfers affect public funding for education and how they ultimately affect student schooling and learning outcomes. Through a careful analysis of how fiscal transfers have affected education systems in different contexts, the investigation develops a set of principles to support improvements in the design and implementation of transfer systems with a specific focus on the provision of education services. The study is centered on seven country case studies that aim to answer a set of common research questions using a similar approach. Country case studies were conducted in Brazil, Bulgaria, China, Colombia, Indonesia, Sudan, and Uganda. The analysis shows that fiscal transfer mechanisms can improve the adequacy of public education spending, reduce spending inequalities between regions, and improve spending efficiency. Moreover, the study highlights that carefully designed and implemented transfer systems can help raise overall education outcomes and reduce education inequality. This publication was funded by a grant from the Results in Education for All Children (REACH) trust fund at the World Bank. REACH is supported by the government of Germany through the Federal Ministry for Economic Cooperation and Development, the government of Norway through NORAD, and the government of the United States of America through the U.S. Agency for International Development.
Accepted: 2021-06-28T14:28:37Z KerkoCite.ItemAlsoKnownAs: 10.1596/978-1-4648-1693-2 2339240:6R2LBJUB 2405685:RN7PVKFV 4656463:K5KKTKWC
Keywords: Education; Education Equity; Education Finance; Education Outcomes; Education Spending; Fiscal Decentralization; Fiscal Transfers; Public Expenditure

Safeguarding Her: A call to action to educating girls in vulnerable situations - Break Free Alliance (Education for All, 2021)
For millions of girls across Africa, the thought of joining school remains far-fetched. Here are 6 recommendations we consider vital to ensure girls’ better access to education and secure their futures.
KerkoCite.ItemAlsoKnownAs: 2339240:36KPCI4X 2405685:P5HCFXSZ

Brazil Case Study - Mello, Ursula; Loureiro, Andre; Cruz, Louisee (World Bank, 2021)
The majority of the world’s children live in countries where local governments are responsible for the provision of basic education services. Although subnational governments manage their own education systems, they often rely on transfers from the central government for funding. The main purpose of this study is to assess how these fiscal transfers affect public funding for education and how they ultimately affect student schooling and learning outcomes. Through a careful analysis of how fiscal transfers have affected education systems in different contexts, the investigation develops a set of principles to support improvements in the design and implementation of transfer systems with a specific focus on the provision of education services. The study is centered on seven country case studies that aim to answer a set of common research questions using a similar approach. Country case studies were conducted in Brazil, Bulgaria, China, Colombia, Indonesia, Sudan, and Uganda. The analysis shows that fiscal transfer mechanisms can improve the adequacy of public education spending, reduce spending inequalities between regions, and improve spending efficiency. Moreover, the study highlights that carefully designed and implemented transfer systems can help raise overall education outcomes and reduce education inequality. This publication was funded by a grant from the Results in Education for All Children (REACH) trust fund at the World Bank. REACH is supported by the government of Germany through the Federal Ministry for Economic Cooperation and Development, the government of Norway through NORAD, and the government of the United States of America through the U.S. Agency for International Development.
Accepted: 2021-06-28T14:28:37Z KerkoCite.ItemAlsoKnownAs: 10.1596/978-1-4648-1693-2 2339240:IKJT3DUI 2405685:SZCK288Z 4656463:6PMDEFFM
Keywords: Education; Education Equity; Education Finance; Education Outcomes; Education Spending; Fiscal Decentralization; Fiscal Transfers; Public Expenditure

Guidelines for reporting trial protocols and completed trials modified due to the COVID-19 pandemic and other extenuating circumstances: The CONSERVE 2021 Statement - Orkin, Aaron M.; Gill, Peter J.; Ghersi, Davina; Campbell, Lisa; Sugarman, Jeremy; Emsley, Richard; Steg, Philippe Gabriel; Weijer, Charles; Simes, John; Rombey, Tanja; Williams, Hywel C.; Wittes, Janet; et al. (JAMA, 2021)
Extenuating circumstances can trigger unplanned changes to randomized trials and introduce methodological, ethical, feasibility, and analytical challenges that can potentially compromise the validity of findings. Numerous randomized trials have required changes in response to the COVID-19 pandemic, but guidance for reporting such modifications is incomplete.As a joint extension for the CONSORT and SPIRIT reporting guidelines, CONSERVE (CONSORT and SPIRIT Extension for RCTs Revised in Extenuating Circumstances) aims to improve reporting of trial protocols and completed trials that undergo important modifications in response to extenuating circumstances.A panel of 37 international trial investigators, patient representatives, methodologists and statisticians, ethicists, funders, regulators, and journal editors convened to develop the guideline. The panel developed CONSERVE following an accelerated, iterative process between June 2020 and February 2021 involving (1) a rapid literature review of multiple databases (OVID Medline, OVID EMBASE, and EBSCO CINAHL) and gray literature sources from 2003 to March 2021; (2) consensus-based panelist meetings using a modified Delphi process and surveys; and (3) a global survey of trial stakeholders.The rapid review yielded 41 673 citations, of which 38 titles were relevant, including emerging guidance from regulatory and funding agencies for managing the effects of the COVID-19 pandemic on trials. However, no generalizable guidance for all circumstances in which trials and trial protocols might face unanticipated modifications were identified. The CONSERVE panel used these findings to develop a consensus reporting guidelines following 4 rounds of meetings and surveys. Responses were received from 198 professionals from 34 countries, of whom 90% (n = 178) indicated that they understood the concept definitions and 85.4% (n = 169) indicated that they understood and could use the implementation tool. Feedback from survey respondents was used to finalize the guideline and confirm that the guideline’s core concepts were applicable and had utility for the trial community. CONSERVE incorporates an implementation tool and checklists tailored to trial reports and trial protocols for which extenuating circumstances have resulted in important modifications to the intended study procedures. The checklists include 4 sections capturing extenuating circumstances, important modifications, responsible parties, and interim data analyses.CONSERVE offers an extension to CONSORT and SPIRIT that could improve the transparency, quality, and completeness of reporting important modifications to trials in extenuating circumstances such as COVID-19.
KerkoCite.ItemAlsoKnownAs: 10.1001/jama.2021.9941 2339240:5SVZDPZV 2405685:A55Z4Y79

The Importance of Caregiver Engagement in Supporting Learning - Kimathi, Deborah; El-Serafy, Yomna; Plaut, Daniel; Kaye, Tom (EdTech Hub, 2021)
Do you know the importance of caregiver engagement in supporting learning beyond the classroom? Visit our website to learn more.
KerkoCite.ItemAlsoKnownAs: 2339240:MCEFY3WR 2405685:7VZZBHDN

Contract Type and Teacher Absenteeism in Benin: The Role of Teacher’s Supplemental Income - Senou, Barthelemy Mahugnon (2021)
Absenteeism is a phenomenon that has been noted in professional circles with consequences on the income of the wage earner as well as the profits of the firm, consequences that led, according to statistics from 2005, to losses in public finance amounting to close to 70 billion francs for the Government of Benin. Despite such losses, very few studies in economics have focused on the subject in order to try and give an understanding of the real causes of absenteeism and its consequences. The objective of this study is to explore the relationship between the status of the teacher, supplemental income of the teacher, and the absenteeism of the teacher. Using data from PASEC-CONFEMEN 2005, that will be applied to a theoretical model that we are developing, and through the use of a Tobit empirical method, after having taken the endogeneity bias on the practice of supplemental income generating activities by the teacher into account, this study demonstrates that the practice of income generating activities by teachers positively influences their absenteeism, with contract teachers being more frequently absent than those who are on permanent and pensionable employment contracts. Through linking the level of prices in a locality with absenteeism behaviours, we make it clear that the reasons for absenteeism are mostly related to low purchasing power in the context of earning relatively meagre salaries. These results elicit a set of recommendations that essentially suggest that there should be an improvement in the salaries and working conditions of teachers.
KerkoCite.ItemAlsoKnownAs: 2129771:G5ULT28D 2405685:KQA3YITJ 4556019:RK7QIQGC
Keywords: C:Benin; ⛔ No DOI found

Innovations in Social and Emotional Learning Research and Practice: Building from Evidence and Applying Behavioral Insights to the Design of a Social and Emotional Learning Intervention in Northeast Nigeria - Bailey, Rebecca; Raisch, Natasha; Temko, Sonya; Titus, Britt; Bautista, Jonah; Eniola, Tahirat Omolara; Jones, Stephanie M. (International Journal of Environmental Research and Public Health, 2021)
Recent studies suggest that social and emotional learning (SEL) programming has the potential to be effective in conflict-affected regions, yet evidence is limited, and findings to date are mixed. One hypothesis about why SEL interventions in education in emergencies (EiE) settings have not generated the anticipated results is that the SEL content and materials have not been sufficiently localized to the context, leading to poor cultural relevance or fit. A second hypothesis is that SEL program demands tend to be high and capacity for implementation is low, undermining sustainability and impact. The current study addresses these challenges by investing in locally driven SEL content and design as a way to ensure that SEL materials are grounded in local values and needs, culturally appropriate, relevant to the specific context, and feasible to implement. The study draws on the developmental and prevention sciences as well as the field of behavioral insights to test evidence-based interventions intended to encourage desired behaviors around uptake and implementation. This paper documents the activities conducted during the project’s design phase, including landscape research, creation of initial prototypes, design workshops and rapid prototyping, and field testing. Findings suggest that using local values, practices, and framing in SEL programming increases relevance and appropriateness for the Northeast Nigeria setting. Furthermore, targeted behavioral insights interventions increased the uptake, habitual and regular use, as well as correct implementation of SEL activities. The findings contribute to the emerging literature on the cultural variability of SEL and the need to consider the context when designing and implementing programs in any setting.
KerkoCite.ItemAlsoKnownAs: 10.3390/ijerph18147397 2339240:CDB54TJY 2405685:Z8ML2UVR

Beyond partnerships: embracing complexity to understand and improve research collaboration for global development - Fransman, Jude; Hall, Budd; Hayman, Rachel; Narayanan, Pradeep; Newman, Kate; Tandon, Rajesh (Canadian Journal of Development Studies / Revue canadienne d'études du développement, 2021)
While there is a burgeoning literature on the benefits of research collaboration for development, it tends to promote the idea of the “partnership” as a bounded site in which interventions to improve collaborative practice can be made. This article draws on complexity theory and systems thinking to argue that such an assumption is problematic, divorcing collaboration from wider systems of research and practice. Instead, a systemic framework for understanding and evaluating collaboration is proposed. This framework is used to reflect on a set of principles for fair and equitable research collaboration that emerged from a programme of strategic research and capacity strengthening conducted by the Rethinking Research Collaborative (RRC) for the United Kingdom (UK)’s primary research funder: UK Research and Innovation (UKRI). The article concludes that a systemic conceptualisation of collaboration is more responsive than a “partnership” approach, both to the principles of fairness and equity and also to uncertain futures.
Publisher: Routledge _eprint: https://doi.org/10.1080/02255189.2021.1872507
Keywords: Research partnerships; complexity theory; higher education policy; research collaboration; research funding; systems thinking

Rapid versus traditional qualitative analysis using the Consolidated Framework for Implementation Research (CFIR) - Nevedal, Andrea L.; Reardon, Caitlin M.; Opra Widerquist, Marilla A.; Jackson, George L.; Cutrona, Sarah L.; White, Brandolyn S.; Damschroder, Laura J. (Implementation Science, 2021)
Qualitative approaches, alone or in mixed methods, are prominent within implementation science. However, traditional qualitative approaches are resource intensive, which has led to the development of rapid qualitative approaches. Published rapid approaches are often inductive in nature and rely on transcripts of interviews. We describe a deductive rapid analysis approach using the Consolidated Framework for Implementation Research (CFIR) that uses notes and audio recordings. This paper compares our rapid versus traditional deductive CFIR approach.
KerkoCite.ItemAlsoKnownAs: 10.1186/s13012-021-01111-5 2339240:R59M4XJ9 2405685:A87VCNQJ
Keywords: Consolidated Framework for Implementation Research (CFIR); Implementation science; Qualitative methods; Rapid analysis; Veterans

Building back better to avert a learning catastrophe: Estimating learning loss from COVID-19 school shutdowns in Africa and facilitating short-term and long-term learning recovery - Angrist, Noam; de Barros, Andreas; Bhula, Radhika; Chakera, Shiraz; Cummiskey, Chris; DeStefano, Joseph; Floretta, John; Kaffenberger, Michelle; Piper, Benjamin; Stern, Jonathan (International Journal of Educational Development, 2021)
We model learning losses due to the COVID-19 pandemic and the potential for cost-effective strategies to build back better. Data from Early Grade Reading Assessments in Ethiopia, Kenya, Liberia, Tanzania, and Uganda suggest half to over a year’s worth of learning loss. In modeling losses over time, we found that learning deficits for a child in grade 3 could lead to 2.8 years of lost learning by grade 10. While COVID-19 has stymied learning, bold, learning-focused reform consistent with the literature reviewed in this paper—specifically reform on targeted instruction and structured pedagogy—could improve learning even beyond pre-COVID-19 levels.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2021.102397 2339240:6FG39EY3 2339240:LB3VWRGN 2405685:7MUIIRXU
Keywords: COVID-19; Education; Foundational skills; Learning loss; Recovery

Plan national de développement économique et social 2021-2025 (PNDES-II) - Government of Burkina Faso (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KLSRKHU5 2405685:YQCYCEB8

Time to Teach: Teacher Attendance and Time on Task in Primary Schools in Mozambique - Nugroho, Dita; Karamperidou, Despina (UNICEF, 2021)
Teacher attendance is one of the prerequisites on the path toward universal learning in developing countries. Over the past decades, however, studies from across the developing world have found national rates of teacher absenteeism that range from 3 to 27 per cent. Therefore, enhancing teachers' presence in the classroom and ensuring that class time is spent teaching, can contribute significantly to the productivity and inclusive prosperity of a country. This Time to Teach study collates and strengthens the evidence base on primary school teacher absenteeism in Mozambique. The study uses a mix of qualitative and quantitative research methods to provide critical insights into the factors that underpin the multiple forms of teacher absenteeism and time on task. It also examines how factors vary across countries, school types, gender of teacher and other teacher characteristics. Despite high levels of teacher absenteeism, the study shows that teachers are generally committed and that what is needed is education system strengthening. It is hoped that findings will inform workable solutions and policies that will ensure a motivated teaching force, increase opportunities for children to learn at school and, ultimately, improve their life and work opportunities.
KerkoCite.ItemAlsoKnownAs: 2405685:ZP685VWV 4042040:9DF5VZLU 4556019:44PQIP2W 4556019:6P6UPZAV
Keywords: Barriers; C:Mozambique; Developing Nations; Educational Change; Educational Policy; Elementary School Teachers; Employee Absenteeism; Foreign Countries; Gender Differences; Influences; Institutional Characteristics; Rural Urban Differences; Sanctions; Teacher Attendance; Teacher Attitudes; Teacher Characteristics; Teacher Education; Teacher Persistence; Teaching Conditions; Time Management; ⛔ No DOI found

Remote Learning: Evidence from Nepal during COVID-19 - Radhakrishnan, Karthika; Sabarwal, Shwetlena; Sharma, Uttam; Cullen, Claire; Crossley, Colin; Letsomo, Thato; Angrist, Noam (World Bank, 2021)
This note discusses early results from a distance education program on foundational numeracy for primary school students in Nepal during Coronavirus (COVID-19) evaluated in a randomized trial. The trial included 3,700 households with children in public school (grades 3-5). It provided support for foundational numeracy through mobile phone-based tutoring. The trial tested delivery through public school teachers and also through NGO facilitators. It led to a 30 percent increase in foundational numeracy, with teachers being slightly more effective at producing learning gains than NGO facilitators. These results suggest that instructional support through mobile phones can be a high-access and low-cost approach to providing instruction at scale
Accepted: 2021-07-28T17:29:14Z KerkoCite.ItemAlsoKnownAs: 2339240:LFIQ9LIB 2405685:F89QL28Q
Keywords: Coronavirus; Covid-19; Numeracy; Pandemic Impact; Remote Learning; School Closure

Tool for assessing the gender responsiveness of content for digital learning platforms - UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:K9AZY7KG 2405685:ZXCPZH4J

Examination of Teacher Candidates' Views on Peer Learning Performed with Interactive Videos in the Blended Learning Process - Ipek, Jale; Kalay, Abdullah; Ertas, Sercan (Education Quarterly Reviews, 2021)
Today, the speed of the development of technology has various effects in many areas. In the field of education, some concepts, methods, techniques, theories and models come to the fore with the effect of technology and attract the attention of researchers. One of them is blended learning. Blended learning is a learning process in which both face-to-face learning processes and learning processes in online environments coexist. Today's learners are expected to be able to solve problems, work collaboratively, and have strong communication. It is thought that peer learning can be used in constructivist teaching processes in order to gain these features. Peer learning involves learners performing their learning by interacting with each other. In this study, it is aimed to determine the opinions of teacher candidates about peer learning realized with interactive videos in the blended learning process. The study group consists of 37 Computer and Instructional Technologies Education Department teacher candidates, 11 women (29.73%) and 26 men (70.27%) enrolled in the "Special Teaching Methods - II" course in the spring semester of 2018-2019 academic year. In the online part of the study, a web 2.0 tool (Edpuzzle) was used to prepare interactive video content. The videos prepared by the peers regarding the course content were expected to be watched online and before the face-to-face lessons. In the face-to-face learning process, students progressed the learning process interactively with their peers. At the end of the process, the data were collected with the data collection tool named "teacher candidate opinion form" developed by the researchers from the study group. The collected data were analyzed with content analysis and interpreted by the researchers. In the study results, the opinions of the teacher candidates about the process after their learning experiences were determined. It was found that a great majority of the teacher candidates had a positive opinion about the peer learning realized with interactive videos in the blended learning process.
KerkoCite.ItemAlsoKnownAs: 10.31014/aior.1993.04.02.281 2339240:QFNTPDR9 2405685:4CPCU8MQ

Nudges to improve learning and gender parity: Supporting parent engagement and Ghana’s educational response to COVID-19 using mobile phones - Wolf, Sharon; Aurino, Elisabetta; Osei-Akoto, Isaac; Ackwerh, Eunice Yaa Brimfah (World Bank Strategic Impact Evaluation Fund (SIEF), 2021)
Randomized control trial testing impacts of SMS messages to suggest activities that promote social-emotional development at home and to encourage engagement with remote instruction, variants of these messages that have a gender-parity focus, and the duration of these messages (3 months vs. 6 months)
KerkoCite.ItemAlsoKnownAs: 2339240:H7GV3H2Z 2405685:7DVEJE63 2405685:YKSU9467

Empowering parents and caregivers to support learning and a safe return to school - Fuller, Sarah; Brown, Jessica Katherine (UNICEF Europe and Central Asia, 2021)
Ongoing pandemic response, recovery and long-term resilience must consider parents and caregivers if we are to reach every child.
KerkoCite.ItemAlsoKnownAs: 2339240:57DMA7WU 2405685:V3FJEMU9

Teacher Perspectives on Peer-Peer Collaboration and Education Technologies in Rural Tanzanian Classrooms - Uchidiuno, Judith; Koedinger, Ken; Ogan, Amy (ACM SIGCAS Conference on Computing and Sustainable Societies, 2021)
Teachers’ perspectives are critical for understanding classroom culture. They create and enforce rules in classrooms and are responsible for educating students using methods that they perceive to be most effective. Therefore, creating supplementary education technologies without understanding teachers and the culture they promote may lead to interventions that are underutilized or ineffective. Our research specifically investigates how technologies that foster student collaboration fit into teachers’ views of learning in a rural context with limited existing collaboration scaffolds. We interviewed 24 teachers and observed 39 classrooms in a rural Tanzanian village to understand how teachers value peer-peer collaboration in their teaching practice, and the unique challenges they face educating students in rural classroom settings. We uncover insights that inform the design and deployment of supplementary education technologies to support teachers in rural Tanzania and similar demographics.
KerkoCite.ItemAlsoKnownAs: 10.1145/3460112.3471939 2339240:VUXY6J6M 2405685:TWE99YU2
Keywords: Early literacy; Sub-Saharan Africa; educational technologies; peer-peer collaboration

Malaysia Data Protection Overview - Ping, Jillian Chia Yan (DataGuidance, 2021)
June 2021 1. Governing Texts Data protection in Malaysia is primarily governed by the Personal Data Protection Act 2010 ('PDPA') and its subsidiary legislation as outlined below. The PDPA purports to safeguard personal data by requiring data users to comply with certain obligations and conferring certain rights to the data subject in relation to his personal data. 1.1. Key acts, regulations, directives, bills Primary Legislation Prior to 2010, the regulation of personal data was governed mainly by industry specific legislation.
KerkoCite.ItemAlsoKnownAs: 2339240:AVKSZT94 2405685:P7QN448B

Promises to keep: impact of COVID-19 on adolescents in Kenya - Presidential Policy and Strategy Unit (Kenya); Population Council (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:SZHGL7E3 2405685:AHRVVYD2

UNICEF and STEAM for Viet Nam Foundation announce partnership to bring equitable STEAM learning opportunities for children in Viet Nam - UNICEF (UNICEF, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KALJFWLR 2405685:AIDIK3YA

World Development Report 2021: Data for Better Lives - World Bank (The World Bank, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1596/978-1-4648-1600-0 2339240:UMDZ9J6Y 2405685:VZXWSLIJ

Reframing the policy discourse: A comparative analysis of teacher preparation for rural and remote education in Australia, South Africa and Mexico - Ledger, Susan; Masinire, Alfred; Díaz, Miguel Angel; Burgess, Madeline (education policy analysis archives, 2021)
The Organisation for Economic Cooperation and Development (OECD) has highlighted a ‘vicious cycle of decline’ in rural, regional and remote (RRR) regions, with significant inequalities in educational outcomes between rural and urban areas. However, interventions have not resulted in transformative or lasting improvements to education in rural contexts. This paper presents a cross-comparative country analysis of current global policy on RRR education. We used a policy analysis framework to interrogate national policy texts concerning teacher education for RRR contexts in three countries - Australia, South Africa and Mexico. A rigorous selection process of the literature yielded 17 key policy texts, which were examined for the influences, practices, language and outcomes relating to teacher education preparation for RRR locales. Findings highlighted a legacy of historical influences and a metrocentric bias in policy texts, with limited examples of assets-based education. We argue that these factors may be perpetuating the significant and persistent disadvantage in RRR education. We recommend an alternative policy discourse that recognises the productivities and potentialities of an assets-based approach within the local context, where school leaders and teachers are positioned as central change agents in RRR education.
KerkoCite.ItemAlsoKnownAs: 10.14507/epaa.29.6233 2339240:F5WE3FYK 2405685:J5B2NK2G

Eswatini Education Sector Analysis 2021 - World Bank (World Bank, 2021)
The current Education Sector Strategic Plan (ESSP) for 2010-2022 and the first and second National Education and Training Improvement Programs that operationalize the plan, were based on the comprehensive 2010 Education Sector Review (Marope, 2010, MoET, 2010, 2016, 2018b). As the current plan and program come to their end, this education sector analysis (ESA) was undertaken. In addition, complementary studies for the ECDE and TVET sub-sectors will be conducted separately to collect primary data to further help inform the development of the next ESSP. The ESA report examines the recent status of the education system to provide an evidence-based foundation for the Government’s preparation of its next ESSP and help guide the country more generally on the priority issues for the education sector looking forward. This executive summary begins with a brief description of the general context for education followed by an overview of recent achievements in education. The main part of the summary sets out the priority issues identified by the ESA report. The final section concludes with a discussion of selected policy options that may be considered looking ahead.
Accepted: 2021-06-21T21:34:24Z KerkoCite.ItemAlsoKnownAs: 2339240:G89C9EA6 2405685:M6XKMLXA
Keywords: Early Childhood Development; Early Childhood Education; Education Finance; Education Management; Education System; Labor Market; Primary Education; School Administration; Secondary Education; Skills Development; Student Achievement; Student Learning Assessment; Teacher Development; Teacher Recruitment; Teacher Training

Malawi World Bank Approves $100 Million to Improve Skills Development Programs Press Release - World Bank (2021)
The World Bank today approved $100 million in financing from the International Development Association (IDA)* for Malawi to support increased access, particularly for female students, to skills development programs in priority areas of the economy that are most relevant to the labor market— now and in the future.
KerkoCite.ItemAlsoKnownAs: 2339240:TL85HTPK 2405685:U7C5Y7FU 2405685:YAAV4TE4
Keywords: auto_merged

Malawi World Bank Approves $100 Million to Improve Skills Development Programs Press Release - World Bank (2021)
The World Bank today approved $100 million in financing from the International Development Association (IDA)* for Malawi to support increased access, particularly for female students, to skills development programs in priority areas of the economy that are most relevant to the labor market— now and in the future.
KerkoCite.ItemAlsoKnownAs: 2339240:TL85HTPK 2405685:U7C5Y7FU 2405685:YAAV4TE4
Keywords: auto_merged

Transforming how teachers use technology - Wilichowski, Tracy; Cobo, Cristóbal (World Bank Blogs, 2021)
Before the pandemic, there was a widely held notion that technology will revolutionize the field of education.
KerkoCite.ItemAlsoKnownAs: 2339240:HJJ2VM4G 2405685:425BK3MP

Bridging the gender digital divide - UNICEF (UNICEF, 2021)
The gender technology gap is standing in the way of equality. Learn how we're bridging the gender digital divide so girls can access technology.
KerkoCite.ItemAlsoKnownAs: 2339240:NX8EKNQI 2405685:EZQV7F2Y

Implementing Parental Empowerment and Engagement Strategies in Times of Crisis: Experiences from Regional Educational Learning Initiative members in Kenya - Angoye, James (Regional Education Learning Initiative Africa, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:SEU7ZPDH 2405685:FCBGKM5G

Emergency remote education experiences of teachers during the COVID-19 pandemic: a phenomenological research - Eroglu, Mehmet; Senol, Cem (Shanlax International Journal of Education, 2021)
The purpose of the study is to examine teachers' experiences of Emergency Remote Education (ERE) during the COVID-19 pandemic. The study was designed in the qualitative approach and as the research method, "phenomenology" was used. The sample of the study consists of 12 teachers selected by the criterion sampling method. The interview technique was used to collect data. The data were collected through a semi-structured interview form developed by the researchers. The data were analyzed using descriptive analysis. The study results showed that the ERE activity that teachers experienced the most was the online lessons. Teachers have done the ERE activities through various applications such as EIN (Education Information Network), Zoom, WhatsApp, YouTube. Teachers emphasized that ERE was ineffective due to low student participation, insufficient infrastructure, lack of responsibility and motivation for learning, low ICT competency of students and teachers, low socioeconomic status, and inappropriateness of planning and curriculums. In addition, teachers stated that education in the COVID-19 pandemic process should be done in diluted classrooms, hybrid or face to face. It is concluded that the lack of infrastructure, lack of responsibility and motivation for learning created inequality of opportunity for participation in ERE. The lack of infrastructure was mostly due to students being in the low socioeconomic group. In addition, students' learning responsibility and motivation are very important in the effectiveness of ERE.
KerkoCite.ItemAlsoKnownAs: 10.34293/education.v9i3.3918 2339240:QQT6MK3B 2405685:RD4IZKPG
Keywords: Barriers; COVID-19; Distance Education; Electronic Learning; Elementary Secondary Education; Emergency Programs; Foreign Countries; Instructional Effectiveness; Integrated Learning Systems; Internet; Learning Motivation; Pandemics; Phenomenology; Socioeconomic Status; Student Participation; Student Responsibility; Teacher Attitudes; Turkey

Emergency remote teaching and students’ academic performance in higher education during the COVID-19 pandemic: A case study - Iglesias-Pradas, Santiago; Hernández-García, Ángel; Chaparro-Peláez, Julián; Prieto, José Luis (Computers in Human Behavior, 2021)
The COVID-19 pandemic has caused a massive disruption in the way traditional higher education institutions deliver their courses. Unlike transitions from face-to-face teaching to blended, online or flipped classroom in the past, changes in emergency remote teaching –a temporary shift of instructional delivery to an alternate remote delivery mode due to crisis circumstances– happen suddenly and in an unplanned way. This study analyzes the move to emergency remote teaching at the School of Telecommunication Engineering (Universidad Politécnica de Madrid), and the impact of organizational aspects related to unplanned change, instruction-related variables –class size, synchronous/asynchronous delivery– and use of digital supporting technologies, on students' academic performance. Using quantitative data of academic records across all (N = 43) courses of a bachelor's degree programme in Telecommunication Engineering and qualitative data from a questionnaire delivered to all (N = 43) course coordinators, the research also compares the academic results of students during the COVID-19 pandemic with those of previous years. The results of this case study show an increase in students' academic performance in emergency remote teaching, and support the idea that organizational factors may contribute to successful implementation of emergency remote teaching; the analysis does not find differences across courses with different class sizes or delivery modes. The study further explores possible explanations for the results of the analysis, considering organizational, individual and instruction-related aspects.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.chb.2021.106713 2339240:47EZAIGG 2405685:BAEW2B98

Exploring the fundamental factors of digital inequality in Bangladesh - Islam, Muhammad Nazrul; Inan, Toki Tahmid (SAGE Open, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1177/21582440211021407 2339240:C3ZIMHJY 2405685:TDV2W3I9

« TICE en Guinée : usages pour de meilleures pratiques en enseignement-apprentissage et en formation » - Le Centre International de Recherche et de Documentation (CIRD); L’Institut Supérieur de Formation à Distance (ISFAD) (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5GNUP7Z8 2405685:U8VZADZ7

An Investigation into Pre-Service Teachers' Self-Regulated Online Learning Perceptions - Özdemir, Atilla; Önal, Ahmet (International Journal of Contemporary Educational Research, 2021)
The sudden outbreak of COVID-19 pandemics has accelerated the process of technological transformation experienced by educational institutions. Traditional face-to-face education has been replaced by distance education as a precaution to minimize physical contact among the teachers and the students. As a result, self-regulatory skills have become a more significant factor for academic success in distance education. In line with this, the main aim of the study is to identify the level of self-regulated online learning perceptions of pre-service teachers in Turkish higher education context. Furthermore, the study also aims to reveal whether the pre-service teachers' self-regulated online learning perceptions differ according to several variables such as their gender, department, class, level of digital literacy and the time they daily spend online. A total of 353 pre-service teachers from various departments have participated in the study. The findings of the study indicate that pre-service teachers' perceptions of self-regulated online learning are at moderate level; thus, it can be argued that the level of their perceptions is far from satisfactory. Additionally, it has been observed that the pre-service teachers' self-regulated online learning perceptions differ according to their gender, level of digital literacy and time daily spent online. To be more precise, it has been noted that self-regulated online learning perceptions of female pre-service teachers are higher than those of male pre-service teachers. In a similar vein, it has been observed that the higher the level of digital literacy and the more time spent online, the higher the self-regulated online learning perceptions of pre-service teachers. The overall results of the study suggest that self-regulation skills of the pre-service teachers need to be emphasized and improved with the aim of contributing to the efficient implementation of distance education.
Publisher: International Journal of Contemporary Educational Research KerkoCite.ItemAlsoKnownAs: 2339240:62H9WIHB 2405685:P6VB83C6
Keywords: COVID-19; Correlation; Distance Education; Electronic Learning; Foreign Countries; Gender Differences; Pandemics; Preservice Teachers; Self Management; Student Attitudes; Technological Literacy; Time Management; Undergraduate Students; ⛔ No DOI found

Distance learning: Reach & Effectiveness in South Asia - Panth, Brajesh; van Cappelle, Frank; Li, Zhigang; van Kalmthout, Ellen; Gochyyev, Perman; Hayashi, Ryotaro (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:SF5W3G69 2405685:8HZRZR9K

Sierra Leone Public Expenditure Review 2021: Fiscal Policy for a Sustainable Recovery - World Bank (World Bank, 2021)
This Fiscal and Debt Sustainability Note, the first module of a programmatic multisectoral Public Expenditure Review (PER), reviews the recent macro-fiscal challenges, analyzes their causes and consequences and provide policy options for enhancing the conduct of fiscal and PFM policies in the country. The first part of this module draws on the Boost database to provide a comprehensive overview of the budget covering both revenues and expenditures. It analyzes the composition of the budget (based on economic and functional classifications) and discusses the most critical PFM issues the country faces. It also assesses budget execution and the efficiency of public expenditure. The second part of the module focuses on fiscal risks and their implications for medium-term fiscal and debt sustainability. It examines the recent evolution of public debt, its main drivers and relationship to economic growth. It describes recent reforms to address fiscal and debt vulnerabilities and how these reforms have been affected by the global pandemic. It also analyzes the main fiscal risks with a focus on those stemming from State-Own Enterprises (SOEs), local councils, litigations, natural disasters, and health crises. This part uses simulations to analyze the most likely evolution of the public debt path over the next 20 years under alternative risk scenarios. Finally, the module proposes practical and actionable policy options to help improve the macro-fiscal environment over the short term and preserve debt sustainability over the medium term.
Accepted: 2021-06-29T15:28:44Z KerkoCite.ItemAlsoKnownAs: 2339240:QWRVJMBE 2405685:KDMZ7CXM
Keywords: Debt Sustainability; Fiscal Policy; Fiscal Sustainability; Public Debt; Public Expenditure; Public Financial Management; Public Investment Management; State-Owned Enterprises

Shupavu291 Helping Candidates Fulfill Academic Ambitions - Baraka, Peter (Eneza Education, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:NDBFXWPN 2405685:7M8752QV

Re-imagining the future education management information systems, beyond head counts: leveraging data systems to support inclusive and effective learning for all - UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5UBF8HJT 2339240:XEWQYE2N 2405685:32I7B2XX 2405685:SA922BN9 2405685:XDKGCG2W 4656463:CD5YN6NM 4656463:NJH4HU8K

Analysis of Rural-Based Pre-Service Teachers Spatial-Visualisation Skills in Problem Solving in Vector Calculus Using MATLAB - Amevor, Godfred; Bayaga, Anass; Bosse, Michael (International Journal of Emerging Technologies in Learning (iJET), 2021)
In science, technology, engineering and mathematics (STEM) for instance, interdisciplinary studies have noted positive correlation between spatial-visualization (SV skills) and mathematical problem solving. The majority of these studies sharing a link between SV skills and problem solving were contextualized in urban settings and only a few in rural settings. This investigation analyses how rural-based pre-service teachers apply their SV skills in problem-solving in a South African university, in the context of vector calculus. One hundred rural-based pre-service teachers in a second year vector calculus class at University of Zululand (UNIZULU) were randomly selected into control and experimental groups. MATLAB was used as a dynamic visual tool to analyse how research participants applied their SV skills. A mixed method approach was employed in data collection (quantitative and qualitative). Our findings revealed that the rural-based pre-service teachers’ SV skills correlate with their problem-solving skills in vector calculus.
KerkoCite.ItemAlsoKnownAs: 10.3991/ijet.v16i10.19269 2339240:Q22Y38D2 2405685:43VE73IX

What Did Children Do During School Closures? Insights from a Parent Survey in Tanzania - Oza, Shardul; Cilliers, Jacobus (Research on Improving Systems of Education (RISE), 2021)
In this Insight Note, we report results of a phone survey that the RISE Tanzania Research team conducted with 2,240 parents (or alternate primary care-givers) of primary school children following the school closures in Tanzania. After the first case of COVID-19 was confirmed in Tanzania on 16 March 2020, the government ordered all primary schools closed the following day. Schools remained closed until 29 June 2020. Policymakers and other education stakeholders were concerned that the closures would lead to significant learning loss if children did not receive educational support or engagement at home. To help stem learning loss, the government promoted radio, TV, and internet-based learning content to parents of school-age children. The primary aims of the survey were to understand how children and families responded to the school closures, the education related activities they engaged in, and their strategies to send children back to school. The survey also measures households’ engagement with remote learning content over the period of school closures. We supplement the findings of the parent survey with insights from interviews with Ward Education Officers about their activities during the school closures. The survey sample is comprised of primary care-givers (in most cases, parents) of students enrolled in Grades 3 and 4 during the 2020 school year. The survey builds on an existing panel of students assessed in 2019 and 2020 in a nationally representative sample of schools.4 The parent surveys were conducted using Computer Assisted Telephonic Interviewing (CATI) over a two-week period in early September 2020, roughly two months after the re-opening of primary schools. We report the following key findings from this survey: *Almost all (more than 99 percent) of children in our sample were back in school two months after schools re-opened. The vast majority of parents believed it was either safe or extremely safe for their children to return to school. *Only 6 percent of households reported that their children listened to radio lessons during the school closures; and a similar fraction (5.5 percent) tuned into TV lessons over the same period. Less than 1 percent of those surveyed accessed educational programmes on the internet. Households with access to radio or TV reported higher usage. *Approximately 1 in 3 (36 percent) children worked on the family farm during the closures, with most children working either 2 or 3 days a week. Male children were 6.2 percentage points likelier to work on the family farm than female children. *Households have limited access to education materials for their child. While more than 9 out of 10 households have an exercise book, far fewer had access to textbooks (35 percent) or own reading books (31 percent). *One in four parents (24 percent) read a book to their child in the last week.
KerkoCite.ItemAlsoKnownAs: 10.35489/BSG-RISE-RI_2021/027 2339240:4NJ7WZ8K 2405685:8WI6L8RQ

Locked out of school: Pakistan’s digital divide has students struggling - Irfan, Anmol (The Guardian, 2021)
Online lessons can’t reach children in many areas of Covid-hit country even though their parents still have to pay fees
KerkoCite.ItemAlsoKnownAs: 2339240:T8XC53BT 2405685:CSPLGDG7

School Hits the Airwaves: Sierra Leone Turns to Education Radio as a Response to COVID-19 - World Bank (World Bank, 2021)
Sierra Leone's experience with education radio during the 2014 Ebola outbreak has helped strengthen its radio programming during school closures caused by the COVID-19 pandemic.
KerkoCite.ItemAlsoKnownAs: 2339240:XWD4TCC4 2405685:RLJGATUE

School Hits the Airwaves: Sierra Leone Turns to Education Radio as a Response to COVID-19 - World Bank (The World Bank, 2021)
Sierra Leone's experience with education radio during the 2014 Ebola outbreak has helped strengthen its radio programming during school closures caused by the COVID-19 pandemic.
KerkoCite.ItemAlsoKnownAs: 2339240:TQTHH2MX 2405685:55GPK4S9

New data on learning loss in Pakistan - Crawfurd, Lee; Hares, Susannah; Minardi, Ana Luiza (Center for Global Development, 2021)
To get a better picture of the effects of the pandemic on education in Pakistan, we carried out another round of our survey of students and parents. We found gender differences in learning loss, little engagement with government teleschool, dropping parental support for further closures, and more.
KerkoCite.ItemAlsoKnownAs: 2339240:ANJSCDN7 2405685:4P85RKIL 2405685:WY4KS8G3

STEM: breaking gender stereotypes - UNGEI (UNGEI, 2021)
In some Western cultures, pink is for girls, blue is for boys. Why? It just is. You might hear mothers remark with wonder that their little girls just love the pink dress (that was given to them). You may have heard fathers insist that their sons not wear pink clothing. It’s interesting to think that at the end of the nineteenth century in the USA, pink was actually the colour preferred for boys, it being a softer version of military red. Things change. The accepted wisdom that stereotypes originally come from a place of truth is erroneous. No credible research has indicated that girls gravitate to pink things without any cultural prompting. Our gendered behaviour is primarily socially conditioned. Research suggests that the idea of a female brain and a male brain is false [1]. Rather, the plasticity of the brain means that it can be moulded – from birth onwards – through learning, engaging in the world and being socially conditioned. This includes learning and absorbing gender stereotyping. Gendered colours are harmless though, right? No, not really. Any gender stereotype will reinforce a gender bias. In 2019, a Fawcett Society study found that 45 per cent of people said that when they were children, they experienced gender stereotyping as they were expected to behave in a certain way [2]. Seven in 10 younger women (18-34s) affected by stereotypes say their career choices were restricted [3]. Around 70 per cent of individuals in 34 countries associated science with males more than with females [4]. © UNICEF/UN0364176/XimendazCaregivers and teachers often reproduce the stereotype that boys are better in science and mathematics than girls, encouraging girls to aspire to ‘female-oriented’ careers instead of ‘male’ STEM related ones [5,6]. To compound this negative reinforcement, curriculum and learning materials reinforce gender stereotypes and unequal gender norms in STEM. In India, illustrations in math and science textbooks in primary school show 6 per cent girls, but more than 50 per cent boys [7]. The stereotyping sanctioned by parents, teachers and the curriculum itself negatively impacts a girl’s self-belief – and her future aspirations [8]. When three women won the Nobel Prize for science in 2020, it was newsworthy partly because not many women have won the prize over the years. But is it also newsworthy because, even today, many would not expect women to be such high achievers in science, technology, engineering and mathematics. Engineering is for boys. Mechanical toys are for boys. Science experiments are for boys. These are the stereotypes we learn. Where does this thinking come from? There’s obviously a lot to unpack here: traditional roles in society born out of a female’s capability to bear children, or stronger upper body strength, on average, amongst males, for example. But they don’t speak to our cognitive and intellectual potential. And I’m sure there would be many who would dispute every particular of the above. Questioning norms that are the foundation of our interaction with the world is difficult for all of us to do. © UNICEF/UN0145559/SchermbruckerAcknowledging that stereotypes exist is straightforward. Deciding that they shouldn’t constrain our behaviour and life path is a little harder. But confronting and actively challenging these stereotypes – indeed, breaking them! – is an altogether more difficult process. How do we do it? How do we take organic and grassroots solutions toward a tipping point of change? This International Girls in ICT Day (22nd April), UNGEI hosted an Instagram Live event to explore these important questions. Transform Education members Maryam and Nivaal and NASA engineer Farah Alibay talked about working with NASA on the Mars 2020 mission, how to drive progress for gender equality in STEM and why representation matters. Shifting power in STEM starts with listening to the experts and girls themselves, such as the inspiring changemakers on UNICEF’s Teen. Girl. Activist site. Debunking stereotypes is in their very capable hands… The first thing we need to do is recognize that there is a societal bias... let’s recognize that we are treating girls differently and that they are not being given the same opportunities. Now that we’ve started to recognize that problem, I think...normalizing STEM for girls, providing resources, and providing a safe space for girls is really important. Farah Alibay, Systems Engineer, NASA (UNGEI International Girls in ICT IG Live Event) Some choose to tackle stereotypes head-on, like the ‘Talent Viewer’ in the Netherlands, to break the stereotype that girls can’t successfully engage in STEM. Girls and boys in primary school (aged 9 to 12) assign talents to each other, discuss them, then investigate what STEM professions used these talents. This looks at certain talents being appropriate for STEM, not gender. A woman working in a STEM field talks to the classes about her job, effectively role modelling for girls. Critically, parents are encouraged to discuss the talents with their child and teachers participate in professional development on gender awareness, STEM education and talent development. The evaluation of the programme has indicated a positive change in attitude in both girls and boys towards girls’ participation in STEM. Around 46,000 children have engaged in this exciting work to date. © UNICEF/UNI363793/AryanAnother approach is simply to place girls in STEM-related industries, to show that it’s a natural place for both men and women, like the ‘Technogirls’ programme. This is a public-private partnership in South Africa that seeks to enhance the career uptake by disadvantaged girls in STEM fields (which is critical to the country’s economic growth). It identifies school-going young women from disadvantaged communities and places them in corporate mentorship and job-shadowing programmes. So far, 11,241 girls have engaged in structured job-shadowing programmes – and 78 per cent of them who have gone on to study in one of three scarce skills STEM fields in the country. These women become role models for the next generation and many of them are now mentors to new intakes of girls. The best investment is...girls' quality STEM education. And if we can give support to girls for quality STEM education, they will pay back successfully in the future to make a better world. Nasrin Siddiqa, Brookings Echidna Global Scholar (UNGEI@20 Forum) Other education systems have worked on how they teach STEM to ensure that girls aren’t overlooked or left behind. UNICEF in Ghana has worked with the Korea International Cooperation Agency and the Ghana Education Service on the ‘Better Life for Girls’ project. Focused on dismantling gender norms, the project included gender-responsive pedagogy (teaching and learning processes that pay attention to the specific learning needs of girls and boys) in mathematics and science, and providing life skills and leadership training for adolescent girls – helping more than 4,000 girls to stay in school and explore their potential. Training teachers on gender-responsive pedagogy helped to change girls’ perceptions of their own abilities – and this has a knock-on effect in the learning they pursue. If girls had believed the stereotype about not being good at mathematics, what other stereotypes can they challenge? And that is surely a question for all of us. During UNGEI’s 20th Anniversary Forum (UNGEI@20), activists, experts and leaders came together to explore what it will take to close the STEM gender gap in education and thus help girls fulfil their leadership potential. The event concluded that we need a gender-transformative approach to education, increasing opportunities for girls to develop digital skills and building their confidence and aspirations to pursue careers as STEM professionals. Technology is such a useful tool because it doesn't just provide mentors. It provides resources. It provides community. When you take away that access to tech, you take away that access to education as well, that basic human right. Audrey Pe, WiTech Founder (UNGEI@20 Forum) In the pursuit of equity in digital literacy and STEM skills, especially as we look toward a world of work where 9 in 10 jobs will require digital skills, UNICEF is proud to mobilize commitments alongside other public and private partners as an Action Coalition for Technology and Innovation as part of the Generation Equality Forum. These commitments include advancing girl-designed solutions to learning fit for a digital world, and advancing an outcome fund for digital literacy equity that brings together the best of public and private human and financial resources. © UNICEF/UNI363793/AryanIn the context of the Covid-19 crisis, which exposed structural inequalities in education and access to technology, these types of interventions are more important than ever. If we are to deliver on our global commitments to Sustainable Development Goals (SDGs) 4 and 5, we need to understand just how much harm stereotypes of any kind can be, particularly to young, vulnerable, curious children. If we are serious about helping children to achieve their potential – for their own development and so they can contribute to their communities and the world – then we need to minimize the forces that limit that potential. This includes gender stereotyping. We need to start celebrating children for who they are, not who we think they should be, based on a pointless stereotype. Let’s help them to access their rights to be themselves. Let’s help them to wear whatever colour they like.
KerkoCite.ItemAlsoKnownAs: 2339240:RFBQ67SV 2405685:PWYK67HD

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.
KerkoCite.ItemAlsoKnownAs: 10.1162/rest_a_00911 2339240:YSZWN3WD 2405685:IJLK42YK 4656463:SK8JBZHG

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.
KerkoCite.ItemAlsoKnownAs: 10.1162/rest_a_00911 2339240:YSZWN3WD 2405685:IJLK42YK 4656463:SK8JBZHG

Making the grade: The sensitivity of education program effectiveness to input choices and outcome measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.
KerkoCite.ItemAlsoKnownAs: 10.1162/rest_a_00911 2339240:YSZWN3WD 2405685:IJLK42YK 4656463:SK8JBZHG

2019 Survey on Socio-Economic Status of 53 Ethnic Minorities - General Statistics Office (Government of the Socialist Republic of Vietnam, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KFTSMSKD 2405685:6YBH5EW2

Influence of COVID-19 on Students’ Sign Language Learning in a Teacher-Preparation Program in Saudi Arabia: Moving to E-Learning - Alawajee, Omar (Contemporary Educational Technology, 2021)
KerkoCite.ItemAlsoKnownAs: 10.30935/cedtech/10886 2339240:Z6B9WIX9 2405685:3CNS5VW3

How can real-time performance data lead to better education outcomes? - Sharma, Aarushi; Gustafsson-Wright, Emily; Osbourne, Sarah (Brookings, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:SZWXK6WN 2405685:JNRNE6CJ 4656463:GFXAJF9E

Children's learning and development in conflict- and crisis-affected countries: Building a science for action - Aber, J. Lawrence; Dolan, Carly Tubbs; Kim, Ha Yeon; Brown, Lindsay (Development and Psychopathology, 2021)
This paper critically reviews the opportunities and challenges in designing and conducting actionable research on the learning and development of children in conflict- and crisis-affected countries. We approached our review through two perspectives championed by Edward Zigler: (a) child development and social policy and (b) developmental psychopathology in context. The aim of the work was to answer the following questions: What works to enhance children's learning and development in such contexts? By what mechanisms? For whom? Under what conditions? How do experiences and conditions of crisis affect the basic processes of children's typical development? The review is based on a research–practice partnership started in the Democratic Republic of the Congo in 2010 and expanded to research in Niger and Lebanon in 2016. The focus of the research is on the impact of Healing Classrooms (a set of classroom practices) and Healing Classrooms Plus (an additional set of targeted social and emotional learning activities), developed by the International Rescue Committee, on children's academic outcomes and social and emotional learning. We sought to extract lessons from this decade of research for building a global developmental science for action. Special attention is paid to the importance of research–practice partnerships, conceptual frameworks, measurement and methodology. We conclude by highlighting several essential features of a global developmental science for action.
KerkoCite.ItemAlsoKnownAs: 10.1017/S0954579420001789 2405685:YKV2MFJA
Keywords: global science for action; refugee education; research–practice partnership; social–emotional learning

Are the eﬀects of informational interventions driven by salience? - Bettinger, Eric; Cunha, Nina; Lichand, Guilherme; Madeira, Ricardo (University of Zurich Department of Economics, 2021)
Informational interventions have been shown to signiﬁcantly change behavior across a variety of settings. Is that because they lead subjects to merely update beliefs in the right direction? Or, alternatively, is it to a large extent because they increase the salience of the decision they target, aﬀecting behavior even in the absence of inputs for belief updating? We study this question in the context of an informational intervention with school parents in Brazil. We randomly assign parents to either an information group, who receives text messages with weekly data on their child’s attendance and school eﬀort, or a salience group, who receives messages that try to redirect their attention without child-speciﬁc information. We ﬁnd that information makes parents more accurate about student attendance, and has large impacts on their test scores and grade promotion relative to the control group. Even though salience messages, in contrast, do not make parents more accurate about attendance levels, learning outcomes in the salience group improve by at least as much. Why? We show that treated parents across both conditions become more accurate about changes in their children’s grades over time, although not about grade levels. Such coarse belief updating is consistent with independent information acquisition in response to salience eﬀects from both interventions. Our results have implications for the design and interpretation of informational interventions across a range of domains.
KerkoCite.ItemAlsoKnownAs: 2339240:BRBKHQ3F 2405685:V3BN4GC8
Keywords: ❓ Multiple DOI

Equitable learning with ICT: study of an intervention at scale for underserved students in India - Chandran, M.G.; Sarangapani, P. (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:94XX23CS 2534378:RKB8G5HH

Zotero Workbook (v4) - Haßler, Björn; McBurnie, Chris; Murphy, Mary; Nourie, Kristi (2021)
Previous_DOI: 10.5281/zenodo.3406140 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4719821 2405685:ISD67Q83

Cambodia Secondary Education Blueprint 2030 - Ministry of Education, Youth and Sports, Kingdom of Cambodia (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:SUR9LL27 2405685:HD54DUP6

Practical guide to blended/remote learning and children with disabilities - UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:CZYK5ZJL 2405685:D5ZB5QCJ
Keywords: ⛔ No INSPIRE recid found

Challenges and Opportunities as Students Return to School: Evidence from Caregiver and Staff Surveys across Rising Academy Network School - Caballero, Erika Montoya; McManus, Jeff; Njogu-Ndongwe, Frida; Fall, Sokhna Mously (IDinsight, 2021)
This report shares survey findings on the barriers that children face as they transition back to school after prolonged closures with evidence from caregiver and staff surveys across Rising Academy Network Schools.
KerkoCite.ItemAlsoKnownAs: 2339240:YXEGBXY2 2405685:HMTL6PX2

A 35-hour a year CPD entitlement could stop 12,000 teachers quitting - Henshaw, Pete (SecEd, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:V3CA53IQ 2405685:T2GWCZ9P

What is Hybrid Learning? How can countries get it right? - Barron, Maria; Cobo, Cristobal; Ciarrusta, Inaki Sanchez; Munoz-Najar, Alberto (Education for Global Development, 2021)
What is Hybrid Learning? How can countries get it right?
KerkoCite.ItemAlsoKnownAs: 2339240:392QJFI9 2339240:Z6VGWSAD 2405685:HH6SV3WK 2405685:NFXBM7SR

Learning loss due to school closures during the COVID-19 pandemic - Engzell, Per; Frey, Arun; Verhagen, Mark D. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Suspension of face-to-face instruction in schools during the COVID-19 pandemic has led to concerns about consequences for students' learning. So far, data to study this question have been limited. Here we evaluate the effect of school closures on primary school performance using exceptionally rich data from The Netherlands (n ≈ 350,000). We use the fact that national examinations took place before and after lockdown and compare progress during this period to the same period in the 3 previous years. The Netherlands underwent only a relatively short lockdown (8 wk) and features an equitable system of school funding and the world's highest rate of broadband access. Still, our results reveal a learning loss of about 3 percentile points or 0.08 standard deviations. The effect is equivalent to one-fifth of a school year, the same period that schools remained closed. Losses are up to 60% larger among students from less-educated homes, confirming worries about the uneven toll of the pandemic on children and families. Investigating mechanisms, we find that most of the effect reflects the cumulative impact of knowledge learned rather than transitory influences on the day of testing. Results remain robust when balancing on the estimated propensity of treatment and using maximum-entropy weights or with fixed-effects specifications that compare students within the same school and family. The findings imply that students made little or no progress while learning from home and suggest losses even larger in countries with weaker infrastructure or longer school closures.
KerkoCite.ItemAlsoKnownAs: 10.1073/pnas.2022376118 2339240:FQ7T9968 2405685:BRNCTXQM
Keywords: COVID-19; Child; Female; Humans; Learning; Male; Netherlands; Pandemics; Quarantine; SARS-CoV-2; Schools; digital divide; learning loss; school closures; social inequality

Learning loss due to school closures during the COVID-19 pandemic - Engzell, Per; Frey, Arun; Verhagen, Mark D. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Suspension of face-to-face instruction in schools during the COVID-19 pandemic has led to concerns about consequences for students' learning. So far, data to study this question have been limited. Here we evaluate the effect of school closures on primary school performance using exceptionally rich data from The Netherlands (n ≈ 350,000). We use the fact that national examinations took place before and after lockdown and compare progress during this period to the same period in the 3 previous years. The Netherlands underwent only a relatively short lockdown (8 wk) and features an equitable system of school funding and the world's highest rate of broadband access. Still, our results reveal a learning loss of about 3 percentile points or 0.08 standard deviations. The effect is equivalent to one-fifth of a school year, the same period that schools remained closed. Losses are up to 60% larger among students from less-educated homes, confirming worries about the uneven toll of the pandemic on children and families. Investigating mechanisms, we find that most of the effect reflects the cumulative impact of knowledge learned rather than transitory influences on the day of testing. Results remain robust when balancing on the estimated propensity of treatment and using maximum-entropy weights or with fixed-effects specifications that compare students within the same school and family. The findings imply that students made little or no progress while learning from home and suggest losses even larger in countries with weaker infrastructure or longer school closures.
KerkoCite.ItemAlsoKnownAs: 10.1073/pnas.2022376118 2339240:FQ7T9968 2405685:BRNCTXQM
Keywords: COVID-19; Child; Female; Humans; Learning; Male; Netherlands; Pandemics; Quarantine; SARS-CoV-2; Schools; digital divide; learning loss; school closures; social inequality

Development and evaluation of an open-source, online training for the measurement of adult-child responsivity at home and in early childhood education and care settings - Rodrigues, Michelle; Schneider, Alessandra; Sokolovic, Nina; Brunsek, Ashley; Oré, Beatriz; Perlman, Michal; Jenkins, Jennifer (The International Review of Research in Open and Distributed Learning, 2021)
Efforts to monitor and improve responsive caregiving for young children, because of its importance for child development, are part of the United Nations Sustainable Development Goals. Two brief observational measures of responsive caregiving have been developed and validated (Responsive Interactions for Learning—parent [RIFL-P] and educator [RIFL-Ed] versions), with the RIFL-P available in English, Portuguese, and Spanish. The aim of the current study was to present and evaluate two online training programs for the RIFL measures. These distance learning courses were designed as open-source and asynchronous to enable their use in low- and middle-income countries and remote areas. The following course components are used: readings, lectures, observation of interactions on video, coding practice with automated feedback on item coding, and quizzes. Of the 76 trainees who registered for one of the online courses, 58 (76%) completed all theoretical module components. Student performance was generally high. Marks on quizzes ranged between 83%–100%. Ninety percent of those who took the reliability tests passed (40/44). Student satisfaction during and after the course was high. The effective online training programs are available free of charge and the RIFL suite of measures is efficient to implement. Implications for research and practice are discussed.
KerkoCite.ItemAlsoKnownAs: 10.19173/irrodl.v22i3.5472 2339240:ZYGZ755K 2405685:7ECQ5DZ7

Evidence to Strengthen Tech-Supported Teacher Development in Madagascar - Coflan, Caitlin Moss; Koomar, Saalim; Rasolohery, Hasiniavo (EdTech Hub, 2021)
Our latest blog looks at using evidence to strengthen tech-supported teacher professional development in Madagascar. For more details, visit our website.
KerkoCite.ItemAlsoKnownAs: 2339240:ANDK8LBN 2405685:DRXSJH4U

Let's Read — How Tusome Leveraged EdTech to Improve National Learning Outcomes. Governing Digital Transformation: Improving Outcomes in Education Systems - Myers, Christina; Kaye, Tom; Khalayleh, Abdullah (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:2J7K7DAQ 2486141:3ILITC56

A review of Artificial Intelligence (AI) in education from 2010 to 2020 - Zhai, Xuesong; Chu, Xiaoyan; Chai, Ching Sing; Jong, Morris Siu Yung; Istenic, Andreja; Spector, Michael; Liu, Jia-Bao; Yuan, Jing; Li, Yan (Complexity, 2021)
This study provided a content analysis of studies aiming to disclose how artificial intelligence (AI) has been applied to the education sector and explore the potential research trends and challenges of AI in education. A total of 100 papers including 63 empirical papers (74 studies) and 37 analytic papers were selected from the education and educational research category of Social Sciences Citation Index database from 2010 to 2020. The content analysis showed that the research questions could be classified into development layer (classification, matching, recommendation, and deep learning), application layer (feedback, reasoning, and adaptive learning), and integration layer (affection computing, role-playing, immersive learning, and gamification). Moreover, four research trends, including Internet of Things, swarm intelligence, deep learning, and neuroscience, as well as an assessment of AI in education, were suggested for further investigation. However, we also proposed the challenges in education may be caused by AI with regard to inappropriate use of AI techniques, changing roles of teachers and students, as well as social and ethical issues. The results provide insights into an overview of the AI used for education domain, which helps to strengthen the theoretical foundation of AI in education and provides a promising channel for educators and AI engineers to carry out further collaborative research.
Publisher: Hindawi KerkoCite.ItemAlsoKnownAs: 10.1155/2021/8812542 2405685:T7U5VLI3 2486141:LZ7DG3FE

Combatting the impact of COVID-19 school closures in Bangladesh - Rahman, Tashmina; Ahmed, Ramim (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:N456FTY7 2405685:27LNFHVR

National Education Infrastructure Management System Report as at 12 April 2021 - Department of Basic Education, Republic of South Africa (Government of the Republic of South Africa, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ECR78M4N 2405685:E6DHFE74 4656463:EMQS6MGJ

Children’s and adolescents’ digital access in Chile: the role of digital access modalities in digital uses and skills - Cabello, Patricio; Claro, Magdalena; Rojas, Rodrigo; Trucco, Daniela (Journal of Children and Media, 2021)
This article analyses the modes of physical access that facilitate participation in digital opportunities and the development of digital skills in children and adolescents (9 to 17 years old). We analysed the data obtained from the Kids Online survey in Chile. A latent class analysis (LCA) was conducted to identify groups based on access points and devices of use; access modalities were then composed crossing these variables. Four access modalities were found: cellphone-home; cellphone-ubiquitous; multi-device-home; multi-device-ubiquitous. Multiple logistic regression analysis showed that ubiquitous modalities (multi-device and cellphone varieties) predicted digital use and skills among young Chileans, while the more static modalities (cellphone and home and multi-device and home) did not. These results are critical to addressing what can be deﬁned as “enabling access” among young Internet users in the context of digital inclusion policies.
KerkoCite.ItemAlsoKnownAs: 10.1080/17482798.2020.1744176 2339240:BQ495K6E 2405685:XJRHE5YU

Motivating online learning through project-based learning during the 2020 COVID-19 pandemic - Hira, Avneet; Anderson, Emma (IAFOR Journal of Education, 2021)
The transition of traditional schooling to online learning during the COVID-19 pandemic disrupted formal school education. Though at home, teachers and students continued teaching and learning in socially distant ways using online technologies. From various teacher surveys, only about 60% of students in the United States regularly engaged with learning activities. Teachers and parents also expressed a significant need for help to keep students motivated and engaged in learning activities. During the pandemic, online learning left teachers and parents needing support for learning activities that motivate and engage students. Project-based learning is an increasingly popular pedagogical practice centered around students working collaboratively on projects while the teacher facilitates learning activities and progression. Project-based learning embodies several factors considered central to motivation in online learning. In this paper, we inquire how this approach presents itself as a candidate for learning during the pandemic when considering students’ motivation to learn through online learning experiences. We construct a conceptual framework informed by motivational theories that share core tenets with this form of learning and use the framework to analyze interviews of 11 teachers from 4 schools that taught with a project-based learning approach before the pandemic and transitioned to teaching, using it online, in the Spring of 2020. From our analyses of the teachers’ narratives, we discuss teaching aspects of the approach that lend themselves well to online teaching, elements that the teachers believe are missing, and how educators might cater to these missing aspects with a focus on student motivation to learn.
KerkoCite.ItemAlsoKnownAs: 10.22492/ije.9.2.06 2339240:KMIB34A6 2405685:BTUKQQCY

The pathway to progress on SDG 4 requires the global education architecture to focus on foundational learning and to hold ourselves accountable for achieving it - Beeharry, Girindre (International Journal of Educational Development, 2021)
Levels of reading comprehension and ability to do basic mathematics are shockingly low among primary-age children in low-income countries, despite the efforts of global education actors. This essay will argue that to make real progress on improving learning, actors in the sector need to prioritize a few key goals – in particular foundational literacy and numeracy – monitor progress to achieve them, and hold ourselves collectively accountable for improving results. Recent efforts such as the World Bank’s Foundational Learning Compact show promise but will require the support and scrutiny of other actors.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2021.102375 2339240:MBCWCTFT 2339240:UQGCU5P5 2405685:IWU8MQJ7 2405685:WFTBEXII
Keywords: Foundational learning; Foundational literacy and numeracy; Global education; Global education architecture

A structured model of the dynamics of student learning in developing countries, with applications to policy - Kaffenberger, Michelle; Pritchett, Lant (International Journal of Educational Development, 2021)
Learning trajectories vary amazingly widely across countries, regions, and individual students in dynamic ways. In this paper we develop a parametrized structural model of the dynamics of the learning process and use the model for suggestive policy applications. We first synthesize the existing empirical literature on learning profiles, which suggest a clear set of parameters that formally characterize the learning process. We then calibrate this model of the learning process to reproduce the distribution of observed learning outcomes in low- and middle-income countries. Applying our calibrated model to policy simulations, we find that expanding schooling to universal attainment of basic education without changing the dynamics of the learning process would produce very little additional learning. Adjusting other parameters in the model, however, has large, positive effects. Slowing the pace of curriculum, so that more children can keep up, increases average learning in grade 10 by the learning equivalent of 1.6 years of schooling. Expanding the student skill levels that learn from a given level of instruction to account for within classroom heterogeneity of learning levels increases average grade 10 learning by the equivalent of a full year of schooling. The parameters we use are flexible, to accommodate the learning process in different contexts, and future work could explore additional parameterizations and calibrations for informing plans to improve education systems’ coherence for learning.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2021.102371 2339240:CA826UNI 2405685:ZMA5UBXJ
Keywords: Dynamics of learning; Education policy; Learning trajectories; Low and middle income countries; Modelling learning

A comprehensive analysis of personalized learning components - Shemshack, Atikah; Kinshuk; Spector, Jonathan (Journal of Computers in Education, 2021)
Personalized learning is a learning approach that aims to personalize the learning experience according to the unique needs, goals, and skills of individuals which can be achieved by using current instructional technology that provides unique learning experiences in different learning environments. Technology is the main component that will enable and enrich personalized learning experience; however, even though technology is available to personalize the learning experience, there is still a lack of unified agreement on what components need to be considered for a dynamic personalized learning approach that is to be able to provide a unique and effective learning experience to each learner. To address this need, this study aims to analyze and synthesize different personalized learning approaches that consider different learning components, so that we have an evolving agreement on personalized learning models and approaches. The findings of this research identified the following main components: learner profiles and attitudes, previous knowledge and beliefs, personalized adaptive learning paths, and flexible self-paced learning environments that are generated by learning analytics. These prominent characteristics imply that a personalized learning environment (PLE) would need to be dynamic to maintain a current record of learner interests and attitudes, past experiences and performance, and activities and interactions likely to match a particular learner and learning goal.
KerkoCite.ItemAlsoKnownAs: 10.1007/s40692-021-00188-7 2339240:QSBTLZSS 2405685:AYW2Z9VQ

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:CMRDCH96 2405685:IGLNLHEN
Keywords: ⛔ No INSPIRE recid found

Consequences of school closure on access to education: lessons from the 2013–2016 Ebola pandemic - Smith, William C. (International Review of Education, 2021)
The COVID-19 pandemic has seen an unprecedented shutdown of society. Among the various safety measures taken, much attention has been given to school closure as a non-pharmaceutical mitigation tool to curb the spread of the disease through ensuring “social” (physical) distancing. Nearly 1.725 billion children in over 95% of countries worldwide have been affected by school closures implemented in April 2020 as the virus continued to spread. In the field of education, policymakers’ attention has been directed at keeping students on board through remote learning and addressing the immediate needs of schools upon reopening. The study presented in this article focuses on who remains absent after schools resume. Using publicly available survey data from the USAID Demographic Health Surveys Program and the UNICEF Multiple Indicator Cluster Survey from before and after the 2013–2016 Ebola pandemic in Guinea and Sierra Leone in West Africa, the author examined changes in school enrolment and dropout patterns, with targeted consideration given to traditionally marginalised groups. At the time, schools closed for between seven to nine months in the two countries; this length and intensity makes this Ebola pandemic the only health crisis in the recent past to come close to the pandemic-related school closures experienced in 2020. The author’s findings suggest that post-Ebola, youth in the poorest households saw the largest increase in school dropout. Exceeding expected pre-Ebola dropout rates, an additional 17,400 of the poorest secondary-age youth were out of school. This evidence is important for minimising the likely post-COVID-19 expansion in inequality. The author’s findings point to the need for sustainable planning that looks beyond the reopening of educational institutions to include comprehensive financial support packages for groups most likely to be affected.
KerkoCite.ItemAlsoKnownAs: 10.1007/s11159-021-09900-2 2339240:JKCDRWKL 2405685:JFZ4ET3L

Emanant themes of blended learning in K-12 educational environments: lessons from the Every Student Succeeds Act - Yang, Sohyun; Carter, Richard, Jr; Zhang, Ling; Hunt, Tiffany (Computers & Education, 2021)
Blended learning (BL) is an instructional design structure that facilitates the benefits of technology, paired with face-to-face instruction, to address the variance in student learning. BL has been widely utilized in education with the rapid development of technology. While the Every Student Succeeds Act (ESSA, 2015) of the United States emphasizes supporting states to implement BL by facilitating the use of technology, it is unclear how states intend to operationalize BL in practice based on the federal statute. Therefore, this study investigated how many states referenced BL and how they operationalized BL in state ESSA plans by using thematic analysis. Results suggested a total of 17 states addressed BL in their finalized state ESSA plans. While these states referenced BL in various titles and parts, the researchers identified three major themes that operationalize BL, including (a) BL leveraging technology to support learning, (b) BL in professional development, and (c) BL as an alternative pathway. In the discussion, the researchers noted the ambiguity of the definition of BL among stakeholders (e.g., states) as well as the possibility of the use of BL towards enabling personalized learning in K-12. The researchers also discussed how to empower educators in the context of BL.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.compedu.2020.104116 2339240:NMIPJUID 2405685:DQW7UFZ4

Understanding the Impact of Covid-19 on Education in Jordan - Galliver, Lizzy; Karlidag, Melike; Van Ommering, Erik (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:PPULI994 2405685:7UCE2C9S

The Relationship between Teachers' Attitudes to Distance Education and Their Life Satisfaction - Kirkiç, Kamil Arif; Yahsi, Ömer (Malaysian Online Journal of Educational Sciences, 2021)
Teachers' attitudes toward distance education are important in terms of the effectiveness of the distance education process. They become even more critical during this time of global pandemics when face-to-face education has been compulsorily replaced by distance education. The worldwide coronavirus pandemic has changed the practices of the teaching profession. This period has revealed how teachers' life satisfaction while carrying out their profession can be affected by changes in education delivery. The aim of this study is to examine the relationship between teachers' attitudes toward distance education and their life satisfaction during the distance education process. This research used the correlational survey method, a method in quantitative research. The sample group consisted of teachers (1,233 male and 3,671 female educators) working in different branches in Izmir. The "Life Satisfaction Scale" and "Attitude toward Distance Education Scale" were applied. Participants' demographic information was obtained using a "Personal Information Form" designed by the researchers. According to the results of the study, while there is a notable difference in teachers' limitations toward distance education and life satisfaction according to gender, there is no difference in the advantages gained from and attitudes toward distance education.
Publisher: University of Malaya Faculty of Education KerkoCite.ItemAlsoKnownAs: 2339240:ZILZ6A6N 2405685:FTADKX9J
Keywords: COVID-19; Correlation; Distance Education; Educational Attainment; Elementary School Teachers; Foreign Countries; Gender Differences; Income; Instructional Effectiveness; Knowledge Level; Life Satisfaction; Pandemics; Secondary School Teachers; Teacher Attitudes; Teacher Characteristics; ⛔ No DOI found

Parental Involvement, Learning Participation and Online Learning Commitment of Adolescent Learners during the COVID-19 lockdown - Lawrence, Kehinde Clement; Fakuade, Olubasayo Victor (Research in Learning Technology, 2021)
During the escalating coronavirus disease-2019 (COVID-19) pandemic, attempting to contain its spread, a large number of educational institutions shut down face-to-face teaching and learning activities globally due to a complete lockdown. This lockdown revealed emerging vulnerabilities of education systems in the lowand middle-income countries of the world, with Nigeria being no exception. Given these concerns, this research study assessed parental involvement, learning participation and the commitment to online learning of adolescent learners during the COVID-19 lockdown in Nigeria. An online survey questionnaire was employed to examine the level of online learning commitment and the contributory roles of each of the factors to online learning commitment of adolescent learners. In total, 1407 adolescents (male = 38.8%; female 61.2%) aged between 12 and 20 years (mean = 15: SD = 4.24) responded to the online survey, which was open for 2 months. Data were analysed using descriptive statistics of frequency distribution and inferential statistics of multiple regression. The findings revealed that the commitment level of adolescent learners to online learning was high. The findings further yielded a coefficient of R = 0.439 and R2 = 0.192 variance in the prediction of the outcome measure. Parental involvement contributed 32% (β = 0.322, p < 0.05) and learning participation contributed 23% (β = 0.234, p < 0.05) towards online learning. The study concludes that parental involvement and learning participation played a significant and positive role in the commitment of adolescent learners towards online learning during the COVID-19 lockdown in Nigeria. The authors suggest that parents be encouraged to synergise with the digitalised revolution, while the need for further in-depth research on the subject is emphasised in the suggestions for future research.
KerkoCite.ItemAlsoKnownAs: 10.25304/rlt.v29.2544 2339240:DSGJRP6C 2405685:KNYG37D4

Kenya: How Rogue Officials Inflated Enrolment, Used Ghost Schools to Steal Billions - Muchunguh, David (The Nation in Allafrica.com, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:HPKQLIY4 2405685:6QAGBDTM 4656463:3VX5BIBW

Using educational transitions to estimate learning loss due to COVID-19 school closures: The case of Complementary Basic Education in Ghana - Sabates, Ricardo; Carter, Emma; Stern, Jonathan M.B. (International Journal of Educational Development, 2021)
• Estimate learning losses during grade transition for disadvantaged and previously out of school students in Ghana. • The estimated average learning loss is around 66 % of previous learning gains in foundational numeracy during this transition period. • Widening gaps in learning loss are found according to availability of home learning support, as well as home learning resources. • Learning at home and in communities has to be reimagined if gains are to be achieved and losses are to be mitigated in the post-COVID 19 era. Learning loss is expected for millions of children who have been out of school as a result of the current COVID-19 pandemic. Unfortunately, it is uncertain how much learning will be lost and how wide the gaps may be for disadvantaged children. This paper uses a unique longitudinal dataset to estimate learning loss during a three-month transition from Complementary Basic Education to government schools in Ghana. Our results show an average learning loss of 66 % of previous learning gains in foundational numeracy during this transition period. More importantly, we estimate widening gaps in learning loss according to lack of home learning support, as well as lack of home learning resources. Our results have implications for the provision of learning activities and support at home, not just during current school closures due to COVID-19, but also during transitions between academic years.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2021.102377 2339240:SQ7VK9VL 2405685:KHANG6IQ
Keywords: BASIC education; CHILDREN with social disabilities; COVID-19 pandemic; COVID-19 school closure; EDUCATIONAL outcomes; Equity; Ghana; Learning; Literacy; Numeracy; SCHOOL closings

UNICEF Global Database on Information and Communication Technology (ICT) Skills - UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:YL9BXDTN 2405685:VU7YGIHC

Software preference for online learning of science and biology teachers under COVID-19 pandemic - Khaleyla, Firas; Wisanti, Wisanti; Ambarwati, Reni; Rahayu, Dwi Anggorowati; Putri, Eva Kristinawati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
As measure against the rapid spreading of coronavirus disease 2019 (COVID-19) which now has reached global level, Indonesian government established Large-scale Social Distancing (LsSD). As consequence, learning method used in junior and senior high school is substituted from face-to-face learning in class to online distance learning, including for science and biology. This study was conducted to know software preference used by science and biology junior and senior high school teachers for online learning during LsSD measure. A total of 189 science and biology junior and senior high school teachers from various area had given their response via questionnaire. Data was analyzed using quantitative descriptive method. About 57% respondents had never manage online learning before COVID-19 pandemic while the remaining 43% had experience in managing one before, however almost all managed online learning. Non-paid software used the most (81%) among respondents to manage online science/biology learning. Software types used were social networking (64%) especially WhatsApp, learning management system (LMS) (51%) especially Google Classroom, teleconference applications (12%), and assessment software outside of LMSs (15%). Software chosen were mostly non-paid, easily accessed by all people, already familiar among Indonesian, and its interface were easily mastered.
KerkoCite.ItemAlsoKnownAs: 10.22219/jpbi.v7i1.14253 2339240:B2NF22CZ 2405685:9Z5QJX7F

Academic Recovery Programme: Synthesis of Qualitative Data and High-level Overview - Haßler, Björn; Blower, Thomas; Megha-Bongnkar, Ghislaine; Regis, Callista (Open Development & Education, 2021)
Colophon: Commissioned by the Organization of Eastern Caribbean States, Castries, Saint Lucia. KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4555874 2129771:XAMQ949U 2405685:I9KQL5GV
Keywords: Author:Haßler; AuthorFirst:Haßler; _C:Dominica DMA; _C:Grenada GRD; _C:Saint Lucia LCA; _C:Saint Vincent and the Grenadines VCT; _yl:c

"Aprendo en Línea" mantendrá acceso gratuito desde dispositivos móviles - mineduc (Ministerio de educación, 2021)
“Aprendo en Línea” cuenta con más de 80.000 recursos pedagógicos digitales para estudiantes, apoderados, docentes y directivos.
KerkoCite.ItemAlsoKnownAs: 2339240:2JKEXBRV 2405685:VBF82GCL

The Absent Voices of Development Economics - Subramanian, Arvind; Kapur, Devesh (Project Syndicate, 2021)
Development economics focuses on improving the well-being of billions of people in low-income countries, but the Global South is severely underrepresented in the field. A small number of rich-country institutions dominate, and their growing use of randomized controlled trials in research is entrenching the imbalance.
Section: Economics & Finance KerkoCite.ItemAlsoKnownAs: 2339240:JI4Z5G8C 2405685:DZA5YC5V

Lao People’s Democratic Republic – ASEM Education - Asia-Europe Meeting (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:9C8XNI7E 2405685:4L9ZZA6N
Keywords: ⛔ No INSPIRE recid found

Needed: An Ecosystem for Meaningful Digital Innovation in Northern Kenya - Aslan Afrika (Aslan Afrika, 2021)
The information and communications technology (ICT) industry thrives in Kenyan cities, but vast rural tracts in Northern Kenya are stranded on the wrong side of the digital divide. One of the weakest links is a lack of infrastructure, both for […]
KerkoCite.ItemAlsoKnownAs: 2339240:M9U4C6IJ 2405685:4LVDHQIG

Our Kids Are Not Broken - Berger, Ron (The Atlantic, 2021)
I am concerned about how this growing narrative of loss will affect our students, emotionally and academically.
Section: Ideas KerkoCite.ItemAlsoKnownAs: 2339240:PDGZ2NCM 2405685:CCCBBVG4

One year into COVID-19 education disruption: Where do we stand? - UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:LCIHMACX 2405685:Q97KARUR

What ‘learning loss’ really means - The Washington Post - Strauss, Valerie (the Washington Post, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5DSLK69D 2405685:EFD7J6UK

GIS for Education Working Group launches to promote data-driven decision-making - The Education Comission (the Education Commission, 2021)
Around the world, individuals are using maps to power everyday decisions: how do I navigate from my home to the nearest hospital? How many supermarkets are in my community? What public transportation is available for me to take to work?
Section: Updates KerkoCite.ItemAlsoKnownAs: 2405685:Y735WFTU 4042040:JMFPTRHK

Delivering Quality Education and Health Care to All: Preparing Regions for Demographic Change - OECD (OECD, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1787/83025c02-en 2339240:G6KY28PG 2405685:A5DTA23J

Goodhart’s Law and the gaming of UK public spending numbers - Hood, Christopher; Piotrowska, Barbara (Public Performance & Management Review, 2021)
Goodhart’s Law, originally inspired by money-supply indicators, predicts high-consequence administrative numbers tend to be gamed out of meaningfulness. This paper argues that, in addition to the well-documented manipulation of aggregate input numbers at the top-levels of decision making and performance indicators used for output control at the lower level, meso-level gaming happens also on the input side of public expenditure planning and control. A key mechanism through which it operates is creative categorization in the classification of units of spending. Based on a UK study, we explore three questions: can we find evidence for the existence of gaming in public expenditure control, how does the creative categorization work and how material or consequential is it? Using case studies of “protected” spending, public-private partnerships and accounting changes, we show that gaming understood as creative categorization is readily observable in UK public expenditure control and Goodhart’s Law effects can indeed be material or consequential, both in scale and in their implications for government accountability. We conclude that creating new spending categories to control public expenditure and limit gaming is a two-edged sword since it itself creates new opportunities for gaming.
Publisher: Routledge _eprint: https://doi.org/10.1080/15309576.2020.1749092 KerkoCite.ItemAlsoKnownAs: 10.1080/15309576.2020.1749092 2339240:AL7M3EA4 2405685:ZNMNHT5B 4656463:X439Z2RN
Keywords: Goodhart’s Law; creative categorization; fiscal illusions; gaming; public finance management; public spending; rule bending

The development and policies of ICT supporting educational technology in Singapore, Thailand, Indonesia, and Myanmar - Machmud, Muhammad Takwin; Widiyan, Agung Purwa; Ramadhani, Noer Risky (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study has an objective to identify the development and policies of educational technology application in ASEAN countries. Through the literature review and analysis, this recent study has compared the issue of educational technology development and policies in ASEAN countries. The reviewing country has been chosen based on the Information and Communication Technology (ICT) index amongst the ASEAN countries, that are Singapore (as the highest rank), Thailand & Indonesia (as the middle rank), and Myanmar (as the lowest rank). The result of the study shows that the majority of the countries focused to improve network capabilities in supporting online learning, and the policies of each country showed a similarity in improving the technology equity for the learner. However, Singapore shows more advance technological implementation such as the application of broader Artificial Intelligence in classroom activity, while the use of Artificial Intelligence (AI) in Thailand and Indonesia still in developing progress. In conclusion, the technology education development in ASEAN countries has moved forward through the past year and the policies of educational technology for each country have been similar in strengthening the ASEAN plan.
KerkoCite.ItemAlsoKnownAs: 10.11591/ijere.v10i1.20786 2339240:7BX4XLWD 2405685:R2AWMPUW

Education financing in Nigeria and the impact of the COVID-19 pandemic - Okwuosa, Maryjacob; Whisper to Humanity; Halilu, Mukhtar (Global Partnership for Education, 2021)
As the COVID-19 pandemic strains national economies and budgets, the need to protect domestic education budgets and ensure that education remains a priority for national governments has never been more urgent. GPE Youth Leaders from Nigeria raise awareness on the problems the education sector is facing and call on leaders to increase their ambitions for financing education and development.
KerkoCite.ItemAlsoKnownAs: 2339240:W8F8KVSM 2405685:WXXP4NGC

Annual Status of Education Report. ASER-Pakistan 2021 - ASER Pakistan (ASER Pakistan Secretariate & Idara-e-Taleem-o-Agahi, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:CTU9LA3Q 2339240:MVDNFBGR 2405685:2IATPQCX 2405685:79X8U2KF

Will Every Child Be Able to Read by 2030? Defining Learning Poverty and Mapping the Dimensions of the Challenge - Azevedo, João Pedro; Goldemberg, Diana; Montoya, Silvia; Nayar, Reema; Rogers, Halsey; Saavedra, Jaime; Stacy, Brian William (World Bank Group, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:R5NR9Z2A 2405685:QJ7JZA6T

Nudging at Scale: Experimental Evidence from FAFSA Completion Campaigns - Bird, A., Kelli; Castleman, Benjamin; Denning, Jeffrey; Goodman, Joshua; Lamberton, Cait; Rosinger, Kelly Ochs (Journal of Economic Behaviour & Organization, 2021)
Do nudge interventions that have generated positive impacts at a local level maintain efficacy when scaled state or nationwide? What specific mechanisms explain the positive impacts of promising smaller-scale nudges? We investigate, through two randomized controlled trials, the impact of a national and state-level campaign to encourage students to apply for financial aid for college. The campaigns collectively reached over 800,000 students, with multiple treatment arms to investigate different potential mechanisms. We find no impacts on financial aid receipt or college enrollment overall or for any student subgroups. We find no evidence that different approaches to message framing, delivery, or timing, or access to one-on-one advising affected campaign efficacy. We discuss why nudge strategies that work locally may be hard to scale effectively.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jebo.2020.12.022 2339240:2RVLDCU8 2405685:D63Y92LP

CPD Implementation Roadmap - Cambridge Education (Cambridge Education, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:97LIFQ9D 2405685:APDWFXX2 2405685:AUN7ES7V

Sierra Leone teacher & school MIS developments: Sierra Leone Education Attendance Monitoring System (SLEAMS) and Teacher Records Management (TRM) system - Graham, Hannah (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KB3DUZXF 2405685:5NEC3AR4

Achieving mobile-enabled digital inclusion in Bangladesh - GSMA (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:668LBR98 2405685:W5VR72AL

9th Five-Year National Socio-Economic Development Plan (2021-2025) - Lao People’s Democratic Republic (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:32J3VUXB 2405685:47GEDTUV

Value for money and adaptive programming: Approaches, measurement and management - Laws, Ed; Valters, Craig (Overseas Development Institute (ODI), 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:M3LYTQTZ 2405685:TYR3WR4U

National Policy on Radical Inclusion in Schools - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5UGTMJFK 2405685:K5LB484Z

Gender Mainstreaming Strategic Plan in Education 2021–2025 - Ministry of Education, Youth and Sports, Royal Government of Cambodia (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:RHU8LCF2 2405685:BD9GLI2E

Africa: children out of primary school - Statista (2021)
As of 2019, 18.7 percent of children in primary-school-age were not enrolled in primary or secondary education in Sub-Saharan Africa.
KerkoCite.ItemAlsoKnownAs: 2339240:FY7GASPI 2405685:3ENXC6R5
Keywords: ⛔ No INSPIRE recid found

Language data for Malawi - Translators Without Borders (Translators without Borders, 2021)
Open-source language data and maps about languages spoken in Malawi can improve how we communicate with communities in crisis.
KerkoCite.ItemAlsoKnownAs: 2405685:85LDSX3J 4042040:U37DNB2H

Language of Instruction Country Profile: Malawi - USAID (United States Agency for International Development, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:QB34QBQL 4042040:R9YNHPBC

Policy Linking for Measuring Global Learning Outcomes | Education Links - USAID (2021)
Check out the policy linking video below , Express Interest in an Upcoming Training , USAID has worked closely with global partners including with the World Bank, UNESCO Institute for Statistics (UIS)
KerkoCite.ItemAlsoKnownAs: 2339240:VGYD2PE3 2405685:ZJJI7DL8

Kenya GPE 19 Learning Continuity in Basic Education Project - Implementation Status and Results Report - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:PNX9ZBM7 2405685:LRBZ32RR

Comparative Study of Education Funding in Nigeria - Agbai, Edward; Okafor, Anthony; Egbedoyin, Funminiyi (2021)
This study provides a comparative review of education funding across geopolitical zones in Nigeria and draws a nexus between Nigeria’s budgetary allocation to education and some selected African countries. Education funding in Nigeria has lagged the UNESCO’s advised 15%-20% of the government's annual budget to education in the last three decades. We assess education funding across the six geopolitical zones between 2010 and 2019 using content analysis of the respective states. A review of the WAEC enrollment for states in each zone is performed to compare how education funding impacts WAEC enrollment in Nigeria. The study identifies a link between poverty and income inequality and education funding in Nigeria by leveraging data from the World Bank and Nigeria Bureau of Statistics (NBS) from 2001-2019. We identify low funding of education as the primary driver of poverty and inequality in Nigeria. The study recommends a diversified funding mechanism to enhance the sector's funding and improve the quality of education in the country.
KerkoCite.ItemAlsoKnownAs: 2339240:Y8VIFG7R 2405685:KHV64L6J
Keywords: Education Funding; Nigeria; Poverty and Inequality

COVID-19 and the surge of absenteeism in SA schools - ISSAfrica (ISS Africa, 2021)
The impact of higher-than-expected absence rates is significant and will be compounded by a third wave.
KerkoCite.ItemAlsoKnownAs: 2339240:UCM5WNR7 2405685:GD7MXME8

Education Finance Watch 2021 - Al-Samarrai, Samer; Cerdan-Infantes, Pedro; Bigarinova, Aliya; Bodmer, Juanita; Vital, Marianne Joy Anacleto; Antoninis, Manos; Bakarat, Bilal Fouad; Murakami, Yuki (World Bank Group, 2021)
Education Finance Watch 2021 (English)
KerkoCite.ItemAlsoKnownAs: 2339240:NHKZM26P 2405685:EZIDC645

يونسکو: په کوچنيوالي کې په مورنۍ ژبه زده کړې د يادښت بنسټ دی - الله, نشرونکی امین (بااحساسه محصلين, 2021)
محصلين (شنبه، د کب۲, ۱۳۹۹هـ ق) د ملګرو ملتونو ښوونیز، علمي او کلتوري سازمان يونسکو، د مورنۍ ژبې نړيوالې ورځې ( د فبروري ۲۱) په مناسبت په خپل پیغام کې ويلي دي چې په مورنۍ ژبه زده کړه بايد د وړوکتوب
KerkoCite.ItemAlsoKnownAs: 2405685:SBGXS4W5 4042040:9A9Z5Y9Z

Mother Language Day 2021: Improving data on mother-tongue languages for better learning outcomes - EdTech Hub (2021)
To celebrate International Mother Language Day 2021, EdTech Hub’s Björn Haßler spoke with Alice Castillejo and Mia Marzotto of Translators without Borders. They talked about the importance of mother tongue-based education and the need to support speakers of marginalised languages. This blog post captures their conversation. “How do we know that speakers of marginalised languages are left behind?” Alice: Research…
KerkoCite.ItemAlsoKnownAs: 2405685:EVU4DEWP 4042040:T3S2AEMN

The changing role of teachers and technologies amidst the COVID 19 pandemic: key findings from a cross-country study - Barron, Maria; Cobo, Cristobal; Munoz-Najar, Alberto; Sanchez Ciarrusta, Inaki (World Bank Blogs - Education for Global Development, 2021)
Despite the overwhelming consequences of the pandemic, this global crisis has also been an extraordinary time for learning.
KerkoCite.ItemAlsoKnownAs: 2339240:Q6F976QJ 2339240:UC2VMBYK 2405685:D3QRPSST 2405685:TZGSSJ5F
Keywords: ___working_potential_duplicate

A glimpse into the lived experiences and challenges faced of PWD students towards online learning in the Philippines amidst COVID-19 pandemic - Dianito, Ann Jesamine; Espinosa, Jomarie; Duran, Jimboy; Tus, Jhoselle (International Journal Of Advance Research And Innovative Ideas In Education, 2021)
Amidst the global pandemic, everyone is allowed to be vulnerable and heightened by burnout. But the most unheard and most vulnerable voices linger among persons with disabilities. Persons with disabilities (PWDs) are one of the concerns in society. But, social exclusions and biases put PWDs in a disadvantageous position. There has always been an issue in employment, social roles, and accessibility to education. These issues are eventually turning into self-doubt and feelings of inferiority, which are reasonable evidence suggesting that persons with disabilities received negative attitudes from non-PWD individuals. This study's primary goal is to explore the lived experiences of PWD Students towards online learning during the pandemic, specifically, describe their experiences, challenges faced, and coping mechanisms. Employing the Interpretative Phenomenological Analysis (IPA), the findings of the study were: (1) PWD students experienced social exclusions primarily in the rise of online learning during the pandemic. (2) Most of the PWD students were challenged by the limitations of assistive technologies and internet connectivity. (3) PWD students remained resilient because of having a healthy support system behind them.
KerkoCite.ItemAlsoKnownAs: 10.6084/m9.figshare.14033435.v1 2339240:7BJBAEKH 2405685:CFKEASTA
Keywords: ⛔ No INSPIRE recid found

FOUNDATIONS OF CLASSROOM CHANGE IN DEVELOPING COUNTRIES Vol.2: Synthesis - Guthrie, Gerard (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:XHXMGVY3

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (Zenodo, 2021)
[No description available.]
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4540204 2339240:TTFT62A6 2405685:LNYTJDFW

Characteristics of Effective Technology-Enabled Teacher Learning Circles — Rapid Review of the Literature - Khalayleh, Abdullah; El-Serafy, Yomna; Haßler, Björn (Open Development & Education, 2021)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4537843 2129771:ZBHBQT7T 2405685:XX2BVQGM
Keywords: Author:Haßler; _yl:a

Final report - Khalayleh, Abdullah; El-Serafy, Yomna; Haßler, Björn (Open Development & Education, 2021)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4540043 2129771:6T2RCX4X 2405685:NWZU67FG
Keywords: Author:Haßler; _yl:b

Right to read: Joint efforts to provide books to minority-language learners - Thaung, Nyi Nyi; Gracie, Kristen (Education for All blog, 2021)
During this world-upending pandemic, ethnolinguistic minority learners are falling further through the cracks. Even if they have access to the technology necessary for distance learning, they will likely not receive content in their own language. Here is what organizations like UNESCO are doing to make sure minority learners don’t fall further behind.
KerkoCite.ItemAlsoKnownAs: 2405685:6ZQXE9WA 4042040:GJTQ6L6K

India’s public edtech broadcast system DIKSHA has a private bottleneck - Banerji, Olina (The Ken, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8VZS43UH 2405685:KYKN689Y

Improving secondary education in Sierra Leone - De, Sourovi; Durrani, Zara; Khurshid, Ayesha (Oxford Policy Management, 2021)
We are leading the monitoring, evaluation and research delivery of a five year programme to improve secondary education and long term growth in Sierra Leone
KerkoCite.ItemAlsoKnownAs: 2405685:268JSEX2 2486141:EJ4VUWUC

Preprinting the COVID-19 pandemic - Fraser, Nicholas; Brierley, Liam; Dey, Gautam; Polka, Jessica K.; Pálfy, Máté; Nanni, Federico; Coates, Jonathon Alexis (bioRxiv, 2021)
The world continues to face a life-threatening viral pandemic. The virus underlying the COVID-19 disease, SARS-CoV-2, has caused over 98 million confirmed cases and 2.2 million deaths since January 2020. Although the most recent respiratory viral pandemic swept the globe only a decade ago, the way science operates and responds to current events has experienced a paradigm shift in the interim. The scientific community has responded rapidly to the COVID-19 pandemic, releasing over 125,000 COVID-19 related scientific articles within 10 months of the first confirmed case, of which more than 30,000 were hosted by preprint servers. We focused our analysis on bioRxiv and medRxiv, two growing preprint servers for biomedical research, investigating the attributes of COVID-19 preprints, their access and usage rates, as well as characteristics of their propagation on online platforms. Our data provides evidence for increased scientific and public engagement with preprints related to COVID-19 (COVID-19 preprints are accessed more, cited more, and shared more on various online platforms than non-COVID-19 preprints), as well as changes in the use of preprints by journalists and policymakers. We also find evidence for changes in preprinting and publishing behaviour: COVID-19 preprints are shorter and reviewed faster. Our results highlight the unprecedented role of preprints and preprint servers in the dissemination of COVID-19 science, and the impact of the pandemic on the scientific communication landscape.
Publisher: Cold Spring Harbor Laboratory Section: New Results KerkoCite.ItemAlsoKnownAs: 10.1101/2020.05.22.111294 2129771:5BNWNCDU 2129771:73S9KNMK 2405685:WG9YMLGJ

Uganda: Students back to school, university in March - Kyeyune, Hamza (Anadolu Agency, 2021)
Some more school classes to start March 1, universities to reopen in staggered manner, says president - Anadolu Agency
KerkoCite.ItemAlsoKnownAs: 2339240:2DZ7I775 2405685:WQR3CKZU

What do developing country governments learn from aid? Evidence from survey experiments with 900 education policymakers in 36 countries - Crawfurd, Lee; Hares, Susannah; Khan, Ayesha; Minardi, Ana; Sandefur, Justin (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8GZJF6IU 2405685:3VT4H3Z4

Cochrane Rapid Reviews Methods Group offers evidence-informed guidance to conduct rapid reviews - Garritty, Chantelle; Gartlehner, Gerald; Nussbaumer-Streit, Barbara; King, Valerie J.; Hamel, Candyce; Kamel, Chris; Affengruber, Lisa; Stevens, Adrienne (Journal of Clinical Epidemiology, 2021)
ObjectivesTo develop methods guidance to support the conduct of rapid reviews (RRs) produced within Cochrane and beyond, in response to requests for timely evidence syntheses for decision-making purposes including urgent health issues of high priority.
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.jclinepi.2020.10.007 2339240:Q42ZR8QX 2405685:9HWTVHE9

Computer-assisted instruction tools: A model to guide use in low-and middle-income countries - Kaye, Thomas; Ehren, Melanie (International Journal of Education and Development using Information and Communication Technology, 2021)
Learning outcomes in low- and lower-middle-income countries (LMICs) require significant improvement. With traditional reform efforts taking many years to realise results, education practitioners in LMICs are searching for innovative ways to rapidly strengthen learning outcomes. One tool showing promise is computer-assisted instruction (CAI). While a growing number of studies document CAI’s positive impacts on learning outcomes, others have found nil or negative effects. Research has yet to identify why these differences occur, and, most importantly, which factors must be in place to ensure that CAI contributes to improving learning outcomes. The aim of our research was to fill this gap in the research by developing a model highlighting those factors influencing the results of CAI interventions. Adopting a realist-informed methodology, we analysed 21 resources shared by 13 experts from around the world. We used the results of this analysis to develop a model that outlines key trends that facilitate and/or impede the deployment of CAI tools in LMICs. We find that key factors that should be considered when designing CAI interventions include the operating environment; stakeholder engagement; infrastructure; technological trust; CAI tool design; content curation/creation; student engagement; classroom integration; teacher capacity; student capacity; and data collection and use. This model highlights both these individual elements as well as noting how these elements interact. The model provides a foundation that can guide future research in this under-examined area.
Publisher: University of the West Indies KerkoCite.ItemAlsoKnownAs: 2339240:A3WF6P6D 2339240:KUAK4YAL 2339240:XJJARH42 2405685:8H75L794 2405685:PB6US4IE 2405685:U97W3BR2
Keywords: ⛔ No DOI found

Cochrane Rapid Reviews Methods Group offers evidence-informed guidance to conduct rapid reviews - Garritty, Chantelle; Gartlehner, Gerald; Nussbaumer-Streit, Barbara; King, Valerie J.; Hamel, Candyce; Kamel, Chris; Affengruber, Lisa; Stevens, Adrienne (Journal of Clinical Epidemiology, 2021)
OBJECTIVES: To develop methods guidance to support the conduct of rapid reviews (RRs) produced within Cochrane and beyond, in response to requests for timely evidence syntheses for decision-making purposes including urgent health issues of high priority. STUDY DESIGN AND SETTING: Interim recommendations were informed by a scoping review of the underlying evidence, primary methods studies conducted, and a survey sent to 119 representatives from 20 Cochrane entities, who were asked to rate and rank RR methods across stages of review conduct. Discussions among those with expertise in RR methods further informed the list of recommendations with accompanying rationales provided. RESULTS: Based on survey results from 63 respondents (53% response rate), 26 RR methods recommendations are presented for which there was a high or moderate level of agreement or scored highest in the absence of such agreement. Where possible, how recommendations align with Cochrane methods guidance for systematic reviews is highlighted. CONCLUSION: The Cochrane Rapid Reviews Methods Group offers new, interim guidance to support the conduct of RRs. Because best practice is limited by the lack of currently available evidence for some RR methods shortcuts taken, this guidance will need to be updated as additional abbreviated methods are evaluated.
436 citations (Crossref) [2024-02-28] KerkoCite.ItemAlsoKnownAs: 10.1016/j.jclinepi.2020.10.007 2339240:WP6K2QWK 2405685:MLAZTXPT
Keywords: Decision-making; Evidence synthesis; Rapid review; Systematic review; ⛔ No INSPIRE recid found

Reimagining Girls' Education: Solutions to keep girls learning in emergencies - Guglielmi, Silvia; Jones, Nicola; Nicolai, Susan; Pereznieto, Paola; Plank, Georgia; Vu, Nhung; Sanchez-Tapia, Ingrid; Mackintosh, Alasdair (UNICEF, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:34NUHRTZ 2339240:8ZNTUL5A 2405685:MZB8Q7PA 2405685:TSIVULXP
Keywords: Access to Education; Barriers; Context Effect; Cost Effectiveness; Costs; Disadvantaged Youth; Distance Education; Educational Finance; Educational Technology; Emergency Programs; Equal Education; Evidence Based Practice; Females; Foreign Countries; Gender Bias; Inclusion; Intervention; Planning; Sex Fairness; Sex Stereotypes; Teaching Methods; Technology Uses in Education

Arm-wrestling in the classroom: the non-monotonic effects of monitoring teachers - Lichand, Guilherme; Wolf, Sharon (University of Zurich Department of Economics, 2021)
Teacher absenteeism and shirking are common problems in developing countries. While monitoring teachers should ameliorate those problems, mobilizing parents to do so often leads to small or even negative effects on learning outcomes. This paper provides causal evidence that this might result from non-monotonic effects of monitoring teachers. Cross-randomizing nudges to teachers and parents in Ivory Coast – to motivate and monitor teachers directly, and to mobilize parents –, we find that, in schools where parents are nudged, numeracy and literacy test scores improve by an additional school quarter, and student dropouts decrease by over 50%. In contrast, in schools where both are nudged, there is no effect on either learning outcomes or dropouts – even though the latter also fall by nearly 50% where teachers are nudged alone. In those schools, teachers show up less frequently, allocate less time to career development, and target instruction to top students to a greater extent than in schools where only parents are nudged. Monitoring backfires precisely for teachers who were most motivated at baseline, consistent with monitoring intensity eventually crowding out intrinsic motivation. Our results have implications for the design of accountability programs above and beyond education.
Num Pages: 79 Number: 357 Publisher: University of Zurich KerkoCite.ItemAlsoKnownAs: 2339240:25SIYBSH 2405685:8JXUFKSH

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:JUGDD7MG 2405685:CYTW2JQW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Transforming Education Service Delivery Through Evidence-Informed Policy and Practice - The Ministry of Basic and Senior Secondary Education (MBSSE) (The Ministry of Basic and Senior Secondary Education (MBSSE), 2021)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4550561 2129771:49ZQ5QHA 2405685:F2VBE6CR

Digital Literacy in Education Systems across ASEAN - UNICEF EAPRO (UNICEF East Asia and Pacific Regional Office, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8HH7L8U6 2405685:7QU4PJKQ

An open source machine learning framework for efficient and transparent systematic reviews - van de Schoot, Rens; de Bruin, Jonathan; Schram, Raoul; Zahedi, Parisa; de Boer, Jan; Weijdema, Felix; Kramer, Bianca; Huijts, Martijn; Hoogerwerf, Maarten; Ferdinands, Gerbrich; Harkema, Albert; Willemsen, Joukje; et al. (Nature Machine Intelligence, 2021)
To help researchers conduct a systematic review or meta-analysis as efficiently and transparently as possible, we designed a tool to accelerate the step of screening titles and abstracts. For many tasks—including but not limited to systematic reviews and meta-analyses—the scientific literature needs to be checked systematically. Scholars and practitioners currently screen thousands of studies by hand to determine which studies to include in their review or meta-analysis. This is error prone and inefficient because of extremely imbalanced data: only a fraction of the screened studies is relevant. The future of systematic reviewing will be an interaction with machine learning algorithms to deal with the enormous increase of available text. We therefore developed an open source machine learning-aided pipeline applying active learning: ASReview. We demonstrate by means of simulation studies that active learning can yield far more efficient reviewing than manual reviewing while providing high quality. Furthermore, we describe the options of the free and open source research software and present the results from user experience tests. We invite the community to contribute to open source projects such as our own that provide measurable and reproducible improvements over current practice.
Number: 2 Publisher: Nature Publishing Group KerkoCite.ItemAlsoKnownAs: 10.1038/s42256-020-00287-7 2405685:9JHZVHCH 2405685:QJXHWPWZ 2486141:B2E3YCYA 2486141:JV7SWTDP 2486141:MBP3F287
Keywords: Computational biology and bioinformatics; Computer science; Medical research; SARS-CoV-2; _Added-ailr-2024

Two-Thirds of Poorer Countries Are Cutting Education Budgets Due to COVID-19 - World Bank (World Bank, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:GK2Z7TZH 2405685:HJF56BG6

Jusoor’s WhatsApp-Assisted Learning Programme: Sprint Review 1 - Tutunji, Suha; Boujikian, Michèle; Carter, Alice; Atkinson, Grace (2021)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4468599 2405685:AR38F6N8
Keywords: ___working_potential_duplicate

Summary: Webinar on COVID-19 fallout on poverty and livelihoods in Bangladesh: results from SANEM’s nation-wide survey conducted in Nov-Dec 2020 - SANEM (SANEM, 2021)
The 10th episode of SANEM Shongzog on "COVID-19 Fallout on Poverty and Livelihoods in Bangladesh: Results from SANEM's Nationwide Survey (Nov-Dec 2020)" was held on 23 January 2021.
KerkoCite.ItemAlsoKnownAs: 2339240:KE7K5Y72 2405685:9MSRWZEF

Intentional and logical survey and audience data collection: KoBo Toolbox - Carver, D (The Content Technologist, 2021)
KoBo Toolbox's robust survey platform is free to use for all as a data collection tool, optimized for many devices and environments.
KerkoCite.ItemAlsoKnownAs: 2405685:JI2QVECB 2486141:AR5ECTYZ

South Africa: Schools to stay closed amid surge in coronavirus cases - Ongmu, Kalden (WION, 2021)
The reopening of South African schools for the new academic year has been postponed by two weeks in the wake of rising new covid-19 variant cases. “All stakeholders were united in supporting a delay in the opening of schools. Given the pressure experienced by the health system in the past weeks due to covid-19, the council of education, ministers in conjunction with NCCC and cabinet has taken a decision to delay the reopening of both public and private schools by two weeks, Deputy Minister of Basic Education, Reginah Mhaule said.
KerkoCite.ItemAlsoKnownAs: 2339240:Y3LQKI97 2405685:BTK7JUSE

'Paradox' of Korail slum during COVID-19: ethnography of governance from below - BIGD (2021)
Urban slums are one of the most vulnerable communities during the COVID-19 pandemic; overcrowding and resource constraints make physical distancing and self-quarantine nearly impossible, creating a risk of a rapid spread of the infection. The conversations in the media and among other stakeholders were focused on these risk factors as well as the economic distress of the people in slums created by the pandemic. However, these discussions were primarily based on the perspectives of 'outsiders', with limited understanding of what was happening in the slums. With this gap in mind, we conducted an anthropological exploration of Korail, the largest slum in Dhaka city from September to December 2020, to uncover the emic views of slum dwellers' everyday life during the pandemic and understand the outbreak from their perspective. Findings from the study were presented in our webinar "'Paradox' of Korail slum during COVID-19: Ethnography of Governance from Below" on Thursday, 21 January 2021 from 4:00 pm to 5:30 pm (GMT+6), by Dr Shahaduz Zaman, Reader in Medical Anthropology and Global Health, Brighton and Sussex Medical School. This study is a part of the Covid Collective initiative. Supported by the UK Foreign Commonwealth and Development Office (FCDO), the Covid Collective is based at the Institute of Development Studies (IDS). The Collective brings together the expertise of, UK and Southern-based research partner organisations and offers a rapid social science research response to inform decision-making on some of the most pressing Covid-19 related development challenges.
KerkoCite.ItemAlsoKnownAs: 2339240:KE9IRVX3 2405685:Z8CMANRJ

DEFI Launch Presentation - DEFI Cambridge (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:N39L59NI 2405685:QSW66P3B

Schools in Ghana reopen as covid-19 cases surge - AfricaNews (Africanews, 2021)
Temperature checks and mandatory wearing of masks as schools in Ghana reopen for the 2020/2021 calendar after ten months of closure. The shutdown of the academic calendar was in response to the outbreak of the coronavirus in March last year.
KerkoCite.ItemAlsoKnownAs: 2339240:JRJ8TDSS 2405685:BUVNZQ5M

Coronavirus: Rwanda and Malawi shut schools as cases surge - AfricaNews (Africanews, 2021)
Africa has reported over 3.1 million cases and more than 76,000 deaths since the outbreak started,
KerkoCite.ItemAlsoKnownAs: 2339240:8HEGJ8DW 2405685:FTC6JMP2

World Bank helps Bangladesh provide education and skills training to poor children and youths - ReliefWeb (OCHA, 2021)
English News and Press Release on Bangladesh about Contributions, Education, Epidemic and more; published on 18 Jan 2021 by World Bank
KerkoCite.ItemAlsoKnownAs: 2339240:YW8V8Z46 2405685:BLFQEDDB

Mobile Penetration and Growth in Kenya - Kibuacha, Frankline (GeoPoll, 2021)
Kenya is one of the most technology-advanced countries in Africa, which has had many christen it the Silicon Savannah, powered by its mobile penetration.
KerkoCite.ItemAlsoKnownAs: 2339240:SZABY9CX 2405685:DBYZ5YH6

Effects of school closures on secondary school teachers and leaders in Rwanda: results from a phone survey - Laterite; Research for Equitable Access and Learning (REAL) Centre (The Education and Development Forum (UKFIET), 2021)
This blog was written by Laterite and the Research for Equitable Access and Learning (REAL) Centre at the University of Cambridge, who are working together as learning partners on the Mastercard Foundation’s Leaders in Teachers initiative in Rwanda. On 14 March 2020, the Government of Rwanda announced the closure of all schools in the country […]
KerkoCite.ItemAlsoKnownAs: 2339240:R8H65BXX 2405685:4K2K8SW5

Academic Recovery Programmes in the Eastern Caribbean — Literature Review - Haßler, Björn; Adam, Taskeen; Blower, Thomas; Megha-Bongnkar, Ghislaine (Open Development & Education, 2021)
This report was commissioned by the Organization of the Eastern Caribbean states. It reviews the literature on Academic Recovery Programmes with view to applicability in the Eastern Caribbean, and particularly Dominica, Grenada, Saint Lucia and Saint Vincent and the Grenadines.
Colophon: Commissioned by the Organization of Eastern Caribbean States, Castries, Saint Lucia. KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4555872 2129771:DZA3GVBD 2405685:MNS7ECK7
Keywords: Author:Haßler; AuthorFirst:Haßler; _C:Dominica DMA; _C:Grenada GRD; _C:Saint Lucia LCA; _C:Saint Vincent and the Grenadines VCT; _yl:b

Radio in Education in the Face of COVID-19 - Núñez, Felix (Institute for the Future of Education, 2021)
The pandemic came to reaffirm radio as a flexible, massive, low-cost, and long-range communication medium for education.
KerkoCite.ItemAlsoKnownAs: 2339240:U69AUKVX 2405685:CK8VWPIP

Children in the digital environment: Revised typology of risks - OECD (OECD, 2021)
The digital environment has become an integral part of children’s everyday lives and interactions. The benefits can be tremendous, but there also risks. In 2011, the OECD adopted a Typology of Risks in an effort to broadly categorise those risks. Since then the digital environment has changed significantly, as risks have evolved in nature and new ones have emerged. This report informs the OECD’s broader work on children in the digital environment by examining these trends and presenting an updated Typology of Risks. The Typology provides a high-level overview of the risk landscape, and outlines four risk categories and their manifestations. The Typology also identifies and analyses risks that cut across these four risk categories, and that can therefore have wide-ranging effects on children’s lives.
KerkoCite.ItemAlsoKnownAs: 10.1787/9b8f222e-en 2339240:XHMZ9GF7 2405685:356IBD77

List of types of systems theory - Wikipedia (Wikipedia, 2021)
This list of types of systems theory gives an overview of different types of systems theory, which are mentioned in scientific book titles or articles. The following more than 40 types of systems theory are all explicitly named systems theory and represent a unique conceptual framework in a specific field of science. Systems theory has been formalized since the 1950s, and a long set of specialized systems theories and cybernetics exist. In the beginnings, general systems theory was developed by Ludwig von Bertalanffy to overcome the over-specialisation of the modern times and as a worldview using holism. The systems theories nowadays are closer to the traditional specialisation than to holism, by interdependencies and mutual division by mutually-different specialists.
Page Version ID: 998624856 KerkoCite.ItemAlsoKnownAs: 2339240:9ZNWIT4X 2405685:XFYANJMX

Education in Africa: What are we learning? - Evans, David K; Acosta, Amina Mendez (Journal of African Economies, 2021)
Abstract Countries across Africa continue to face major challenges in education. In this review, we examine 145 recent empirical studies (from 2014 onward) on how to increase access to and improve the quality of education across the continent, specifically examining how these studies update previous research findings. We find that 64% of the studies evaluate government-implemented programs, 36% include detailed cost analysis and 35% evaluate multiple treatment arms. We identify several areas where new studies provide rigorous evidence on topics that do not figure prominently in earlier evidence syntheses. New evidence shows promising impacts of structured pedagogy interventions (which typically provide a variety of inputs, such as lesson plans and training for teachers together with new materials for students) and of mother tongue instruction interventions, as well as from a range of teacher programs, including both remunerative (pay-for-performance of various designs) and non-remunerative (coaching and certain types of training) programs. School feeding delivers gains in both access and learning. New studies also show long-term positive impacts of eliminating school fees for primary school and positive impacts of eliminating fees in secondary school. Education technology interventions have decidedly mixed impacts, as do school grant programs and programs providing individual learning inputs (e.g., uniforms or textbooks).
KerkoCite.ItemAlsoKnownAs: 10.1093/jae/ejaa009 2405685:F7DI6B3X 2405685:ZLY77F8G 2486141:9TKVGU5V 4042040:NZPKHM3S

An Investigation of pre-service teachers' motives for using Instagram: Pre-service teachers' motives for using Instagram - Ramazanoğlu, Mehmet; Toytok, Esef Hakan (International Journal of Curriculum and Instruction, 2021)
The aim of the study was to determine the motivations of pre-service teachers to use Instagram program, which is one of the common social media tools, in the context of developments in information and communication technologies in order to achieve sustainable learning and examine them according to various variables. The study was designed via descriptive survey model in the quantitative method. The population of the research consisted of pre-service teachers who pursued their education at the Faculty of Education of Siirt University in the spring term of 2018-2019 academic year. In the study, convenient sampling (easily accessible) and criterion sampling methods were utilized. In this context, 384 of the 495 scales distributed were returned and 56 of them were excluded from the research because they were not properly filled, 163 of them were excluded from the research because they did not meet the criteria; therefore, opinions of 165 pre-service teachers were included in the research and analysed. Personal demographic form and Instagram usage motivation scale were used as data collection tool of the research. The results obtained in the research showed that pre-service teachers use Instagram for social escape / relaxation and personal development / self-expression the most with respect to their motivations to use Instagram while they use it with the purpose of entertainment / habit the least. It was observed that Instagram using motivations of pre-service teachers show significant differences in different factors according to gender, age, department and daily time spent in Instagram variables. In addition, it was found out that pre-service teachers should be able to use the Instagram program, which is one of the world-renowned social networking software, for a sustainable education and training life more dynamically and effectively.
Number: 1 KerkoCite.ItemAlsoKnownAs: 2339240:CPP7DSJE 2405685:VS56Z2RB
Keywords: ⛔ No DOI found

Edtech disruption logic and policy work: the case of an Israeli edtech unit - Ramiel, Hemy (Learning, Media and Technology, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2020.1737110 2339240:NG3PRUUD 2405685:RZNY4AE7

Assessing cost-effectiveness with equity of a programme targeting marginalised girls in secondary schools in Tanzania - Sabates, Ricardo; Rose, Pauline; Alcott, Benjamin; Delprato, Marcos (Journal of Development Effectiveness, 2021)
Cost-effectiveness studies rarely pay explicit attention to whether resources are used effectively to benefit the most marginalised. By linking a quasi-experimental design with detailed financial information, we analyse the cost-effectiveness of the Campaign for Female Education (CAMFED)’s programme in Tanzania. The programme provides targeted, multi-dimensional support to marginalised girls in government secondary schools in deprived rural areas. We find the cost-effectiveness of CAMFED’s programme to be similar to interventions designed for more advantaged populations who are easier (and less costly) to reach. There is further evidence of positive spill-over effects to boys in the schools supported by CAMFED.
Publisher: Routledge _eprint: https://doi.org/10.1080/19439342.2020.1844782 KerkoCite.ItemAlsoKnownAs: 10.1080/19439342.2020.1844782 2339240:IZUVIXVI 2405685:NV3ND4MJ
Keywords: Cost effectiveness; Girls’ Education; Tanzania; equity

Assessing cost-effectiveness with equity of a programme targeting marginalised girls in secondary schools in Tanzania - Sabates, Ricardo; Rose, Pauline; Alcott, Benjamin; Delprato, Marcos (Journal of Development Effectiveness, 2021)
Cost-effectiveness studies rarely pay explicit attention to whether resources are used effectively to benefit the most marginalised. By linking a quasi-experimental design with detailed financial information, we analyse the cost-effectiveness of the Campaign for Female Education (CAMFED)’s programme in Tanzania. The programme provides targeted, multi-dimensional support to marginalised girls in government secondary schools in deprived rural areas. We find the cost-effectiveness of CAMFED’s programme to be similar to interventions designed for more advantaged populations who are easier (and less costly) to reach. There is further evidence of positive spill-over effects to boys in the schools supported by CAMFED.
Publisher: Routledge _eprint: https://doi.org/10.1080/19439342.2020.1844782 KerkoCite.ItemAlsoKnownAs: 10.1080/19439342.2020.1844782 2339240:FRZIQURK 2405685:VBG6JSIG
Keywords: Cost effectiveness; Girls’ Education; Tanzania; equity

Evaluating an e-learning platform at graduate school based on user experience evaluation technique - Abubakari, M S; Nurkhamid; Hungilo, G (Journal of Physics: Conference Series, 2021)
Abstract This study was aimed to evaluate the e-learning platform in a graduate school by using User Experience Questionnaire (UEQ). The data were collected from 65 respondents and analyzed using an excel data analysis tool. The results indicate that all six scales of the instrument are consistent except the novelty scale. Also, the calculated means of the scales are slightly positive as all values are greater than 0.8 compared to the UEQ benchmark. Although the respondents show a little positive impression with the platform, all scales means are below average category except efficiency scale which is above average as compared to the benchmark. This indicates that the platform needs more improvement in all aspects of user experience for it to be at least in a good category. The findings discussed in this paper are valuable for all academic stakeholders in various educational institutions which implement interactive e-learning systems as well as practitioners of user experience and developers of e-learning systems.
KerkoCite.ItemAlsoKnownAs: 10.1088/1742-6596/1737/1/012019 2339240:Y6AL29ZG 2405685:29F33I7D

How much can we remedy very low learning levels in rural parts of low-income countries? Impact and generalizability of a multi-pronged para-teacher intervention from a cluster-randomized trial in the Gambia - Eble, Alex; Frost, Chris; Camara, Alpha; Bouy, Baboucarr; Bah, Momodou; Sivaraman, Maitri; Hsieh, Pei-Tseng Jenny; Jayanty, Chitra; Brady, Tony; Gawron, Piotr; Vansteelandt, Stijn; Boone, Peter; et al. (Journal of Development Economics, 2021)
Despite large schooling and learning gains in many developing countries, children in highly deprived areas are often unlikely to achieve even basic literacy and numeracy. We study how much of this problem can be resolved using a multi-pronged intervention combining three interventions known to be separately effective. We conducted a cluster-randomized trial in The Gambia evaluating a literacy and numeracy intervention designed for primary-aged children in remote parts of poor countries. The intervention combines para teachers delivering after-school supplementary classes, scripted lesson plans, and frequent monitoring focusing on improving teacher practice (coaching). A similar intervention previously demonstrated large learning gains in rural India. After three academic years, Gambian children allocated to the intervention scored 46 percentage points (3.2 SD) better on a combined literacy and numeracy test than control children. Our results demonstrate that, in this type of area, aggressive interventions can yield far greater learning gains than previously shown.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jdeveco.2020.102539 2339240:SYNTYYVY 2405685:NWHCQ652 4656463:APB653HY

The Views of University Students About the Achievements and Motivations of the Distance Education Process During the Pandemic Period - Güldal Kan, Şebnem; Çaltıkuşu, Çilem; Şensoy, Şeniz (Propósitos y Representaciones, 2021)
The aim of this study is to examine the views of students about the achievements and motivations of thedistance education processes in universities during the pandemic period. The working group consists of 68 prospective teachers who continue their undergraduate programs in different departments of a private university in Northern Cyprus in the 2019-2020 spring academic year. All these participantsarestudying at thevariousdepartments of theFaculty of Education as 17 are in Pre-school Education, 28 in PrimaryEducationMathematics, 6 in PrimaryEducation, 1 in HistoryTeaching, 12 in Special Needs Education, 4 of them arestudying in Guidance and Psychological Counseling. The study is a qualitative study and the design of the study is determined as a case study. 42 female and 26 male teacher candidates participated in the study group. The majority of the participants are prospective teachers studying in their final year at university. While choosing the participants, easily accessible case sampling from purposeful sampling type was used. A Semi-structured interview form was used as a toolfordata collection. Later, the opinions of the experts were obtained and the interview questions were re-arranged accordingly and applied to the participants. As a result of the research, it was concluded that the psychological trauma experienced by teacher candidates during distance education at thepandemicperiodaffects both the success and motivation of their lessons.
KerkoCite.ItemAlsoKnownAs: 10.20511/pyr2021.v9nSPE3.1165 2339240:3524XZX7 2405685:AE8RCH6V

Does teacher burnout affect students? A systematic review of its association with academic achievement and student-reported outcomes - Madigan, Daniel J.; Kim, Lisa E. (International Journal of Educational Research, 2021)
We provide the first systematic review of studies examining the consequences of teacher burnout for students. In doing so, we focused on academic achievement and student-reported outcomes. A systematic literature search returned 14 studies including 5,311 teachers and 50,616 of their students. The findings provided some evidence that teacher burnout is associated with worse academic achievement and lower quality student motivation, but little evidence that it is associated with student wellbeing. There is a clear need for more studies in this area, especially those adopting more robust designs, exploring moderating factors, and examining the mechanisms that explain these relationships. Nonetheless, the present findings provide preliminary evidence that teacher burnout can affect the students they teach.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijer.2020.101714 2339240:895IRKQ8 2405685:PXI58R4B
Keywords: Academic achievement; Burnout; Exhaustion; Mental health; Student performance; Students; Teacher attrition

Google Scholar, Microsoft Academic, Scopus, Dimensions, Web of Science, and OpenCitations’ COCI: a multidisciplinary comparison of coverage via citations - Martín-Martín, Alberto; Thelwall, Mike; Orduna-Malea, Enrique; Delgado López-Cózar, Emilio (Scientometrics, 2021)
New sources of citation data have recently become available, such as Microsoft Academic, Dimensions, and the OpenCitations Index of CrossRef open DOI-to-DOI citations (COCI). Although these have been compared to the Web of Science Core Collection (WoS), Scopus, or Google Scholar, there is no systematic evidence of their differences across subject categories. In response, this paper investigates 3,073,351 citations found by these six data sources to 2,515 English-language highly-cited documents published in 2006 from 252 subject categories, expanding and updating the largest previous study. Google Scholar found 88% of all citations, many of which were not found by the other sources, and nearly all citations found by the remaining sources (89–94%). A similar pattern held within most subject categories. Microsoft Academic is the second largest overall (60% of all citations), including 82% of Scopus citations and 86% of WoS citations. In most categories, Microsoft Academic found more citations than Scopus and WoS (182 and 223 subject categories, respectively), but had coverage gaps in some areas, such as Physics and some Humanities categories. After Scopus, Dimensions is fourth largest (54% of all citations), including 84% of Scopus citations and 88% of WoS citations. It found more citations than Scopus in 36 categories, more than WoS in 185, and displays some coverage gaps, especially in the Humanities. Following WoS, COCI is the smallest, with 28% of all citations. Google Scholar is still the most comprehensive source. In many subject categories Microsoft Academic and Dimensions are good alternatives to Scopus and WoS in terms of coverage.
arXiv: 2004.14329 KerkoCite.ItemAlsoKnownAs: 10.1007/s11192-020-03690-4 2129771:IWZPRDY7 2129771:XUN8HY6M 2129771:Z9YDWKR6 2405685:SN9E5TSM
Keywords: Computer Science - Digital Libraries

The last mile in school access: Mapping education deserts in developing countries - Rodriguez-Segura, Daniel; Kim, Brian Heseung (Development Engineering, 2021)
With recent advances in high-resolution satellite imagery and machine vision algorithms, fine-grain geospatial data on population are now widely available: kilometer-by-kilometer, worldwide. In this paper, we showcase how researchers and policymakers in developing countries can leverage these novel data to precisely identify “education deserts” – localized areas where families lack physical access to education – at unprecedented scale, detail, and cost-effectiveness. We demonstrate how these analyses could valuably inform educational access initiatives like school construction and transportation investments, and outline a variety of analytic extensions to gain deeper insight into the state of school access across a given country. We conduct a proof-of-concept analysis in the context of Guatemala, which has historically struggled with educational access, as a demonstration of the utility, viability, and flexibility of our proposed approach. We find that the vast majority of Guatemalan population lives within 3 km of a public primary school, indicating a generally low incidence of distance as a barrier to education in that context. However, we still identify concentrated pockets of population for whom the distance to school remains prohibitive, revealing important geographic variation within the strong country-wide average. Finally, we show how even a small number of optimally-placed schools in these areas, using a simple algorithm we develop, could substantially reduce the incidence of education deserts in this context. We make our entire codebase available to the public – fully free, open-source, heavily documented, and designed for broad use – allowing analysts across contexts to easily replicate our proposed analyses for other countries, educational levels, and public goods more generally.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.deveng.2021.100064 2405685:RIEFMI2C 4042040:NKVNSSIM
Keywords: Access to education; Education deserts; Education in developing countries; School placement

Reopening Schools - When and how - Campe (Evernote, 2021)
Timing of the survey - The survey was conducted between 7 to 22 November 2020. Slide 9 - % students who participated in distance learning in the last 2 weeks prior to the survey Primary - 31.4% Second...
KerkoCite.ItemAlsoKnownAs: 2339240:3PDAXZPR 2405685:MUJGM6QH

Students' attitudes towards using interactive whiteboard in mathematics classrooms - Erdener, Kevser (International Journal of Technology in Teaching and Learning, 2021)
The purpose of the study is to investigate the students' attitudes towards using interactive whiteboard in mathematics classrooms in the middle and high school. The IWB survey was used to measure students' attitudes. The research sampling consisted of 112 students in middle schools and 231 students in high schools in Balikesir in Turkey. The structural validity of scale was tested through confirmatory factor analysis. The reliability of the scales was tested through Cronbach's Alpha Coefficient. The item discrimination of the scales was calculated through the corrected item total correlation and a comparison between the top and bottom 27% groups. The results of analysis show that students have positive attitude towards the use of IWB. Also t-test method was used to test whether students' attitudes differ in terms of gender, school type and mathematics achievement.
ERIC Number: EJ1330728 KerkoCite.ItemAlsoKnownAs: 2339240:BPM5YK44 2405685:GH4FEUJY 6018420:PJD7IULL
Keywords: Educational Technology; Foreign Countries; Gender Differences; High School Students; Interaction; Mathematics Achievement; Mathematics Education; Middle School Students; Student Attitudes; Visual Aids

A Design Approach to Mathematics Teacher Educator Development in East Africa - Golding, Jennie; Batiibwe, Marjorie Sarah K. (Journal of Research and Advances in Mathematics Education, 2021)
Mathematical functioning in sub-Saharan Africa remains persistently weak in global terms. This limits the flourishing of young people and communities in the region. Moreover, affordable, effective ways to address the issue are not well established. This paper analyses outcomes from a blended learning 'Mathematical Thinking and IT' course, iteratively adapted for East African primary mathematics teacher educators. The course adopted theoretical approaches derived from the mathematics, teacher and technology education literatures. It aimed to address the problem of low mathematical functioning by equipping participants for their own work, and also for supporting local collaborative teacher development workshops. The reported study asked, 'What are the affordances and constraints of the adapted course and the available technology for mathematics teacher educator development in this context?' A variety of qualitative tools were used to track the course's impact on the ten mathematics teacher educator participants over six months, as they attempted to transfer course learning to their home professional context. The analysis adopted an ethnographic lens. Outcomes suggested participants with a broad mathematical and pedagogical capacity for change, including critical levels of reflection, made significant progress in their technological, mathematical and mathematics pedagogical expertise. However, teacher educators without such a threshold capacity appeared not able to re-envision practice. Free subject-specific software was appreciated by all participants, but not yet reliably accessible in these teacher educators' institutional contexts. The reported study evidences the potential for affordable, sustainable, development of many mathematics teacher educators in this context, but further research is needed. Similar courses should take account of local technological and education constraints.
Publisher: Universitas Muhammadiyah Surakarta Department of Education KerkoCite.ItemAlsoKnownAs: 10.23917/jramathedu.v6i1.11898 2339240:2HL3R784 2405685:T28BZSGT
Keywords: Blended Learning; Distance Education; Elementary School Mathematics; Foreign Countries; Mathematics Teachers; Pedagogical Content Knowledge; Professional Development; Program Effectiveness; Teacher Collaboration; Teacher Educators; Technological Literacy; Technology Integration

Academic and social effects of inclusion on students without disabilities: A review of the literature - Kart, Ayse; Kart, Mehmet (Education Sciences, 2021)
In many countries, educational practices are changing to inclusive education. Inclusive education is educating students with disabilities in general education classrooms with their peers without disabilities. If inclusive education is spreading, research needs to investigate the effects of inclusion not only for students with special needs but also for typically developing students. However, there is more research on the outcomes of inclusion for students with disabilities and less for students without disabilities in inclusive settings. Research shows academic and social gains for students with disabilities, but there is less clarity regarding the influence of inclusion on general education students. Therefore, the purpose of this review is to summarize and organize the literature on the academic and social outcomes of inclusion on students without disabilities. Academic effects of inclusion on students without disabilities are mixed, and the levels of schooling may have a differential impact on the achievement of students without disabilities. The literature indicates mostly positive or neutral effects of inclusion on the academic achievement of typically developing students in the lower grades, whereas neutral or negative influence is indicated for later grades. Additionally, students without disabilities have socially benefited from being in inclusive classrooms with students with disabilities. Mainly, the social effects of inclusion are reduction of fear, hostility, prejudice, and discrimination as well as increase of tolerance, acceptance, and understanding.
32 citations (Crossref) [2024-04-17] Number: 1 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/educsci11010016 2339240:IUXFBDKW 2405685:F5W6PCVI
Keywords: academic achievement; inclusion; social effects; students without disabilities; ⛔ No INSPIRE recid found

Incentives for Mayors to Improve Learning: Evidence from State Reforms in Ceará, Brazil - Lautharte, Ildo; de Oliveira, Victor Hugo; Loureiro, Andre (World Bank, 2021)
Financial incentives for students, teachers, and schools are often used to promote learning. Yet, little is known about whether similar incentives for mayors produce analogous findings. This paper investigates this question by exploring a results-based financing reform in Ceará, Brazil, which redistributes state resources to municipalities based on education performance. Comparing schools on both sides of Ceará's border over key implementation periods, the paper shows that ninth grade students who were exposed to the results-based financing performed 0.15 standard deviation higher on mathematics and language tests. These impacts increase twofold when Ceará offers technical assistance to municipalities (pedagogical and managerial) and become significant for fifth graders. These gains are seen among students in the top performance quantiles, but reformulating the results-based financing rule to penalize municipalities with more low performers significantly reduces learning gaps. The paper discuss several mechanisms: the selection of school principals, teacher training, the provision and quality of textbooks, curriculum coverage, and school homework.
Accepted: 2021-01-21T14:36:24Z KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-9509 2339240:GKGSBWGY 2405685:ZJ2R4FBX 4656463:YFBR67RD
Keywords: Education; Learning Incentives; Municipal Governance; Public Sector Reform; Results-Based Financing; Secondary Education; Student Performance; Teacher Effectiveness; Teacher Training; Technical Assistance

A Roadmap for Measuring Distance Learning - Morris, Emily; Farrell, Anna; Venetis, Emma (USAID, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:FCKJVJ9N 2405685:KLDWAH4G

A Simulation of COVID-19 School Closure Impact on Student Learning in Bangladesh [Report] - Rahman, Tashmina; Sharma, Uttam (World Bank, 2021)
This Note presents results from a series of simulations that aim to capture the impacts that school closures in Bangladesh might have on the learning levels, enrollment and future earnings of children and students using a methodological tool developed by the Education Global Practice of the World Bank . We find that overall loss in learning for every child enrolled in school even in the most optimistic scenario is expected to be substantial and the economic implications of the learning losses are huge. Available data also indicates that remote learning requires to be made more effective. It is hoped that the insights from this note will be useful for the government, non-government, private sector and civil society engaged in education service delivery as they are attempting to forge effective partnerships during and after the crisis. There is an urgent need to substantially reduce additional dropouts and absenteeism through stipends and safe school opening and communication campaigns.
Accepted: 2021-01-25T16:58:03Z KerkoCite.ItemAlsoKnownAs: 2339240:A2JMJBKU 2405685:TU8UCJ3G
Keywords: Coronavirus; Covid-19; Distance Learning; Education Quality; Pandemic Impact; Primary Education; School Closure; School Dropout; Secondary Education; Student Learning

A Simulation of COVID-19 School Closure Impact on Student Learning in Bangladesh [Web page] - Rahman, Tashmina; Sharma, Uttam (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KMHYAN74 2405685:5NGZFQW4

A simulation of COVID-19 school closure impact on student learning in Bangladesh - Rahman, Tashmina; Sharma, Uttam; World Bank (World Bank, 2021)
This Note presents results from a series of simulations that aim to capture the impacts that school closures in Bangladesh might have on the learning levels, enrollment and future earnings of children and students using a methodological tool developed by the Education Global Practice of the World Bank. We find that overall loss in learning for every child enrolled in school even in the most optimistic scenario is expected to be substantial and the economic implications of the learning losses are huge. Available data also indicates that remote learning requires to be made more effective. It is hoped that the insights from this note will be useful for the government, non-government, private sector and civil society engaged in education service delivery as they are attempting to forge effective partnerships during and after the crisis. There is an urgent need to substantially reduce additional dropouts and absenteeism through stipends and safe school opening and communication campaigns.
KerkoCite.ItemAlsoKnownAs: 2339240:WGZJQAIX 2405685:BS37TZAZ
Keywords: Access to Computers; Access to Education; Achievement Gains; Age Differences; At Risk Students; Attendance; Bangladesh; Barriers; COVID-19; Delivery Systems; Disadvantaged Youth; Distance Education; Dropout Prevention; Economic Impact; Elementary Secondary Education; Foreign Countries; Gender Differences; Handheld Devices; Income; Pandemics; Partnerships in Education; Program Effectiveness; Radio; Remedial Instruction; Rural Urban Differences; School Closing; Simulation; Telecommunications; Television

Keep Kenya Learning Project (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:IH6LDXJY 2405685:78Y3ZEGR

Scoping call notes (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:NS49QAFX 2405685:FQ95A2N2

SWOT analysis - Wikipedia (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:4BSUXA84 2405685:237C543A

The STEM Gap: Women and Girls in Science, Technology, Engineering and Mathematics - Aauw (AAUW : Empowering Women Since 1881, 2021)
Giving women equal opportunities to pursue — and thrive in — STEM careers helps narrow the gender pay gap, enhances women’s economic security and ensures a diverse and talented STEM workforce and prevents biases in these fields and the products and services they produce.
KerkoCite.ItemAlsoKnownAs: 2339240:BFKLH3RF 2405685:EVC72RBB

Emergency online learning in low-resource settings: Effective student engagement strategies - Abou-Khalil, Victoria; Helou, Samar; Khalifé, Eliane; Chen, MeiRong Alice; Majumdar, Rwitajit; Ogata, Hiroaki (Education Sciences, 2021)
We aim to identify the engagement strategies that higher education students, engaging in emergency online learning in low-resource settings, perceive to be effective. We conducted a sequential mixed-methods study based on Moore’s interaction framework for distance education. We administered a questionnaire to 313 students engaging in emergency online learning in low-resource settings to examine their perceptions of different engagement strategies. Our results showed that student–content engagement strategies, e.g., screen sharing, summaries, and class recordings, are perceived as the most effective, closely followed by student–teacher strategies, e.g., Q and A sessions and reminders. Student–student strategies, e.g., group chat and collaborative work, are perceived as the least effective. The perceived effectiveness of engagement strategies varies based on the students’ gender and technology access. To support instructors, instructional designers, and researchers, we propose a 10-level guide for engaging students during emergency online classes in low-resource settings.
Number: 1 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/educsci11010024 2339240:LYZBWC56 2405685:PLHA9YRF
Keywords: COVID-19; Moore framework; distance learning; emergency; engagement; low-resource settings; online learning; student perception; survey

Pakistan Education Statistics 2017-18 - Academy of Educational Planning and Management (Government of Pakistan, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:X4RR987V 2405685:YAJNGEUA

Catch-up Programmes: 10 principles to help learners catch up and return to learning - Accelerated Education Working Group (AEWG) (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:ZF7LXERY

Improving teaching quality and effectiveness in Timor-Leste - ACER (Australian Council for Educational Research) (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:SAX4EAEX 2405685:IBI52H9Y

Guide to Cognitive Disabilities - ADA Site Compliance (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:CRWLINF3 2405685:J6BZP4PT
Keywords: ⛔ No INSPIRE recid found

Advancing Learning Outcomes for Transformational Change III - African Population and Health Research Center (African Population and Health Research Center, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:W7FEWQUN 2405685:CQGHMQKA

Integrating ICT into schools in Sub-Saharan Africa: from teachers’ capacity building to classroom implementation - Agyei, D. D (Education and Information Technologies, 2021)
This study followed up on a selected cohort of 4945 Science, Technology, English and Mathematics (STEM) teacher participants from six Sub-Saharan African countries namely: Kenya, Tanzania, Uganda, Ethiopia, Ghana and Nigeria. The teachers were involved in an instructional digital professional development programme targeted at building their capacity to embed ICT into school organizational and curriculum practices. This study sought to evaluate the impact of the ICT- instructional professional development programme in relation to the quality and the extent of the teachers’ transfer of the programme’s ideas from capacity building to classroom instructional practices. Data for the study were collected using semi-structured survey instrument and diaries kept to maintain records of activities and events during the period of implementation. Findings revealed that the teachers expressed general satisfaction with content and processes of the training programme; however, essential conditions to support transfer of the training’s ideas to school level seemed not adequate during the period of implementation. Implications for effective professional development in integrating ICT into school organization and curriculum practices that have sustainable impact on teaching and learning particularly in Sub-Saharan regions and similar contexts are discussed.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-020-10253-w 2339240:KC5AR578 2405685:7JSGE6JR

Pakistan personal data protection bill termed vague - Pakistan - DAWN.COM - Ali, Kalbe (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:S399V33N 2405685:W7ABZDDN

Computational literature reviews: Method, algorithms, and roadmap - Antons, D.; Breidbach, C.F.; Joshi, A.M. (Organizational Research Methods, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:4JL8RZ7H 2486141:R52FLCHH
Keywords: _Added-ailr-2024; ⛔ No DOI found

Impact Evaluation of Funda Wande Coaching Intervention Midline Findings: Midline II - Ardington, Cally (SALDRU, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:GPB7DA4P

Preservice Classroom Teachers' Views of Distance Education Science Laboratory Activities - Arslan, Ayten (International Online Journal of Education and Teaching, 2021)
This study investigated preservice classroom teachers' views of distance education science laboratory (lab) activities (DESLA). The study adopted a phenomenology design, which is a qualitative research method. The sample consisted of 34 students (25 women and nine men) from the department of classroom teaching of the education faculty of a public university. Participants were recruited using convenience sampling. Data were collected online (Google Forms) via Google Drive using an open-ended question form developed by the researcher based on a literature review and expert feedback. The data were analyzed using content analysis, a qualitative data analysis method. The results showed that participants had positive and negative opinions about DESLA. They had numerous academic, social, and professional experiences but also faced some challenges. They pointed out the pros and cons of DESLA. Most participants stated that they preferred face-to-face science lab activities to DESLA. The results also showed that DESLA improved participants' attitudes towards science lab activities in general.
Publisher: Informascope KerkoCite.ItemAlsoKnownAs: 2339240:4SZS5FV2 2405685:RCBWSW7G
Keywords: Barriers; COVID-19; Distance Education; Educational Technology; Foreign Countries; Pandemics; Preservice Teachers; Program Effectiveness; School Closing; Science Instruction; Science Laboratories; Student Attitudes; Technology Uses in Education; ⛔ No DOI found

How Accessible are Journal Articles on Education Written by Sub-Saharan Africa-based Researchers? - Asare, Samuel; Mitchell, Rafael; Rose, Pauline (Development and Change, 2021)
This article investigates the extent to which education publications authored by researchers based in sub-Saharan Africa are published as open access (OA). We draw on bibliometric analysis of 1,858 peer-reviewed articles over the period 2010‒18, together with interviews with 31 academics based in the region. Overall, we find a steady increase in OA publishing in the region over this period, although the proportion of OA publications remains low. The study finds that: (1) open access articles by researchers in sub-Saharan Africa are concentrated in journals with a lower impact factor; and (2) authors in sub-Saharan Africa tend to publish in higher quality journals behind a paywall, rather than in lower quality journals that either have no or lower cost for open access.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/dech.12639 KerkoCite.ItemAlsoKnownAs: 10.1111/dech.12639 2339240:AK4DTNUU 2405685:M7Q436YL

Measuring the Impact of COVID-19 on Education in Pakistan - ASER (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:BCG436IW 2405685:8TYDD3BX

A better Environment for Education in Sudan - Ashii, Hadeel Agab (2021)
In preparation for schools reopening, UNICEF is supporting the rehabilitation of classrooms and latrines in Sudan
KerkoCite.ItemAlsoKnownAs: 2339240:E4TPN65U 2405685:M2LX358G

Formative Evaluation of GPE’s Support for Response to the COVID-19 Crisis - Aslam, Monazza; Rawal, Shenila (GPE, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:2GTLVYSK 2405685:JE4H77VI 4656463:KE8N3UI9

Early reading learning for special needs students: challenges on inclusive primary school during COVID-19 pandemic - Asri, Dahlia Novarianing; Cahyono, Bambang Eko Hari; Trisnani, Rischa Pramudia (Linguistics and Culture Review, 2021)
KerkoCite.ItemAlsoKnownAs: 10.21744/lingcure.v5nS1.1489 2339240:QPIH3CL4 2405685:NWJ2HG9I
Keywords: ⛔ No INSPIRE recid found

ASEAN Digital Masterplan 2025 - Association of Southeast Asian Nations (ASEAN) (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:IWZVWCTS 2405685:PRLXPKYK

Framework for Developing Digital Readiness Among ASEAN Citizens - Association of Southeast Asian Nations (ASEAN) (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:JN9UAH3Y

Improving Adolescent Lives in Pakistan (2015-2019): An impact evaluation - Avdeenko, Alexandra; Frölich, Markus (Center for Evaluation and Development, C4ED, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:XBDBGQ95

The State of the Global Education Crisis : A Path to Recovery - Azevedo, Joao Pedro; Wagner, De; Rogers, F. Halsey; Cloutier, Marie-Helene; Chakroun, Borhene; Chang, Gwang-Chol; Mizunoya, Suguru (UNESCO, UNICEF, World Bank, 2021)
The State of the Global Education Crisis : A Path to Recovery (English)
KerkoCite.ItemAlsoKnownAs: 2339240:ZGAKLDEC 2405685:T4QB58CA

A Practice-Based Approach to Foreign Language Teacher Preparation: A Cross-Continental Collaboration - Barahona, Malba; Davin, Kristin J. (Profile Issues in Teachers` Professional Development, 2021)
Publisher: Universidad Nacional de Colombia. KerkoCite.ItemAlsoKnownAs: 10.15446/profile.v23n1.85326 2339240:GXCBVJNW 2405685:ZDIR8KPV

The kids are not alright: Three ways EdTech can support student’s wellbeing during the COVID-19 pandemic and beyond - Baron, Maria; Twinomugisha, Alex (2021)
The kids are not alright: Three ways EdTech can support student’s wellbeing during the COVID-19 pandemic and beyond
KerkoCite.ItemAlsoKnownAs: 2339240:JQXV6EGN 2405685:I9KKXYVK

How we read now: strategic choices for print, screen, and audio - Baron, Naomi S. (Oxford University Press, 2021)
"The digital revolution has transformed reading. Onscreen text, audiobooks, podcasts, and videos often replace print. We make these swaps for pleasure reading, but also in schools. How We Read Now is a ringside seat to the impact of reading medium on learning. Teachers, administrators, librarians, and policymakers need to make decisions about classroom materials. College students must weigh their options. And parents face choices for their children. Digital selections are often based on cost or convenience, not educational evidence. Current research offers essential findings about how print and digital reading compare when the aim is learning. Yet the gap between what scholars and the larger public know is huge. How We Read Now closes the gap. The book begins by sizing up the state of reading today, revealing how little reading students have been doing. The heart of the book connects research insights to practical applications. Baron draws on work from international researchers, along with results from her collaborative studies of student reading practices ranging from middle school through college. The result is an impartial view of the evidence, including where the jury is still out. The book closes with two challenges. The first is that students increasingly complain print is boring. And second, for all the educational buzz about teaching critical thinking, digital reading is inherently ill-suited for cultivating these habits of mind. Since screens and audio are now entrenched - and valuable - platforms for reading, we need to rethink how to help learners use them wisely"–
KerkoCite.ItemAlsoKnownAs: 2405685:J344M3XP
Keywords: Computers and literacy; Critical thinking; Reading; Reading comprehension; Technological innovations

Remote Learning During the Global School Lockdown: Multi-country lessons - Barron Rodriguez, Maria; Cobo, Cristobal; Muñoz-Najar, Alberto; Sánchez Ciarrusta, Iñaki (World Bank Group, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:3FHSCEXJ

Remote Learning During the Global School Lockdown: Multi-Country Lessons - Barron Rodriguez, Maria; Cobo, Cristobal; Muñoz-Najar, Alberto; Sánchez Ciarrusta, Iñaki (World Bank Group, 2021)
Remote Learning During the Global School Lockdown : Multi-Country Lessons (Vol. 2) : Interactive Document (English)
KerkoCite.ItemAlsoKnownAs: 2405685:6NHFZY7B

The Effects of Micro-Reflective Teaching Practices on the Professional Skill Development of Pre-Service Physics Teachers - Batman, Demet; Saka, Ahmet Zeki (The Turkish Online Journal of Educational Technology, 2021)
The aim of this study is to find out the effects of micro-reflective teaching practices on the professional skill development of pre-service physics teachers. It was planned as an experimental study with one group pretestposttest and supported by the case study method. The data were collected by using professional skill scale, observation form and reflective diaries. The sample of the study composed of 13 (6 female, 7 male) pre-service teachers were studying in a Physics Teaching Program in an education faculty in north-eastern Turkey. Each preservice teacher implemented 5 micro-reflective teaching practice within the scope of the research. These practices were recorded by the camera. At the end of each practice pre-service teachers watched themselves and wrote their reflective diaries. The data obtained from the scales and the observation form were analyzed by using the Wilcoxon Signed Rank Test, and the data acquired from the reflective diaries were examined based on interpretive analysis. The findings based on the data obtained from the professional skill scale, observation forms and the reflective diaries indicate that micro-reflective teaching practices help improve pre-service physics teachers’ basic professional skills; subject matter mastery, planning, communication, classroom management, and evaluation.
KerkoCite.ItemAlsoKnownAs: 2339240:EA3ENAW4 2405685:HPCS26CF
Keywords: ⛔ No DOI found

Take-up, Use, and Effectiveness of Remote Learning Technologies in Bangladesh during COVID-19 - Beam, E; Mukherjee, P; Navarro-Sola, L (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:2BEQ3IEH 2405685:PW8FDPUE

Take-Up, Use, and Effectiveness of Remote Technologies Endline Report - Beam, Emily A.; Mukherjee, Priya; Navarro-Sola, Laia; Ferdosh, Junnatul; Sarwar, Md. Afzal Hossain (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ZM9FYFUF 2405685:L52XXFSJ
Keywords: ⛔ No DOI found

Use of learning assessment data in the planning cycle. Case study – Ghana - Begue-Aguado, Alberto (United States Agency For International Development (USAID), 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:LVZRDNGG 2405685:Z9D5E2KD

Getting girls back into school: strategies for successfully re-enrolling girls in Ghana and Sierra Leone - Belfield, Sophie; Mathur, Meenu; Caine, Ellie (FCDO - GEC, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:GMMKRGS8 2405685:79GPUNG4

Interrater Reliability in Systematic Review Methodology: Exploring Variation in Coder Decision-Making - Belur, Jyoti; Tompson, Lisa; Thornton, Amy; Simon, Miranda (Sociological Methods and Research, 2021)
A methodologically sound systematic review is characterized by transparency, replicability, and a clear inclusion criterion. However, little attention has been paid to reporting the details of interrater reliability (IRR) when multiple coders are used to make decisions at various points in the screening and data extraction stages of a study. Prior research has mentioned the paucity of information on IRR including number of coders involved, at what stages and how IRR tests were conducted, and how disagreements were resolved. This article examines and reflects on the human factors that affect decision-making in systematic reviews via reporting on three IRR tests, conducted at three different points in the screening process, for two distinct reviews. Results of the two studies are discussed in the context of IRR and intrarater reliability in terms of the accuracy, precision, and reliability of coding behavior of multiple coders. Findings indicated that coding behavior changes both between and within individuals over time, emphasizing the importance of conducting regular and systematic IRR and intrarater reliability tests, especially when multiple coders are involved, to ensure consistency and clarity at the screening and coding stages. Implications for good practice while screening/coding for systematic reviews are discussed.
KerkoCite.ItemAlsoKnownAs: 10.1177/0049124118799372 2405685:CL8BQKLI
Keywords: coding; interrater reliability; precision; replicability; screening; systematic review; κ statistic

Language issues in comparative education II: Policy and practice in multilingual education based on non-Dominant languages - Benson, Carol; Kosonen, Kimmo (BRILL, 2021)

Calling the tech industry: Hear from your next generation of female digital talent - Beresford, L. (GSMA, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:G5YBWXGQ 2405685:9YBE276S

Ethical Considerations When Using Geospatial Technologies for Evidence Generation - Berman, G; de la Rosa, S; Accone, T (UNICEF Office of Research- Innocenti, 2021)
Geospatial technologies have transformed the way we visualize and understand situations. They are used to acquire, manipulate, store and visualize geographical information, including information on where individuals, groups and infrastructure are loc
KerkoCite.ItemAlsoKnownAs: 2405685:EPRCM8H8 4042040:7VDIMRPE

EdTech in South-East Asia - Better Purpose; MIT Solve; Octava Foundation (2021)
With Southeast Asia’s recent economic growth, there has been greater government and parental spending on education, thus increasing access to education across much of the region. However, despite this progress, significant educational challenges remain, especially for disadvantaged and marginalized groups. Technology presents an opportunity to complement the work of educators in driving improvements to learning outcomes. Yet, in the region, EdTech has remained largely the preserve of more affluent consumers, and its potential to improve access to quality education for under-served groups has not yet been realized. This paper—by Octava Foundation, Better Purpose, and MIT Solve—presents an overview of the status of education and use of technology to support education (EdTech) in five Southeast Asian markets: Indonesia, Malaysia, Philippines, Thailand and Vietnam.
KerkoCite.ItemAlsoKnownAs: 2339240:Q2R9ZB4R 2405685:8PUN56BH
Keywords: ⛔ No INSPIRE recid found

Remote learning in the times of COVID-19 - Bhushan, Mayank; Joshi, Pratibha; Sharma, Sudhanshu (Central Square Foundation, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:EBAPFZA3 2405685:PHHVIFHN

Transforming Traditional Teaching Laboratories for Effective Remote Delivery–A Review - Bhute, Vijesh J.; Inguva, Pavan; Shah, Umang; Brechtelsbauer, Clemens (Education for Chemical Engineers, 2021)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.ece.2021.01.008 2405685:P26SWL49

Figure of the week: Increasing access to electricity in sub-Saharan Africa - Blankenship, Mary; Golubski, Christina (Brookings Commentary, 2021)
Mary Blankenship and Christina Golubski highlight findings related to Africa from a report on progress toward Sustainable Development Goal 7 on energy.
KerkoCite.ItemAlsoKnownAs: 2339240:IS8R9DQZ 2405685:ZLLEW6VT
Keywords: ⛔ No INSPIRE recid found

China bans for-profit school tutoring in sweeping overhaul - Bloomberg news (Bloomberg News, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:L3KQTJH8 2405685:ERRNQZBS

DIGITAL LEARNING FOR EVERY CHILD: CLOSING THE GAPS FOR AN INCLUSIVE AND PROSPEROUS FUTURE - Brossard, Matt; Carnelli, Marta; Chaudron, Stephane; Di-Gioia, Rosanna; Dreesen, Thomas; Kardefelt-Winther, Daniel; Little, Céline; Yameogo, Jean Luc (UNICEF, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:D9ZQQYQE 2405685:EFSU4PM3
Keywords: ⛔ No DOI found

A model of practice for improving autism knowledge in teachers of mainstream students on the autism spectrum in Australia - Bruck, Susan; Robinson, Ainslie; Gallagher, Emma (Australasian Journal of Special and Inclusive Education, 2021)
Australian mainstream school teachers report a severe shortage of accessible autism-focused resources, strategies, and professional development (PD). This 2-part mixed methods study investigated the effect of using a web-based model of practice (MoP) for PD. The MoP contains evidence-based, autism-specific educational practices and resources designed for mainstream teachers of students on the autism spectrum. The aim was to examine teacher responses to using the MoP and the impact of the mode of delivery. In Part 1, 3 PD delivery conditions for using the MoP were trialled (8 weeks): face-to-face support, online support, or web-based access to detailed resources only. Support was provided by expert autism educators. Teachers (N = 15) reported that the MoP was an accessible, comprehensive, and practical support for educational decision-making, and that support encouraged implementation of the MoP practices. Part 2 trialled a hybrid PD model in 6 regional schools. Limited face-to-face and online support plus access to the MoP was trialled. Interview data indicated that a hybrid model can be an effective method of providing immediate support for teachers.
Edition: 2021/06/07 Publisher: Cambridge University Press KerkoCite.ItemAlsoKnownAs: 10.1017/jsi.2021.7 2339240:R63UCGT2 2405685:5IXNEHQ3
Keywords: autism; confidence; educators; knowledge; professional development; teachers

Historical Mapping of Education Provision for Refugees: A cross-cutting and comparative analysis of three country contexts - Brugha, Meaghan; Hollow, David; Pacitto, Julia; Gladwell, C; Dhillon, P; Ashlee, Amy (Jigsaw Consult, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:JSKWPLJP

Radical solutions for education in a crisis context: COVID-19 as an opportunity for global learning - Burgos, Daniel; Tlili, Ahmed; Tabacco, Anita (2021)
OCLC: 1232510584 KerkoCite.ItemAlsoKnownAs: 2405685:Q67F2S69

Technology in Education. Background paper prepared for the 2023 Global Education Monitoring Report - Burns, Mary (UNESCO, 2021)
This think piece was commissioned by the Global Education Monitoring Report (GEM Report) Team to provide initial conceptual framing for the 2023 GEM Report, which focuses on information and communications technologies in education, or educational technology. The topics in this think piece were proposed by the GEM Report Team. As much as space permits, the think piece takes both a close up and wide-angle approach to technology.The think piece focuses, as much as possible, on research outlining the educational benefits of technology and organises educational technology along three axes: (1) technology as a learning tool; (2) technology to deliver learning; and (3) technology to support learning, outlining the uses, benefits, challenges, and additional areas for research associated with each. It discusses the technology tools associated with each category and poses additional research questions that the GEM Reporting Team may wish to explore for the Global Education Monitoring Report.
KerkoCite.ItemAlsoKnownAs: 2339240:M9QPC59P 2405685:KGTU7JWX

“Why is it speaking to me?”: Refugee-background students’ experiences of education - Câmara, Jáfia Naftali (NORRAG, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:QT8TJHMU 2405685:Y8D7AMRR

Así dio vuelta el consumo mediático en El Salvador durante la COVID-19 - Carballo, Willian; Marroquín, Amparo (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:UWJ58EHE 2405685:B5G65ERZ

GSMA Connected Women - The Mobile Gender Gap Report 2021 - Carboni, Isabelle; Jeffrie, Nadia; Dominca, Lindsey; Shanahan, Matthew; Sibthorpe, Claire (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:73JAB8QX 2405685:BDBKZ3YI

HATUTAN Program in Timor-Leste - CARE International (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:D54MJKC2 2405685:FK3E3X62

MENA Higher Education Pedagogy, Technology and the Refugee Experience - Center for Learning in Practice (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:A3L7DC9E 2405685:W2ZDFBES

Timor-Leste: Policy insights from a multi-year teaching and learning study series - Chainey, Jennie; Cassity, Elizabeth (Australian Council for Educational Research, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:MMJEN62C 2405685:DVHB7W3F
Keywords: ⛔ No INSPIRE recid found

The problematic concept of native speaker in psycholinguistics: Replacing vague and harmful terminology with inclusive and accurate measures. - Cheng, Lauretta S. P.; Burgess, Danielle; Vernooij, Natasha; Solís-Barroso, Cecilia; McDermott, Ashley; Namboodiripad, Savithry (Frontiers in Psychology, 2021)
Though the term NATIVE SPEAKER/SIGNER is frequently used in language research, it is inconsistently conceptualized. Factors, such as age, order, and context of acquisition, in addition to social/cultural identity, are often differentially conflated. While the ambiguity and harmful consequences of the term NATIVE SPEAKER have been problematized across disciplines, much of this literature attempts to repurpose the term in order to include and/or exclude certain populations. This paper problematizes NATIVE SPEAKER within psycholinguistics, arguing that the term is both unhelpful to rigorous theory construction and harmful to marginalized populations by reproducing normative assumptions about behavior, experience, and identity. We propose that language researchers avoid NATIVE SPEAKER altogether, and we suggest alternate ways of characterizing language experience/use. The vagueness of NATIVE SPEAKER can create problems in research design (e.g., through systematically excluding certain populations), recruitment (as participants’ definitions might diverge from researchers’), and analysis (by distilling continuous factors into under-specified binary categories). This can result in barriers to cross-study comparison, which is particularly concerning for theory construction and replicability. From a research ethics perspective, it matters how participants are characterized and included: Excluding participants based on binary/essentialist conceptualizations of nativeness upholds deficit perspectives toward multilingualism and non-hegemonic modes of language acquisition. Finally, by implicitly assuming the existence of a critical period, NATIVE SPEAKER brings with it theoretical baggage which not all researchers may want to carry. Given the issues above and how ‘nativeness’ is racialized (particularly in European and North American contexts), we ask that researchers consider carefully whether exclusion of marginalized/minoritized populations is necessary or justified—particularly when NATIVE SPEAKER is used only as a way to achieve linguistic homogeneity. Instead, we urge psycholinguists to explicitly state the specific axes traditionally implied by NATIVENESS that they wish to target. We outline several of these (e.g., order of acquisition, allegiance, and comfort with providing intuitions) and give examples of how to recruit and describe participants while eschewing NATIVE SPEAKER. Shifting away from harmful conventions, such as NATIVE SPEAKER, will not only improve research design and analysis, but also is one way we can co-create a more just and inclusive field.
KerkoCite.ItemAlsoKnownAs: 2405685:IA87WKAM 4042040:MAGAPHFF

Home Literacy and Numeracy Environments in Asia - Cheung, Sum Kwing; Dulay, Katrina May; Yang, Xiujie; Mohseni, Fateme; McBride, Catherine (Frontiers in Psychology, 2021)
The home learning environment includes what parents do to stimulate children’s literacy and numeracy skills at home and their overall beliefs and attitudes about children’s learning. The home literacy and numeracy environments are two of the most widely discussed aspects of the home learning environment, and past studies have identified how socioeconomic status and parents’ own abilities and interest in these domains also play a part in shaping children’s learning experiences. However, these studies are mostly from the West, and there has been little focus on the situation of homes in Asia, which captures a large geographical area and a wide diversity of social, ethnic, and linguistic groups. Therefore, this paper aims to review extant studies on the home literacy and numeracy environments that have been conducted in different parts of Asia, such as China, the Philippines, India, Iran, Turkey, and the United Arab Emirates. Specifically, we explore how parents in these places perceive their roles in children’s early literacy and numeracy development, the methods they regard as effective for promoting young children’s literacy and numeracy learning, and the frequency with which they engage their young children in different types of home literacy and numeracy activities. We also examine studies on the relationship of the home literacy and numeracy environment with young children’s developmental outcomes, and the effectiveness of parent training programs to improve the home literacy and numeracy environments in these contexts. By examining potential trends in findings obtained in different geographical areas, we can initially determine whether there are characteristics that are potentially unique to contexts in Asia. We propose future research directions that acknowledge the role of cultural values and social factors in shaping the home learning environment, and, by extension, in facilitating children’s early literacy and numeracy development.
KerkoCite.ItemAlsoKnownAs: 2405685:9TNTDVH5 4042040:L9ALXHIR

Colandr Community - Colandr (Colandr Community, 2021)
Colandr is powered by machine learning and natural language processing approaches that drive smart-sorting of citations and predictive document classification
KerkoCite.ItemAlsoKnownAs: 2339240:TV27Q4AH 2405685:DTNEXTYW

La Mochila, una plataforma con herramientas para la vida - Coschool (Coschool, 2021)
Transformar tu entorno desde la educación socioemocional sí es posible, hoy te presentamos LA MOCHILA, una de nuestras herramientas de digitalización donde aprenderás a fortalecer distintas habilidades para la vida,
KerkoCite.ItemAlsoKnownAs: 2339240:KNJUG4ZC 2405685:MTNVCATR

Case Study: Building Girls to Live, Learn, Laugh and ‘SCHIP’ in Strong, Creative, Holistic, Inclusive, Protective, Quality Education - CRANE and Viva (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:WTT4AIYL 2405685:CR5E7AXI

Tech plus teachers: Did one-on-one phone tutorials help kids learn better during school closures in Sierra Leone? - Crawfurd, L; Evans, D; Guiterrez Bernal, M; Hares, S; Sam-Kpakra, R; Sandefur, J; Shojo, M (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5Z8RBH2S 2405685:TF3CV7CH

Understanding Education Policy Preferences: Survey Experiments with Policymakers in 35 Developing Countries - Crawfurd, Lee; Minardi, Ana; Hare, Susannah; Sandefur, Justin (2021)
Foreign aid donors and international organizations supporting education in developing countries have increasingly coalesced around a policy agenda prioritizing foundational learning, measured by test scores in primary school, based on a diagnosis of deficient school quality, and a growing body of empirical evidence about effective interventions to improve quality. We survey over 900 senior government officials working on education in 35 low- and middle-income countries to gauge their alignment with this agenda.
KerkoCite.ItemAlsoKnownAs: 2339240:BAERNQH7 2339240:IA4V4RW2 2405685:8U5XELBU 2405685:UBYPFNLK 4656463:FN977692

Understanding Education Policy Preferences: Survey Experiments with Policymakers in 35 Developing Countries - Crawfurd, Lee; Minardi, Ana; Hare, Susannah; Sandefur, Justin (2021)
Foreign aid donors and international organizations supporting education in developing countries have increasingly coalesced around a policy agenda prioritizing foundational learning, measured by test scores in primary school, based on a diagnosis of deficient school quality, and a growing body of empirical evidence about effective interventions to improve quality. We survey over 900 senior government officials working on education in 35 low- and middle-income countries to gauge their alignment with this agenda.
KerkoCite.ItemAlsoKnownAs: 2339240:BAERNQH7 2339240:IA4V4RW2 2405685:8U5XELBU 2405685:UBYPFNLK 4656463:FN977692

Makhalidwe Athu - Creative Association International (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:6C5I8Z2D 2405685:KDTFJ3QR

Makhalidwe Athu - Creative Association International (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:6C5I8Z2D 2405685:KDTFJ3QR

El programa Aprende en casa, ¿una estrategia que excluye a los usuarios de lenguas minoritarias? - Cruz-Aldrete, Miroslava; Cruz-Aldrete, Miroslava (Educación, 2021)
ResumenEn este trabajo discuto la compleja situación a la que se enfrentaron los grupos lingüísticos minoritarios, en particular los sordos usuarios de la lengua de señas mexicana (LSM), cuya enseñanza bilingüe se vio amenazada ante la crisis educativa ocasionada por la pandemia causada por el nuevo coronavirus. La respuesta del estado mexicano para no interrumpir la educación de los niños y jóvenes hizo patente la discriminación hacia los usuarios de lenguas diferentes al español, al ser esta la lengua vehicular para la programación de Aprende en casa, y no considerar el contexto y los idiomas de las comunidades indígenas y sordas, para su enseñanza-aprendizaje.Palabras clave: lengua de señas; lenguas minoritarias; educación bilingüe
Publisher: Pontificia Universidad Católica del Perú KerkoCite.ItemAlsoKnownAs: 10.18800/educacion.202102.003 2405685:QPNZ8ASS 4042040:5UYI4ZN3

基于雨课堂的《初级维吾尔语精读》 课程混合式教学模式研究 [Research on the Mixed Teaching Mode of Beginner-Level Reading Comprehension in Uyghur based on Rain Class] - Cui, Ran (Theory and Practice of Innovation and Enntrepreneurship, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:S8LC7TBE 4042040:8PNPLI3H
Keywords: ⛔ No DOI found

Calculating the Educational Impact of COVID-19 (Part III): Where will students be when schools reopen? | SharEd - Cummiskey, Chris (RTI, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:P2E3PDHG 2405685:HFMDZPQA

Research on the Influence of Computer Electronic Media on Higher Education in Mother Language - Dai, Wei (Journal of Physics: Conference Series, 2021)
Issue: 3 KerkoCite.ItemAlsoKnownAs: 2405685:MJBK6URB 4042040:EAZZGMUN

Digital in Bangladesh: All the Statistics You Need in 2021 - DataReportal (DataReportal – Global Digital Insights, 2021)
Our huge new collection of statistics and insights into how people in Bangladesh use the internet, social media, mobile, and ecommerce in 2021.
KerkoCite.ItemAlsoKnownAs: 2339240:I94ZZMY6 2339240:J4Q9N36L 2405685:3U3S5NRZ 2405685:G7IWS6TF 2405685:YVMDGILY 2534379:969KQJR3
Keywords: ___working_potential_duplicate

Bridging Latin America's digital divide | White & Case LLP - de Feydeau, Amaury; Menski, Martin; Retana Tello, Ismael Reyes; Perry, Suzanne; Hendel, Pedro (2021)
Subscribe Stay current on your favorite topics In Latin America and the Caribbean, adopting digital solutions has been promoted as a unique opportunity to increase productivity and unlock solutions to sustainable development goals.
KerkoCite.ItemAlsoKnownAs: 2339240:S4GBT9HF 2405685:LUDNBVC8

Framework for Teacher Support During Remote Teaching in a Crisis: COVID-19, as a Case Study - Denden, Mouna; Tlili, Ahmed; Burgos, Daniel; Jemni, Mohamed; Huang, Ronghuai; Essalmi, Fathi; Chang, Ting-Wen (Radical Solutions for Education in a Crisis Context, 2021)
Series Title: Lecture Notes in Educational Technology KerkoCite.ItemAlsoKnownAs: 10.1007/978-981-15-7869-4_10 2405685:QMKS4E7I

Curriculum Assessment Policy Statements (CAPS) - Department of Basic Education (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:XVGSB9NK 2405685:LJYCE59R

Reimagining Digital Learning: Lessons from the learning passport in Timor-Leste - Dewan, Pragya; Carnelli, Marta; Pontuscha, R.; Tubio, M L; Tsuruyama, E (UNICEF Connect: Evidence for Action, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:T3ZZRQD7

DHIS2 - DHIS2 (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:H9WB26RL 2405685:T3H6KKJV

A glimpse into the lived experiences and challenges faced of PWD students towards online learning in the Philippines amidst COVID-19 pandemic - Dianito, Ann Jesamine; Espinosa, Jomarie; Duran, Jimboy; Tus, Jhoselle (International Journal of Advance Research and Innovative Ideas in Education, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:UHTBK37I 2405685:G7L2RPEZ
Keywords: ⛔ No INSPIRE recid found

The Storytelling Project Handbook - Dixon, Miranda; Patuck, Lil (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5Y3NRH26 2405685:TJTKAKJD

Results-Based Financing (RBF) in the Education Sector : Country-Level Analysis : An Assessment of RBF in Education - Final Assessment Report : Tanzania - Dom, Catherine; Fraser, Alasdair; Mhina, Edward (Mokoro for World Bank, 2021)
Results-Based Financing (RBF) in the Education Sector : Country-Level Analysis : An Assessment of RBF in Education - Final Assessment Report : Tanzania (English)
KerkoCite.ItemAlsoKnownAs: 2339240:6T2VNQMC 2339240:86HU868K 2405685:5SHZXXCP 2405685:HQGHMPDL 4656463:7QDZJIDM 4656463:QEAAR59A

The Impact of COVID-19 on Education – Recommendations and Opportunities for Ukraine - Donnelly, Robin; Patrinos, Harry A.; James Gresham (World Bank, 2021)
School closures due to COVID-19 have brought significant disruptions to education across Europe. Emerging evidence from some of the region’s highest-income countries indicate that the pandemic is giving rise to learning losses and increases in inequality.
KerkoCite.ItemAlsoKnownAs: 2339240:83DNVT85 2405685:YPNFD58A

The influence of technology on academic distraction: A review - Dontre, Alexander J. (Human Behavior and Emerging Technologies, 2021)
The detrimental effects of academic distraction have become increasingly problematic in recent years due to student media multitasking. In recent years, educators have gradually transitioned many classes to the online learning environment, effectively reducing teacher supervision. This has been greatly exacerbated with the advent of coronavirus disease 2019 and subsequent social distancing guidelines. In an effort to help students and educators better understand the implications of technology on academic distraction and academic performance, this literature review discusses the effects of three forms on technology on student distraction: laptops, smartphones, and social media use, particularly the social media platform Facebook. While the effects of student laptops on academic distraction are somewhat ambivalent, the debate is largely moot in the current educational environment. The detrimental effects of student smartphone and social media use on academic distraction are more conspicuous, especially with the pervasiveness of personal digital devices. Potential self-regulatory and environmental interventions are discussed.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/hbe2.229 KerkoCite.ItemAlsoKnownAs: 10.1002/hbe2.229 10/gkggqq 2339240:ALCAJNCB 2405685:2PRYNM2B
Keywords: Facebook; academic distraction; laptops; learning; media multitasking; online learning; performance; phubbing; smartphones; social media

Unlocking Learning: The implementation and effectiveness of digital learning for Syrian refugees in Lebanon, Innocenti Research Report - Dreesen, Thomas; Kamei, Akito; Karamperidou, Despina; Abou Fakher, Sara; Marji, Lama; Ortiz Correa, Javier Santiago (UNICEF Office of Research - Innocenti, 2021)
Digital learning has the potential to offer interactive and personalized learning for children, in and out of school, including the most marginalized. However, depending on programme design, delivery, and use, digital learning can also exacerbate learning inequalities. This report presents tangible findings on the implementation and use of digital learning to improve outcomes for marginalized children in Lebanon. This report focuses on the UNICEF-Akelius Foundation Partnership and its implementation of a digital course used on tablets and mobile phones for language learning of Syrian refugees in Lebanon. The report provides findings across three areas: First, the report investigates the digital course’s use in a blended learning environment where it was used on tablets by students as part of traditional face-to-face classroom instruction with teachers. Second, the analysis examines the transition to remote learning where the course was used on devices owned by the household, supported by teachers remotely. Third, the report estimates the effectiveness of the use of the digital course during this period of remote learning from August–November 2020 showing positive results for language and art competencies.
KerkoCite.ItemAlsoKnownAs: 2339240:7ANL23GH 2405685:CBVBP2KY

Incorporating Digital E-Learning Teaching Technologies Into Africa’s Primary School Education Systems - Dugbazah, Justina; Glover, Barbara; Mbuli, Bhekani; Kungade, Chifundo (AUDA-NEPAD, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:XHFVF964 2405685:485FPK7F
Keywords: ⛔ No INSPIRE recid found

Global Climate Risk Index 2021: Who Suffers Most from Extreme Weather Events? - Eckstein, David; Kunzel, Vera; Shafer, Laura (German Watch, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:R6827BCW 2405685:GJDSJQFE

Challenges and opportunities for secondary education in Latin America and the Caribbean during and after the pandemic - ECLAC (2021)
The pandemic has had a critical impact on the educational trajectories of children and adolescents in Latin America. Video-call interviews with more than 150 students, teachers, and parents in eight countries in the region (namely, Argentina, Bolivarian Republic of Venezuela, Chile, Ecuador, Costa Rica, Honduras, Mexico, and Uruguay) in 2020 and 2021 reveal the challenges and
Last Modified: 2021-12-27T13:29-03:00 Publisher: CEPAL KerkoCite.ItemAlsoKnownAs: 2339240:VIRJKUAZ 2405685:Y3VKPZY8

EdCamp Days Report: EdCamp Ukraine’s Activities 2018–2020 - EdCamp Ukraine (EdCamp Ukraine, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:PE79IL7Q 2405685:HNI3HGER

Focus country: Bangladesh - EdTech Hub (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:R62Y25DW 2405685:IFIR3QC9

Research - EdTech Hub (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:S7VNMT74 2405685:SGN72ZXM

EdTech Tulna Standards - EdTech Tulna (2021)
The EdTech Tulna standards define a set of expectations for the design of EdTech products
KerkoCite.ItemAlsoKnownAs: 2339240:RFTZFTZ7 2405685:ZLSZ2CID

Education for All: An Integrated Approach (Phase II) - Education Above All (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:4FY4NCDN 2405685:DJBN3VPT

The Egyptian Ministry of Education’s E-Learning Portal - Egyptian Ministry of Education (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:MDAHAACH 2405685:LUET6JSM

How gender equality in STEM education leads to economic growth - Eige (European Institute for Gender Equality, 2021)
Reducing the gender gap in Science, Technology, Engineering and Mathematics (STEM) education areas could help reduce skills gap, increase employment and productivity of women and reduce occupational segregation. Ultimately this would foster economic growth via both higher productivity and increased labour market activity. However, despite good employment opportunities and highly productive jobs in this area, there is currently a low proportion of women studying and graduating in STEM subjects.
KerkoCite.ItemAlsoKnownAs: 2339240:DPW6J56H 2405685:APWKXFWI

High, Low, or No Tech? A Roundtable Discussion on the Role of Technology in Refugee Education - El-Sefary, Yomna; Ozegovic, Mia; Wagner, Emma; Benchiba, Soraya (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:N9TG6QCP 2405685:3RGI8CQ4

High, Low, or No Tech? A Roundtable Discussion on the Role of Technology in Refugee Education - El-Serafy, Yomna; Ozegovic, Mia (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:U276A6AB 2405685:KKSLA49T

The Market Design Approach to Teacher Assignment: Evidence from Ecuador - Elacqua, Gregory; Sophie West Olsen, Anne; Velez-Ferro, Santiago (Inter-American Development Bank, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:AS8ZD2GB 2486141:R5SU5NST

The impact of online learning as emerging technology on parents: Case study of parents of primary school children in Nairobi, Kenya. - Emmanuel, Jadesola; Oduor, Collins (Journal of Language, Technology & Entrepreneurship in Africa, 2021)
Kenya, as a nation has a stable schooling system based on synchronous classroom learning. The advent of the COVID 19 pandemic has led to the sudden shift in paradigm to remote schooling learning systems. Several studies have been carried out on remote schooling systems and the impact of parent’s involvement in children’s remote school, but none has been sighted on its impact on parents. The objective of this study was to determine the impact of the sudden paradigm shift on parents of remote schooling pupils in Kenya during this pandemic. A descriptive survey design was utilized. Primary data was collected by online questionnaires and secondary data from past studied. The analysis was done with a statistical application. It was found out that, remote schooling may be easily accepted by many Kenyan parents with 39.8% of parents indicating that they will recommend remote schooling having indicated some benefits derived from it and 24.8% indicating that they will not. It was therefore recommended that the national government should address factors that may hinder effective remote learning, thus encouraging parental involvement and support. It was also recommended that the government and education practitioners should officially develop and implement standards and curriculum for the implementation of remote learning in Kenya in preparation for future pandemics. Keywords: remote schooling, remote learning, descriptive survey design
Number: 2 KerkoCite.ItemAlsoKnownAs: 2339240:TJDZK82V 2405685:PGNATP5K
Keywords: ⛔ No DOI found

Learning loss due to school closures during the COVID-19 pandemic - Engzell, Per; Frey, Arun; Verhagen, Mark D. (Proceedings of the National Academy of Sciences, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1073/pnas.2022376118 2339240:44J4M2BJ 2405685:DRSWVWNR

Learning loss due to school closures during the COVID-19 pandemic - Engzell, Per; Frey, Arun; Verhagen, Mark D. (Proceedings of the National Academy of Sciences, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1073/pnas.2022376118 2339240:44J4M2BJ 2405685:DRSWVWNR

Digital Skills Ecosystem and Gap Assessment in Malawi: Final Report - Ernst & Young (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:WKQWSM76 2405685:YYDHA82Z

The Praxis Study Companion, Teaching Reading: Elementary - ETS Praxis (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:LAULQW5V 2405685:AQNUQW96

Ukraine Education, Training and Employment Developments 2021 - European Training Foundation (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:WR6AN63L 2405685:RNKSXE3F

Foundational Literacy and Numeracy Skills Are Important, Obviously. But Are They More Important than All Other Education Investments? - Evans, David; Hares, Susannah (Center for Global Development | Ideas to Action, 2021)
It’s rare to read an education report these days that doesn’t mention the learning crisis. That’s not surprising. Literacy and numeracy skills among children are dismally low: less than half of all children in low- and middle-income countries can read by the time they are 10 years old. As these data have emerged in recent years, the global education community has swung its focus sharply toward learning.
KerkoCite.ItemAlsoKnownAs: 2339240:BJ9YWMP2 2405685:893JHMDE

It’s been a year since schools started to close due to COVID-19 - Evans, David; Hares, Susannah; Mendez Acosta, A.; Saintis, C. (Center For Global Development, 2021)
Twelve months ago, the world was watching as schools closed across China and millions of students began learning online from their homes. Most of us didn’t think for a moment that just a few weeks later, almost every country in the world would close their schools and the education of more than a billion children would be disrupted. Since then, millions of students have not had any school-based, face-to-face education.
KerkoCite.ItemAlsoKnownAs: 2339240:2I9FNGHD 2339240:83VL88IT 2405685:9UUEEEJJ 2405685:C9KY68SX

The Relative Wealth Index - Facebook (Facebook Data for Good, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:GBMXFBFX 2405685:35MTZ9KF

Digital Technology and the Futures of Education: Towards ‘Non-Stupid’ Optimism - Facer, Keri; Selwyn, Neil (2021)
Publisher: Unesco KerkoCite.ItemAlsoKnownAs: 2339240:2U3BB9Z8 2405685:69QN5JJU
Keywords: ⛔ No DOI found

Remote Learning During COVID School Closures in West Africa: Evidence Across Caregiver Surveys at Rising Academy Network Schools - Fall, S. M.; Jiminez Gallardo, M. A.; McManus, J; Njogu-Ndongwe, F (IDinsight, 2021)
Evidence across caregiver surveys at Rising Academy Network schools
KerkoCite.ItemAlsoKnownAs: 2339240:CEEMGD65 2339240:JLQMXZH3 2339240:VQJS97AG 2405685:26QEKWPG 2405685:9QZNWNVR 2405685:PURHG3K5 2405685:ZRUU9436 2534379:EEUS34W6
Keywords: ___working_potential_duplicate

Large Learning Gains in Pockets of Extreme Poverty: Experimental Evidence from Guinea Bissau - Fazzio, Ila; Eble, Alex; Lumsdaine, Robin L; Boone, Peter; Bouy, Baboucarr; Hsieh, Pei-Tseng Jenny; Jayanty, Chitra; Johnson, Simon; Silva, Ana Filipa (2021)
Children in many extremely poor, remote regions are growing up illiterate and innumerate despite high reported school enrollment ratios. Possible explanations for such poor outcomes include demand – for example, low perceived returns to education compared to opportunity cost; and supply – poor state provision and inability of parents to coordinate and finance better schooling. We conducted a cluster-randomized trial in rural Guinea Bissau to understand the effectiveness and cost of concerted supply-based interventions in such contexts. Our intervention created simple schools offering four years of education to primary-school aged children in lieu of the government. At endline, children receiving the intervention scored 58.1 percentage points better than controls on early grade reading and math tests, demonstrating that the intervention taught children to read and perform basic arithmetic, from a counterfactual condition of very high illiteracy. Our results provide evidence that particularly needy areas may require more concerted, dramatic interventions in education than those usually considered, but that such interventions hold great potential for increasing education levels among the world’s poorest people.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jpubeco.2021.104385 2339240:DAU6XEE6 2405685:FSYXBS55 4656463:NYQXYQP2

Digitalisation Report - Federal Ministry for Digital and Economic Affairs (Austrian Federal Government, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:AC4928ZM

Inspire - Federal Ministry of Education (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:BFIG2QTW 2405685:HI5LYZW7

National Policy on Education Management Information System (EMIS) and Implementation Guidelines - Federal Ministry of Education (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KYEEW5TB 2405685:Y3L37949

FHI 360 Nigeria - FHI 360 (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:6EPG59YI 2405685:TCBQPSX5

Technologies for Data Collection, Processing and Communication in Education in Emergencies: Mapping Practices and Opportunities in the MENA region and Globally - FHI360; USAID (2021)

Centroamérica: Tendencias de las ecnologías de la Información y Comunicación 2010-2019 - Figueroa, Héctor (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:7NPNIIZ6 2405685:VB3ZCVN2

Uso de la Plataforma Zoom y la Competencia se comunica Oralmente en su Lengua Materna en Estudiantes de Educación Secundaria de la Institución Educativa Unión Zapotillo N°64647-Yarinacocha 2020 - Flores Fasanando, Giuliana (Universidad Nacional de Ucayali, 2021)
La finalidad de esta investigación fue, determinar la relación que existe entre el uso de la plataforma zoom y la competencia se comunica oralmente en su lengua materna en estudiantes de educación secundaria de la institución educativa Unión Zapotillo N° 64647 - Yarinacocha 2020. De muestreo no probabilístico, de tipo básica o pura con diseño no experimental descriptivo correlacional con una muestra de 91 estudiantes. Como instrumento se utilizó un cuestionario para evaluar el uso de la plataforma Zoom y una guía de observación para evaluar la capacidad se comunica oralmente en su lengua materna. Finalmente, los datos fueron a la base de datos de Excel para procesarlos obteniendo un coeficiente de correlación de Pearson de r=0,720, se obtuvo un p=0.000, lo que confirma la existencia de una relación significativa, ya que p es menor a 0,05. Es decir, existe una correlación directa entre el uso de plataforma zoom y la competencia se comunica oralmente como lengua materna en estudiantes de educación secundaria de la institución educativa Unión Zapotillo N° 64647- Yarinacocha 2020.
Accepted: 2022-02-12T02:07:15Z Publisher: Universidad Nacional de Ucayali KerkoCite.ItemAlsoKnownAs: 2405685:86Q2HBRN 4042040:5Q42TUEA
Keywords: ⛔ No DOI found

Conditional Cash Transfer, Loss Framing, and SMS Nudges: Evidence from a Randomized Field Experiment in Bangladesh - Fujii, Tomoki; Ho, Christine; Ray, Rohan; Shonchoy, Abu (2021)
Conditional cash transfers (CCTs) have become one of the most common policy interventions to increase school attendance, but the cost-eﬀectiveness of such interventions has not attracted the attention it deserves. Hence, in addition to a standard CCT implementation, we experimentally study two potential ways to improve the cost-eﬀectiveness of school attendance interventions: (i) SMS information nudges and (ii) loss framing in CCTs. The former provides school attendance information to parents and the latter exploits the endowment eﬀect. Consistent with the existing literature, CCT intervention signiﬁcantly increases school attendance. We also ﬁnd that the loss framing marginally increases attendance over and above the ∗We would like to thank Joseph Altonji, James Berry, Barbara Biasi, Gaurav Dutt, Maulik Jagnani, Costas Meghir, Rohini Pande, Rebecca Thornton, and seminar attendees at Monash and Yale for insightful comments and suggestions. We also thank Akshat Daga, Alekhyo Roychowdhury, Ishaan Malik, and Snehal Modi for research assistance. We beneﬁted from data collection support from MOMODa Foundation and technical support from the Metakave team to automate the process of sending SMS. Finally, we express our sincere gratitude to the participating schools, the students, their parents, and the teachers. Funding from the Shirin Fozdar and Singapore Ministry of Education Academic Research Fund Tier 1 Grant (17-C244-SMU-004) and Japan Center for Economic Research are gratefully acknowledged. This research was approved by the Singapore Management University Institutional Review Board (IRB-16-082-A092-C2(220)). The trial in this study was registered in the AEA RCT registry under AEARCTR-0002373. All mistakes remain ours.
KerkoCite.ItemAlsoKnownAs: 2339240:KUH42MFY 2405685:JG23VUNM
Keywords: ⛔ No DOI found

How Secure Is the Bitcoin Blockchain, and Is Your Cryptocurrency Safe? - Gadgets 360 Newsdesk (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:6E92774L 2405685:3XQ56SMC

The problem of issuance of fake degrees and its implications - Garg, Rachit (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:EEBZSLKE 2405685:C4L4IT2R

Cochrane Rapid Reviews Methods Group offers evidence-informed guidance to conduct rapid reviews - Garritty, Chantelle; Gartlehner, Gerald; Nussbaumer-Streit, Barbara; King, Valerie J.; Hamel, Candyce; Kamel, Chris; Affengruber, Lisa; Stevens, Adrienne (Journal of Clinical Epidemiology, 2021)
To develop methods guidance to support the conduct of rapid reviews (RRs) produced within Cochrane and beyond, in response to requests for timely evidence syntheses for decision-making purposes including urgent health issues of high priority. Interim recommendations were informed by a scoping review of the underlying evidence, primary methods studies conducted, and a survey sent to 119 representatives from 20 Cochrane entities, who were asked to rate and rank RR methods across stages of review conduct. Discussions among those with expertise in RR methods further informed the list of recommendations with accompanying rationales provided. Based on survey results from 63 respondents (53% response rate), 26 RR methods recommendations are presented for which there was a high or moderate level of agreement or scored highest in the absence of such agreement. Where possible, how recommendations align with Cochrane methods guidance for systematic reviews is highlighted. The Cochrane Rapid Reviews Methods Group offers new, interim guidance to support the conduct of RRs. Because best practice is limited by the lack of currently available evidence for some RR methods shortcuts taken, this guidance will need to be updated as additional abbreviated methods are evaluated.
471 citations (Crossref) [2024-04-17] Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.jclinepi.2020.10.007 2339240:DBVSNUE5 2405685:JP82BBZU
Keywords: ⛔ No INSPIRE recid found

Case study: Sisters for Sisters' Education - GEC (VSO, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:9DGDKIFH 2405685:WVH3AK35

GEARR-ing Up for Success After School - GEC (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:LNVJIPEC 2405685:A2NV3XRR

Report on Sisters for Sisters’ Education Evaluation II Project Endline Evaluation by Foundation for Development Management - GEC (Foundation for Development Management, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KH82C3DR 2405685:XQH9K8HR

Sisters for Sisters’ Education - GEC (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KXE8UM9Q 2405685:ISDLUSFB

Sisters for Sisters' Education project Final reflections: Achievements and lessons learned - GEC (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:GVCVCCV2 2405685:L56MJKYJ

Enem 2021: Geekie Teste cobre 100% dos assuntos de Matemática e 93% de Ciências da Natureza - Geekie (Geekie, 2021)
Veja como continuar suas aulas com o apoio do Geekie One Nós somos a Geekie! Apoiamos escolas de todo o Brasil...
KerkoCite.ItemAlsoKnownAs: 2339240:F4SM5NJ8 2405685:HGK3Y6KK

Retrospectiva Geekie 2021: (re)encontros de pessoas, caminhos e possibilidades - Geekie (Geekie, 2021)
Veja como continuar suas aulas com o apoio do Geekie One Nós somos a Geekie! Apoiamos escolas de todo o Brasil...
KerkoCite.ItemAlsoKnownAs: 2339240:DCAHYDUU 2405685:IYDYJ3KN

CHỈ SỐ PHÁT TRIỂN CON NGƯỜI CỦA VIỆT NAM GIAI ĐOẠN 2016-2020 - General Statistics Office (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KAGX3WUS 2405685:UY6C2RJK

Results of the Viet Nam Household Living Standards Survey 2020 - General Statistics Office (Government of the Socialist Republic of Vietnam., 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:I88AEGGM 2339240:YJUCIJAE 2405685:9SPQYFYM

Survey measuring Viet Nam Sustainable Development Goal indicators on Children and Women 2020-2021, Survey Findings Report - General Statistics Office; UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:XLDSLMG6 2405685:HI25ZIAN

e-modul: Gerbang Kurikulum - Gerbang Kurikulum (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:9JLQGZ47 2405685:XU2ECZNW

Country Briefing: Nepal - Girls' Education Challenge (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:L8CW5FFU 2405685:9AZIITFL

Designing and monitoring distance teaching and learning interventions: A guide for projects and implementers - Girls' Education Challenge; Fund Manager; EdTech Hub (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:58CZ6GI8 2405685:ATJRX6DV

Regional Communications Infrastructure Program (RCIP) Malawi - Global Infrastructure Hub (2021)
Only one in ten people in Malawi have access to information and communications technology (as of 2016). This is due to the high cost and complexity of developing the infrastructure and end-user service offering. However, the government plans to improve access to, and the affordability of, broadband connections. It is initiating projects to reach out to the most disadvantaged groups in society.
KerkoCite.ItemAlsoKnownAs: 2339240:N5IPDHHZ 2405685:U3PJDBD6

Education in Pakistan - Global Partnership for Education (Global Partnership for Education, 2021)
See education data for Pakistan and learn about GPE programs, grants, results and progress.
KerkoCite.ItemAlsoKnownAs: 2339240:ZEWKSVKM 2405685:DXUGPUV7

Education in Tanzania - Global Partnership for Education (Global Partnership for Education website, 2021)
See education data for Tanzania and learn about GPE programs, grants, results and progress.
KerkoCite.ItemAlsoKnownAs: 2339240:4K7E29Y5 2405685:EFXBWES9

Global Partnership for Education - Global Partnership for Education (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:K2UK6QF4 2405685:XTNVEKFL

A Cascade Teacher Training Model in Disaster Education: A Case of Turkey - Gökmenoğlu, Tuba; Sönmez, Elif Daşçı; Yavuz, İbrahim (2021)
Individuals' reluctance to take precautions before the disasters happen is one of the most critical concerns of the disaster management area. The disaster education given through schools is a critical process in addressing this problem. The purpose of this paper is to introduce the teacher training program model and the implementation practices of Turkey's School-Based Disaster Education Project. In Turkey, there are few studies regarding the planning, development, implementation, and evaluation stages of Disaster Risk Reduction education for teachers. The project has been carried out within the framework of the Ministry of National Education and Japan International Cooperation Agency. An at-scale cascade teacher professional development model was implemented. The model reached 135,375 teachers in 67 provinces by the 567 trainer teachers in a relatively short time with the cascade training system. This project has brought a significant nationwide disaster risk reduction training experience for Turkey with its economic and sustainable structure.
KerkoCite.ItemAlsoKnownAs: 10.31704/ijocis.2021.002 2339240:MBVV772A 2405685:FC827Z2K

2021-2022 Budget Document Archives - Government of Balochistan (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:EX4JHH8J 2405685:AY6FUCK2 4656463:BYB9ZQ87

DIKSHA - Government of India (DIKSHA - Government of India, 2021)
National Digital Infrastructure for Our Teachers, Our Heroes.
KerkoCite.ItemAlsoKnownAs: 2339240:I4KA3S36 2405685:I68RZN78

National Electrification Strategy - Government of Mozambique (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:YENGEM59 2405685:AS3Q3HQY
Keywords: ⛔ No INSPIRE recid found

Key Findings Report PSLM District Level Survey 2019/20 - Government of Pakistan (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:7WY876U4 2405685:D7GVPXME

Pakistan Social and Living Standards Measurement: District Level - Government of Pakistan (Pakistan Bureau of Statistics, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:974WTH3V 2405685:5EY2VN83

Tanzania National Development Vision 2025 - Government of Tanzania (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8JRRC5P2 2405685:KHS6R9D2

Decree 81/2021/Nd-Cp Policies Financing for Learning Fees in Education and Training Sectors - Government of the Socialist Republic of Vietnam (2021)
Ngày 27/08/2021,Chính phủ đã ban hành Decree 81/2021/ND-CP policies financing for learning fees in education and training sectors Thuộc lĩnh vực Thuế - Phí - Lệ Phí, Giáo dục và sẽ có hiệu lực kể từ ngày 15/10/2021
KerkoCite.ItemAlsoKnownAs: 2339240:VB3R9IPJ 2405685:3RKNHPVH

Resolution No. 28/NQ-CP dated March 03, 2021 on issuance of national strategy for gender equality in 2021-2030 28/NQ-CP,Nghị quyết 28 2021 - Government of the Socialist Republic of Vietnam (2021)
Resolution No. 28/NQ-CP dated March 03, 2021 on issuance of national strategy for gender equality in 2021 - 2030 28/NQ-CP,Nghị quyết 28 2021
KerkoCite.ItemAlsoKnownAs: 2339240:B34SELJY 2405685:5IFAGEWC 2405685:Z97K2IU6

Situation Analysis of Children in Timor- Leste - Government of Timor-Leste; UNICEF (UNICEF, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:VM4BNEQ7 2405685:E6SR4E49
Keywords: ⛔ No INSPIRE recid found

Methodological Guidelines for Education Sector Analysis. Volume 3 | Documents | Global Partnership for Education - GPE (2021)
The Methodological Guidelines provide methods for carrying out a comprehensive analysis of the education sector in lower-income countries.
KerkoCite.ItemAlsoKnownAs: 2339240:LH8ZMZQ6 2405685:B8UBK5Y5 4656463:F393WJPS

Education Technology Market Size & Growth Report, 2030 - Grand View Research (Grand View Research, 2021)
The global education technology market size was valued at USD 106.46 billion in 2021 and is expected to expand at a compound annual growth rate (CAGR) of 16.5% from 2022 to 2030
KerkoCite.ItemAlsoKnownAs: 2339240:AECNU4GS 2405685:WBZ2RQQS

Resource Pack to Support Remote Learning - Radio - Grant, Ursula; Jordan, Caroline; Kamal, Helen; Kube-Barth, Sabine; Waistell, Daniel; Williamson, Sue; Hedges, Claire; Power, Tom; Richardson, Alison Mead (World Bank Group, 2021)
Resource Pack to Support Remote Learning - Radio (English)
KerkoCite.ItemAlsoKnownAs: 10/P1742520930bf702708f2601bdb63d95ee0 2405685:PE8R2AUP

Republic of Sierra Leone Settlement Extents - GRID3 (Center for International Earth Science Information Network (CIESIN), Columbia University and Novel-T, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:HAJEN8QZ 2405685:M3AVWB8Q

Addressing the Mobile Gender Gap in Pakistan - GSMA (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:M5U8DX98 2405685:VNM86856
Keywords: ⛔ No DOI found

Connected Women The Mobile Gender Gap Report 2021 - GSMA (GSMA, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:VWI82KI4 2405685:4CDL58E7

End education crisis in Northern Kenya - The Standard - Guleid, Mohamed (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:BJZ6LCF2 2405685:YB9Q6BTQ

A return to boom and bust (in births) • Resolution Foundation - Gustafsson, Maja; Willetts, David (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:QJZQZHWS 2405685:2GFBNJ5G 4656463:XBIB57W6

A qualitative study of autism services and supports in Singapore: Perspectives of service providers, autistic adults and caregivers - Han, Emeline; Tan, Melisa Mei Jin; Crane, Laura; Legido-Quigley, Helena (Autism, 2021)
The lifelong and complex nature of autism necessitates an array of services and supports spanning across different sectors and providers at different life stages of an autistic individual. However, research has shown that autistic individuals and their families often experience barriers accessing the autism-related services and supports that they need. This is the first qualitative study to explore the provision and coordination of autism services and supports in Singapore from the perspectives of service providers, autistic adults and caregivers. Semi-structured interviews with 21 participants revealed three main themes: (1) improving access to autism-specific services, (2) creating flexible supports in an inclusive environment and (3) addressing stigma and changing societal attitudes. Our findings suggest that Singapore may have achieved rapid growth in autism services, but broader social structures may be slower to change. To better support autistic individuals in society, autistic voices need to be amplified and a collective effort is needed to achieve a paradigm shift from impairment to capability. Lay abstract Because autism is a lifelong and complex condition, autistic people may need a range of supports cutting across different sectors (e.g. health, education and social care) at different stages of their lives. Studies in some countries have shown that autistic people and their families face difficulties accessing the services they need, but no research has been done on this topic in Singapore. To start addressing this gap, we interviewed 21 service providers, autistic adults and caregivers/parents of autistic children to find out their perceptions and experiences of autism services and supports in Singapore. Our participants told us that beyond improving access to autism-specific services, they also hoped to see more flexible supports in an inclusive environment and a broader change in societal attitudes. This study highlights that autism service provision should be informed by autistic voices and not only focus on impairment but also recognise the strengths of autistic people alongside their very real needs. The whole of society – including policymakers, professionals, employers, educators, families and autistic people themselves – needs to work together to fight autism stigma and discrimination.
8 citations (Crossref) [2024-04-29] KerkoCite.ItemAlsoKnownAs: 10.1177/13623613211016112 2339240:VHU9QSLT 2405685:MNN7VZ8M
Keywords: ⛔ No INSPIRE recid found

Grant report on mCARE: Mobile-based care for children with autism spectrum disorder (ASD) for low- and middle-income countries (LMICs) - Haque, Munirul M.; Rabbani, Masud; Dipal, Dipranjan Das; Zarif, Md Ishrak Islam; Iqbal, Anik; Akhter, Shaheen; Parveen, Shahana; Rasel, Mohammad; Rabbani, Golam; Alam, Faruq; Soron, Tanjir Rashid; Ahmed, Syed Ishtiaque; et al. (Journal of Psychiatry and Brain Science, 2021)
Publisher: Hapres KerkoCite.ItemAlsoKnownAs: 10.20900/jpbs.20210004 2339240:9CURHEV2 2405685:LD97CLJ5

Teacher professional development in sub-Saharan Africa: Equity and scale - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (Embedding Social Justice in Teacher Education and Development in Africa, 2021)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
KerkoCite.ItemAlsoKnownAs: 2129771:E2Q73NBN 2129771:EPYMVB2W 2405685:SM8RY6F9
Keywords: Author:Haßler; Björn-CV-OECS; _yl:a; dode_eth-src-dode; dode_eth-trf2-dode

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessey, Sarah; Jordan, Katy; Wagner, Daniel; EdTech Hub Team (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:P8FGXBPB 2405685:F8WM8674
Keywords: ⛔ No INSPIRE recid found

Supporting practitioner-led inquiry into classroom dialogue with a research-informed professional learning resource: A design-based approach - Hennessy, S; Kershner, R; Calcagni, E; Ahmed, F (Review of Education, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1002/rev3.3269 2339240:CHQCGVJ2 2405685:H94TBG7S 2405685:W3JZM7A8 2534378:AP82HE4R
Keywords: ⛔ No DOI found; ❓ Multiple DOI

Malawi Economic Monitor : Investing in Digital Transformation - Hettinger, Patrick Shawn; Mboob, Ida S; Robinson, DanielleSimone; Nyirenda, Yalenga Loraine; Galal, Rami Mikko Ahmed; Chilima, Efrem Zephnath (World Bank, 2021)
Malawi Economic Monitor : Investing in Digital Transformation (English)
KerkoCite.ItemAlsoKnownAs: 2339240:4E283TFK 2405685:A54C4DV2

Figures on Ethnic Minority Women and Men in Viet Nam 2015-2019 from the Findings of Surveys on the Socio-Economic Situation Amongst 53 Ethnic Minority Groups 2015-2019 - Hien, Bui Ton; Nguyen, Thi Bich Thuy; Nguyen, Bao Cuong; Hoang, Thu Hang; Ly, Vu Phuong (2021)
From the findings of Surveys on the socioeconomic situation amongst 53 Ethnic Minority Groups 2015-2019
KerkoCite.ItemAlsoKnownAs: 2339240:4ZSS7VWA 2339240:S9H2X6LQ 2405685:APEL4CI8 2405685:TAPAQG6H

International Development Committee Oral evidence: UK aid to Pakistan - House of Commons (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KYXRQAF6 2405685:TP8T24RG

Measuring the impact of COVID-19 on education in Pakistan - Idara-e-Taleem-o-Aagahi (Islamabad, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:2FKH8MX9 2405685:LXSIR7IK

Midterm Evaluation Report - IMC Worldwide (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:X6NTWCQM 2405685:75DWT6LL

Basic Overview of how LTI ® Works - IMS Global (IMS Global, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:L7CLZYZ3 2405685:UUXI6GJK

Encuesta para la Medición del Impacto COVID-19 en la Educación (ECOVID-ED) 2020 - INEGI (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:TS5IE4H9 2405685:BPRVAVR3

Education and Sustainable Development Challenges - Information and Decision Support Center (2021)
التعليم وتحديات التنمية المستدامة,الخميس. 09 سبتمبر., 2021,أ.د. سعيد المصري,
KerkoCite.ItemAlsoKnownAs: 2339240:C6ZJGRKB 2405685:PEZ4Q8F7

Instructure | Educational Software Development - Instructure (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:PY5GM76E 2405685:5YM28JSG

Mind the Gap: The State of Girls’ Education in Crisis and Conflict - Inter-agency Network for Education in Emergencies (INEE, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:DWS86NS8 2405685:54KVWNVR

Teacher Wellbeing Resources Mapping & Gap Analysis - Inter-Agency Network for Education in Emergencies (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8AFTF3MZ 2405685:X759APEH

Mozambique - International Energy Agency (IEA, 2021)
In Mozambique, around 40% of people have access to electricity, through the grid or mini/off-grid systems. The government has promoted solar PV solutions in rural areas, reporting that 700 schools and 800 other public buildings now have electricity from s
KerkoCite.ItemAlsoKnownAs: 2339240:KNXFHKY2 2405685:Q6K2LV3I
Keywords: ⛔ No INSPIRE recid found

Closing the gap: Ensuring there are enough qualified and supported teachers in sub-Saharan Africa - International Task Force on Teachers for Education 2030 (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:6C5GZT9V 2405685:6G8LSNVP

Digital trends in Asia and the Pacific 2021 Information and communication technology trends and developments in the Asia-Pacific region, 2017-2020 - International Telecommunication Union (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:4QTXAM49

Targeting within universalism - Jacques, Olivier; Noel, Alain (Journal of European Social Policy, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1177/0958928720918973 2339240:4RNKX4CG 2405685:PUWB7MI7

Reopening with Resilience: Lessons from Remote Learning during COVID-19 in East Asia and the Pacific. - Jeon, Youngkwang; Dreesen, Thomas; Fushimi, Akihiro; Koeppl, Dominik (UNICEF, 2021)
Publisher: ERIC KerkoCite.ItemAlsoKnownAs: 2339240:WWUUXIKS 2405685:463PM8AB
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Comparative Analysis of Personal Data Protection Bill 2020 - Kalyar, Barrister Jannat Ali (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:SSQQGN7R 2405685:JVHAYIPE

Improved teacher capacity and strong school leadership are key for better school performance - Karakaya, Irem (UNICEF Lao People's Democratic Republic, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:GZEYRJU9 2405685:GTC3NYP7

Educational technology to improve capacity - integrating adaptive programmes in public schools in Kenya - Kaye, Tom (2021)
KerkoCite.ItemAlsoKnownAs: 10.4324/9780429344855 2339240:KH9YGR3M 2405685:W42JAPNN

Tax Farming Redux: Experimental Evidence on Performance Pay for Tax Collectors - Khan, Adnan Q.; Khwaja, Asim I.; Olken, Benjamin A. (National Bureau of Economic Research, 2021)
Performance pay for tax collectors has the potential to raise revenues, but might come at a cost if taxpayers face undue pressure from collectors. We report the first large-scale field experiment on these issues, where we experimentally allocated 482 property tax units in Punjab, Pakistan into one of three performance-pay schemes or a control. After two years, incentivized units had 9.3 log points higher revenue than controls, which translates to a 46 percent higher growth rate. The scheme that rewarded purely on revenue did best, increasing revenue by 12.8 log points (62 percent higher growth rate), with little penalty for customer satisfaction and assessment accuracy compared to the two other schemes that explicitly also rewarded these dimensions. Further analysis reveals that these revenue gains accrue from a small number of properties becoming taxed at their true value, which is substantially more than they had been taxed at previously. The majority of properties in incentivized areas in fact pay no more taxes, but do report higher bribes. The results are consistent with a collusive setting in which performance pay increases collector's bargaining power over taxpayers, who either have to pay higher bribes to avoid being reassessed, or pay substantially higher taxes if collusion breaks down.
KerkoCite.ItemAlsoKnownAs: 10.3386/w20627 2339240:BAJEUIIS 2405685:NRLTA3UK 4656463:Z5GTYX4D

Crisis-Led Approaches to Teaching and Learning in Bangladesh - Khan, Maluba; Smith, Thomas; Islam, Mohammed Zakiul; Anand, Kusha; Hossain, Tahrima; Ahmed, Shakil; Islam, Rakibul; Atuly, Afsana Sadiq; Nayeem, Azwa; Sabbab, Salman; Hassan, Mehdi; Sarwar, Afzal Hossain (Cardiff University, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:X6A6NBMS 2405685:JSN76N4D
Keywords: ⛔ No INSPIRE recid found

Child education in the time of pandemic: Learning loss and dropout - Khan, Muhammad Jehangir; Ahmed, Junaid (Children and Youth Services Review, 2021)
The disruptive effects of the COVID-19 pandemic had affected the education sector at an unprecedented scale. In order to contain the spread of the virus, a large number of countries across the globe have shut their schools to handle the pandemic. However, it has adversely affected students’ learning and school attendance. In this regard, we assess the impact of COVID-19 on the learning loss, school dropout, and the economic costs in term of foregone earnings for children in Pakistan. The study finds a substantial decrease in Learning Adjusted Years of Schooling (LAYS) with worsening consequences for girls than boys. Likewise, the aggregate economic cost amounts to 107 billion dollars when adjusted for human capital utilisation. Besides, our simulation results suggest that about 7.2 million children dropout due to a reduction in household expenditure by 50 percent. In comparison, the dropout is more pronounced at the primary level of schooling. The results recommend that the government design robust social protection and remote education strategies to mitigate school closure’s adverse effect on children’s learning. The emphasis should be rather on the long run strategies to cope with a resilient education system of futuristic orientation.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.childyouth.2021.106065 2339240:ZZFSPD7I 2405685:SB69LBNY

Innovative Methods to Train Teachers of Blind Children - Kibet, Amon; Kweyu, Ignatius; Koszorus, Ferenc (EdTech Hub, 2021)
Discover what we learned using innovative methods such as virtual training via WhatAapp to train teachers of blind children. Click to read more.
KerkoCite.ItemAlsoKnownAs: 2339240:ULNM6MVY 2405685:9872JIDA

Multilingualism in Timor-Leste - Klinken, Catharina Williams-van; Lucas, Olinda (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:SN2PVGLX 2405685:BCDQINA9
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Health status of children with Down syndrome in Myanmar - Ko, Khine Mi Mi; Linn, Kyaw; Aye, Aye Mya Min; Saw, Mon Thander; Aung, Pyae Phyo (BMJ Paediatrics Open, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:WJS68H8U 2405685:QD99ED9V
Keywords: ⛔ No INSPIRE recid found

Using a Participatory Approach to Create SEL Programming: The Case of Ahlan Simsim - Kohn, Shanna; Foulds, Kim; Cole, Charlotte; Matthews, Mackenzie; Hussein, Laila (Journal on Education in Emergencies, 2021)
This paper highlights the use of a participatory, trauma-informed approach in the creation of Ahlan Simsim, a Sesame Street television program for the Middle East, and asserts the importance of using a participatory approach to designing culturally relevant social and emotional learning (SEL) content. Ahlan Simsim is a component of a larger initiative of the same name, which was created by Sesame Workshop and the International Rescue Committee and funded by the MacArthur and LEGO foundations. This program brings early learning and nurturing care to children and families affected by the Syrian crisis through a combination of mass media and direct service programming. In this article, we present a review of the research and consultations Sesame Workshop conducted with local communities and local child-development experts in Iraq, Jordan, Syria, and Lebanon from August to November 2018. Sesame Workshop’s aim was to identify and refine the television program’s focus area and to create locally relevant, trauma-informed content that draws from SEL strategies that resonate most and have the greatest impact with audiences in the Syrian response region. We argue that, for SEL programming to achieve maximum impact, it is critical that program designers develop socialemotional frameworks for children from the ground up by working with local caregivers and practitioners.
KerkoCite.ItemAlsoKnownAs: 10.33682/hxrv-2g8g 2339240:CUZ5VVAB 2405685:JNHJGIBB

What is Kubernetes - Kubernetes (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8HDPPTVT 2405685:3W2PF2VN

E-learning theories, components, and cloud computing-based learning platforms: - Kumar, Vikas; Sharma, Deepika (International Journal of Web-Based Learning and Teaching Technologies, 2021)
The student habit of using the digital platforms can be used to compliment the traditional learning methods. Specifically, designed digital learning platform can support the learning with convenience of time, place, and pace. They can increase the engagement of students and produce higher learning outcomes with increased satisfaction and competence. With a number of embedded features, cloud computing technology-based platforms can deliver the convenience and flexibility in learning environment to compliment the traditional learning pedagogies. The present work identifies the essential learning components that comprise the e-learning environment and categorizes them according to the established learning theories. Further, the prominent cloud-based learning platforms have been mapped to these platforms to see their effectiveness through the existing theories. The work is targeted to form a basis for the development and implementation of successful e-learning tools using the cloud-based platforms.
KerkoCite.ItemAlsoKnownAs: 10.4018/IJWLTT.20210501.oa1 2339240:Q8D3BRHW 2405685:4LQMP9XK

Edtech Startups in Latin America 2021 Survey Results - Lavca (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:6BCNJVMR 2405685:V8X7UX4K

Mapping education data in sub-Saharan Africa - Lawson, Laté; Heady, Lucy (Education Sub Saharan Africa (ESSA), 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:HC6RUIMQ 2339240:MTMGPY6E 2405685:3GG5SPKY 2405685:TT9S4YV2 8836279:77XCCW4B 8836279:PNHCGL86 8836279:S2UPNP2W 8836279:TRTQSCA2

The future of language education in Europe: case studies of innovative practices - Le Pichon-Vorstman, Emmanuelle; Siarova, Hanna; Szőnyi, Eszter (European Journal of Language Policy, 2021)
Publisher: Liverpool University Press KerkoCite.ItemAlsoKnownAs: 2405685:T5E3RHZ5 4042040:3TYPTL5I

Principal Dashboard - Leh Wi Lan (Leh Wi Lan, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:QQ28IZKC 2405685:ZHDNZNFK

Recovering from school closures in Sierra Leone: Status of pupil learning outcomes in junior and senior secondary schools - Leh Wi Lan (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:TVYLJS4I 2405685:IUJU327A

UNICEF’s lessons learned from the education response to the COVID-19 crisis and reflections on the implications for education policy - Lennox, Janet; Reuge, Nicolas; Benavides, Francisco (International Journal of Educational Development, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2021.102429 2339240:SJDHVGLR 2405685:EFBKUW46

Case Study: TEAM Girl Malawi - Link Education International (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:VTNN7IW4 2405685:C9CRSJF9

Case study: Team Girl Malawi - Link Education International (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:B9EEH33I

Outlier Vietnam and the Problem of Embeddedness: Contributions to the Political Economy of Learning. . - London, Jonathan (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:C9DT58AH 2405685:9HR7QQQ6 4656463:PC9PS3MC

Assessing outside of the “classroom box” while schools are closed: The potential of phone-based formative assessments to support learning continuity - Luna-Bazaldua, D; Liberman, J; Levin, V (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:JBQUWG4K 2405685:RTBSFRAE

Short and Long-Run Distributional Impacts of COVID-19 in Latin America - Lustig, Nora; Martinez Pabon, Valentina; Neidhöfer, Guido (2021)
We simulate the short- and long-term distributional consequences of COVID-19 in the four largest Latin American economies: Argentina, Brazil, Colombia and Mexico. We show that the shortterm impact on income inequality and poverty can be very significant, but that additional spending on social assistance more than offsets the effect in Brazil. The offsetting effect is significant in Argentina and Colombia, and nil in Mexico where there has been no such expansion. We find that a universal basic income that would have produced the same reduction in the poverty gap as actual policies would have cost slightly more but would have benefited the poor (the nonpoor) slightly less (more). To project the long-term consequences, we estimate the impact of the pandemic on school achievement and its intergenerational persistence. We use information on school closures, educational mitigation policies, and account for educational losses related to health shocks and parental job loss. Our findings show that in all four countries the impact is strongly asymmetric and affects particularly the high-school completion rates of children from disadvantaged families. Our simulations suggest that mitigation policies seem to have a minor impact on containing these negative effects.
KerkoCite.ItemAlsoKnownAs: 2339240:TURVV9V3 2405685:R7SG8FJ4

Early effects of the COVID-19 lockdown on children in rural Bangladesh - Makino, Momoe; Shonchoy, Abu S; Wahhaj, Zaki (2021)
Using data collected through a telephone-based survey in rural Bangladesh during the height of the pandemic, we present evidence on the eﬀects of COVID-19-led lockdown and school closures on children, focusing on three child-related outcomes: time use of children during the school closure, plans regarding children’s schooling continuation, and the incidence of child marriages. Our analysis reveals heterogeneity in the eﬀects of lockdown and school closure in terms of the child’s gender and the type of shocks. We ﬁnd a decrease in children’s study time and an increase in time spent on household chores during the school closure, and these changes were signiﬁcantly larger for girls than for boys. Within the household, respiratory illness lowered expectations that a child would return to school and increased the probability of marriage-related discussions for girls. Our ﬁndings oﬀer a cautionary tale regarding the potential longterm eﬀects of pandemic for girls in developing countries.
KerkoCite.ItemAlsoKnownAs: 2339240:EHS3BXYL 2405685:HBIVSCZT
Keywords: ⛔ No DOI found

Malala Fund releases report on girls’ education and COVID-19 | Malala Fund Newsroom - Malala Fund (Malala Fund | Newsroom, 2021)
Our latest report reveals the pandemic's lasting effects for the most marginalised girls.
KerkoCite.ItemAlsoKnownAs: 2339240:5TFZT53N 2405685:6YT5WWUX

The effect of school closures on standardised student test outcomes - Maldonado, Joana Elisa; De Witte, Kristof (British Educational Research Journal, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:F5KVHGL5 2405685:47YC8CVL

The effect of school closures on standardised student test outcomes - Maldonado, Joana Elisa; De Witte, Kristof (British Educational Research Journal, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:F5KVHGL5 2405685:47YC8CVL

A Global Mapping of Delivery Approaches - Mansoor, Zahra; Qarout, Dana; Anderson, Kate; Carano, Celeste; Dvorakova, Veronika; Williams, Martin J (2021)
The past 25 years has seen numerous governments worldwide adopting new institutional forms, such as delivery units and reform labs, to try to improve service delivery. We conduct a systematic global search and mapping of these delivery approaches. We identify 152 instances of delivery approach (DA) adoption from 80 diﬀerent countries, ranging from the center of government down to provincial and local levels, with an accelerating trend of adoption since 2010. The majority of these include education as a focus sector. The main ﬁnding that emerges from our analysis is that there is no single model that characterizes the design of such approaches or the purposes for which they are adopted. However, we do identify a number of patterns, including that DAs in lower-income countries are more likely to focus mainly on output-type goals (as opposed to outcomes), use external consultants, and utilize accountability- and incentive-driven mechanisms relatively more heavily than their counterparts in middle- and high-income countries. While our ﬁndings are purely descriptive and cannot be used to infer whether DAs are eﬀective, they give an indication to policymakers about the menu of potential options available to them in designing DAs. This global mapping can also provide useful context for existing and future country-level case studies that investigate the eﬀectiveness of DAs and seek to explore which designs might be more eﬀective in diﬀerent contexts and for diﬀerent purposes.
KerkoCite.ItemAlsoKnownAs: 2339240:Z24GD989 2405685:YBYBTSS3 4656463:753W7S4E
Keywords: ⛔ No DOI found

Gender-Transformative Programming in UNICEF Selected Case Studies - Marcus, Rachel; Samuels, Fiona; Belachew, H; Jalal, S (2021)
Reflections and Lessons for UNICEF’s Gender Policy and Action Plan (2022-2025), A compendium of papers, Florence: UNICEF Innocenti Research Centre
KerkoCite.ItemAlsoKnownAs: 2339240:22VUKTDE 2405685:TNP9V4TF

Online learning and COVID-19 outbreak in Mozambique – academics’ experience during suspension of face-to-face classes - Martins, Hélio Rogério; Manjate, José Luís; Tinga, Iolanda Cavaleiro; Matusse, Ana Paula Xavier; Sitoe, Lénia Cecília Alberto (Interactive Learning Environments, 2021)
The COVID-19 outbreak had a significant impact on social life and the education system, leading to the suspension of face-to-face classes and the adoption of online learning as a strategy to continue the teaching and learning process in many countries around the world, including Mozambique. Thus, we conducted the present study to analyze the teaching and learning process using digital platforms during a state of emergency due to COVID-19. We inquired 417 academics who responded to an online survey open between the 4th and 12th of May 2020 and released via WhatsApp and email. For data analysis, we used descriptive statistics to present the results in simple tables. 263 (61.3%) were male, and the average age was 39.7 years. Seventy-one percent (71%) of the academics received guidance to proceed with the teaching and learning process during the emergency, and several platforms were used for this purpose, where WhatsApp and email (49.2%) were the most used. About 67% of the academics faced some difficulty with the digital learning platforms, and half managed to teach all classes. This process challenged the academic staff, who had to rely on several learning platforms and adopt different teaching strategies in conditions never experienced before.
2 citations (Crossref) [2024-03-22] Publisher: Routledge _eprint: https://doi.org/10.1080/10494820.2021.1969954 KerkoCite.ItemAlsoKnownAs: 10.1080/10494820.2021.1969954 2339240:QKPTU7B8 2405685:2MHLIPYH
Keywords: Academics - Emergency; COVID-19; Online learning; ⛔ No INSPIRE recid found

Children’s remote learning experiences in Italy during the COVID-19 pandemic - Mascheroni, Giovanna; Saeed, Marium; Valenza, Marco; Cino, Davide; Dreesen, Thomas; Zaffaroni, Lorenzo Giuseppe; Kardefelt-Winther, Daniel (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KBCDZDRK 2405685:N6BT886I
Keywords: ⛔ No DOI found

Supporting Teachers Moving Online, using a MOOC, During the COVID-19 Pandemic - Mays, Tony John; Ogange, Betty; Naidu, Som; Perris, Kirk (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:BK6R4LIP 2405685:676ZMM3I

Learning Renewed: ten lessons from the pandemic - McAleavy, Tony; Riggall, Anna; Korin, Astrid (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5ZRP2HCK 2405685:ARSSKSPN
Keywords: ⛔ No DOI found

Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs - McIntyre, Nora; Sabates, Ricardo; Jamieson Eberhardt, Molly (EdTech Hub, 2021)
ZenodoArchiveID: 4575561 PreviousDOI: 10.5281/zenodo.4468852 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4575561 2339240:BJT3BKFR 2405685:V9FUFGLQ

MHPSS and EIE Toolkit - Mental Health & Psychosocial Support Network (2021)
The MHPSS and EiE Toolkit offers access to key documents and resources of relevance to those working in the fields of Education in Emergencies (EiE) and of Mental Health and Psychosocial Support (MHPSS).
KerkoCite.ItemAlsoKnownAs: 2339240:ZWQZVS7K 2405685:GSIF2L54

How educational are 'educational' apps for young children? App store content analysis using the Four Pillars of Learning framework - Meyer, Marisa; Zosh, Jennifer M.; McLaren, Caroline; Robb, Michael; McCafferty, Harlan; Golinkoff, Roberta Michnick; Hirsh-Pasek, Kathy; Radesky, Jenny (Journal of Children and Media, 2021)
Experts have expressed concerns about the lack of evidence demonstrating that children's "educational" applications (apps) have educational value. This study aimed to operationalize Hirsh-Pasek, Zosh, et al.'s (2015) Four Pillars of Learning into a reliable coding scheme (Pillar 1: Active Learning, Pillar 2: Engagement in the Learning Process, Pillar 3: Meaningful Learning, Pillar 4: Social Interaction), describe the educational quality of commercially-available apps, and examine differences in educational quality between free and paid apps. We analyzed 100 children's educational apps with the highest downloads from Google Play and Apple app stores, as well as 24 apps most frequently played by preschool-age children in a longitudinal cohort study. We developed a coding scheme in which each app earned a value of 0-3 for each Pillar, defining lower-quality apps as those scoring ≤ 4, summed across the Four Pillars. Overall scores were low across all Pillars. Free apps had significantly lower Pillar 2 (Engagement in Learning Process) scores (t-test, p < .0001) and overall scores (t-test, p < .0047) when compared to paid apps, due to the presence of distracting enhancements. These results highlight the need for improved design of educational apps guided by developmental science.
KerkoCite.ItemAlsoKnownAs: 10.1080/17482798.2021.1882516 2339240:DAP57ZEF 2405685:9KM825BK
Keywords: Digital Media; Digital Play; Early Childhood; Educational Apps; Four Pillars of Learning; Mobile Devices

Teachers’ Learning Communities for Developing High Order Thinking Skills—A Case Study of a School Pedagogical Change - Miedijensky, Shirley; Sasson, Irit; Yehuda, Itamar (Interchange (Toronto. 1984), 2021)
This study deals with an elementary school that is undergoing a process of pedagogical change. The teachers understood that their weak point was excessive use of teaching based on memorization rather than developing high-order thinking (HOT) skills. The school therefore established teachers’ learning communities for peer learning and designing learning tasks that encourage the development of HOT skills. Quantitative and qualitative research tools were used in this study as a formative assessment. The data included learning tasks and interviews with teachers. The findings indicate an increase in the expression of critical thinking and the cognitive levels of application, analysis, and synthesis. The national test scores indicate an increase in students’ performance in most subjects. It appears that educators recognize the need for a transition from teaching that emphasize memorizing information to methods that develop students’ thinking skills and independent learning and initiated a successful pedagogical change.
Place: Dordrecht Publisher: Springer Netherlands KerkoCite.ItemAlsoKnownAs: 10.1007/s10780-021-09423-7 2339240:JUVZA2U4 2405685:QTXG5999
Keywords: Case studies; Collaboration; Critical thinking; Education; Educational Philosophy; Educational Policy and Politics; Elementary schools; Formative assessment; High-order thinking; Learning; Memorization; Pedagogical change; Pedagogy; Peer learning; Qualitative research; Teachers; Teachers’ learning communities; Teaching; Teaching methods; Test scores; Thinking skills

Technological Plan for Education (PTE) - Ministerio De Educación, Enseñanza Universitaria Y Deportes (República De Guinea Ecuatorial, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:VVGM4WVD 2405685:N9BTI8FU

2020 Annual Schools Census Report - Ministry of Basic and Senior Secondary Education (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5S3TQR6D 2405685:JMH9T363

About TMIS - Ministry of Basic and Senior Secondary Education (Teacher Management Information System, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:VT3W8CAF 2405685:8XXCWVUM

Annual School Census - Ministry of Basic and Senior Secondary Education (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:PSR8CRAP 2405685:HK8SFD2T

Annual School Census Report - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ELC26RCU 2405685:2GVLUELP 2405685:6I3545CN 2405685:UP66E9KW 2486141:U5LTFSMK
Keywords: auto_merged

LWL: Numbers and impact by 2020/21 school year - Ministry of Basic and Senior Secondary Education (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:569UWV3B 2486141:BQRLTAA6

National policy on radical inclusion in schools - Ministry of Basic and Senior Secondary Education (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:CYWMBVW8

Concept on mapping technical and vocational educational and training data in Kenya - Ministry of Education (State Department for Vocational and Technical Training, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:W9CQUI3Y 2405685:9S4JGQTN

During the first month of operation, the All-Ukrainian Online School platform was used almost 5 million times - Ministry of Education and Science of Ukraine (2021)
During the first month of operation of the online platform "All-Ukrainian Online School" since its launch on December 11, 2020, it was visited by more than 2 million users who interacted with the platform almost 5 million times
KerkoCite.ItemAlsoKnownAs: 2339240:FZ56BN6W 2405685:Q82RX4QQ

EMIS - Ministry of Education, Government of Timor-Leste (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:EBVA7NE2 2405685:Q2KEG3ZJ

Educational Technology Plan - Ministry of Education (Singapore) (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:XH7WCXVJ 2405685:4AZVTWBW

2020 Annual Report on the Petroleum Funds | Ministry of Finance | Ghana - Ministry of Finance (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:JH3SZELK 2405685:DDPAL29F 4656463:XGB3IXY9

Cambodia’s Science Technology and Innovation Roadmap 2030 - Ministry of Industry, Science, Technology and Innovation, Royal Government of Cambodia (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ELQ7W88X 2405685:G2968WIN

Personal Data Protection Bill 2020 - Ministry of Information Technology and Telecommunication (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:F2C93XEX 2405685:AWDES5PD

Technological Federalism : A Building Block to Constitutionalise the Digital Sphere - Mittal, Anushka (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:MANBX9Z8 2405685:5MPF4DCD
Keywords: ⛔ No DOI found

OER may be free, but you still need to invest to use them: Part I - Mogos, Ariam; Gacicio, Esther; Gaible, Edmond (2021)
Calls for access and equity underpin the OER (Open Educational Resources) movement, but it’s yet to be seen if the potential impact of OER will materialize in education - something COVID-19 may help change.
KerkoCite.ItemAlsoKnownAs: 2405685:9KXMVHL3

Motor development in children with autism spectrum disorder - Mohd Nordin, Ashikin; Ismail, Juriza; Kamal Nor, Norazlin (Frontiers in Pediatrics, 2021)
Objective: This study was conducted to determine the gross and fine motor profiles of children with autism spectrum disorder compared to typically developing children. Additionally, we also assessed if the motor delay was more pronounced with increasing age. Method: This was a retrospective study involving children aged 12–60 months of age comparing motor development in children with autism spectrum disorder with typically developing children. Their developmental profile was assessed using Schedule of Growing Skills II. Descriptive statistics was used to analyse the developmental profile between the groups. Results: ASD children had significant gross motor (6.7%) and fine motor delay (38.5%) compared to typically developing children, who did not show any delay. The motor delay in ASD children was more prominent in older children. Conclusion: It is important to assess motor development in ASD children as there is significant motor delay in these children compared to typically developing children, and the delay becomes more prominent with age. Early detection of motor delay could allow provision of early intervention services to optimize developmental outcomes.
KerkoCite.ItemAlsoKnownAs: 10.3389/fped.2021.598276 2339240:I68BYGJ8 2405685:5IZ7PUSC

Resource Pack to Support Remote Learning : Digital - Mohn, Giti; Atif, Rafique; Cardoso De Barros, Jorge Manuel; Twinomugisha, Alex; Hawkins, Robert J; Barron Rodriguez, Maria Rebeca (World Bank Group, 2021)
Resource Pack to Support Remote Learning : Digital (English)

Resource Pack to Support Remote Learning : Introduction - Mohn, Giti; Atif, Rafique; Cardoso De Barros, Jorge Manuel; Twinomugisha, Alex; Hawkins, Robert J; Barron Rodriguez, Maria Rebeca (World Bank Group, 2021)
Resource Pack to Support Remote Learning : Introduction (English)
KerkoCite.ItemAlsoKnownAs: 2405685:P4ZV3WJ6

Resource Pack to Support Remote Learning : Mobile - Mohn, Giti; Atif, Rafique; Cardoso De Barros, Jorge Manuel; Twinomugisha, Alex; Hawkins, Robert J; Barron Rodriguez, Maria Rebeca (World Bank Group, 2021)
Resource Pack to Support Remote Learning : Mobile (English)
KerkoCite.ItemAlsoKnownAs: 2405685:MLCVFR3W

Resource Pack to Support Remote Learning : Print - Mohn, Giti; Atif, Rafique; Cardoso De Barros, Jorge Manuel; Twinomugisha, Alex; Hawkins, Robert J; Barron Rodriguez, Maria Rebeca (World Bank Group, 2021)
Resource Pack to Support Remote Learning : Print (English)
KerkoCite.ItemAlsoKnownAs: 2405685:TIYRFXSF

Resource Pack to Support Remote Learning : Television - Mohn, Giti; Atif, Rafique; Cardoso De Barros, Jorge Manuel; Twinomugisha, Alex; Hawkins, Robert J; Barron Rodriguez, Maria Rebeca (World Bank Group, 2021)
Resource Pack to Support Remote Learning : Television (English)
KerkoCite.ItemAlsoKnownAs: 2405685:ENYQ2YWR

Resource Pack to Support Remote Learning : Formative Assessment - Mohn, Giti; Rafique, Giti; Cardoso De Barros, Jorge Manuel; Twinomugisha, Alex; Hawkins, Robert J; Barron Rodriguez, Maria Rebeca (World Bank, 2021)
Resource Pack to Support Remote Learning : Formative Assessment (English)
KerkoCite.ItemAlsoKnownAs: 2405685:WFPQL8XD

El engagement en la educación virtual: experiencias durante la pandemia COVID-19 - Molina, Odiel Estrada; Cancell, Dieter Reynaldo Fuentes; Hernández, Alién García (Texto Livre: Linguagem e Tecnologia, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:5B3ZQV8Z
Keywords: ⛔ No DOI found

Moodle - Open-source learning platform | Moodle.org - Moodle (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:Q2JQYS7R 2405685:ZSDT9976

Pedagogical strategies in medical education to the challenges of Covid-19: Scoping review - Moretti-Pires, RM; de Campos, DA; Tesser Junior, C; de Oliveira Junior, JB; de Oliveira Turatti, B; de Oliveira, DC (Revista Brasileira De Educação Médica, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:VNX9FVCS 2405685:M9X5KZTN
Keywords: ⛔ No DOI found

Toolkit for Designing a Comprehensive Distance Learning Strategy - Morris, Emily; Tan, Yvette (USAID, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8CCGV3KW 2405685:3QQ8X8NF

Remote teaching during COVID-19: Implications from a national survey of language educators - Moser, Kelly; Wei, Tianlan; Brenner, Devon (System, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.system.2020.102431 2339240:X35CVX3P 2405685:C5WZCIS4

Education in Times of Crisis: Effective Approaches to distance learning. Sharing teachers' expertise and experiences - Müller, Lisa Maria; Goldenberg, Gemma (Chartered College of Teaching, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:2NYZML8X 2405685:7F5R43QX

Strengthening Education Management Information Systems (EMIS) and Data for Increased Resilience to Crisis: country case study: South Soudan - Mwaniki, David (UNESCO, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:LRSS84YD
Keywords: auto_merged

Pakistan Education Statistics 2017-18 - NEMIS (National Education Management Information System, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:57U6FLU9 2405685:2KAH2NJR

Pakistan Education Statistics 2017-18 - NEMIS (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:SZQJUSLX 2405685:HWFDLM38

Pakistan Education Statistics 2017-18 - NEMIS (National Education Management Information System, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:57U6FLU9 2405685:2KAH2NJR

Nigeria Learning Passport - Nigeria Federal Ministry of Education (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:4TAPVKN4 2405685:CCRKKXJS

Teacher attendance and time on task in primary schools in Mozambique - Nugroho, Dita; Karamperidou, Despina (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:XI9TB42I 2405685:VZR6RFUF

Creditor Reporting System (CRS) - OECD (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:GKAXYNKY 2405685:QF9A6M5Z
Keywords: ___working_potential_duplicate

Scaling education innovations for impact in low-and-middle-income countries during COVID - Olsen, Brad (Brookings Institution, 2021)
In 2020, the Center for Universal Education (CUE) at the Brookings Institution joined the Global Partnership for Education’s (GPE) Knowledge and Innovation Exchange (KIX), a joint partnership between the Global Partnership for Education and the International Development Research Centre (IDRC), to facilitate a cross-national, multiteam, design-based research and professional support initiative called Research on Scaling the Impact of Innovations in Education (ROSIE). The intention of ROSIE is to bring together researchers and practitioners to study the process of scaling education initiatives. This first annual brief reflects on scaling insights from different scaling teams across many low- and middle-income countries to jointly learn and share best practices related to scaling in education. Effective scaling is not just about designing and delivering promising innovations for use but also embedding them in thoughtful, mutifaceted ways to ensure that they grow, deepen, and have lasting impact. This brief discusses how several teams went about this work during the difficult last year.
KerkoCite.ItemAlsoKnownAs: 2339240:S7V2Y764 2405685:Y9VGSW9N

Mobile-based solutions can strengthen human capital gains disrupted by COVID-19 in developing countries - Orozco, Victor (2021)
Education technology is leveraging smartphones to reverse the pandemic-induced learning crisis.
KerkoCite.ItemAlsoKnownAs: 2339240:5G6GXMV4 2405685:VC52RJ7L

Psychological Well-Being Levels of Teacher Candidates in the Distance Education Process - Özkul, Ramazan; Kirbaç, Metin; Kaya, Fatih (2021)
The expansion of the global communication network with the help of technological developments has undoubtedly shown its greatest impact in the field of education. As a matter of fact, the spread of communication networks between countries and individuals, in the field of education; it has created a global perception of education by accelerating the circulation of information resources, ideas and products. Especially with the COVID-19 epidemic, the transition to distance education has accelerated. In this context, it is considered important to investigate the behaviors and psychological states of students and to contribute to their good management of this process. The aim of this study is to examine the psychological well-being levels of teacher candidates in the distance education process. This research, which aims to examine the psychological well-being levels of teacher candidates in the distance education process, is a quantitative method with a causal comparison model. The study population of the research consists of Inönü University Faculty of Education students. The sample of the study consisted of 584 participants determined by the random stratified sampling method from the population. The data of the study were collected with the "Psychological Well-Being Scale". Obtained data, independent groups t-test, one-way ANOVA and descriptive statistics tests were performed. Research findings showed that participants had high levels of psychological well-being.
ISSN: 2501-9120 Issue: 2 Pages: 82-97 Publication Title: Online Submission KerkoCite.ItemAlsoKnownAs: 2339240:MRF5YWGN 2405685:JHHP36ST
Keywords: Access to Computers; COVID-19; Correlation; Distance Education; Foreign Countries; Gender Differences; Handheld Devices; Internet; Mental Health; Pandemics; Physical Environment; Preferences; Preservice Teachers; Rural Urban Differences; Study Habits; Synchronous Communication; Telecommunications; Undergraduate Students; Well Being

Case Study: GEARR-ing Up for Success After School - PEAS (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:9WEWV2NE 2405685:YR2PLC48

GENDER TRANSFORMATIVE EDUCATION - PLAN International; UNICEF; Transform Education; UNGEI (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:IUJFLDHR 2405685:V9KDIPXS

SIS Tanzania (LIVE) - PORALG (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:9U7CNQTK 2405685:3D9IMZVK

Turning to technology: A global survey of teachers' responses to the Covid-19 pandemic - Pota, Vikas; Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam; Zubairi, Asma; Aerts, Carla; Gault, Claire (T4 Education & EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:7CKKU8RW 2405685:L43R48P2

Turning to technology: A global survey of teachers' responses to the Covid-19 pandemic - Pota, Vikas; Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam; Zubairi, Asma; Aerts, Carla; Gault, Claire (T4 Education & EdTech Hub, 2021)
A global survey of teachers’ responses to the Covid-19 pandemic
KerkoCite.ItemAlsoKnownAs: 2339240:L9HFYFBK 2339240:PG5K4YH4 2339240:VJ8NQRB8 2405685:452IQSGM 2405685:8993UPBX 2405685:SMFP44X2

DigiMap – Digital Malawi Project - Public Private Partnership Commission (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:BBWYTFNJ 2405685:N6IH9MK6

Teaching of Naazrah Quran Grade I-V as a separate compulsory subject - Punjab Curriculum & Textbook Board (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:IXHBSJZJ 2405685:RRM79XR4

Connect To Learn: Aiming to Improve Learning Outcomes of Underprivileged Students in Myanmar - Qualcomm (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:UBIG23M2 2405685:I89FFXZ4
Keywords: ⛔ No INSPIRE recid found

Revisiting the impact of covid-19 on adolescents in urban slums in Dhaka, Bangladesh: round 2 - Raha, Samira Ahmed; Rana, Sajib; Mamun, Saklain Al; Anik, Mehedi Hasan; Roy, Prantik; Alam, Farhana; Sultan, Maheen (Gender and Adolescence: Global Evidence, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:WYUAE2BS 2405685:Y2LGTIPF
Keywords: ⛔ No DOI found

PPRC-BIGD COVID-19 Livelihoods & Recovery Panel Survey - Rahman, Hossain Zillur; Matin, Dr Imran; Rahman, Atiya; Das, Dr Narayan C; Zillur, Umama; Ahmen, Md. Shakil; Hashemi, Dr Syed M; Wazed, Mohammad Abdul; Mozumder, Tanvir Ahmed; Gain, Sabrina Miti; Mohammad, Fatema; Khan, Tahsina Naz; et al. (BRAC Institute of Governance and Development (BIGD), 2021)
The COVID-19 pandemic brought the world to an economic stand-still, and the poor and vulnerable populations are bearing the brunt of this crisis. Power and Participation Research Centre (PPRC) and BRAC Institute of Governance and Development (BIGD) have been jointly conducting a multi-phase study since April 2020 to capture the changing impact of the COVID-19 health and economic crisis on low-income communities...
KerkoCite.ItemAlsoKnownAs: 2339240:IK9VLKRP 2405685:84RHZ5EU

Investigating the mediating role of online learning motivation in the COVID-19 pandemic situation in Bangladesh - Rahman, Md. H Asibur; Uddin, Mohammad Shahab; Dey, Anamika (Journal of Computer Assisted Learning, 2021)
The purpose of this paper is to investigate the mediating role of online learning motivation (OLM) in the COVID-19 pandemic situation in Bangladesh by observing and comparing direct lectures (DL), instructor–learner interaction (ILI), learner–learner interaction (LLI), and internet self-efficacy (ISE) as predictors of OLM and online learning satisfaction (OLS). Data were collected from 442 undergraduate and graduate students from more than 35 universities in Bangladesh. To test the hypotheses, the PLS-SEM approach was applied using SmartPLS 3.0. The study shows a significant mediating role of OLM between the independent variables and learning satisfaction. In addition, DL, ILI, and ISE are shown to be significant predictors of student satisfaction. The findings have a number of valuable implications for education policy makers, universities, instructors, and students. Moreover, the study suggests some new research perspectives to overcome the limitations of this research and to gain precise knowledge on students' learning motivation and satisfaction regarding other online classes for different categories of students (e.g., high school and college, professional, and PhD).
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/jcal.12535 KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12535 2339240:D2LCXIHU 2405685:DUEDNPFM
Keywords: Bangladesh; COVID-19; interactions; learning motivation; learning satisfaction; online education

A Simulation of COVID-19 School Closure Impact on Student Learning in Bangladesh [Book Chapter] - Rahman, Tashmina; Sharma, Uttam (World Bank, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1596/35043 2339240:4MHUSRIF 2405685:RDF4ZFYM

Exploring the summer reading effect through visual analysis of multiple datasets - Reed, Deborah K.; Aloe, Ariel M.; Park, Seohee; Reeger, Adam J. (Journal of Research in Reading, 2021)
Historically, there has been concern about students losing reading ability over extended breaks from school, commonly in the summer, but studies of this phenomenon have produced inconsistent results. We applied exploratory visual analysis of multiple datasets to examine whether students in Grades K-5 appear to lose or improve in various reading abilities over the summer and across consecutive school years. Archival data were obtained on students of different U.S. school districts who did not participate in a formal summer reading programme. Data were disaggregated by groups considered most vulnerable to summer loss: those from economically disadvantaged backgrounds and those identified with disabilities. Given the variety of measure types and scores, we centred scores on each measure's cut point for proficiency in a particular grade level to depict how students' scores deviated from the proficiency classifications before and after a summer break. Overall, students' scores relative to the benchmark appeared on average to have maintained or improved, and there was no observed accumulated decrement in reading performance across years. For anomalous instances of summer loss, we offer possible alternative explanations such as measurement artefacts and unrehearsed learning. Visual analysis of the datasets suggested that summer breaks were not associated with systematic losses of students' reading ability, even among those considered most vulnerable to the phenomenon. However, available assessments and benchmarks are not designed to measure summer learning specifically, and little is known about the kinds of literacy experiences students not in formal programmes might be having. Thus, more research on summer maturation and degeneration is warranted.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/1467-9817.12357 KerkoCite.ItemAlsoKnownAs: 10.1111/1467-9817.12357 2339240:JHHW65S2 2405685:EXZINYW5
Keywords: elementary; exploratory visual analysis; reading; summer loss

Pakistan - Data Protection Overview - Rehman, Shafaq (RIAA Barker Gillette, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:JE7WKN5X 2405685:MTKT9C36

Pakistan - Data Protection Overview - Rehman, Shafaq (RIAA Barker Gillette, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:JE7WKN5X 2405685:MTKT9C36

ICT in Education and Training Policy - Republic of Kenya. (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:BG82ZNVW

Policy on Information and Communication Technology in Education and Training | Ministry of Education - Kenya - Republic of Kenya Ministry of Education (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:SAZ7AWKZ 2405685:X8LUX9DH

Logros y Desafíos del Plan Ceibal - Reyes, Olga; Valdés-Rodríguez, Ofelia (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:JJUPMKNB 2405685:XXNI324J

Spotlight Initiative to eliminate violence against women & girls in Timor-Leste - Robinson, Alex; Kiefel-Johnson, Felix (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ACGCCMFU 2405685:VVIKL45L

Co-Develop: Digital Public Infrastructure for an Equitable Recovery - Rockefeller Foundation (The Rockefeller Foundation, 2021)
As we build back better from the Covid-19 pandemic, we have an unprecedented opportunity to build digital public infrastructure that promotes inclusion, human rights, and progress toward global goals. This report outlines an agenda for international cooperation on digital public infrastructure to guide future investments and expansion of this critical tool.
KerkoCite.ItemAlsoKnownAs: 2339240:37L4BB6S 2405685:RWZW3IGV 4656463:V2H3KQ6Y

Financing for the EdTech Ecosystem: A Working Paper - Roddis, Suzanne; Collis, With Victoria; Steer, Liesbet; Cunningham, Madelyn Swift (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:FPKG8YWE 2405685:ZIXZZ9DF
Keywords: ⛔ No DOI found

Current initiatives, barriers, and opportunities for networked learning in Latin America | SpringerLink - Romero-Hall, Enilda (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:7BL7UJES 2405685:T3EWN6KP

Levar sala de aula até sala de casa é bom negócio na Geekie - Rosa, Joao Luiz (Valor Econômico, 2021)
Isolamento social ajudou ‘edtech’ a elevar o faturamento em mais de 170% no ano passado
KerkoCite.ItemAlsoKnownAs: 2339240:4UAQBJVI 2405685:F7RAB35E

Independent Evaluation of the Girls’ Education Challenge Phase II - Teachers and Teaching for Marginalised Girls - Rose, Pauline; Aslam, Monazza; Downing, Phoebe (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:MLHNPK96 2405685:PYNX3JW6

Do High-Stakes Exams Promote Consistent Educational Standards? - Rossiter, Jack; Abreh, Might Kojo; Ali, Aisha; Sandefur, Justin (Center for Global Development, 2021)
Each year over two million secondary-school students across English-speaking West Africa sit coordinated exams, with the explicit goal of maintaining consistent educational standards across schools and over time. We find that scores across math items drawn from different exam years—when taken by an identical group of students on the same day—closely track fluctuations in Ghana’s national pass rates over time, absent any role for cheating or changes in real performance.
KerkoCite.ItemAlsoKnownAs: 2339240:P76Y3ZMS 2339240:Q7EM36CB 2405685:8CHDNRL6 2405685:CNXH9CPT 4656463:DM8NI9DR

Digitizing taxation and premature formalization in developing countries - Roy, Pallavi; Khan, Mushtaq H. (Development and Change, 2021)
The digitization of taxation systems can assist inclusion. However, it can also inadvertently lead to adverse outcomes for the poor in developing countries where many firms in the informal sector have low capabilities. Moreover, larger formal sector firms are often politically networked and in a position to engage in extractive informal transactions that digitization alone cannot restrict. Thus, while digitization creates tools for the enforcement of formal regulations, formalization can be unequal. This contribution focuses on digitized taxation as an application of a more general problem with digitization as a tool for formalization, referring to evidence from the rollout of the Goods and Services Tax (GST) in India. Using the analysis of political settlements, the authors distinguish between types of rule violations in developing economies. Networked higher-capability firms engage in ‘informal’ transactions when they violate rules to extract rents. This is different from the informality of unregistered micro and small enterprises in the informal sector who often violate rules they cannot adhere to, and make informal payments to enforcers to continue operating. When digital technologies are used in these contexts, adverse outcomes for welfare and inclusion can follow from ‘premature formalization’. A more cautious and inclusive path to formalization is necessary to protect vulnerable groups.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/dech.12662 KerkoCite.ItemAlsoKnownAs: 10.1111/dech.12662 2339240:MU6W52WZ 2405685:UGRBR3L5 4656463:R9NF9UEB

Cambodia Digital Economy and Society Policy Framework 2021–2035 - Royal Government of Cambodia (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ZCPRMATT 2405685:NSEFRBZY

Science of Teaching - Overview: Structured Pedagogy Guides, and a Note to Education Leaders - RTI International (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:QGPIU5LP 2405685:RY5I3VX9

Digitalization in teaching and education in Malawi: Digitalization, the future of work and the teaching profession project - Saka, Tionge Weddington (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:9BDZPJAA 2405685:Z9HNTSCR

'Leave no one behind' - five years into Agenda 2030: Guidelines for turning the concept into action - Samman, Emma; Roche, Jose Manuael; Sarwar, Moizza Binat; Evans, Martin (Overseas Development Institute, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:7VTSZ8FZ 2405685:9KJFUTGQ

Using community-based structures in education programming - Sarton, Emma; Thukral, Hetal (2021)
This Thematic Review summarises the learning around how community-based structures (CBSs) supported projects during COVID-19 school and community-based education closures. It examines the role of CBSs in supporting Girls’ Education Challenge projects to pivot successfully and identifies six characteristics of successful utilisation of CBSs. This Thematic Review is primarily aimed at projects, implementors and non-governmental organisations interested in working with CBSs to maximise project outcomes now and in the future. It is also useful for researchers and policy makers, supporting conversations about how to best work with communities and CBSs.
KerkoCite.ItemAlsoKnownAs: 2405685:I7BQJD5E 2405685:YNTJPK4A

Pathways towards quality primary education: improving completion and learning outcomes - Sarwar, Moizza Binat; Moreno, Diego Benitez; Homonchuk, Olha; Roche, Jose Manuel; Nicolai, Susan (Overseas Development Institute, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:9HKATEYG 2405685:DV2ABWB9

Progress Under Threat: Refugee education one year on from the Global Refugee Forum and the impact of COVID-19 - Save the Children (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:XVRCBEFV 2405685:UCCHVDR4

Digitizing Curriculum Standards to Unlock the Potential of Open Educational Resources in a Global Context. - Savov, Ivan (UNHCR, Vodafone Foundation, Google.org, and UNESCO, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:9CQZLXPE 2405685:57EEB3JT

Assistive Technologies and Other Supports for People with Brain Impairment. - Scherer, M. J. (Springer Publishing Co, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:EKI7Z54P 2405685:LTA7V78K

A Cautionary Tale of Tutoring Hard-to-Reach Students in Kenya - Schueler, Beth E.; Rodriguez-Segura, Daniel (Annenberg Institute, 2021)
Covid-19-induced school closures generated great interest in tutoring as a strategy to make up for lost learning time. Tutoring is backed by a rigorous body of research, but it is unclear whether it can be delivered effectively remotely. We study the effect of teacher-student phone call interventions in Kenya when schools were closed. Schools (n=105) were randomly assigned for their 3rd, 5th and 6th graders (n=8,319) to receive one of two versions of a 7-week weekly mathfocused intervention—5-minute accountability checks or 15-minute mini-tutoring sessions—or to the control group. Although calls increased student perceptions that teachers cared, accountability checks had no effect on math performance up to four months after the intervention and tutoring decreased math achievement among students who returned to their schools after reopening. This was, in part, because the relatively low-achieving students most likely to benefit from calls were least likely to return and take in-person assessments. Tutoring substituted away from more productive uses of time, at least among returning students. Neither intervention affected enrollment. Tutoring remains a valuable tool but to avoid unintended consequences, careful attention should be paid to aligning tutoring interventions with best practices and targeting interventions to those who will benefit most.
Publisher: EdWorkingPapers.com KerkoCite.ItemAlsoKnownAs: 2339240:XZCEK22N 2405685:9BBHUUTN

Listening to Young Lives at Work in Vietnam: Third call - Scott, Douglas; Favara, Marta; Porter, Catherine (Young Lives, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:J7TJ927N 2405685:UYZGG43L

Pupil Census 2021 - Scottish Government (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:4D6YIEHN 2405685:ARL37MGE 4656463:QLGNII8D

Forum Guide to Strategies for Education Data Collection and Reporting - SEDCR (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:A47PU2CT 2405685:C4RHBJCS
Keywords: ⛔ No DOI found

A Framework for Creating Short Forms of Internationally Used Direct Assessments - Seiden, Jonathan (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:6YINVI8Z 2405685:THAGKHBH

Educación en pausa - Seusan, Laura Andreea; Maradiegue, Rocío (2021)
Una generación de niños y niñas en América Latina y el Caribe está perdiendo la escolarización debido al COVID-19
KerkoCite.ItemAlsoKnownAs: 2339240:VSYTIGBE 2405685:8WE9SR6T

Addressing the Mobile Gender Gap in Pakistan - Shanahan, M (GSMA, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:F44W5HRU 2405685:NG43I2P9

Education through ICT Initiatives during the pandemic in India - Sharma, Anchal (Center for Sustainable Development, Columbia University, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:E9PCK69E 2405685:MKUWVX9Q

The Role Played by Parents in the Abrupt Transition to Online Education During the Covid-19 Pandemic - Sharmacharya, Ratan (2021)
Publisher: Georgia Institute of Technology KerkoCite.ItemAlsoKnownAs: 2405685:QA6TSP7N
Keywords: ⛔ No DOI found

The effect of distance learning on learning outcomes of children with special needs in inclusive schools in the new normal - Sholikhati, Nur Indah; Prayogo, Muhaimi Mughni; Santoso, Joko (Indonesian Journal of Disability Studies, 2021)
KerkoCite.ItemAlsoKnownAs: 10.21776/ub.ijds.2021.008.01.11 2339240:8RMCQ44M 2405685:NFGHFAVD
Keywords: ⛔ No INSPIRE recid found

Emergency Response in Educational Policies during COVID-19 in Nepal: A Critical Review. - Shrestha, Sagun; Gnawali, Laxman (IAFOR Journal of Education, 2021)
KerkoCite.ItemAlsoKnownAs: 10.22492/ije.9.2.10 2405685:ZT9NPHVL

English Language Teachers with Disabilities: An Exploratory Study Across Four Countries - Singal, N; Ware, H (Report submitted to the British Council., 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:N2ZF6XUR 2405685:TV46MJDJ

What makes a good school? | UNICEF Lao People's Democratic Republic - Siriphongphanh, Siriphone (2021)
Lao PDR rolls out Study to understand why certain Lao schools outperform others to help identify better practices
KerkoCite.ItemAlsoKnownAs: 2339240:TV2EGF7F 2405685:5TU2WGTZ
Keywords: ⛔ No INSPIRE recid found

Laws, decrees and strategies on teachers in Lao PDR: a situation analysis - Sithirajvongsa, Sisamone (UNESCO, 2021)
Sisamone
KerkoCite.ItemAlsoKnownAs: 2339240:EYNX572J 2405685:LI4FUFM4
Keywords: ⛔ No INSPIRE recid found

Use of Reserve of Education Subvention - SKL International (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:WGZR7STL 2405685:FNRE2GUV

4 challenges of adopting blockchain in education & potential solutions - SotaTek (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:CAGQSMUC 2405685:DBKUN2KR

Here are 5 blockchain use cases in the education sector - SotaTek (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:TWM5R849 2405685:UNCMR5FT

Key factors in Knowledge Sharing Behavior in Virtual Communities of Practice: A Systematic Review - Soto, ROBERTO Hernández; Ortega, MÓNICA Gutiérrez; Avi, BARTOLOMÉ Rubia (Education in the Knowledge Society (EKS), 2021)
Virtual Communities of Practice (VCOP) are environments widely recognized as knowledge management instruments, and their sociocultural contrib ...
Publisher: EDICIONES UNIVERSIDAD DE SALAMANCA KerkoCite.ItemAlsoKnownAs: 10.14201/eks.22715 2339240:ZXUKA5SG 2405685:UAD45DRW

Strengthening Education Management Information Systems (EMIS) and Data for Increased Resilience to Crisis: country case study: Uganda - UNESCO Digital Library - Sparkes, James (UNESCO, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:JQ46TXEN 2405685:R3LKFNTY 4656463:YXDH6NK2

Speedtest Global Index – Internet Speed around the world - Speedtest (Speedtest Global Index, 2021)
Find out which countries have the fastest internet speeds in the world. View global monthly comparisons of fixed and mobile internet speeds.
KerkoCite.ItemAlsoKnownAs: 2339240:2ECMCE46 2405685:H545VPCC

SSAMS - SSAMS (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:WQPVWNYV 2405685:TEPKSTVC

Investigating risks and opportunities for children in a digital world: A rapid review of the evidence on children's internet use and outcomes - Stoilova, M.; Livingstone, S.; Khazbak, R. (UNICEF, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:6EVYCKBZ 2405685:7VBGU59I

Sunbird - Sunbird (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KWNV5KHW 2405685:9ZDBQZW8

Use of Twitter Technology in Educational Learning - Sunday, Ajibo Anthony (The Turkish Online Journal of Educational Technology, 2021)
This paper explores the use of Twitter technology in educational learning and teaching in education system. The objectives of this study emphasizes on the contributions of Twitter to personal and educational learning experience, and its adoption for professional development in 21st century. Twitter technology was invented as a media outlet in 2006, to provide a unique kind of communication that allows only 140 numbers of characters. It is a technology that permits users to send and receive information on website, from mobile or computer-enabled internet. A Twitter requires a valid email address to sign up for an account and equally set up private profiles in line with the system command. Users share pictures, videos among other educational materials of what is happening in the world. Twitter is a social media platform that has drawn the attention of its users, especially the students and educators around the world. Secondary sources of data collection were adopted in the paper review. In spite of the short comings of Twitter technology, major findings revealed that the use of Twitter technology is becoming a common usage among students and professional development of educators across the world. Recommendations include the need for sustained campaign of the use of Twitter technology in institutions of learning across the world, especially in the developing countries, and the pedagogical adoption of Twitter for professional development of the future of education, as opposed to traditional method of teaching.
KerkoCite.ItemAlsoKnownAs: 2339240:NQYY6PUR 2405685:ZCBI9SUI
Keywords: ⛔ No DOI found

Digital training for increasing English teachers’ professionalism at junior high school - Syafryadin, Syafryadin; Wardhana, Dian Eka Chandra; Febriani, R.Bunga (Journal of Education and Learning (EduLearn), 2021)
This research aimed to know the problems and the implementation of the training as the solution and evaluation of digital training that can increase the English teachers’ professionalism at SMP Negeri 13 Bengkulu, Indonesia. This study used a descriptive qualitative method with the number of trainees were 10 English teachers. The procedures of collecting data were observation, documentation and interview. Then, the data analysis were done by comparing the result of the interview from the English teachers at SMP Negeri 13 Bengkulu, Indonesia before they joined and after joining digital training provided by the researchers and finally concluded. The first research finding is the English teachers had problems in terms of knowledge, difficult to apply the application or technology, and never joining training. The second finding is the implementation of digital training had many benefits namely increased the English teachers’ professionalism, experienced and innovated their knowledge and skills toward the use of digital learning, it brought a good quality for learning outcomes and it helped to be better in an advanced educational institution, particularly at SMP Negeri 13 Bengkulu, Indonesia. The last finding is that after implementation, the English teachers still got problems in using the application and need more training. The implication of this study is digital training can be an advanced way in educational development which needs good participation from the trainers, trainees and educational institution.
KerkoCite.ItemAlsoKnownAs: 10.11591/edulearn.v15i1.16937 2339240:A4FKY9HP 2405685:4K8W84RI

Syafunda Digital Library - Syafunda (Syafunda, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:GL857VQ8 2405685:39F7D2XS

T4 Insights Report: World's largest teacher post-Covid-19 - T4 (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:72JBFMAQ 2405685:VCPYXYC2

Gendered Impacts of COVID-19 on Higher Education in Cambodia: Perspectives of Female Lecturers and Students - Tann, Boravin; Tuy, Sophorn (Gender and Human Rights in The Context of Covid-19 Pandemic: Findings from Four Countries, 2021)
0 citations (Crossref) [2024-04-29] Institution: Koninklijke Brill NV KerkoCite.ItemAlsoKnownAs: 10.1163/1570-6664_iyb_SIM_org_39387 2339240:LFJH6AUM 2405685:VAJLGNBN
Keywords: ⛔ No INSPIRE recid found

National Plan for Teachers’ Continuous Professional Development (4a) - Tanzania Institute of Education (Tanzania Institute of Education, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:9K72XNGD 2405685:T66WS3U5

Building Resilient Education Systems: A Rapid Review of the Education in Emergencies Literature - Tarricone, Pina; Mestan, Kemran; Teo, Ian (Australian Council for Educational Research, 2021)
The COVID-19 pandemic has highlighted the vulnerabilities and inequalities of national education systems and hindered the education of millions of children globally. In response, the Global Education Monitoring (GEM) Centre, which is a long-term, strategic partnership between the Australian Council for Educational Research (ACER) and the Australian Government’s Department of Foreign Affairs and Trade (DFAT), undertook a rapid review of literature to support policymakers. The research has six evidence-based outcomes that can help policymakers to build resilient education systems and thereby enhance education quality and equity during emergencies. The COVID-19 emergency provided the impetus for this research, with much of the reported data associated with this pandemic. Learnings from past education in emergencies situations have informed the understandings of the impacts and implications of the COVID-19 emergency, and have been synthesised with the COVID-19 literature to inform policymakers about how to build resilient education systems. This report presents evidence relating to two main types of emergencies affecting education: natural disasters and communicable disease, and political conflicts. Both types of emergencies can also coalesce within the same education system, resulting in complex and often protracted emergencies. This review found that emergencies impact education in two main ways: endangering children’s wellbeing, and exacerbating unequal learning outcomes.
KerkoCite.ItemAlsoKnownAs: 10.37517/978-1-74286-639-0 2339240:MBDBTMKX 2405685:G9BYVZHN

Flexible strategies for ensuring quality learning outcomes in education in emergencies (NEQMAP 2021 thematic review) - Tarricone, Pina; Teo, Ian; Mestan, Kemran; Sundarsagar, Kris; Killimangalam, Ashtamurthy; Abd Razak, Nordin (International Education Research, 2021)
The COVID-19 pandemic has interrupted schooling for students globally and challenged how policy-makers might respond and recover from this protracted emergency. In collaboration with NEQMAP, the GEM Centre has conducted a rapid review of policy and practice documents for 14 countries, and an online survey with policy-makers in 7 of them to identify the types of flexible learning strategies that were implemented over the course of this pandemic. An education in emergencies Policy Monitoring Framework was used both to guide the analysis of documents and survey data, and to provide the basis for reporting findings. The range of flexible learning strategies identified in this review focused on: enhancing system level processes to ensure quality learning outcomes; streamlining the curriculum; utilising a range of student assessment and monitoring approaches; improving inclusion and equity for vulnerable learner groups; and supporting school leaders and teachers using education tools and resources, professional development courses, and support networks.
Publisher: United Nations Educational, Scientific and Cultural Organization KerkoCite.ItemAlsoKnownAs: 2339240:Y44U25U8 2405685:B2STUPZ6
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Teachers' Attitudes Towards Gender Equality - Tavdgiridze, Lela; Khasaia, Ia; Sherozia, Nato; Turmanidze, Lela (2021)

The Teachers’ Research Exchange (T-REX): Connecting Teaching, Research and Practice in Initial Teacher Education - Teachers' Research Exchange (National Forum for the Enhancement of Teaching and Learning in Higher Education, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:MBS83S74 2405685:M6FU72GG

Teacher Deployment Protocol - Teaching Service Commission (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:YHSCP3RW 2405685:6D9F755H

Technical Report on Teacher Deployment - Teaching Service Commission (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:Q4WTX5XU 2405685:59NJRPWV

Teachers and Teaching in Sierra Leone - The World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:346EVURZ 2405685:I5ZDCPFW

The Global Report on the Status of Teachers 2021 - Thompson, Greg (2021)
The status of teachers remains a concern in many jurisdictions. Teachers are aware that holding the same qualifications or levels of training as other professions does not bring the same status, despite teaching and facilitating learning being complex work that requires significant expertise. The mandate for this Report was to consider the status of the teaching profession in the three years since the 2018 Report. Rather than simply covering the same ground as the previous Report, the survey was encouraged to maintain its strong focus on status, pay, and conditions while responding to pressing contemporary issues. In the midst of the global COVID-19 pandemic, with concern around the impact that this was having on school communities in general, and the teacher workforce in particular, a focus of this survey concerns the perspectives of unions across the world regarding the impact of COVID-19. [Publisher summary, ed]
OCLC: 1294427345 KerkoCite.ItemAlsoKnownAs: 2339240:P7UV6GX6 2405685:GXZIVFUX

Educational gains of in-person vs. distance learning in primary and secondary schools: A natural experiment during the COVID-19 pandemic school closures in Switzerland - Tomasik, Martin J.; Helbling, Laura A.; Moser, Urs (International Journal of Psychology, 2021)
Using data from a computer-based formative feedback system, we compare learning gains in the 8 weeks of school closures related to the COVID-19 pandemic in Switzerland with learning gains in the 8 weeks before these school closures. The school performance in mathematics and language of N = 28,685 pupils is modelled in second-order piecewise latent growth models with strict measurement invariance for the two periods under investigation. While secondary school pupils remain largely unaffected by the school closures in terms of learning gains, for primary school pupils learning slows down and at the same time interindividual variance in learning gains increases. Distance learning arrangements seem an effective means to substitute for in-person learning, at least in an emergency situation, but not all pupils benefit to the same degree.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/ijop.12728 KerkoCite.ItemAlsoKnownAs: 10.1002/ijop.12728 2339240:38N2MJS4 2405685:GEGK86LW
Keywords: COVID-19; Distance learning; Learning progress; School achievement; School closures

Language data for Malawi - Translators without Borders (Translators without Borders, 2021)
Open-source language data and maps about languages spoken in Malawi can improve how we communicate with communities in crisis.
KerkoCite.ItemAlsoKnownAs: 2339240:PCZ7W4YF 2405685:59QEPFPY

Tsugi - Tsugi (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:2TJABVDQ 2405685:GEH3A8N4

What is Interactive Voice Response (IVR?) Definitions and Benefits. - TTEC (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:NKW57528 2405685:VF469FPB

What we know about the gender digital divide for girls: A literature review - Tyers-Chowdhury, Alexandra; Binder, Gerda (UNICEF, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:I6PWKQXN 2405685:YXQRTSSA

The National Funding Formulae for schools and high needs – 2022-23 - UK Department for Education (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:YZD5CLHY 2405685:3ZMRG492 4656463:QYFUZA2M

School workforce in England, Reporting Year 2020 - UK Government (2021)
This release is largely based on the School Workforce Census. The census collects information from schools and local authorities on the school workforce in state-funded schools in England. Independent schools, non-maintained special schools, sixth-form colleges and further education establishments are not included. The latest data relates to November 2020 and so this is the first data in the series to relate to the coronavirus (COVID-19) pandemic. Coronavirus (COVID-19): Change to statistics To reduce burden on schools and local authorities during the pandemic, data on qualifications and staff absences were not collected in 2020. They will be collected again in 2021. Data on school workforce absence during the pandemic has been collected via the Department's education settings survey. Specific guidance can be found within affected sections of this statistic.
KerkoCite.ItemAlsoKnownAs: 2339240:V4JNURZK 2405685:AARN4AJQ 4656463:2DTJRBXV

Data sharing agreements - UK Information Commissioner's Office (2021)
Publisher: ICO KerkoCite.ItemAlsoKnownAs: 2339240:KR74YVJ2 2405685:NDIMW83H

Country Gender Equality Profile Viet Nam 2021 - UN Women (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:3GXHKDY5 2405685:PAY2R8RK

Review Report on the Implementation of the National Strategy on Gender Equality (NSGE) 2011-2020 - UN Women (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:SMUCIVHE

Technology and Innovation Report 2021: Catching Technological Waves Innovation with Equity - UNCTAD (2021)
OCLC: 1245847334 KerkoCite.ItemAlsoKnownAs: 2339240:3J8FAXYC 2405685:SSF84XQK

Sustainable Development Cooperation Framework 2021–2025 - UNDP (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:PBYPE6CD 2405685:XPAK3XCQ

Show me the data: Leveraging digital tools for Nepal’s COVID response - UNDP SURGE (Medium, 2021)
UNDP Nepal joined hands with the Accelerator Labs and SURGE Data Hub to assess the impact of COVID-19 in Gandaki Province
KerkoCite.ItemAlsoKnownAs: 2405685:LY6VBCGI

A snapshot of educational challenges and opportunities for recovery in Africa - UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ZEZLGCRU 2405685:U277VM6A
Keywords: ⛔ No INSPIRE recid found

Background information on education statistics in the UIS database - UNESCO (UNESCO Institute of Statistics, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:HXNGPX3L 2405685:HPLQP9BZ 8836279:67D7XNEP 8836279:E62VYPBG 8836279:ZKI42HRX

COVID 19, Technology-based Education and Disability: The case of Bangladesh - UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5B34JWFZ 2405685:7K7JA456

Handbook for interactive audio instruction: Planning and implementing radio lessons in sub-Saharan Africa - UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:VDH9N8QZ 2405685:26WIARR2
Keywords: ⛔ No INSPIRE recid found

Lao People's Democratic Republic | INCLUSION | Education Profiles - UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:PSQ98E9A 2405685:ILAEKQIZ
Keywords: ⛔ No INSPIRE recid found

SDG 4 – Country Profiles - UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:S6GXAMFV 2405685:SY75JTXU

Situation analysis on the effects of and responses to COVID-19 on the Education Sector in Asia: Bhutan case study - UNESCO Digital Library - UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:9KDK6Q9R

Strengthening education management information systems for increased resilience to crises: A synthesis of case studies - UNESCO (UNESCO, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:QKU6TYXM

The digital learning turn in Africa: The role of local ecosystems - UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8QQC6RMJ 2405685:96BH5E3W
Keywords: ⛔ No INSPIRE recid found

The integration of Education Management Information Systems (EMIS) with other information systems - UNESCO (UNESCO, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8L4JHQH4 2405685:VNJBVC5F 4656463:X4SLJ5PL

Teachers deployment and retention | Education | IIEP Policy Toolbox - UNESCO-IIEP (2021)
The surge in primary school enrolment and the push for improved quality has resulted in an acute shortage of teachers, making proper deployment and retention policies fundamental.
KerkoCite.ItemAlsoKnownAs: 2129771:NY77RCA2 2405685:GY9P8AJV 4556019:53D54ZXQ
Keywords: C:LMIC

Malawi: Education Statistics - UNESCO Institute for Statistics (2021)
...
Last Modified: 2017-04-12 KerkoCite.ItemAlsoKnownAs: 2339240:ZU5965YA 2405685:2IXF4RSK

The Use of Learning Assessment Data. Ghana - UNESCO Institute for Statistics (UIS, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:V6M9FYDV 2405685:Q8QGX967

UIS Statistics - UNESCO Institute for Statistics (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:PCUFFB5N 2405685:4ZWW73JI

UIS Statistics - UNESCO Institute for Statistics (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:PCUFFB5N 2405685:4ZWW73JI

Data centre - UNESCO-UIS (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:DPXIU8FL 2405685:VNTWEW4U

The state of the global education crisis: A path to recovery - UNESCO; World Bank; United Nations Children's Fund (UNESCO, 2021)
KerkoCite.ItemAlsoKnownAs: 10.54675/JLUG7649 2339240:W7BZTFMN 2405685:LQKWRKQD

Overview of Refugee and Asylum-Seekers Population as of December 31, 2021 - UNHCR (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KL4BMB6C 2405685:2UX5E4SB

Pakistan Overview of Refugee and Asylum-Seekers Population as of December 31, 2021 - UNHCR (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:4GSG5KEM 2405685:MJM5NJKK

Accelerating results for children with technology and digital innovation - UNICEF (UNICEF, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:P5N87XZQ 2405685:4NB8WA2S

Accenture, Dubai Cares, Microsoft and UNICEF launch digital education platform under Generation Unlimited to help address global learning crisis - UNICEF (2021)
‘Passport to Earning’—part of the Generation Unlimited partnership—will provide free, quality, digital education for young people to help prepare them for the world of work
KerkoCite.ItemAlsoKnownAs: 2339240:I4FACV7C 2405685:EPGRAAN8

Around 2 in 3 children are still out of the classroom in Latin America and the Caribbean - UNICEF (2021)
UNICEF urges countries in the region to scale up the return to in-person learning
KerkoCite.ItemAlsoKnownAs: 2339240:FTG6UT9X 2405685:ASVER7KM

Digital UNICEF: Harnessing the power of technology and digital innovation for children - UNICEF (2021)
Harnessing the power of technology and digital innovation for children
KerkoCite.ItemAlsoKnownAs: 2339240:T7FCGJBW 2405685:GHE9QHPU

Education: Giving every child the right to education - UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:RCI9IIDH 2405685:AT8JDYZL

Ensuring equal access to education in future crises: findings of the new Remote Learning Readiness Index - UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:I4DIY8UM 2405685:NCTNEYTY

Ghana COVID-19 Situation Report: 14 - UNICEF (UNICEF, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8CNN3BQT 2405685:PTCCZDKR

How Shahnaz became Mohammed Saleem so she could study - UNICEF (2021)
With support from her father, 12-year-old Shahnaz pretended to be a boy so she would not have to delay her schooling at a UNICEF-supported ALP center funded
KerkoCite.ItemAlsoKnownAs: 2339240:DT724KCC 2405685:N3N58A9G

LACRO COVID-19 Education response: Update 29 Status of schools reopening - UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ZZLQWAX2 2405685:PARGWSS7

Lao Education and Sports Teaching and Learning Platform | UNICEF Lao People's Democratic Republic - UNICEF (2021)
Learning Never Stops: Investing in ICT-enabled Teaching and Learning to Strengthen Access to Education in Lao PDR
KerkoCite.ItemAlsoKnownAs: 2339240:QGRFF5EI 2405685:UT42DYIS
Keywords: ⛔ No INSPIRE recid found

Nigeria: Country Office Annual Report 2021 - UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:RT37HCBV 2405685:N2E4PSG5

Pakistan Annual Report 2020 - UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:QMUFEZ69 2405685:WCQ4N9GG

Radio-based learning gets its day in the sun in Mali - UNICEF (2021)
Solar-powered radios are helping conflict-affected and displaced children follow lessons outside of the classroom
KerkoCite.ItemAlsoKnownAs: 2339240:TVKEZZH8 2405685:N82S7THH

Reimaginar la educación y el desarrollo de habilidades para niños, niñas y adolescentes - UNICEF (2021)
Invertir en niños, niñas y adolescentes a medida que construimos una futura y mejor normalidad en América Latina y el Caribe
KerkoCite.ItemAlsoKnownAs: 2339240:VJMX74YK 2405685:5Q7XW87N

Reimagining Girls' Education - UNICEF (2021)
Solutions to Keep Girls Learning in Emergencies
KerkoCite.ItemAlsoKnownAs: 2339240:5BT5RMVJ 2405685:CPLL4QU6

Reopening with Resilience: Lessons from remote learning during COVID-19 - UNICEF (UNICEF Office of Research - Innocenti, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:V5HXX64Y 2405685:U6VFUV5G

SEA-PLM 2019 Latest Evidence in Basic Education Boys’ and Girls’ Learning in 6 Southeast Asian Countries - UNICEF (UNICEF, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:P2L5M3KX 2405685:MPYTARYK
Keywords: ⛔ No INSPIRE recid found

Situational Analysis on Digital Learning in Indonesia - UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:62U8RGK4 2339240:G35N8PXX 2405685:RZ4IXFCP 2405685:YNI7AT77
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

The Case for Better Governance of Children’s Data: A Manifesto - UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:7GEM65T2 2405685:Y7BQTTLM

The future of 800 million children across Asia at risk as their education has been severely affected by the COVID-19 pandemic - UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:CH7FKL4R 2405685:LWHC49W9
Keywords: ⛔ No INSPIRE recid found

Brief on learning continuity amidst COVID19 - UNICEF Pakistan (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:XGGMIWR6 2405685:S6CDN5A7

Education: Giving every child the right to education - UNICEF Pakistan (2021)
Providing quality education to all
KerkoCite.ItemAlsoKnownAs: 2339240:463I9Y7Q 2405685:WS4TG3Q5

E-learning Strategy - UNICEF Sudan (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:CL56P42H 2405685:8BT62CM9

Education: Annual Report 2020 - UNICEF Sudan (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8GTHJZUJ 2405685:VVMSF86T

Learning Passport Launched in Sudan - UNICEF Sudan (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:2LAD9A3D 2405685:LNHCQBGI

Situation Analysis on the Effects of and Responses to COVID-19 on the Education Sector in Asia - UNICEF & UNESCO (2021)
Case Study from Pakistan
KerkoCite.ItemAlsoKnownAs: 2339240:PU9A6DBP 2405685:YVTFJUXU

Guidance for Safe and Healthy Journeys to School: During the COVID-19 Pandemic and Beyond (English) - UNICEF; FIA Foundation (Humanitarian UNICEF, 2021)
As schools reopen, we have a unique opportunity to look not only at measures to help keep students safe on school premises, but also on the journey to school. These measures help to keep students safe during the coronavirus disease (COVID-19) and help to address other safety issues such as road traffic crashes, the number one killer of young people aged 5-29 years. This guidance is for education authorities and policymakers, school administrators, teachers and staff, parents, caregivers, community members, and students. It complements the UNICEF, UNESCO, World Bank, World Food Programme and UNHCR global framework for reopening schools and the Inter Agency Standing Committee (IASC) interim guidance for COVID-19 Prevention and Control in Schools. This guidance suggests practical steps to build back better health and safety systems – to address COVID-19 and promote active transport like walking and cycling to improve air quality, physical activity and road safety. September 2021
KerkoCite.ItemAlsoKnownAs: 2339240:GJ5DM3MP 2405685:VSL5E24J

Viet Nam Sustainable Development Goal Indicators on Children and Women Survey 2020–2021: Mass Media, Communications and Internet - UNICEF; General Statistics Office of Viet Nam (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:BFNNPWXD

Sindh: Multiple Indicator Cluster Survey 2018/19 - UNICEF; Government of Sindh (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:TZYPTSNX 2405685:C5ESTBMZ

Brief on learning continuity amidst COVID-19 school closures in Pakistan - UNICEF; Viamo (UNICEF Regional Office for South Asia (ROSA), 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:AL2VQD4K 2339240:X7YESBUZ 2405685:PZRG8IXK 2405685:TZ4FTP8N

With Almost Half of World’s Population Still Offline, Digital Divide Risks Becoming ‘New Face of Inequality’, Deputy Secretary-General Warns General Assembly | UN Press - United Nations (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:D4YCESHH 2405685:XLBER8A5

Latest Human Development Index Ranking | Human Development Reports - United Nations Development Programme (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:48II6EQI 2405685:547724LQ

Unlocking Talent - Unlocking Talent (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:VGLYSWAB 2405685:7RUAVAA4

Language of Instruction Country Profile: Malawi - USAID (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:BK7VYG8H 2405685:UQ6JNHZN
Keywords: ⛔ No DOI found

Are All Our Children Learning? - Uwezo (Usawa Agenda, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:DFJ494IE

Uwezo Learning Assessment 2021 – UsawaAgenda - Uwezo (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:A5WCMKRW 2405685:DXCMMK3F

The current level of competence of schoolteachers on how to use cloud technologies in the educational process during COVID-19 and the Russian-Ukrainian war - Vakaliuk, Tetiana; Spirin, Oleg; Antoniuk, Dmytro; Medvedieva, Mariia; Osova, Olha; Novitska, Inesa (Proceedings of the 2nd Myroslav I. Zhaldak Symposium on Advances in Educational Technology, 2021)
During the period of total lockdown, teachers had to move to distance learning to organize a continuous educational process, which is not possible without the active use of modern information and communication technologies, including cloud services. Because of this, at the beginning of the pandemic, Zhytomyr Polytechnic State University conducted several free distance online courses for teachers, which included studying the possibilities of using cloud technologies in teaching in a pandemic. Somewhat later, some secondary schools in Zhytomyr expressed a desire to take the same courses, but in person. 98 teachers of schools of the city of Zhytomyr were covered by training on courses “Cloud technologies in the educational process in the conditions of quarantine”. After face-to-face courses, teachers in Zhytomyr schools have significantly increased their competence in the use of cloud technologies in the educational process in the context of the COVID-19 pandemic. Not only has their level increased in general, but the horizons regarding the variety of cloud services that should be used in distance learning have expanded. Course training, organized according to scientifically sound methods, helps to increase the motivation of students (teachers) to self-study, as well as to the future use of cloud technologies in the educational process. The two-year pandemic and the start of a full-scale war between Russia and Ukraine contributed to the fact that teachers of secondary schools began to actively engage in self-education and self-development. If earlier (at the beginning of the pandemic) it was difficult for teachers to switch to online learning, then with the outbreak of war, teachers were already ready to use various online tools in their practice. As the study showed, all the interviewed teachers continued their self-education in different ways, studied a large number of services that can be used in the educational process, and provided the authors with ideas for further expanding the courses according to their desires, which should be used in the educational process. It should be noted that it is important that all the respondents unanimously approved that they use the acquired competencies in their professional activities during the period of Russian aggression. In addition, in additional comments, teachers noted that among their acquaintances there are many teachers who want to take such courses since at one time they had no desire or motivation.
KerkoCite.ItemAlsoKnownAs: 10.5220/0012066300003431 2339240:HESKGASH 2405685:5MU7CCH4

An overview of 25 years of research on digital personalised learning in primary and secondary education: A systematic review of conceptual and methodological trends - Van Schoors, Rani; Elen, Jan; Raes, Annelies; Depaepe, Fien (British Journal of Educational Technology, 2021)
Due to the increasing digitisation, interest in digital personalised learning (DPL) continues to grow. Many empirical studies on the effect of adaptive tools have used a wide variety of conceptualisations and operationalisations of DPL. This systematic review aims to address the lack of consensus by presenting an analysis of empirical studies on technology for DPL in primary and secondary education. The work is guided by the following questions: (1) What are some different conceptualisations used in DPL research? (2) What types of tools are used in the studies and how are they implemented? (3) What is the current evidence on the impact of DPL with regard to student outcomes considering the nature of the current studies? A Boolean search string was used in the databases Web of Science and ERIC, resulting in a dataset containing 6,908 papers. A screening based on specific inclusion and exclusion criteria yielded 53 papers. Our findings revealed a great diversity in DPL conceptualisations, with several authors not defining the concept and others providing information regarding different elements such as technology, personalisation, personalisation target, personalisation source, personalisation method and personalisation outcomes. In line with these differences in conceptualisation of DPL, several DPL tools were used across the studies. Concerning the impact of DPL, a positive trend was observed on learning outcomes, although methodological differences need to be considered. The review ends with guidelines for future research. Practitioner notes What is already known There are many definitions and terms concerning DPL, resulting in a lack of consensus in conceptualisation. There is a wide variety of DPL tools with different adaptive dimensions. Many authors emphasise the benefits of DPL in educational practice including a possible impact on learning gains. What this paper adds Contribution to a thorough understanding of the conceptualisation of DPL. Insights into the diversity in DPL tools building on a framework of adaptivity by Vandewaetere and Clarebout (2014) and adds focus on tool implementation as a context element. Insight into the impact of DPL taking into account study design and outcome indicators. Implications for practice and/or policy An overview of the affordances of DPL to educational researchers, educational policy makers, and teachers is provided that can encourage them to think about its opportunities for everyday practice. Concrete suggestions for future research are discussed.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13148 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13148 2339240:YZ9DIDAF 2405685:UARVNXGN
Keywords: adaptive learning; adaptive technology; digital personalised learning; educational technology; systematic review

Endogenous development in Lao PDR in the era of globalization: Contrastive case studies of external assistance for a sustainable rural development path - Vongxay, Phonemany; Suzuki, Noriyuki (Journal of Mekong Societies, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:BTI5HE6I 2405685:JET5AWJ9
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Case Study: Sisters for Sisters’ Education - VSO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:RG2TTDYG 2405685:ITHDIVKP

Teacher motivation for online learning: piloting a microlearning support system | VVOB in Rwanda - VVOB (VVOB, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:I252ES6E 2405685:IYMV8VDP

Cost Analysis Guidance for USAID-Funded Education Activities - Walls, Elena; Tulloch, Caitlin; Harris-Van Keuren, Christine (USAID, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:GMGJ794Z 2405685:YNE5QGG7

Cost Analysis Guidance for USAID-Funded Education Activities - Walls, Elena; Tulloch, Caitlin; Harris-Van Keuren, Christine (USAID, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:GMGJ794Z 2405685:YNE5QGG7

The relationship between educational television and mathematics capability in Tanzania - Watson, Joe; Hennessy, Sara; Vignoles, Anna (British Journal of Educational Technology, 2021)
Previous studies have often demonstrated that educational television can have a positive effect on learning outcomes in low-income countries when delivered in controlled settings. However, existing research in low-resource contexts has scarcely considered the association between child outcomes and viewing in usual environments (ie, at their home, a friend’s home or a relative’s home). This lack of research is striking, as evidence from controlled settings might provide limited information on the effects of normal television exposure. This paper, therefore, investigates the relationship between normal exposure to a popular Tanzania-produced cartoon, Ubongo Kids and mathematics capability, as represented by plausible values derived from an item response theory model applied to children’s test responses. Cross-sectional investigation of a sample of 38 682 Tanzanian children suggested normal educational television exposure to be significantly associated with mathematics capability, when controlling for age, sex, school enrolment, Kiswahili attainment and household fixed effects. While cross-sectional results are not necessarily causal, the findings in this paper broadly correspond with those from previous designs using repeated observations. What is more, considering association results alongside cost and viewership estimates suggests television-based interventions to be highly cost effective. Practitioner Notes What is already known about this topic National data for Tanzania suggests the country to have both low levels of mathematics proficiency and considerable access to television technology. Educational television-based interventions might, therefore, be worthy of consideration by educational policymakers, especially given that studies conducted in controlled settings indicate that television can deliver learning benefits. There is, however, little evidence concerning educational television exposure outside of controlled settings. Only one such study in a low-income context that concerned the association between learning outcomes and viewing among primary-age children has been identified. What this paper adds This paper addresses this dearth of research by investigating the association between normal exposure to a Tanzanian cartoon, Ubongo Kids and mathematics capability, as derived from an item response theory model applied to the test responses of 38 682 children. Cross-sectional findings suggest the association between normal television exposure and mathematics capability to be significant. Further, a cost-effectiveness comparison with alternate interventions in comparable contexts indicates that educational television is highly cost-effective. Implications for practice and/or policy The findings presented in this paper concerning educational television viewership in usual environments act to triangulate those from prior research conducted in controlled settings. As such, policymakers in low-income contexts now possess more convincing evidence on the potential influence of educational television interventions. Additionally, the cost-effectiveness comparison made suggests that educational television should be considered a viable option by policymakers seeking to address learning outcomes with limited resources.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13047 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13047 2339240:7RAS7H3N 2405685:MVRBU5UB
Keywords: Tanzania; cost effectiveness; educational television; mathematics

Measuring the Impact of COVID-19 on Learning in Rural Kenya’ by Whizz Education (April 2021 - Whizz education (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:3A29VK33 2405685:MP8QB9LZ

Nudges to improve learning and gender parity: Supporting parent engagement and Ghana’s educational response to Covid-19 using mobile phones - Wolf, Sharon; Aurino, Elisabetta (American Economic Association, 2021)
While recent evidence from Brazil and Ivory Coast suggests that SMS messages to nudge parents' engagement in their children's education have large effects on educational outcomes, the Covid-19 pandemic raises additional concerns. In particular, learning deficits and school dropouts are likely to increase following school shutdowns, especially among vulnerable populations such as older girls who need to work to support their families or due to early marriage, childbearing and adolescent pregnancy. A further knowledge gap relates to the optimal period of exposure to the nudges, which is critical to scale-up. This study investigates whether sending nudges to parents can improve parental engagement in child education and broader development across child age groups and gender, in the low-resource setting of Ghana, by randomly assigning whether parents receive two different versions of nudges, with one version including content promoting girls’ education and addressing some common stereotypes around gender, and whether the duration of these different modalities vary between three and six months.
KerkoCite.ItemAlsoKnownAs: 10.1257/rct.6118-1.4000000000000001 2339240:35CNTCTC 2405685:A3B8URQN

WORLD BANK STRATEGIC IMPACT EVALUATION FUND (SIEF) - Wolf, Sharon; Aurino, Elisabetta; Brown, Autumn; Tsinigo, Edward (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:SA6TMDDV 2405685:869WDDDL
Keywords: ⛔ No DOI found

Learning in the time of a pandemic and implications for returning to school: effects of COVID-19 in Ghana - Wolf, Sharon; Aurino, Elisabetta; Suntheimer, Noelle; Avornyo, Esinam; Tsinigo, Edward; Jordan, Jasmine; Samanhyia, Soloman; Aber, J Lawrence; Behrman, Jere R (Consortium for Policy Research in Education (CPRE), 2021)
The Covid-19 pandemic led to school closures all over the world, leaving children across diverse contexts without formal education for nearly a year. Remote-learning programs were designed and rapidly implemented to promote learning continuity throughout the crisis. There were inequalities in who was able to access remote-learning during school closures, though little systematic evidence documenting these gaps exists, particularly in sub-Saharan Africa. In this study, we surveyed 1,844 children in the Greater Accra Region of Ghana, as well as their caregivers and teachers, regarding their engagement in remote learning, literacy and math test scores, and household economic hardships. We document inequalities in access to and engagement in remote-learning activities during the ten months in 2020 in which schools were closed in Ghana. Specifically, children in private schools and children in highersocioeconomic status households engaged in remote-learning at higher rates and received more support from their schools and caregivers. Further, controlling for demographic characteristics and pre-pandemic learning outcomes, we document gaps in children’s literacy and math test scores, with food insecure and low-SES children, as well as children enrolled in public schools before the pandemic, performing significantly worse than their peers (0.2-0.3 SD gap). Finally, children in households that experienced more economic hardships during the pandemic engaged in fewer remote learning activities and had lower literacy and numeracy assessment scores. The findings speak to the potential consequences of increased inequalities due to the pandemic as schools re-open in Ghana and around the world and provide insight into how schools may address these inequalities as children return to the classroom.
KerkoCite.ItemAlsoKnownAs: 2339240:IHPERKZR 2405685:Z7A2W9D6
Keywords: ⛔ No DOI found

Lao PDR: Policy Insights from a Multi-year Teaching and Learning Study Series - Wong, Debbie; Hollingsworth, Hilary (Department of Foreign Affairs and Trade (DFAT), 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:CJMA6Q84 2405685:YQYVXB6X
Keywords: ⛔ No INSPIRE recid found

Access to electricity (% of population) - Sub-Saharan Africa | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:CVGJ4HKR 2405685:7D3MAR35

Actuemos ya para Proteger el Capital Humano de Nuestros Niños : Los Costos y la Respuesta ante el Impacto de la Pandemia de COVID-19 en el Sector Educativo de América Latina y el Caribe. - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8BGKS5BP 2405685:7QTA3QSU

Bangladesh - Overview - World Bank (World Bank, 2021)
The International Development Association (IDA) has supported Bangladesh since 1972, just after the country’s independence. Since then, the World Bank through its concessional lending arm has committed nearly $26 billion in grants and interest-free credits to Bangladesh.
KerkoCite.ItemAlsoKnownAs: 2339240:9GAMGSVG 2405685:RUP3LCB2

Cambodia Country Profile - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:B2H7C4JF 2405685:CMYC4E9W

Development Projects : Lao PDR Global Partnership for Education III: Learning and Equity Acceleration Project - World Bank (World Bank, 2021)
Development Projects : Lao PDR Global Partnership for Education III: Learning and Equity Acceleration Project - P173407
KerkoCite.ItemAlsoKnownAs: 2339240:6XEIKV5D 2405685:X9W9SNBZ
Keywords: ⛔ No INSPIRE recid found

Development Projects : Sierra Leone Free Education Project - P167897 - World Bank (World Bank, 2021)
Development Projects : Sierra Leone Free Education Project - P167897
KerkoCite.ItemAlsoKnownAs: 2339240:LFUH26HS 2405685:GZU9SWN9

Digital technologies in education - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KYQYJ7CD 2405685:XJFUKGMR

GDP per capita (current US$) | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:SU7RTRS5 2405685:DWIEX6VJ

GDP per capita (current US$) - Malawi | Data - World Bank (World Bank, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KXZG4ANK 2405685:VUM5AGV3

Girls education - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:K48JVUER 2405685:7JY3TDUN

Girls education - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8VSSYE2T 2405685:S3MXCJY8

Human Capital Project - World Bank (2021)
The World Bank believes accelerating investments in people, also known as Investing in Human Capital is essential to achieving greater equity and economic growth. Check the definition of human capital in the World Bank Project brief.
KerkoCite.ItemAlsoKnownAs: 2339240:BTCFQ5AH 2405685:4GEV8ITE

Keeping Bangladesh’s Students Learning During the COVID-19 Pandemic - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ARRPM4JP 2405685:B9E9UBBB

Lao Basic Education Boost through $47 million Project - World Bank (World Bank, 2021)
The World Bank Global Partnership for Education III Learning and Equity Acceleration project will improve Lao education performance and teaching systems.
KerkoCite.ItemAlsoKnownAs: 2339240:LSU6M8RR 2405685:SIJRS9LM
Keywords: ⛔ No INSPIRE recid found

Lao PDR Global Partnership for Education III: Learning and Equity Acceleration Project - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:EU4B8X32 2405685:4IRPCQEC
Keywords: ⛔ No INSPIRE recid found

Lao Peoples Democratic Republic – Learning and Equity Acceleration Project - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:2LYS5U6S 2405685:BGDBGZK8
Keywords: ⛔ No INSPIRE recid found

Learners with Disabilities & COVID-19 School Closure - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5KFUIK8T 2405685:XXZ4QDWB

Leveraging Malawi’s Existing Digital Infrastructure to Boost Economic Growth - World Bank (World Bank, 2021)
The latest economic analysis of Malawi says the country has an opportunity to kickstart digital transformation by enabling the growth of a robust digital economy ecosystem
KerkoCite.ItemAlsoKnownAs: 2339240:F9MIWM7B 2405685:6ZM5SVJE

Malawi Overview - World Bank (World Bank, 2021)
The World Bank Group supports Malawi’s efforts to reduce poverty and promote economic growth by working with the government, development partners, and civil society.
KerkoCite.ItemAlsoKnownAs: 2339240:JPCM7M8E 2405685:ZFIJNHAT

Malawi World Bank Approves $100 Million to Improve Skills Development Programs - World Bank (World Bank, 2021)
The World Bank today approved $100 million in financing from the International Development Association (IDA)* for Malawi to support increased access, particularly for female students, to skills development programs in priority areas of the economy that are most relevant to the labor market— now and in the future.
KerkoCite.ItemAlsoKnownAs: 2339240:P7XWBIFX 2405685:28VJ9MRA

Nigeria to Improve Electricity Access and Services to Citizens - World Bank (World Bank, 2021)
The World Bank approved $500 million to support the government of Nigeria in improving its electricity distribution sector.
KerkoCite.ItemAlsoKnownAs: 2339240:XYTNNNPV 2405685:TWC8WUQN

Population ages 0-14 (% of total population) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:QGQ9PZAD 2339240:R4T4RZYH 2405685:6VPIRD86 2405685:BS9S34JU

Population ages 15-64 (% of total population) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:7R2JJF4R 2405685:5NXMIQQ7

Population growth (annual %) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:56YJRP9F 2405685:GTPKXNXJ

Population growth (annual %) - Kenya | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8KHUQBA8 2405685:R6CMAJQN

Population, total - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:HXP4NC9X 2405685:FY2PMI2Y

Population, total | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:C4C8XEF9 2405685:IDA67HP9

Population, total - Kenya | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:Q6Z5SVEF 2405685:FEM79MKN

Report on Education Crisis in Latin America and the Caribbean: Urgent Action is Needed to Address the Enormous Education Crisis in Latin America and the Caribbean - World Bank (The World Bank, 2021)
Following the massive school closures, as of February 2021, about 120 million school-age children had already lost or were at risk of losing a full academic year of presential education, with serious educational impacts, according to the report, Acting now to protect the human capital of our children: The costs of and response to the COVID-19 pandemic impact on the education sector in Latin America and the Caribbean.
KerkoCite.ItemAlsoKnownAs: 2339240:KYLHSKFL 2405685:IPTWDKD4

Rural population (% of total population) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:VDAAYFPJ 2405685:3K9WFJ7B

Rural population (% of total population) | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:IZKV8UX5 2405685:KKXBML6W

School enrollment, primary (% net) - Kenya | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:23A3R2N9 2405685:WCD9B49P

School enrollment, secondary (% net) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:2E6RZ789 2405685:V7GDFZV7

Secondary education, pupils - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KTBRX27R 2405685:F2U9JVYV

Secondary education, pupils (% female) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KPLXFGAC 2405685:LDBMGJIF

Secondary education, teachers - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:UDK7XP58 2405685:EKHHRCF2

Secondary education, teachers, female - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:EB4PD5EG 2405685:LB4ZKJHT

Teachers and Teaching in Sierra Leone : Teacher Quality and Management Study - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2129771:X6L76LFL 2405685:4KSNK63S 4556019:BHQLRIPR
Keywords: _C:Sierra Leone

The Urgent Need to Focus on Foundational Skills - World Bank (2021)
The urgent need to focus on foundational skills
KerkoCite.ItemAlsoKnownAs: 2339240:6SWW2M8X 2405685:X8SFP7AT

There will be no recovery without empowered, motivated and effective teachers - World Bank (2021)
There will be no recovery without empowered, motivated and effective teachers
KerkoCite.ItemAlsoKnownAs: 2339240:A5HPTSYV 2405685:RH6KQCUY

Thinking inside the "Box": Pakistan turns to education TV during Covid-19 - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:NSUIHXSL 2405685:4JZ63KJI

Trained teachers in primary education (% of total teachers) - Ghana | Data - World Bank (The World Bank Open Data, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:FZSPCLGY 2405685:WG6VWPK4

World Bank Open Data portal - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:B72R4M6V 2405685:G9KNEYVM

World Development Indicators - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:76GX39L8 2405685:2QBLXZAJ

Education Finance Watch 2021 - World Bank; UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:IH8UXUCR 2405685:QQ5SXSCG

The State of the Global Education Crisis: A Path to Recovery. - World Bank; UNESCO; UNICEF (2021)
"The global disruption to education caused by the COVD-19 pandemic is without parallel and the effects on learning are severe. The crisis brought education systems across the world to a halt, with school closures affecting more than 1.6 billion learners. While nearly every country in the world offered remote learning opportunities for students, the quality and reach of such initiatives varied greatly and were at best partial substitutes for in-person learning. Now, 21 months later, schools remain closed for millions of children and youth, and millions more are at risk of never returning to education. Evidence of the detrimental impacts of school closures on children's learning offer a harrowing reality: learning losses are substantial, with the most marginalized children and youth often disproportionately affected. Countries have an opportunity to accelerate learning recovery and make schools more efficient, equitable, and resilient by building on investments made and lessons learned during the crisis. Now is the time to shift from crisis to recovery - and beyond recovery, to resilient and transformative education systems that truly deliver learning and well-being for all children and youth."–The World Bank website
KerkoCite.ItemAlsoKnownAs: 2339240:2XRTUYDC 2339240:LTHF5A7Z 2339240:YVUFRD28 2405685:6VY4DUDI 2405685:D4UWQ8K9 2405685:ZPIAXKQS

The Global Cost of Inclusive Refugee Education - World Bank; UNHCR (World Bank, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1596/35238 2339240:K5ZC573B 2405685:ILJJ7SF3

6 Data Policy Issues Experts Are Tracking Right Now - World Economic Forum (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:NH8HP834 2405685:2WCIVPEY

World Hearing Day - World Health Organization (2021)
Statement by Dr Poonam Khetrapal Singh, WHO Regional Director for South-East Asia
KerkoCite.ItemAlsoKnownAs: 2339240:TVEXWZA5 2405685:NZCC38FE
Keywords: ⛔ No INSPIRE recid found

Bangladesh - World Inequality Database (WID - World Inequality Database, 2021)
Bangladesh The source for global inequality data. Open access, high quality wealth and income inequality data developed by an international academic consortium.
KerkoCite.ItemAlsoKnownAs: 2339240:QDDJSFXN 2405685:NF7Q3FVW

Countries by Density - World Population Review (World Population Review, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:QLHYHSIQ 2405685:S4R4KANR

Bangladesh Population (2021) - Worldometer (2021)
Population of Bangladesh: current, historical, and projected population, growth rate, immigration, median age, total fertility rate (TFR), population density, urbanization, urban population, country's share of world population, and global rank. Data tables, maps, charts, and live population clock
KerkoCite.ItemAlsoKnownAs: 2339240:6KUWCRCQ 2405685:2LS69KMG

Population by Country - Worldometer (World Population Review, 2021)
List of countries and dependencies in the world ranked by population, from the most populated. Growth rate, median age, fertility rate, area, density, population density, urbanization, urban population, share of world population.
KerkoCite.ItemAlsoKnownAs: 2339240:SI7BVSX4 2405685:A3INEC8H

International Handbook on Education in South East Asia - Ximenes, Pedro Barreto (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:2S9UHS4C 2405685:E5AUNS9T

International Handbook on Education in South East Asia - Ximenes, Pedro Barreto (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:2S9UHS4C 2405685:E5AUNS9T

How Much Does Universal Digital Learining Cost? - Yao, Haogen; Brossard, Matt; Mizunoya, Suguru; Nasir, Bassem; Walumgembe, Patrick; Cooper, Rachel; Rafique; Reuge, Nicolas (UNICEF Office of Research - Innocenti, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:FRKJIUZJ 2405685:ZUEAQXF9

Examining Pre-Service Teachers’ Views about Online Chemistry Laboratory Learning Experiences Amid the Covid-19 Pandemic - Yeşi̇Loğlu, Sevinç Nihal; Gençer, Sinem; Eki̇Ci̇, Funda; Işik, Burcu (Journal of Turkish Science Education, 2021)
With the continued spread of the COVID-19 crisis, the universities were closed temporarily in Turkey just as in the rest of the world. As a result of this, many educators and students tried to adapt online education quickly. This research study examined 67 pre-service teachers' views on online chemistry laboratory learning experiences amid the COVID-19 pandemic. A data collection tool consisting of seven open-ended questions was used. Data sources included responses given to open-ended questions about the online chemistry laboratory learning experiences, the applications used for the chemistry experiments (e.g., simulations, images, and videos), the methods used for assessing online learning, and the system used for the virtual classroom platform. Content analysis was applied to participants’ responses. Participants’ views about online chemistry laboratories amid the COVID-19 pandemic were gathered in five themes: (i) advantages and disadvantages of online chemistry laboratories, (ii) effects of online chemistry laboratories on learning outcomes, (iii) views on technological applications used in online chemistry laboratories, (iv) views on measurement and assessment methods used in online chemistry laboratories, and (v) views of pre-service teachers on the virtual classroom platform used in online chemistry laboratories. The findings of the study highlighted that online laboratory learning has both advantages and disadvantages. The findings also included the strengths and weaknesses of the system used for the virtual classroom platform. The findings may provide useful information on how to design a positive online laboratory experience such as integrating hands-on activities as a part of the online laboratories to overcome the lack of “learning by doing” and using videos containing more detailed explanations about the experimental setup.
KerkoCite.ItemAlsoKnownAs: 2339240:DSRLDWSX 2405685:UGUM9APX
Keywords: ⛔ No DOI found

COVID-19 could reverse two decades of progress: Emerging policy recommendations to support young people in developing countries - Young Lives (Young Lives, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:99CVVYHF 2405685:SAA7C9VV

Blended Learning in Universities in East Africa: Lessons from the PEBL Partnership - Young, John; Nzegwu, Dr Femi; Schaeffler, Dr Veronika; Khandoker, Fiona; Calamassi, Sara; Perris, Dr Kirk; George, Dr; Ikiara, Dr Lucy (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:JLFHYFLF 2405685:4A39VGZ8
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Special education teachers’ perceptions toward online learning during the Covid-19 pandemic - Yunita, Vania Martha; Sunardi, Sunardi; Kristiyanto, Agus (JPI (Jurnal Pendidikan Indonesia), 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:WGMWMERT 2405685:3RZ2MMSM
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

After COVID-19, let’s reimagine education in Kenya - Zaman, Maniza (2021)
Digital learning should be part of a basic package of essential services for every child
KerkoCite.ItemAlsoKnownAs: 2339240:YEMKMSZT 2405685:4TIDEWQM

La educación virtual en tiempos del COVID-19: Una experiencia en la maestría de Educación - Zea, Miriam Patricia Cárdenas; Quimi, Wendy Diana Carranza; Panta, Karina Alexandra Plua; García, Mariana Solís; Torres, Marioxy Morales (Universidad y Sociedad, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:UYX22NH2
Keywords: ⛔ No DOI found

Teacher Turnover in Rwanda - Zeitlin, Andrew (Journal of African Economies, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1093/jae/ejaa013 2339240:MK8XIA4D 2405685:XX2WB7E8

An Exploration of China-Africa Cooperation in Higher Education: Opportunities and Challenges in Open Distance Learning - Zhu, Xia; Chikwa, Gladson (Open Praxis, 2021)
Cognisant of the wide range of cooperation between China and Africa and the existing strong Sino-African relationship, this article explores the international cooperation between Africa and China in the higher education domain, especially in the field of Open Distance Learning (ODL). The study employed data triangulation relying on both secondary and primary sources to address the main research questions. It sheds light on the development of ODL in Chinese Higher Education Institutions (HEIs) with a focus on professional development of university teachers. The article argues that ODL is crucial for emerging economies' sustainable development. Key factors such as political, technological and socio-cultural features play a crucial role in the development and effective implementation of ODL. By exploring the potential opportunities and identifying related challenges, this article contributes to an understanding of how mutually beneficial partnerships between African universities and Chinese HEIs can be developed within the wider framework of Sino-African relationship.
Publisher: International Council for Open and Distance Education KerkoCite.ItemAlsoKnownAs: 10.5944/openpraxis.13.1.1154 2339240:QGE68QAY 2405685:24EKHU7N
Keywords: Distance Education; Educational Development; Educational Technology; Faculty Development; Foreign Countries; Higher Education; International Cooperation; Lifelong Learning; Open Education; Partnerships in Education; Sustainable Development